14C AMS Dating of Wooden Cores from Historic Buildings for Archaeological and Dendrochronological Research in High Asia. - Scharf, Andreas; Bräuning, Achim; Kretschmer, Wolfgang; Wegner, B; Darragon, Frederique Martine (Radiocarbon, 2013)
We had the opportunity to collect valuable wooden core samples from historic monasteries, temples, and secular buildings in 4 regions of High Asia, namely Dolpo (Nepal), ancient Nyangpo, Gyalrong/Minyag, and Lhasa and surroundings (all on the Tibetan Plateau, China). Tree species collected for dating include Pinus wallichiana (Dolpo), Juniperus tibetica, Pinus densata, and several species of the genera Picea (spruce), Larix (larch), and Abies (fir) on the Tibetan Plateau, which could not always be determined to the species level due to the parallel occurrence of species of the same genus in these regions. Some of the wood samples were successfully dendro-dated with local tree-ring chronologies, but many could not, indicating a potentially higher age than the existing local chronologies. By accelerator mass spectrometry (AMS) dating and wiggle-matching 199 14C samples from 73 collected timbers, it was possible to date these wood samples with high precision, and important information about the possible time of construction of these important historic buildings was obtained for the first time. Floating chronologies of 14C-dated wood span the periods AD 650 to 900 in Dolpo and 200 BC to AD 420 on the Tibetan Plateau. Besides dating of the wood samples from these historic monuments, 14C AMS dating with wiggle-matching gives the opportunity to extend the range of the currently existing regional tree-ring chronologies for future environmental reconstructions on the Tibetan Plateau and the Himalayas.
Keywords: Dendrochronology; Radiocarbon

3-D Reconstruction of Historical Documents using an X-Ray C-Arm CT System - Stromer, Daniel; Christlein, Vincent; Anton, Gisela; Kugler, Patrick; Maier, Andreas (Proceedings of the 31th conference on Image and Vision Computing New Zealand 2016, 2016)
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.IMMD5.3dreco_2
Keywords: X-Ray imaging; Iron gall ink reconstruction; Historical Document Analysis

3D Tensor Reconstruction in X-Ray Dark-Field Tomography: The First Phantom Result - Hu, Shiyang; Riess, Christian; Hornegger, Joachim; Fischer, Peter; Bayer, Florian; Weber, Thomas; Anton, Gisela; Maier, Andreas (Bildverarbeitung für die Medizin 2015, 2015)

A 3-D Projection Model for X-ray Dark-field Imaging - Felsner, Lina; Hu, Shiyang; Maier, Andreas; Bopp, Johannes; Ludwig, Veronika; Anton, Gisela; Riess, Christian (Scientific Reports, 2019)

A 3-D Projection Model for X-ray Dark-field Imaging - Hu, Shiyang; Felsner, Lina; Maier, Andreas; Ludwig, Veronika; Anton, Gisela; Riess, Christian (2018)

A 3-D Scattering Model for Orientation-dependent X-ray Dark-field Imaging - Hu, Shiyang; Maier, Andreas; Hornegger, Joachim; Bayer, Florian; Weber, Thomas; Anton, Gisela; Riess, Christian (Fully Three-Dimensional Image Reconstruction in Radiology and Nuclear Medicine, 2015)

Acceleration of petaelectronvolt protons in the Galactic Centre - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, M.; Balzer, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; Bernhard, S.; Bernloehr, K.; et al. (Nature, 2016)
Galactic cosmic rays reach energies of at least a few petaelectronvolts(1) (of the order of 1015 electronvolts). This implies that our Galaxy contains petaelectronvolt accelerators ('PeVatrons'), but all proposed models of Galactic cosmic-ray accelerators encounter difficulties at exactly these energies(2). Dozens of Galactic accelerators capable of accelerating particles to energies of tens of teraelectronvolts (of the order of 10(13) electronvolts) were inferred from recent gamma-ray observations(3). However, none of the currently known accelerators-not even the handful of shell-type supernova remnants commonly believed to supply most Galactic cosmic rays-has shown the characteristic tracers of petaelectronvolt particles, namely, power-law spectra of.-rays extending without a cut-off or a spectral break to tens of teraelectronvolts(4). Here we report deep.-ray observations with arcminute angular resolution of the region surrounding the Galactic Centre, which show the expected tracer of the presence of petaelectronvolt protons within the central 10 parsecs of the Galaxy. We propose that the supermassive black hole Sagittarius A* is linked to this PeVatron. Sagittarius A* went through active phases in the past, as demonstrated by X-ray outbursts(5) and an outflow from the Galactic Centre(6). Although its current rate of particle acceleration is not sufficient to provide a substantial contribution to Galactic cosmic rays, Sagittarius A* could have plausibly been more active over the last 10(6)-10(7) years, and therefore should be considered as a viable alternative to supernova remnants as a source of petaelectronvolt Galactic cosmic rays.

Acceptance Tests of more than 10 000 Photomultiplier Tubes for the multi-PMT Digital Optical Modules of the IceCube Upgrade - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Journal of Instrumentation, 2024)
More than 10 000 photomultiplier tubes (PMTs) with a diameter of 80 mm will be installed in multi-PMT Digital Optical Modules (mDOMs) of the IceCube Upgrade. These have been tested and pre-calibrated at two sites. A throughput of more than 1000 PMTs per week with both sites was achieved with a modular design of the testing facilities and highly automated testing procedures. The testing facilities can easily be adapted to other PMTs, such that they can, e.g., be re-used for testing the PMTs for IceCube-Gen2. Single photoelectron response, high voltage dependence, time resolution, prepulse, late pulse, afterpulse probabilities, and dark rates were measured for each PMT. We describe the design of the testing facilities, the testing procedures, and the results of the acceptance tests.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Cherenkov detectors; Neutrino detectors; Photon detectors for UV; HPDs; others); visible and IR photons (vacuum) (photomultipliers

Accounting for changing snow over 10 years of IceTop, and its impact on the all-particle cosmic ray spectrum - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
The IceTop surface detector of the IceCube Neutrino Observatory measures extensive air showers (EAS). Coincident signals in both tanks of an IceTop station result primarily from the electromagnetic component of the EAS, and events which trigger at least 5 stations correspond to energies roughly above the knee, with an energy threshold and reconstruction behavior that changes over time as snow accumulates above the array. We present a status report of an analysis of ≥ 5-station events in IceTop from 2011-2021, which will be used to measure the all-particle spectrum of cosmic rays in the transition region from galactic to extragalactic sources up to EeV range, using updated simulations and improved treatments of snow attenuation. In particular, a snow model has been developed which takes the non-attenuating muon content of tank signals, as well as their saturation behavior, into account.
CRIS-Team Scopus Importer:2025-02-04

A convolutional neural network based cascade reconstruction for the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Journal of Instrumentation, 2021)
Continued improvements on existing reconstruction methods are vital to the success of high-energy physics experiments, such as the IceCube Neutrino Observatory. In IceCube, further challenges arise as the detector is situated at the geographic South Pole where computational resources are limited. However, to perform real-time analyses and to issue alerts to telescopes around the world, powerful and fast reconstruction methods are desired. Deep neural networks can be extremely powerful, and their usage is computationally inexpensive once the networks are trained. These characteristics make a deep learning-based approach an excellent candidate for the application in IceCube. A reconstruction method based on convolutional architectures and hexagonally shaped kernels is presented. The presented method is robust towards systematic uncertainties in the simulation and has been tested on experimental data. In comparison to standard reconstruction methods in IceCube, it can improve upon the reconstruction accuracy, while reducing the time necessary to run the reconstruction by two to three orders of magnitude.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Calibration; Cluster finding; Data analysis; Fitting methods; Neutrino detectors; Pattern recognition

Active Personal Eye Lens Dosimetry with the Hybrid Pixelated Dosepix Detector - Beiser, Florian; Haag, Dennis; Ballabriga, Rafael; Behrens, Rolf; Campbell, Michael; Fuhg, Christian; Hufschmidt, Patrick; Hupe, Oliver; Kupillas, Carolin; Llopart, Xavier; Roth, Jurgen; Schmidt, Sebastian; et al. (IEEE Transactions on Radiation and Plasma Medical Sciences, 2023)
Eye lens dosimetry has been an important field of research in the last decade. Dose measurements with a prototype of an active personal eye lens dosemeter based on the Dosepix detector are presented. The personal dose equivalent at 3 mm depth of soft tissue, Hp(3), was measured in the center front of a water-filled cylinder phantom with a height and diameter of 20 cm. The energy dependence of the normalized response is investigated for mean photon energies between 12.4 keV and 248 keV for continuous reference radiation fields (N-series) according to ISO 4037. The response normalized to N-60 (E=47.9 keV) at 0∘ angle of irradiation stays within the approval limits of IEC 61526 for angles of incidence between -75∘ and +75∘. Performance in pulsed photon fields was tested for varying dose rates from 0.1 Svh up to 1000 Svh and pulse durations from 1 ms up to 10 s. The dose measurement works well within the approval limits (acc. to IEC 61526) up to 1 Svh. No significant influence of the pulse duration on the measured dose is found. Reproducibility measurements yield a coefficient of variation which does not exceed 1 % for two tested eye lens dosemeter prototypes.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Active personal dosemeter; Detectors; Dosepix; Dosimetry; dosimetry for interventional procedures; dosimetry for radiation based medical applications; eye lens dosimetry; Histograms; Lenses; Phantoms; Photonics; Prototypes; pulsed x-ray fields; radiation detectors for medical applications: semiconductors

A fast alignment method for grating-based X-ray phase-contrast imaging systems - Schuster, Max; Ludwig, Veronika; Akstaller, Bernhard; Seifert, Maria; Wolf, Andreas; Michel, Thilo; Neumayer, P.; Funk, Stefan; Anton, Gisela (Journal of Instrumentation, 2019)
The alignment of a grating-based X-ray phase-contrast interferometer is an iterative process that requires numerous steps of changing the distances and angles between the gratings. For each alignment step an image is acquired to evaluate the detected intensity signature in order to optimize the observed moir'e pattern. Thus, a large number of images has to be taken for the alignment procedure. This is not feasible within reasonable time at X-ray sources like X-ray backlighters where the time between two X-ray shots is on the scale of hours. Here, we report on the development of a stable and transportable setup ready-to-use for grating-based X-ray phase-contrast imaging. A comprehensive set of reference images taken at a continuous beam serves as a look-up table which enables the grating alignment within very few alignment steps. Since this method features a fast, reliable and predictable alignment, it is also beneficial for grating-based X-ray phase-contrast imaging systems at common X-ray sources.
CRIS-Team Scopus Importer:2019-10-08
Keywords: Inspection with x-rays; Plasma diagnostics - interferometry; spectroscopy and imaging; X-ray radiography and digital radiography (DR)

A first search for coincident gravitational waves and high energy neutrinos using LIGO, Virgo and ANTARES data from 2007 - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
We present the results of the first search for gravitational wave bursts associated with high energy neutrinos. Together, these messengers could reveal new, hidden sources that are not observed by conventional photon astronomy, particularly at high energy. Our search uses neutrinos detected by the underwater neutrino telescope ANTARES in its 5 line configuration during the period January - September 2007, which coincided with the fifth and first science runs of LIGO and Virgo, respectively. The LIGO-Virgo data were analysed for candidate gravitational-wave signals coincident in time and direction with the neutrino events. No significant coincident events were observed. We place limits on the density of joint high energy neutrino - gravitational wave emission events in the local universe, and compare them with densities of merger and core-collapse events.
Keywords: gravitational waves / experiments; neutrino astronomy

A Hierarchical Bayesian Approach to Point-source Analysis in High-energy Neutrino Telescopes - Capel, Francesca; Kuhlmann, Julian; Haack, Christian; Ha Minh, Martin; Niederhausen, Hans; Schumacher, Lisa (Astrophysical Journal, 2024)
We propose a novel approach to the detection of point-like sources of high-energy neutrinos. Motivated by evidence for emerging sources in existing data, we focus on the characterization and interpretation of these sources rather than the rejection of the background-only hypothesis. The hierarchical Bayesian model is implemented in the Stan platform, enabling computation of the posterior distribution with a Hamiltonian Monte Carlo algorithm. We simulate a population of weak neutrino sources detected by the IceCube experiment and use the resulting data set to demonstrate and validate our framework. We show that even for the challenging case of sources at the threshold of detection and using limited prior information, it is possible to correctly infer the source properties. Additionally, we demonstrate how modeling flexible connections between similar sources can be used to recover the contribution of sources that would not be detectable individually. While a direct comparison of our method to existing approaches is challenged by the fundamental differences in frequentist and Bayesian frameworks, we draw parallels where possible. In particular, we highlight how including more complexity into the source modeling can increase the sensitivity to sources and their populations.
CRIS-Team Scopus Importer:2024-11-29

All-flavor constraints on nonstandard neutrino interactions and generalized matter potential with three years of IceCube DeepCore data - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Physical Review D, 2021)
We report constraints on nonstandard neutrino interactions (NSI) from the observation of atmospheric neutrinos with IceCube, limiting all individual coupling strengths from a single dataset. Furthermore, IceCube is the first experiment to constrain flavor-violating and nonuniversal couplings simultaneously. Hypothetical NSI are generically expected to arise due to the exchange of a new heavy mediator particle. Neutrinos propagating in matter scatter off fermions in the forward direction with negligible momentum transfer. Hence the study of the matter effect on neutrinos propagating in the Earth is sensitive to NSI independently of the energy scale of new physics. We present constraints on NSI obtained with an all-flavor event sample of atmospheric neutrinos based on three years of IceCube DeepCore data. The analysis uses neutrinos arriving from all directions, with reconstructed energies between 5.6 GeV and 100 GeV. We report constraints on the individual NSI coupling strengths considered singly, allowing for complex phases in the case of flavor-violating couplings. This demonstrates that IceCube is sensitive to the full NSI flavor structure at a level competitive with limits from the global analysis of all other experiments. In addition, we investigate a generalized matter potential, whose overall scale and flavor structure are also constrained.
CRIS-Team Scopus Importer:2021-10-29

All-flavor Search for a Diffuse Flux of Cosmic Neutrinos with Nine Years of ANTARES Data - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Astrophysical Journal Letters, 2018)
The ANTARES detector is at present the most sensitive neutrino telescope in the northern hemisphere. The highly significant cosmic neutrino excess observed by the Antarctic IceCube detector can be studied with ANTARES, exploiting its complementing field of view, exposure, and lower energy threshold. Searches for an all-flavor diffuse neutrino signal, covering nine years of ANTARES data taking, are presented in this Letter. Upward-going events are used to reduce the atmospheric muon background. This work includes for the first time in ANTARES both track-like (mainly nu mu) and shower-like (mainly nu(e)) events in this kind of analysis. Track-like events allow for an increase of the effective volume of the detector thanks to the long path traveled by muons in rock and/ or sea water. Shower-like events are well reconstructed only when the neutrino interaction vertex is close to, or inside, the instrumented volume. A mild excess of high-energy events over the expected background is observed in nine years of ANTARES data in both samples. The best fit for a single power-law cosmic neutrino spectrum, in terms of perflavor flux at 100 TeV, is Phi(1f)(0) (100 TeV) = (1.7 +/- 1.0) x 10(-18) GeV-1 cm(-2) s(-1) sr(-1) with spectral index Gamma = 2.4(-0.4)(+0.5) .The null cosmic flux assumption is rejected with a significance of 1.6 sigma .
Keywords: astroparticle physics; neutrinos

All-sky Measurement of the Anisotropy of Cosmic Rays at 10 TeV and Mapping of the Local Interstellar Magnetic Field - Abeysekara, A. U.; Alfaro, R.; Alvarez, C.; Arceo, R.; Arteaga-Velazquez, J. C.; Avila Rojas, D.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; Capistran, T.; Carramiana, A.; Casanova, S.; et al. (Astrophysical Journal, 2019)
We present the first full-sky analysis of the cosmic ray arrival direction distribution with data collected by the High-Altitude Water Cherenkov and IceCube observatories in the northern and southern hemispheres at the same median primary particle energy of 10 TeV. The combined sky map and angular power spectrum largely eliminate biases that result from partial sky coverage and present a key to probe into the propagation properties of TeV cosmic rays through our local interstellar medium and the interaction between the interstellar and heliospheric magnetic fields. From the map, we determine the horizontal dipole components of the anisotropy δ 0h = 9.16 ×10 -4 and δ 6h = 7.25 ×10 -4 (±0.04 × 10 -4 ). In addition, we infer the direction (229.°2 ± 3.°5 R.A., 11.°4 ± 3.°0 decl.) of the interstellar magnetic field from the boundary between large-scale excess and deficit regions from which we estimate the missing corresponding vertical dipole component of the large-scale anisotropy to be δN ∼ -3.97 +1.0 -2.0 × 10 -4 .
CRIS-Team Scopus Importer:2019-05-02
Keywords: astroparticle physics; cosmic rays; ISM: magnetic fields

All-sky search for high-energy neutrinos from gravitational wave event GW170104 with the Antares neutrino telescope: The ANTARES Collaboration - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (European Physical Journal C, 2017)
Advanced LIGO detected a significant gravitational wave signal (GW170104) originating from the coalescence of two black holes during the second observation run on January 4th, 2017. Anall-sky high-energy neutrino follow-up search has been made using data from the Antares neutrino telescope, including both upgoing and downgoing events in two separate analyses. No neutrino candidates were found within +/- 500 s around the GW event time nor any time clustering of events over an extended time window of +/- 3 months. The non-detection is used to constrain isotropic-equivalent high-energy neutrino emission from GW170104 to less than similar to 1.2 x 10(55) erg for a E-2 spectrum. This constraint is valid in the energy range corresponding to the 5-95% quantiles of the neutrino flux [3.2 TeV; 3.6 PeV], if the GW emitter was below the Antares horizon at the alert time.

A method for detection of muon induced electromagnetic showers with the ANTARES detector - Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Auberth, J. J.; Baret, B.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2012)
The primary aim of ANTARES is neutrino astronomy with upward going muons created in charged current muon neutrino interactions in the detector and its surroundings. Downward going muons are background for neutrino searches. These muons are the decay products of cosmic-ray collisions in the Earth's atmosphere far above the detector. This paper presents a method to identify and count electromagnetic showers induced along atmospheric muon tracks with the ANTARES detector. The method is applied to both cosmic muon data and simulations and its applicability to the reconstruction of muon event energies is demonstrated. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino telescope; Electromagnetic shower identification; High energy muons; Energy reconstruction

A method to stabilise the performance of negatively fed KM3NeT photomultipliers - Adrián-Martínez, S.; Ageron, M.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Avgitas, T.; et al. (Journal of Instrumentation, 2016)
The KM3NeT research infrastructure, currently under construction in the Mediterranean Sea, will host neutrino telescopes for the identification of neutrino sources in the Universe and for studies of the neutrino mass hierarchy. These telescopes will house hundreds of thousands of photomultiplier tubes that will have to be operated in a stable and reliable fashion. In this context, the stability of the dark counts has been investigated for photomultiplier tubes with negative high voltage on the photocathode and held in insulating support structures made of 3D printed nylon material. Small gaps between the rigid support structure and the photomultiplier tubes in the presence of electric fields can lead to discharges that produce dark count rates that are highly variable. A solution was found by applying the same insulating varnish as used for the high voltage bases directly to the outside of the photomultiplier tubes. This transparent conformal coating provides a convenient and inexpensive method of insulation.
Keywords: Instrument optimization; Large detector systems for particle and astroparticle physics; Neutrino detectors; Photon detectors for UV; visible and IR photons (gas) (gas-photocathodes; solid-photocathodes)

A model-independent analysis of neutrino flares detected in IceCube from X-ray selected blazars - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Proceedings of Science, 2022)
Blazars are among the most powerful steady sources in the Universe. Multi-messenger searches for blazars have traditionally focused on their gamma-ray emission, which can be produced simultaneously with neutrinos in photohadronic interactions. However, X-ray data can be equally vital to constrain the SED of these sources, since the hadronically co-produced gamma-rays could get absorbed by the ambient photon fields and cascade down to X-ray energies before escaping. In this work, we present the outline for an untriggered, time-dependent analysis of neutrino flares from the direction of X-ray selected blazars using 10 years of IceCube data. A binomial test will be performed on the population to reveal if a subcategory of sources has statistically significant emission. The sources are selected from RomaBZCat, and the p-values and best-fit flare parameters are obtained for each source using the method of unbinned likelihood maximisation.
CRIS-Team Scopus Importer:2024-12-16

A muon-track reconstruction exploiting stochastic losses for large-scale Cherenkov detectors - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Journal of Instrumentation, 2021)
IceCube is a cubic-kilometer Cherenkov telescope operating at the South Pole. The main goal of IceCube is the detection of astrophysical neutrinos and the identification of their sources. High-energy muon neutrinos are observed via the secondary muons produced in charge current interactions with nuclei in the ice. Currently, the best performing muon track directional reconstruction is based on a maximum likelihood method using the arrival time distribution of Cherenkov photons registered by the experiment's photomultipliers. A known systematic shortcoming of the prevailing method is to assume a continuous energy loss along the muon track. However at energies >1 TeV the light yield from muons is dominated by stochastic showers. This paper discusses a generalized ansatz where the expected arrival time distribution is parametrized by a stochastic muon energy loss pattern. This more realistic parametrization of the loss profile leads to an improvement of the muon angular resolution of up to 20% for through-going tracks and up to a factor 2 for starting tracks over existing algorithms. Additionally, the procedure to estimate the directional reconstruction uncertainty has been improved to be more robust against numerical errors.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Cherenkov detectors; Data analysis; Neutrino detectors

An algorithm for the reconstruction of high-energy neutrino-induced particle showers and its application to the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (European Physical Journal C, 2017)
A novel algorithm to reconstruct neutrino-induced particle showers within the ANTARES neutrino telescope is presented. The method achieves a median angular resolution of 6. for shower energies below 100TeV. Applying this algorithm to 6 years of data taken with theANTARES detector, 8 events with reconstructed shower energies above 10TeV are observed. This is consistent with the expectation of about 5 events from atmospheric backgrounds, but also compatible with diffuse astrophysical flux measurements by the IceCube collaboration, from which 2-4 additional events are expected. A 90% C.L. upper limit on the diffuse astrophysical neutrino flux with a value per neutrino flavour of E-2.Phi(90%) = 4.9 . 10(-8) GeV.cm(-2).s(-1).sr(-1) is set, applicable to the energy range from 23TeV to 7.8PeV, assuming an unbroken E-2 spectrum and neutrino flavour equipartition at Earth.

An Algorithm for the Reconstruction of Neutrino-induced Showers in the ANTARES Neutrino Telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Astronomical Journal, 2017)
Muons created by nu(mu) charged current (CC) interactions in the water surrounding the ANTARES neutrino telescope have been almost exclusively used so far in searches for cosmic neutrino sources. Due to their long range, highly energetic muons inducing Cherenkov radiation in the water are reconstructed with dedicated algorithms that allow for the determination of the parent neutrino direction with a median angular resolution of about 0 degrees.4 for an E-2 neutrino spectrum. In this paper, an algorithm optimized for accurate reconstruction of energy and direction of shower events in the ANTARES detector is presented. Hadronic showers of electrically charged particles are produced by the disintegration of the nucleus both in CC and neutral current interactions of neutrinos in water. In addition, electromagnetic showers result from the CC interactions of electron neutrinos while the decay of a tau lepton produced in nu(tau) CC interactions will, in most cases, lead to either a hadronic or an electromagnetic shower. A shower can be approximated as a point source of photons. With the presented method, the shower position is reconstructed with a precision of about 1 m; the neutrino direction is reconstructed with a median angular resolution between 2 degrees and 3 degrees in the energy range of 1-1000 TeV. In this energy interval, the uncertainty on the reconstructed neutrino energy is about 5%-10%. The increase in the detector sensitivity due to the use of additional information from shower events in the searches for a cosmic neutrino flux is also presented.
Keywords: neutrinos; telescopes

Analysis framework for Multi-messenger Astronomy with IceCube - Fan, Kwok Lung; Evans, John; Larson, Michael; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; et al. (Proceedings of Science, 2022)
Combining observational data from multiple instruments for multi-messenger astronomy can be challenging due to the complexity of the instrument response functions and likelihood calculation. We introduce a python-based unbinned-likelihood analysis package called i3mla (IceCube Maximum Likelihood Analysis). i3mla is designed to be compatible with the Multi-Mission Maximum Likelihood (3ML) framework, which enables multi-messenger astronomy analyses by combining the likelihood across different instruments. By making it possible to use IceCube data in the 3ML framework, we aim to facilitate the use of neutrino data in multi-messenger astronomy. In this work we illustrate how to use the i3mla package with 3ML and present preliminary sensitivities using the i3mla package and 3ML through a joint-fit with HAWC Public dataset.
CRIS-Team Scopus Importer:2024-12-16

Analysis Of A Deconvolution-Based Information Retrieval Algorithm In X-Ray Grating-Based Phase-Contrast Imaging - Horn, Florian; Bayer, Florian; Pelzer, Georg; Rieger, Jens; Ritter, André; Weber, Thomas; Zang, Andrea; Michel, Thilo; Anton, Gisela (2014)
Several measurements were carried out using melamine foams as phantoms. We analysed the dependency of the deconvolution-based method with respect to the dark-field image on different parameters such as dose, number of iterations of the iterative deconvolution-algorithm and dark-field signal. A disagreement was found in the reconstructed dark-field values between the FFT method and the iterative method. Usage of the resulting characteristics might be helpful in future applications.
Keywords: X-ray imaging; differential phase-contrast; Talbot-Lau interferometry; grating-interferometry ultra small angle X-ray scattering; deconvolution-based reconstruction; Lucy-Richardson deconvolution

A new SNR with TeV shell-type morphology: HESS J1731-347 - Abramowski, A.; Acero, Fabio; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Becherini, Y.; Becker, J.; Behera, B.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2011)
Aims. The recent discovery of the radio shell-type supernova remnant (SNR), G353.6-0.7, in spatial coincidence with the unidentified TeV source HESS J1731-347 has motivated further observations of the source with the High Energy Stereoscopic System (HESS) Cherenkov telescope array to test a possible association of the γ-ray emission with the SNR. Methods. With a total of 59 h of observation, representing about four times the initial exposure available in the discovery paper of HESS J1731-347, the γ-ray morphology is investigated and compared with the radio morphology. An estimate of the distance is derived by comparing the interstellar absorption derived from X-rays and the one obtained from CO and HI observations. Results. The deeper γ-ray observation of the source has revealed a large shell-type structure with similar position and extension (r ∼ 0.25°) as the radio SNR, thus confirming their association. By accounting for the HESS angular resolution and projection effects within a simple shell model, the radial profile is compatible with a thin, spatially unresolved, rim. Together with RX J1713.7-3946, RX J0852.0-4622 and SN 1006, HESS J1731-347 is now the fourth SNR with a significant shell morphology at TeV energies. The derived lower limit on the distance of the SNR of 3.2 kpc is used together with radio and X-ray data to discuss the possible origin of the γ-ray emission, either via inverse Compton scattering of electrons or the decay of neutral pions resulting from proton-proton interaction. © 2011 ESO.
Keywords: Astroparticle physics; Cosmic rays; ISM: supernova remnants

A next-generation optical sensor for IceCube-Gen2 - Ishihara, Aya; Shimizu, Nobuhiro; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Alves, A. A.; Amin, N. M.; et al. (Proceedings of Science, 2022)
For the in-ice component of the next generation neutrino observatory at the South Pole, IceCubeGen2, a new sensor module is being developed, which is an evolution of the D-Egg and mDOM sensors developed for the IceCube Upgrade. The sensor design features up to 18 4-inch PMTs distributed homogeneously in a borosilicate glass pressure vessel. Challenges arise for the mechanical design from the tight constraints on the bore hole diameter (which will be 2 inches smaller than for IceCube Upgrade) and from the close packing of the PMTs. The electronics design must meet the space constraints posed by the mechanical design as well as the power consumption and cost considerations from over 10,000 optical modules being deployed. This contribution presents forward-looking solutions to these design considerations. Prototype modules will be installed and integrated in the IceCube Upgrade.
CRIS-Team Scopus Importer:2023-08-15

An improved infrastructure for the IceCube realtime system - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
The IceCube realtime alert system has been operating since 2016. It provides prompt alerts on high-energy neutrino events to the astroparticle physics community. The localization regions for the incoming direction of neutrinos are published through NASA’s Gamma-ray Coordinate Network (GCN). The IceCube realtime system consists of infrastructure dedicated to the selection of alert events, the reconstruction of their topology and arrival direction, the calculation of directional uncertainty contours and the distribution of the event information through public alert networks. Using a message-based workflow management system, a dedicated software (SkyDriver) provides a representational state transfer (REST) interface to parallelized reconstruction algorithms. In this contribution, we outline the improvements of the internal infrastructure of the IceCube realtime system that aims to streamline the internal handling of neutrino events, their distribution to the SkyDriver interface, the collection of the reconstruction results as well as their conversion into human- and machine-readable alerts to be publicly distributed through different alert networks. An approach for the long-term storage and cataloging of alert events according to findability, accessibility, interoperability and reusability (FAIR) principles is outlined.
CRIS-Team Scopus Importer:2025-02-04

ANTARES constrains a blazar origin of two IceCube PeV neutrino events - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Astronomy & Astrophysics, 2015)
Results. Both blazars predicted to be the most neutrino-bright in the TANAMI sample (1653-329 and 1714-336) have a signal flux fitted by the likelihood analysis corresponding to approximately one event. This observation is consistent with the blazar-origin hypothesis of the IceCube event IC 14 for a broad range of blazar spectra, although an atmospheric origin cannot be excluded. No ANTARES events are observed from any of the other four blazars, including the three associated with IceCube event IC20. This excludes at a 90% confidence level the possibility that this event was produced by these blazars unless the neutrino spectrum is flatter than -2.4.
Keywords: neutrinos; galaxies: active; quasars: general

ANTARES Neutrino Search for Time and Space Correlations with IceCube High-energy Neutrino Events - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Astrophysical Journal, 2019)
In past years the IceCube Collaboration has reported the observation of astrophysical high-energy neutrino events in several analyses. Despite compelling evidence for the first identification of a neutrino source, TXS 0506+056, the origin of the majority of these events is still unknown. In this paper, we search for a possible transient origin of the IceCube astrophysical events using neutrino events detected by the ANTARES telescope. The arrival time and direction of 6894 track-like and 160 shower-like events detected over 2346 days of livetime are examined to search for coincidences with 54 IceCube high-energy track-like neutrino events, by means of a maximum likelihood method. No significant correlation is observed and upper limits on the one-flavor neutrino fluence from the direction of the IceCube candidates are derived. The nonobservation of time and space correlation within the time window of 0.1 days with the two most energetic IceCube events constrains the spectral index of a possible point-like transient neutrino source to be harder than -2.3 and -2.4 for each event, respectively.
CRIS-Team WoS Importer:2019-07-26

ANTARES Search for Point Sources of Neutrinos Using Astrophysical Catalogs: A Likelihood Analysis - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, Simone; et al. (Astrophysical Journal, 2021)
A search for astrophysical pointlike neutrino sources using the data collected by the ANTARES detector between 2007 January 29 and 2017 December 31 is presented. A likelihood method is used to assess the significance of an excess of muon neutrinos inducing track-like events in correlation with the location of a list of possible sources. Different sets of objects are tested in the analysis: (a) a subsample of the Fermi 3LAC catalog of blazars, (b) a jet-obscured population of active galactic nuclei, (c) a sample of hard X-ray selected radio galaxies, (d) a star-forming galaxy catalog, and (e) a public sample of 56 very-high-energy track events from the IceCube experiment. None of the tested sources shows a significant association with the sample of neutrinos detected by ANTARES. The smallest p-value is obtained for the catalog of radio galaxies with an equal-weights hypothesis, with a pre-trial p-value equivalent to a 2.8 sigma excess, which is equivalent to 1.6 sigma post-trial. In addition, the results of a dedicated analysis for the blazar MG3 J225517+2409 are also reported: this source is found to be the most significant within the Fermi 3LAC sample, with five ANTARES events located less than one degree from the source. This blazar showed evidence of flaring activity in Fermi data, in spacetime coincidence with a high-energy track detected by IceCube. An a posteriori significance of 2.6 sigma for the combination of ANTARES and IceCube data is reported.
CRIS-Team WoS Importer:2021-04-30

ANTARES upper limits on the multi-TeV neutrino emission from the GRBs detected by IACTs - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2021)
The first gamma-ray burst detections by Imaging Atmospheric Cherenkov Telescopes have been recently announced: GRB 190114C, detected by MAGIC, GRB 180720B and GRB 190829A, observed by H.E.S.S. A dedicated search for neutrinos in space and time coincidence with the gamma-ray emission observed by IACTs has been performed using ANTARES data. The search covers both the prompt and afterglow phases, yielding no neutrinos in coincidence with the three GRBs studied. Upper limits on the energetics of the neutrino emission are inferred. The resulting upper limits are several orders of magnitude above the observed gamma-ray emission, and they do not allow to constrain the available models.
CRIS-Team Scopus Importer:2021-04-16

A phase-sampling method for an X-ray Talbot-Lau scanner with continuous grating movement - Ludwig, Veronika; Akstaller, Bernhard; Schuster, Max; Seifert, Maria; Wolf, Andreas; Michel, Thilo; Anton, Gisela (Journal of Instrumentation, 2020)
A Talbot-Lau scanner enables fast grating-based X-ray phase-contrast and dark-field imaging of large samples. We present a fast and robust scanning method based on continuous phase-sampling during the usual scan process. For that purpose the source grating is moved back and forth during the whole image acquisition procedure. The scanning method needs no specific detuning of the interferometer. The acquired images are compared to the results of a standard phase-stepping procedure. We show that high quality images are obtained by this continuous phase-sampling scanning method. One main advantage of the method is its independence of the occurring moir'e pattern shape, thus enabling an optimal alignment of the interferometer. Furthermore, the method works with a priori unknown phase-step positions. To our knowledge, this is the first time a grating is moved continuously back and forth while also the sample is in linear motion during a continuous image acquisition in Talbot-Lau imaging.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Data acquisition concepts; Inspection with x-rays; X-ray radiography and digital radiography (DR)

A polarized fast radio burst at low Galactic latitude - Petroff, E.; Burke-Spolaor, S.; Keane, E. F.; Mclaughlin, M. A.; Miller, R.; Andreoni, I.; Bailes, Matthew; Barr, E. D.; Bernard, S. R.; Bhandari, S.; Bhat, N. D. R.; Burgay, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We report on the discovery of a new fast radio burst (FRB), FRB 150215, with the Parkes radio telescope on 2015 February 15. The burst was detected in real time with a dispersion measure (DM) of 1105.6 +/- 0.8 pc cm(-3), a pulse duration of 2.8(-0.5)(+1.2) ms, and a measured peak flux density assuming that the burst was at beam centre of 0.7(-0.1)(+0.2) Jy. The FRB originated at a Galactic longitude and latitude of 24.66 degrees, 5.28 degrees and 25 degrees away from the Galactic Center. The burst was found to be 43 +/- 5 per cent linearly polarized with a rotation measure (RM) in the range -9 < RM < 12 rad m(-2) (95 per cent confidence level), consistent with zero. The burst was followed up with 11 telescopes to search for radio, optical, X-ray, gamma-ray and neutrino emission. Neither transient nor variable emission was found to be associated with the burst and no repeat pulses have been observed in 17.25 h of observing. The sightline to the burst is close to the Galactic plane and the observed physical properties of FRB 150215 demonstrate the existence of sight lines of anomalously low RM for a given electron column density. The Galactic RM foreground may approach a null value due to magnetic field reversals along the line of sight, a decreased total electron column density from the Milky Way, or some combination of these effects. A lower Galactic DM contribution might explain why this burst was detectable whereas previous searches at low latitude have had lower detection rates than those out of the plane.
Keywords: polarization; methods: data analysis; surveys; ISM: structure

A Posterior Analysis on IceCube Double Pulse Tau Neutrino Candidates - Tian, Wei; Zhang, Fuyudi; Xu, Donglian; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; et al. (Proceedings of Science, 2022)
The IceCube Neutrino Observatory at the South Pole detects Cherenkov light emitted by charged secondary particles created by primary neutrino interactions. Double pulse waveforms can arise from charged current interactions of astrophysical tau neutrinos with nucleons in the ice and the subsequent decay of tau leptons. The previous 8-year tau double pulse analysis found three tau neutrino candidate events. Among them, the most promising one observed in 2014 is located very near the dust layer in the middle of the detector. A posterior analysis on this event will be presented in this paper, using a new ice model treatment with continuously varying nuisance parameters to do the targeted Monte Carlo re-simulation for tau and other background neutrino ensembles. The impact of different ice models on the expected signal and background statistics will also be discussed.
CRIS-Team Scopus Importer:2024-12-16

A scintillating fibre detector for the Crystal Barrel experiment at ELSA - Suft, Gabriele; Anton, Gisela; Bogendörfer, Regina; Ehmanns, A.; Fösel, Angela; Hößl, Jürgen; Kalinowsky, H.; Küppersbusch, C. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2005)
A scintillating fibre detector with high spatial granularity was built for the Crystal Barrel experiment at ELSA (CB-ELSA) in Bonn. It consists of 513 scintillating fibres with 2 mm in diameter, arranged in three layers with cylindrical geometry inside the Crystal Barrel detector surrounding the target cell. Two layers are wound in opposite directions, the third is parallel to the incident beam direction, resulting in an unambiguous hit reconstruction and a position resolution better than 1.6 mm for charged particles. The read-out is done with 16-channel multi-anode photomultipliers. The detector was designed to cover the full angular acceptance of the Crystal Barrel detector with an angular range of <span class="formulatext stixSupport mathImg" data-mathurl="/science?_ob=MathURL&_method=retrieve&_eid=1-s2.0-S0168900204021783&_mathId=si12.gif&_user=111111111&_pii=S0168900204021783&_rdoc=1&_issn=01689002&md5=3abfc4cc212dc889dc9d48a2f15ea12a" title="Click to view the MathML source">12∘⩽θ⩽168∘12∘⩽θ⩽168∘ and <span class="formulatext stixSupport mathImg" data-mathurl="/science?_ob=MathURL&_method=retrieve&_eid=1-s2.0-S0168900204021783&_mathId=si13.gif&_user=111111111&_pii=S0168900204021783&_rdoc=1&_issn=01689002&md5=88b4bcd163c291c85497ee8c99b5cda8" title="Click to view the MathML source">0∘⩽φ⩽360∘0∘⩽φ⩽360∘ in the lab frame.

A Search for Cosmic Neutrino and Gamma-Ray Emitting Transients in 7.3 yr of ANTARES and Fermi LAT Data - Solares, H. A. Ayala; Cowen, D. F.; Delaunay, J. J.; Fox, D. B.; Keivani, A.; Mostafa, M.; Murase, K.; Turley, C. F.; Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; et al. (Astrophysical Journal, 2019)
We analyze 7.3 yr of ANTARES high-energy neutrino and Fermi Large Area Telescope (LAT) gamma-ray data in search of cosmic neutrino + gamma-ray (nu + gamma) transient sources or source populations. Our analysis has the potential to detect either individual nu + gamma transient sources (durations delta t less than or similar to 1000 s), if they exhibit sufficient gamma-ray or neutrino multiplicity, or a statistical excess of nu + gamma transients of individually lower multiplicities. Individual high gamma-ray multiplicity events could be produced, for example, by a single ANTARES neutrino in coincidence with a LAT-detected gamma-ray burst. Treating ANTARES track and cascade event types separately, we establish detection thresholds by Monte Carlo scrambling of the neutrino data, and determine our analysis sensitivity by signal injection against these scrambled data sets. We find our analysis is sensitive to nu + gamma transient populations responsible for >5% of the observed gamma-coincident neutrinos in the track data at 90% confidence. Applying our analysis to the unscrambled data reveals no individual nu + gamma events of high significance; two ANTARES track + Fermi gamma-ray events are identified that exceed a once per decade false alarm rate threshold (p = 17%). No evidence for subthreshold nu + gamma source populations is found among the track (p = 39%) or cascade (p = 60%) events. Exploring a possible correlation of high-energy neutrino directions with Fermi gamma-ray sky brightness identified in previous work yields no added support for this correlation. While TXS.0506+056, a blazar and variable (nontransient) Fermi gamma-ray source, has recently been identified as the first source of high-energy neutrinos, the challenges in reconciling observations of the Fermi gamma-ray sky, the IceCube high-energy cosmic neutrinos, and ultrahigh-energy cosmic rays using only blazars suggest a significant contribution by other source populations. Searches for transient sources of high-energy neutrinos thus remain interesting, with the potential for either neutrino clustering or multimessenger coincidence searches to lead to discovery of the first nu + gamma transients.
CRIS-Team WoS Importer:2020-01-03

A Search for IceCube Events in the Direction of ANITA Neutrino Candidates - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Arguëlles, C.; et al. (Astrophysical Journal, 2020)
During the first three flights of the Antarctic Impulsive Transient Antenna (ANITA) experiment, the collaboration detected several neutrino candidates. Two of these candidate events were consistent with an ultra-high-energy upgoing air shower and compatible with a tau neutrino interpretation. A third neutrino candidate event was detected in a search for Askaryan radiation in the Antarctic ice, although it is also consistent with the background expectation. The inferred emergence angle of the first two events is in tension with IceCube and ANITA limits on isotropic cosmogenic neutrino fluxes. Here we test the hypothesis that these events are astrophysical in origin, possibly caused by a point source in the reconstructed direction. Given that any ultra-high-energy tau neutrino flux traversing the Earth should be accompanied by a secondary flux in the TeV-PeV range, we search for these secondary counterparts in 7 yr of IceCube data using three complementary approaches. In the absence of any significant detection, we set upper limits on the neutrino flux from potential point sources. We compare these limits to ANITA's sensitivity in the same direction and show that an astrophysical explanation of these anomalous events under standard model assumptions is severely constrained regardless of source spectrum.
CRIS-Team Scopus Importer:2020-05-15

A search for neutrino emission from the Fermi bubbles with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J; Baret, B.; Barrios-Marti, J.; Basa, S.; et al. (European Physical Journal C, 2014)
Analysis of the Fermi-LAT data has revealed two extended structures above and below the Galactic Centre emitting gamma rays with a hard spectrum, the so-called Fermi bubbles. Hadronic models attempting to explain the origin of the Fermi bubbles predict the emission of high-energy neutrinos and gamma rays with similar fluxes. The ANTARES detector, a neutrino telescope located in the Mediterranean Sea, has a good visibility to the Fermi bubble regions. Using data collected from 2008 to 2011 no statistically significant excess of events is observed and therefore upper limits on the neutrino flux in TeV range from the Fermi bubbles are derived for various assumed energy cutoffs of the source.

A search for neutrino point-source populations in 7 yr of icecube data with neutrino-count statistics - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (Astrophysical Journal, 2020)
The presence of a population of point sources in a data set modifies the underlying neutrino-count statistics from the Poisson distribution. This deviation can be exactly quantified using the non-Poissonian template fitting technique, and in this work we present the first application of this approach to the IceCube high-energy neutrino data set. Using this method, we search in 7 yr of IceCube data for point-source populations correlated with the disk of the Milky Way, the Fermi bubbles, the Schlegel, Finkbeiner, and Davis dust map, or with the isotropic extragalactic sky. No evidence for such a population is found in the data using this technique, and in the absence of a signal, we establish constraints on population models with source-count distribution functions that can be described by a power law with a single break. The derived limits can be interpreted in the context of many possible source classes. In order to enhance the flexibility of the results, we publish the full posterior from our analysis, which can be used to establish limits on specific population models that would contribute to the observed IceCube neutrino flux.
CRIS-Team Scopus Importer:2020-06-02

A Search for Neutrinos from Decaying Dark Matter in Galaxy Clusters and Galaxies with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Proceedings of Science, 2022)
The observed dark matter abundance in the Universe can be explained with non-thermal, heavy dark matter models. In order for dark matter to still be present today, its lifetime has to far exceed the age of the Universe. In these scenarios, dark matter decay can produce highly energetic neutrinos, along with other Standard Model particles. To date, the IceCube Neutrino Observatory is the world’s largest neutrino telescope, located at the geographic South Pole. In 2013, the IceCube collaboration reported the first observation of high-energy astrophysical neutrinos. Since then, IceCube has collected a large amount of astrophysical neutrino data with energies up to tens of PeV, allowing us to probe the heavy dark matter models using neutrinos. We search the IceCube data for neutrinos from decaying dark matter in galaxy clusters and galaxies. The targeted dark matter masses range from 10 TeV to 10 PeV. In this contribution, we present the method and sensitivities of the analysis.
CRIS-Team Scopus Importer:2024-12-16

A Search for Neutrino Sources with Cascade Events in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Proceedings of Science, 2022)
IceCube has discovered a flux of astrophysical neutrinos, and more recently has used muon-neutrino datasets to present evidence for one source; a flaring blazar known as TXS 0506+056. However, the sources responsible for the majority of the astrophysical neutrino flux remain elusive. Opening up new channels for detection can improve sensitivity and increase the discovery potential. In this work we present a new neutrino dataset relying heavily on Deep-Neural-Networks (DNN) to select cascade events produced from neutral-current interactions of all flavors and charged-current interactions with flavors other than muon-neutrino. The speed of DNN processing makes it possible to select events in near realtime with a single GPU. Cascade events have reduced angular resolution when compared to muon-neutrino events, however the resulting dataset has a lower energy threshold in the southern sky and a lower background rate. These benefits lead to an factor of 2-3 improvement in sensitivity to sources in the Southern Sky when compared to muon-neutrino datasets. This dataset is particularly promising for identifying transient neutrino sources in the Southern Sky and neutrino production from the galactic plane.
CRIS-Team Scopus Importer:2024-12-16

A search for Secluded Dark Matter in the Sun with the ANTARES neutrino telescope - Adrián-Martínez, S.; Albert, A.; André, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2016)
A search for Secluded Dark Matter annihilation in the Sun using 2007-2012 data of the ANTARES neutrino telescope is presented. Three different cases are considered: a) detection of dimuons that result from the decay of the mediator, or neutrino detection from: b) mediator that decays into a dimuon and, in turn, into neutrinos, and c) mediator that decays directly into neutrinos. As no significant excess over background is observed, constraints are derived on the dark matter mass and the lifetime of the mediator.
Keywords: dark matter detectors; dark matter experiments; neutrino astronomy; neutrino detectors

Assessment of the additional clinical potential of X-ray dark-field imaging for breast cancer in a preclinical setup - Emons, J.; Fasching, Peter; Wunderle, M.; Heindl, F.; Rieger, Jens; Horn, Florian; Pelzer, Georg; Ritter, André; Weber, Thomas; Radicke, M.; Polifka, Iris; Wachter, David Lukas; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Assessment of the additional clinical potential of X-ray dark-field imaging for breast cancer in a preclinical setup - Emons, Julius; Fasching, Peter; Wunderle, Marius; Heindl, Felix; Rieger, Jens; Horn, Florian; Pelzer, Georg; Ritter, André; Weber, Thomas; Radicke, Marcus; Polifka, Iris; Wachter, David; et al. (Therapeutic Advances in Medical Oncology, 2020)
Background: Mammography can identify calcifications up to 50–100 μm in size as a surrogate parameter for breast cancer or ductal carcinoma in situ (DCIS). Microcalcifications measuring <50 µm are also associated with breast cancer or DCIS and are frequently not detected on mammography, although they can be detected with dark-field imaging. This study examined whether additional breast examination using X-ray dark-field imaging can increase the detection rate of calcifications. Advances in knowledge: (1) evaluation of additional modality of breast imaging; (2) specific evaluation of breast calcifications. Implications for patient care: the addition of X-ray dark-field imaging to conventional mammography could detect additional calcifications. Methods: Talbot–Lau X-ray phase–contrast imaging and X-ray dark-field imaging were used to acquire images of breast specimens. The radiation dosage with the technique is comparable with conventional mammography. Three X-ray gratings with periods of 5–10 µm between the X-ray tube and the flat-panel detector provide three different images in a single sequence: the conventional attenuation image, differential phase image, and dark-field image. The images were read by radiologists. Radiological findings were marked and examined pathologically. The results were described in a descriptive manner. Results: A total of 81 breast specimens were investigated with the two methods; 199 significant structures were processed pathologically, consisting of 123 benign and 76 malignant lesions (DCIS or invasive breast cancer). X-ray dark-field imaging identified 15 additional histologically confirmed carcinoma lesions that were visible but not declared suspicious on digital mammography alone. Another four malignant lesions that were not visible on mammography were exclusively detected with X-ray dark-field imaging. Conclusions: Adding X-ray dark-field imaging to digital mammography increases the detection rate for breast cancer and DCIS associated lesions with micrometer-sized calcifications. The use of X-ray dark-field imaging may be able to provide more accurate and detailed radiological classification of suspicious breast lesions. Adding X-ray dark-field imaging to mammography may be able to increase the detection rate and improve preoperative planning in deciding between mastectomy or breast-conserving therapy, particularly in patients with invasive lobular breast cancer.
CRIS-Team Scopus Importer:2020-09-25
Keywords: breast cancer; interferometry; mammography; microcalcifications

A time-independent search for neutrinos from galaxy clusters with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Proceedings of Science, 2022)
Clusters of galaxies — with their turbulent magnetic fields and abundant matter content — are a promising class of potential neutrino sources. Cosmic rays accelerated within the large-scale shocks, Active Galactic Nuclei (AGN), or both can be confined in galaxy clusters over cosmological timescales and produce a steady flux of neutrinos in secondary interactions. The IceCube Neutrino Observatory has detected a diffuse flux of high-energy astrophysical neutrinos. After ten years of operations, however, the origin of this flux remains largely unconstrained. In this work, we perform a stacked search for neutrinos, using a population of over one thousand galaxy clusters detected by the Planck Satellite via the Sunyaev-Zeldovich (SZ) effect up to a redshift z = 1. We present the first results on the contribution of galaxy clusters to the diffuse neutrino flux and discuss the implications for various models of cosmic-ray acceleration in large-scale structures.
CRIS-Team Scopus Importer:2024-12-16

Auf der Suche nach neuen Energiequellen - Öffentliche Vortragsreihe der Universität Erlangen-Nürnberg - Hosemann, Gerhard; Finckh, Eberhard (Universitätsbund Erlangen, 1982)
UnivIS-Import:2017-12-18:Pub.1982.tech.IE.leen.aufder

Automated 3D Defect Detection based on Simulated Reference - Sukowski, Frank; Suth, Daniel; Waldyra, Adrian; Grulich, Tobias; Jung, Alexander (2023)

Beyond dating: Archeological wood as a source of information of environmental changes in High Asia - Bräuning, Achim; Scharf, Andreas; Kretschmer, Wolfgang; Burchardt, Iris (TRACE - Tree Rings in Archaeology, Climatology and Ecology, Vol. 11: Proceedings of the DENDROSYMPOSIUM 2012 Scientific Technical Report STR13/05, GFZ Potsdam, 2013)

Beyond the null hypothesis: Physics-driven searches for astrophysical neutrino sources - Capel, Francesca; Kuhlmann, Julian; Haack, Christian; Minh, Martin Ha; Niederhausen, Hans; Schumacher, Lisa (Proceedings of Science, 2024)
While there have been multiple reports of potential links between astrophysical sources and high-energy neutrinos, definitively identifying these sources remains challenging. No single result has surpassed the significance threshold for discovery, and the theoretical interpretation of these observations has revealed new questions for the bigger picture of neutrino astrophysics. In response to these difficulties, we propose a novel approach that combines state-of-the-art methods with the wealth of information from multi-messenger observations and theoretical models. Our physics-first strategy utilizes advanced techniques such as Hamiltonian Monte Carlo and hierarchical modelling to navigate the high-dimensional space of parameters and uncertainties in this complex setting. Implementing these methods within a Bayesian framework offers a unique perspective on source discovery while enabling us to avoid pitfalls associated with trial factors. Furthermore, considering source populations provides additional constraints from observations and uncovers further implications from a broader perspective, making the most of the existing high-energy neutrino data. We demonstrate the impact of these methods through application to simulated data, considering relevant multi-messenger scenarios for sources and their populations. Our approach complements existing techniques while offering increased sensitivity and interpretability in the context of investigating specific physical models, potentially accelerating decisive discoveries.
CRIS-Team Scopus Importer:2025-02-04

Characterisation of the Hamamatsu photomultipliers for the KM3NeT Neutrino Telescope - Aiello, S.; Akrame, S. E.; Ameli, F.; Anassontzis, E. G.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Avgitas, T.; Baars, M.; et al. (Journal of Instrumentation, 2018)
The Hamamatsu R12199-023-inch photomultiplier tube is the photodetector chosen for the first phase of the KM3NeT neutrino telescope. About 7000 photomultipliers have been characterised for dark count rate, timing spread and spurious pulses. The quantum efficiency, the gain and the peak-to-valley ratio have also been measured for a sub-sample in order to determine parameter values needed as input to numerical simulations of the detector.
Keywords: Cherenkov detectors; Large detector systems for particle and astroparticle physics; Neutrino detectors; Photon detectors for UV; visible and IR photons (vacuum)

Characteristics of the Diffuse Astrophysical Electron and Tau Neutrino Flux with Six Years of IceCube High Energy Cascade Data - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau,; Anton, Gisela; Arguelles, C.; et al. (Physical Review Letters, 2020)
We report on the first measurement of the astrophysical neutrino flux using particle showers (cascades) in IceCube data from 2010-2015. Assuming standard oscillations, the astrophysical neutrinos in this dedicated cascade sample are dominated (similar to 90%) by electron and tau flavors. The flux, observed in the sensitive energy range from 16 TeV to 2.6 PeV, is consistent with a single power-law model as expected from Fermi-type acceleration of high energy particles at astrophysical sources. We find the flux spectral index to be gamma = 2.53 +/- 0.07 and a flux normalization for each neutrino flavor of phi(astro) = 1.66(-0.27)(+0.25) at E-0 = 100 TeV, in agreement with IceCube's complementary muon neutrino results and with all-neutrino flavor fit results. In the measured energy range we reject spectral indices gamma <= 2.28 at >= 3 sigma significance level. Because of high neutrino energy resolution and low atmospheric neutrino backgrounds, this analysis provides the most detailed characterization of the neutrino flux at energies below similar to 100 TeV compared to previous IceCube results. Results from fits assuming more complex neutrino flux models suggest a flux softening at high energies and a flux hardening at low energies (p value >= 0.06). The sizable and smooth flux measured below similar to 100 TeV remains a puzzle. In order to not violate the isotropic diffuse gamma-ray background as measured by the Fermi Large Area Telescope, it suggests the existence of astrophysical neutrino sources characterized by dense environments which are opaque to gamma rays.
CRIS-Team WoS Importer:2020-10-02

Characterization of a polychromatic microfocus X-ray fluorescence imaging setup with metallic contrast agents in a microphysiological tumor model - Kumar, Kunal; Fachet, Melanie; Al-Maatoq, Marwah; Chakraborty, Amit; Khismatrao, Rahul S.; Oka, Shreyas V.; Staufer, Theresa; Grüner, Florian; Michel, Thilo; Walles, Heike; Hoeschen, Christoph (Frontiers in Physics, 2023)
Introduction: Accurate diagnosis and personalized treatments involving site-targeted cancer localization, drug delivery, therapeutic strategy, and disease pathways identification, rely on a precise understanding of biomarker kinetics, drug pharmacokinetics, and mechanistic behaviour of functionalized tracers through in vitro and in vivo studies. X-ray fluorescence (XRF) computed tomography (XFCT) offers a potential alternative to current 3D imaging techniques for spatiotemporal localization of nanoparticle-tracers with high spatial resolution and sensitivity. In this work, the applicability of a benchtop cone-beam system with a polychromatic X-ray source was examined with regard to physical constraints of engineered tissue models. Methods: A tissue engineering approach based on a decellularized scaffold was used to establish a 3D breast cancer model with MDA-MB-231 cells in co-culture with primary human fibroblasts. The 3D breast cancer system, in combination with small-animal-sized phantoms, was used to demonstrate the novel integrated pre-clinical imaging approach to perform in vitro surrogate investigations and non-destructive analysis on biophantoms. These models are adopted to evaluate the functionality and optimize the setup for high-spatial-resolution, fast, and fully-3D quantitative imaging. Polychromatic X-rays from a microfocus source are used for XRF stimulation from conventional Gadolinium (Gd) and nanoparticle-based Molybdenum (MoNPs) contrast agents. Results and Discussion: The intestinal scaffold allowed the invasion of the breast cancer cells over this barrier and therefore provides a valuable tool to study metastasis formation of tumor cells from epithelial origin. The breast cancer model was well suited for the development and validation of the proposed XRF imaging, with spatial resolution under <2 mm and contrast dose in the order of a few 100 μg/mL (∼0.3 mg/mL for Gd and ∼0.5 mg/mL for MoNPs), radiation dose in the order of a few 100 cGy (280 cGy for Gd and 94 cGy for MoNPs, with a possible reduction of an order of magnitude for Gd and 67% for MoNPs), and imaging time in the order of 10 min for Gd (33 min total) and 100 min (2.8 h total) for MoNPs, approaching in vivo conform conditions for pre-clinical studies. High-resolution XFCT for tissue-engineered cancer models would be of significant interest in biomedical research and diagnostic imaging, e.g., for an increased mechanistic understanding of molecular processes in tumor formation or early cancer detection.
CRIS-Team Scopus Importer:2023-05-19
Keywords: in vitro cancer models; in vivo pharmacokinetics; molecular imaging; nanoparticle contrast agents; tissue engineering; X-ray fluorescence computed tomography

Characterization of the astrophysical diffuse neutrino flux using starting track events in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Physical Review D, 2024)
A measurement of the diffuse astrophysical neutrino spectrum is presented using IceCube data collected from 2011-2022 (10.3 years). We developed novel detection techniques to search for events with a contained vertex and exiting track induced by muon neutrinos undergoing a charged-current interaction. Searching for these starting track events allows us to not only more effectively reject atmospheric muons but also atmospheric neutrino backgrounds in the southern sky, opening a new window to the sub-100 TeV astrophysical neutrino sky. The event selection is constructed using a dynamic starting track veto and machine learning algorithms. We use this data to measure the astrophysical diffuse flux as a single power law flux (SPL) with a best-fit spectral index of γ=2.58-0.09+0.10 and per-flavor normalization of φper-flavorAstro=1.68-0.22+0.19×10-18×GeV-1 cm-2 s-1 sr-1 (at 100 TeV). The sensitive energy range for this dataset is 3-550 TeV under the SPL assumption. This data was also used to measure the flux under a broken power law, however we did not find any evidence of a low energy cutoff.
CRIS-Team Scopus Importer:2024-07-19

Characterization of the Hamamatsu VUV4 MPPCs for nEXO - Gallina, G.; Giampa, P.; Retière, F.; Kroeger, J.; Zhang, G.; Ward, M.; Margetak, P.; Li, G.; Tsang, T.; Doria, L.; Al Kharusi, S.; Alfaris, M.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
In this paper we report on the characterization of the Hamamatsu VUV4 (S/N: S13370-6152) Vacuum Ultra-Violet (VUV) sensitive Multi-Pixel Photon Counters (MPPC)s as part of the development of a solution for the detection of liquid xenon scintillation light for the nEXO experiment. Various MPPC features, such as: dark noise, gain, correlated avalanches, direct crosstalk and Photon Detection Efficiency (PDE) were measured in a dedicated setup at TRIUMF. MPPCs were characterized in the range 163K≤T≤233K. At an over voltage of 3.1±0.2 V and at T=163K we report a number of Correlated Avalanches (CAs) per pulse in the 1μs interval following the trigger pulse of 0.161±0.005. At the same settings the Dark-Noise (DN) rate is 0.137±0.002Hz/mm2. Both the number of CAs and the DN rate are within nEXO specifications. The PDE of the Hamamatsu VUV4 was measured for two different devices at T=233K for a mean wavelength of 189±7nm. At 3.6±0.2 V and 3.5±0.2 V of over voltage we report a PDE of 13.4±2.6% and 11±2%, corresponding to a saturation PDE of 14.8±2.8% and 12.2±2.3%, respectively. Both values are well below the 24% saturation PDE advertised by Hamamatsu. More generally, the second device tested at 3.5±0.2 V of over voltage is below the nEXO PDE requirement. The first one instead yields a PDE that is marginally close to meeting the nEXO specifications. This suggests that with modest improvements the Hamamatsu VUV4 MPPCs could be considered as an alternative to the FBK-LF Silicon Photo-Multipliers for the final design of the nEXO detector.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Hamamatsu; MPPCs; nEXO; PDE; SiPMs; VUV4

Characterization of the PeV astrophysical neutrino energy spectrum with IceCube using down-going tracks - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Proceedings of Science, 2022)
The IceCube Neutrino Observatory has observed a diffuse flux of astrophysical neutrinos with energies from TeV to a few PeV. Recent IceCube analyses have limited sensitivity to PeV neutrinos because upward-going neutrino fluxes are attenuated by the Earth while the Extremely High Energy (EHE) result targets cosmogenic neutrinos only above 10 PeV. In this work, we present a new event selection that fills the gap between 1 PeV and 10 PeV. This sample is obtained by selecting high-energy down-going through-going tracks from 8 years of data. To reduce the atmospheric muon backgrounds and achieve a high signal-to-background ratio, we combine two techniques. The first technique selects events with high stochasticity because single muons created by neutrinos lose energy more stochastically than atmospheric muon bundles whose energy losses are smoothened due to large muon multiplicities. The second technique uses the IceTop surface array as a veto of atmospheric background events. To characterize the astrophysical neutrino flux and test the existence of a cut-off in the neutrino energy spectrum at a few PeV, a global fit will be performed by combining this sample with results from the 7-year High Energy Starting Events (HESE) analysis.
CRIS-Team Scopus Importer:2024-12-16

Characterizing the γ-ray long-term variability of PKS 2155 - 304 with H.E.S.S. and Fermi-LAT - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Astronomy & Astrophysics, 2017)
Studying the temporal variability of BL Lac objects at the highest energies provides unique insights into the extreme physical processes occurring in relativistic jets and in the vicinity of super-massive black holes. To this end, the long-term variability of the BL Lac object PKS 2155 304 is analyzed in the high (HE, 100MeV < E < 300 GeV) and very high energy (VHE, E > 200 GeV) gamma-ray domain. Over the course of similar to 9 yr of H. E. S. S. observations the VHE light curve in the quiescent state is consistent with a log-normal behavior. The VHE variability in this state is well described by flicker noise (power-spectral-density index beta(VHE) = 1 .10(+ 0 : 10) (0 : 13)) on timescales larger than one day. An analysis of similar to 5.5 yr of HE Fermi-LAT data gives consistent results (beta(HE) = 1 : 20(+ 0 : 21) (0 : 23), on timescales larger than 10 days) compatible with the VHE findings. The HE and VHE power spectral densities show a scale invariance across the probed time ranges. A direct linear correlation between the VHE and HE fluxes could neither be excluded nor firmly established. These long-term-variability properties are discussed and compared to the red noise behavior (beta similar to 2) seen on shorter timescales during VHE-flaring states. The difference in power spectral noise behavior at VHE energies during quiescent and flaring states provides evidence that these states are influenced by different physical processes, while the compatibility of the HE and VHE long-term results is suggestive of a common physical link as it might be introduced by an underlying jet-disk connection.
Keywords: BL Lacertae objects: individual: PKS 2155-304; Galaxies: active; Galaxies: jets; Galaxies: nuclei; Gamma rays: galaxies; Radiation mechanisms: non-thermal

Citizen science for IceCube: Name that Neutrino - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (European Physical Journal Plus, 2024)
Name that Neutrino is a citizen science project where volunteers aid in classification of events for the IceCube Neutrino Observatory, an immense particle detector at the geographic South Pole. From March 2023 to September 2023, volunteers did classifications of videos produced from simulated data of both neutrino signal and background interactions. Name that Neutrino obtained more than 128,000 classifications by over 1800 registered volunteers that were compared to results obtained by a deep neural network machine-learning algorithm. Possible improvements for both Name that Neutrino and the deep neural network are discussed.
CRIS-Team Scopus Importer:2024-06-28

Coincidence of a high-fluence blazar outburst with a PeV-energy neutrino event - Kadler, Matthias; Krauss, Felicia; Mannheim, K.; Ojha, R.; Mueller, C.; Schulz, R.; Anton, Gisela; Baumgartner, W.; Beuchert, T.; Buson, S.; Carpenter, B.; Eberl, Thomas; et al. (Nature Physics, 2016)
The astrophysical sources of the extraterrestrial, very high-energy neutrinos detected by the IceCube collaboration remain to be identified. Gamma-ray (3-ray) blazars have been predicted to yield a cumulative neutrino signal exceeding the atmospheric background above energies of 100 TeV, assuming that both the neutrinos and the 3-ray photons are produced by accelerated protons in relativistic jets. As the background spectrum falls steeply with increasing energy, the individual events with the clearest signature of being of extraterrestrial origin are those at petaelectronvolt energies. Inside the large positional-uncertainty fields of the first two petaelectronvolt neutrinos detected by IceCube, the integrated emission of the blazar population has a sufficiently high electromagnetic flux to explain the detected IceCube events, but fluences of individual objects are too low to make an unambiguous source association. Here, we report that a major outburst of the blazar PKS B1424-418 occurred in temporal and positional coincidence with a third petaelectronvolt-energy neutrino event (HESE-35) detected by IceCube. On the basis of an analysis of the full sample of 3-ray blazars in the HESE-35 field, we show that the long-term average 3-ray emission of blazars as a class is in agreement with both the measured all-sky flux of petaelectronvolt neutrinos and the spectral slope of the IceCube signal. The outburst of PKS B1424-418 provides an energy output high enough to explain the observed petaelectronvolt event, suggestive of a direct physical association.

Combined search for neutrinos from dark matter self-annihilation in the Galactic Center with ANTARES and IceCube - Albert, A.; Andre, M.; Domi, Alba; Anghinolfi, M.; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin,; Biagi, Simone; et al. (Physical Review D, 2020)
We present the results of the first combined dark matter search targeting the Galactic Center using the ANTARES and IceCube neutrino telescopes. For dark matter particles with masses from 50 to 1000 GeV, the sensitivities on the self-annihilation cross section set by ANTARES and IceCube are comparable, making this mass range particularly interesting for a joint analysis. Dark matter self-annihilation through the tau(+)tau(-) , mu(+)mu(-) , b (b) over bar, and W+W- channels is considered for both the Navarro-Frenk-White and Burkert halo profiles. In the combination of 2101.6 days of ANTARES data and 1007 days of IceCube data, no excess over the expected background is observed. Limits on the thermally averaged dark matter annihilation cross section are set. These limits present an improvement of up to a factor of 2 in the studied dark matter mass range with respect to the individual limits published by both collaborations. When considering dark matter particles with a mass of 200 GeV annihilating through the tau(+)tau(-)channel, the value obtained for the limit is 7.44 x 10(-24) cm(3) s(-1 )for the Navarro-Frenk-White halo profile. For the purpose of this joint analysis, the model parameters and the likelihood are unified, providing a benchmark for forthcoming dark matter searches performed by neutrino telescopes.
CRIS-Team WoS Importer:2020-11-13

Combining Maximum-Likelihood with Deep Learning for Event Reconstruction in IceCube - Hünnefeld, Mirco; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
The field of deep learning has become increasingly important for particle physics experiments, yielding a multitude of advances, predominantly in event classification and reconstruction tasks. Many of these applications have been adopted from other domains. However, data in the field of physics are unique in the context of machine learning, insofar as their generation process and the laws and symmetries they abide by are usually well understood. Most commonly used deep learning architectures fail at utilizing this available information. In contrast, more traditional likelihood-based methods are capable of exploiting domain knowledge, but they are often limited by computational complexity. In this contribution, a hybrid approach is presented that utilizes generative neural networks to approximate the likelihood, which may then be used in a traditional maximum-likelihood setting. Domain knowledge, such as invariances and detector characteristics, can easily be incorporated in this approach. The hybrid approach is illustrated by the example of event reconstruction in IceCube.
CRIS-Team Scopus Importer:2024-12-16

Comparing different approaches for stellar intensity interferometry - Karl, Sebastian; Zmija, Andreas; Richter, Stefan; Vogel, Naomi; Malyshev, Dmitry; Zink, Adrian; Michel, Thilo; Anton, Gisela; von Zanthier, Joachim; Funk, Stefan (Monthly Notices of the Royal Astronomical Society, 2022)
Stellar intensity interferometers correlate photons within their coherence time and could overcome the baseline limitations of existing amplitude interferometers. Intensity interferometers do not rely on phase coherence of the optical elements and thus function without high-grade optics and light combining delay lines. However, the coherence time of starlight observed with realistic optical filter bandwidths (> 0.1 nm) is usually much smaller than the time resolution of the detection system (> 10 ps), resulting in a greatly reduced correlation signal. Reaching high signal-to-noise ratio in a reasonably short measurement time can be achieved in different ways: either by increasing the time resolution, which increases the correlation signal height, or by increasing the photon rate, which decreases statistical uncertainties of the measurement. We present laboratory measurements employing both approaches and directly compare them in terms of signal-to-noise ratio. A high-time-resolution interferometry setup designed for small-to-intermediate-sized optical telescopes and thus lower photon rates (diameters < some metres) is compared to a setup capable of measuring high photon rates, which is planned to be installed at Cherenkov telescopes with dish diameters of > 10 m. We use a xenon lamp as a common light source simulating starlight. Both setups measure the expected correlation signal and work at the expected shot-noise limit of statistical uncertainties for measurement times between 10 min and 23 h. We discuss the quantitative differences in the measurement results and give an overview of suitable operation regimes for each of the interferometer concepts.
CRIS-Team WoS Importer:2022-04-08
Keywords: instrumentation: high angular resolution; instrumentation: interferometers; telescopes; stars: imaging

Completing Aganta Kairos: Capturing Metaphysical Time on the Seventh Continent - Madsen, Jim; Mulot, Laurent; Spiering, Christian; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; et al. (Proceedings of Science, 2022)
We present an overview of the art project Aganta Kairos (To Fish the Metaphysical Time). This project celebrates the neutrino-the ghost particle-which scientists consider a cosmic messenger and the artist regards as a link between people who care about their relationship to the cosmos and question their origins. The artwork is based on a performance of celebration and seeks to build a human community that encompasses different knowledge domains and interpretations of the universe. This intersection of knowledge is realized during the performance of placing a plaque, held with witnesses, and during subsequent exhibitions. Images, sounds, videos, and sculpture testify to the diversity of approaches to questioning our origins, ranging from traditional western science to ancient shamanism. The sites were selected for their global coverage and, for the South Pole, Mediterranean, and Lake Baikal, their connection to ongoing neutrino experiments. In December 2020, a plaque was installed at the South Pole IceCube Laboratory, the seventh and final site. We provide examples of images and links to additional images and videos.
CRIS-Team Scopus Importer:2024-12-16

Computational techniques for the analysis of small signals in high-statistics neutrino oscillation experiments - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2020)
The current and upcoming generation of Very Large Volume Neutrino Telescopes – collecting unprecedented quantities of neutrino events – can be used to explore subtle effects in oscillation physics, such as (but not restricted to) the neutrino mass ordering. The sensitivity of an experiment to these effects can be estimated from Monte Carlo simulations. With the high number of events that will be collected, there is a trade-off between the computational expense of running such simulations and the inherent statistical uncertainty in the determined values. In such a scenario, it becomes impractical to produce and use adequately-sized sets of simulated events with traditional methods, such as Monte Carlo weighting. In this work we present a staged approach to the generation of expected distributions of observables in order to overcome these challenges. By combining multiple integration and smoothing techniques which address limited statistics from simulation it arrives at reliable analysis results using modest computational resources.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Data analysis; Detector; KDE; MC; Monte Carlo; Neutrino; Neutrino mass ordering; Smoothing; Statistics; VLVνT

Concept Study of a Radio Array Embedded in a Deep Gen2-like Optical Array - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
The IceCube Neutrino Observatory has discovered a diffuse astrophysical flux up to 10 PeV and is now planning a large extension with IceCube-Gen2, including an optical array and a large radio array at shallow depth [1]. Neutrino searches for energies >100 PeV are best done with such shallow radio detectors like the Askaryan Radio Array (ARA) or similar (buried as deep as 200 meters below the surface) as they are cheaper to deploy. This poster explores the potential of opportunistically burying radio antennas within the planned IceCube-Gen2 detector volume (between 1350 meters and 2600 meters below the surface). A hybrid detection of events in optical and radio could substantially improve the uncertainty of neutrino cascade direction as radio signals do not scatter in ice. We show the first results of simulating neutrinos from an astrophysical and a cosmogenic flux interacting with 9760 ARA-style vertically polarized radio antennas distributed evenly across 122 strings.
CRIS-Team Scopus Importer:2023-08-15

Constraining Non-Standard Dark Matter-Nucleon Interactions with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Proceedings of Science, 2022)
After scattering off nuclei in the Sun, dark matter particles can be gravitationally captured by the Sun, accumulate in the Sun’s core and annihilate into Standard Model particles. Neutrinos originating from these annihilations can be detected by the IceCube Neutrino Observatory, located at the South Pole. Due to the non-observation of these neutrinos, constraints on the standard spin-dependent and spin-independent dark matter-nucleon scattering cross sections have been placed. Based on these constraints, we present upper limits on the coupling constants of the non-relativistic effective theory of dark matter-nucleon interactions, including velocity and momentum dependent interactions.
CRIS-Team Scopus Importer:2024-12-16

Constraining the contribution of Gamma-Ray Bursts to the high-energy diffuse neutrino flux with 10 yr of ANTARES data - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin,; Biagi, S.; et al. (Monthly Notices of the Royal Astronomical Society, 2021)
Addressing the origin of the astrophysical neutrino flux observed by IceCube is of paramount importance. Gamma-Ray Bursts (GRBs) are among the few astrophysical sources capable of achieving the required energy to contribute to such neutrino flux through p gamma interactions. In this work, ANTARFS data have been used to search for upward going muon neutrinos in spatial and temporal coincidence with 784 GRBs occurred from 2007 to 2017. For each GRB, the expected neutrino flux has been calculated in the framework of the internal shock model and the impact of the lack of knowledge on the majority of source redshifts and on other intrinsic parameters of the emission mechanism has been quantified. It is found that the model parameters that set the radial distance where shock collisions occur have the largest impact on neutrino flux expectations. In particular, the bulk Lorentz factor of the source ejecta and the minimum variability time-scale are found to contribute significantly to the GRB-neutrino flux uncertainty. For the selected sources, ANTARES data have been analysed by maximizing the discovery probability of the stacking sample through an extended maximum-likelihood strategy. Since no neutrino event passed the quality cuts set by the optimization procedure, 90 per cent confidence level upper limits (with their uncertainty) on the total expected diffuse neutrino flux have been derived, according to the model. The GRB contribution to the observed diffuse astrophysical neutrino flux around 100 TeV is constrained to be less than 10 percent.
CRIS-Team WoS Importer:2021-01-29

Constraining the neutrino emission of gravitationally lensed Flat-Spectrum Radio Quasars with ANTARES data - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagii, S.; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2014)
This paper proposes to exploit gravitational lensing effects to improve the sensitivity of neutrino telescopes to the intrinsic neutrino emission of distant blazar populations. This strategy is illustrated with a search for cosmic neutrinos in the direction of four distant and gravitationally lensed Flat-Spectrum Radio Quasars. The magnification factor is estimated for each system assuming a singular isothermal profile for the lens. Based on data collected from 2007 to 2012 by the ANTARES neutrino telescope, the strongest constraint is obtained from the lensed quasar B0218+357, providing a limit on the total neutrino luminosity of this source of 1.08 x 10(46) erg s(-1) This limit is about one order of magnitude lower than those previously obtained in the ANTARES standard point source searches with non-lensed Flat-Spectrum Radio Quasars.
Keywords: gravitational lensing; neutrino astronomy

Constraints on an annihilation signal from a core of constant dark matter density around the milky way center with H.E.S.S. - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Physical Review Letters, 2015)

Constraints on axionlike particles with H.E.S.S. from the irregularity of the PKS 2155-304 energy spectrum - Abramowski, A.; Acero, F.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2013)
Axionlike particles (ALPs) are hypothetical light (sub-eV) bosons predicted in some extensions of the Standard Model of particle physics. In astrophysical environments comprising high-energy gamma rays and turbulent magnetic fields, the existence of ALPs can modify the energy spectrum of the gamma rays for a sufficiently large coupling between ALPs and photons. This modification would take the form of an irregular behavior of the energy spectrum in a limited energy range. Data from the H.E.S.S. observations of the distant BL Lac object PKS 2155-304 (z=0.116) are used to derive upper limits at the 95% C.L. on the strength of the ALP coupling to photons, g<2. 1×1011 GeV1 for an ALP mass between 15 and 60 neV. The results depend on assumptions on the magnetic field around the source, which are chosen conservatively. The derived constraints apply to both light pseudoscalar and scalar bosons that couple to the electromagnetic field. © 2013 American Physical Society.

Constraints on Minute-Scale Transient Astrophysical Neutrino Sources - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Al Samarai, I.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; et al. (Physical Review Letters, 2019)
High-energy neutrino emission has been predicted for several short-lived astrophysical transients including gamma-ray bursts (GRBs), core-collapse supernovae with choked jets, and neutron star mergers. IceCube's optical and x-ray follow-up program searches for such transient sources by looking for two or more muon neutrino candidates in directional coincidence and arriving within 100 s. The measured rate of neutrino alerts is consistent with the expected rate of chance coincidences of atmospheric background events and no likely electromagnetic counterparts have been identified in Swift follow-up observations. Here, we calculate generic bounds on the neutrino flux of short-lived transient sources. Assuming an E-2.5 neutrino spectrum, we find that the neutrino flux of rare sources, like long gamma-ray bursts, is constrained to < 5% of the detected astrophysical flux and the energy released in neutrinos (100 GeV to 10 PeV) by a median bright GRB-like source is < 10(52.5) erg. For a harder E-2.13 neutrino spectrum up to 30% of the flux could be produced by GRBs and the allowed median source energy is < 10(52) erg. A hypothetical population of transient sources has to be more common than 10(-5) Mpc(-3) yr(-1) (5 x 10(-8) Mpc(-3) yr(-1) for the E-2.13 spectrum) to account for the complete astrophysical neutrino flux.
CRIS-Team WoS Importer:2019-02-21

Constraints on particle acceleration in SS433/W50 from MAGIC and HESS observations - Ahnen, M. L.; Ansoldi, S.; Antonelli, L. A.; Arcaro, C.; Babie, A.; Banerjee, Biswajit; Bangale, P.; De Almeida, U. Barres; Barrio, J. A.; Gonzalez, J. Becerra; Bednarek, W.; Bernardini, Elisa; et al. (Astronomy & Astrophysics, 2018)
Context. The large jet kinetic power and non-thermal processes occurring in the microquasar SS 433 make this source a good candidate for a very high-energy (VHE) gamma-ray emitter. Gamma-ray fluxes above the sensitivity limits of current Cherenkov telescopes have been predicted for both the central X-ray binary system and the interaction regions of SS 433 jets with the surrounding W50 nebula. Non-thermal emission at lower energies has been previously reported, indicating that efficient particle acceleration is taking place in the system.
CRIS-Team WoS Importer:2020-01-15
Keywords: X-rays: binaries; Gamma rays: general; ISM: jets and outflows; Stars: black holes

Constraints on Populations of Neutrino Sources from Searches in the Directions of IceCube Neutrino Alerts - Abbasi, R.; Ackermann, M.; Adams, J.; Aggarwal, N.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Anton, Gisela; et al. (Astrophysical Journal, 2023)
Beginning in 2016, the IceCube Neutrino Observatory has sent out alerts in real time containing the information of high-energy (E ≳ 100 TeV) neutrino candidate events with moderate to high (≳30%) probability of astrophysical origin. In this work, we use a recent catalog of such alert events, which, in addition to events announced in real time, includes events that were identified retroactively and covers the time period of 2011-2020. We also search for additional, lower-energy neutrinos from the arrival directions of these IceCube alerts. We show how performing such an analysis can constrain the contribution of rare populations of cosmic neutrino sources to the diffuse astrophysical neutrino flux. After searching for neutrino emission coincident with these alert events on various timescales, we find no significant evidence of either minute-scale or day-scale transient neutrino emission or of steady neutrino emission in the direction of these alert events. This study also shows how numerous a population of neutrino sources has to be to account for the complete astrophysical neutrino flux. Assuming that sources have the same luminosity, an E −2.5 neutrino spectrum, and number densities that follow star formation rates, the population of sources has to be more numerous than 7 × 10−9 Mpc−3. This number changes to 3 × 10−7 Mpc−3 if number densities instead have no cosmic evolution.
CRIS-Team Scopus Importer:2023-07-21

Constraints on the gamma-ray emission from the cluster-scale AGN outburst in the Hydra A galaxy cluster - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2012)
Context. In some galaxy clusters, powerful active galactic nuclei (AGN) have blown bubbles with cluster scale extent into the ambient medium. The main pressure support of these bubbles is not known to date, but cosmic rays are a viable possibility. For such a scenario copious gamma-ray emission is expected as a tracer of cosmic rays from these systems. Aims. Hydra A, the closest galaxy cluster hosting a cluster scale AGN outburst, located at a redshift of 0.0538, is investigated for being a gamma-ray emitter with the High Energy Stereoscopic System (H.E.S.S.) array and the Fermi Large Area Telescope (Fermi-LAT). Methods. Data obtained in 20.2 h of dedicated H.E.S.S. observations and 38 months of Fermi-LAT data, gathered by its usual all-sky scanning mode, have been analyzed to search for a gamma-ray signal. Results. No signal has been found in either data set. Upper limits on the gamma-ray flux are derived and are compared to models. These are the first limits on gamma-ray emission ever presented for galaxy clusters hosting cluster scale AGN outbursts. Conclusions. The non-detection of Hydra A in gamma-rays has important implications on the particle populations and physical conditions inside the bubbles in this system. For the case of bubbles mainly supported by hadronic cosmic rays, the most favorable scenario, which involves full mixing between cosmic rays and embedding medium, can be excluded. However, hadronic cosmic rays still remain a viable pressure support agent to sustain the bubbles against the thermal pressure of the ambient medium. The largest population of highly-energetic electrons, which are relevant for inverse-Compton gamma-ray production is found in the youngest inner lobes of Hydra A. The limit on the inverse-Compton gamma-ray flux excludes a magnetic field below half of the equipartition value of 16 μG in the inner lobes. © 2012 ESO.
Keywords: Galaxies: active; Galaxies: clusters: individual: Hydra A; Gamma rays: galaxies: clusters

Constraints on the multi-TeV particle population in the Coma galaxy cluster with HESS observations - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Brion, E.; et al. (Astronomy & Astrophysics, 2009)
Alms. Galaxy clusters are key targets in the search for ultra high energy particle accelerators. The Coma cluster represents one of the best candidates for such a search owing to its high mass, proximity, and the established non-thermal radio emission centred on the cluster core. Methods. The HESS (High Energy Stereoscopic System) telescopes observed Coma for ∼8 h in a search for γ-ray emission at energies >1 TeV. The large 3.5° FWHM field of view of HESS is ideal for viewing a range of targets at various sizes including the Coma cluster core, the radio-relic (1253+275) and merger/infall (NGC 4839) regions to the southwest, and features greater than 1° away. Results. No evidence for point-like nor extended TeV γ-ray emission was found and upper limits to the TeV flux F(E) for E > 1, >5, and > 10 TeV were set for the Coma core and other regions. Converting these limits to an energy flux E F(E) the lowest or most constraining is the E > 5 TeV upper limit for the Coma core (0.2° radius) at ∼8% Crab flux units or ∼10 ph cm s . Conclusions. The upper limits for the Coma core were compared with a prediction for the γ-ray emission from proton-proton interactions, the level of which ultimately scales with the mass of the Coma cluster. A direct constraint using our most stringent limit for E > 5 TeV, on the total energy content in non-thermal protons with injection energy spectrum αE and spatial distribution following the thermal gas in the cluster, is found to be ∼0.2 times the thermal energy, or ∼10 erg. The E > 5 TeV γ-ray threshold in this case corresponds to cosmic- ray proton energies ≳50 TeV. Our upper limits rule out the most optimistic theoretical models for gamma ray emission from clusters and complement radio observations which constrain the cosmic ray content in clusters at significantly lower proton energies, subject to assumptions on the magnetic field strength. ©ESO 2009.
Keywords: Galaxies: Clusters: Individual: Coma (ACO 1656); Gamma rays: Observations

Constraints on the neutrino emission from the Galactic Ridge with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; et al. (Physics Letters B, 2016)
A highly significant excess of high-energy astrophysical neutrinos has been reported by the IceCube Collaboration. Some features of the energy and declination distributions of IceCube events hint at a North/South asymmetry of the neutrino flux. This could be due to the presence of the bulk of our Galaxy in the Southern hemisphere. The ANTARES neutrino telescope, located in the Mediterranean Sea, has been taking data since 2007. It offers the best sensitivity to muon neutrinos produced by galactic cosmic ray interactions in this region of the sky. In this letter a search for an extended neutrino flux from the Galactic Ridge region is presented. Different models of neutrino production by cosmic ray propagation are tested. No excess of events is observed and upper limits for different neutrino flux spectral indices Γ are set. For Γ=2.4 the 90% confidence level flux upper limit at 100 TeV for one neutrino flavour corresponds to Φ (100 TeV)=2.0⋅10 GeVcmssr. Under this assumption, at most two events of the IceCube cosmic candidates can originate from the Galactic Ridge. A simple power-law extrapolation of the Fermi-LAT flux to account for IceCube High Energy Starting Events is excluded at 90% confidence level.
Keywords: ANTARES; Diffuse muon neutrino flux; Neutrino telescope

Cosmic ray spectrum and composition from PeV to EeV using 3 years of data from IceTop and IceCube - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau,; Anton, Gisela; Arguelles, C.; et al. (Physical Review D, 2019)
We report on measurements of the all-particle cosmic ray energy spectrum and composition in the PeV to EeV energy range using 3 years of data from the IceCube Neutrino Observatory. The IceTop detector measures cosmic ray induced air showers on the surface of the ice, from which the energy spectrum of cosmic rays is determined by making additional assumptions about the mass composition. A separate measurement is performed when IceTop data are analyzed in coincidence with the high-energy muon energy loss information from the deep in-ice IceCube detector. In this measurement, both the spectrum and the mass composition of the primary cosmic rays are simultaneously reconstructed using a neural network trained on observables from both detectors. The performance and relative advantages of these two distinct analyses are discussed, including the systematic uncertainties and the dependence on the hadronic interaction models, and both all-particle spectra as well as individual spectra for elemental groups are presented.
CRIS-Team WoS Importer:2019-11-05

Data-based evaluation of direction reconstruction for IceCube cascade events by utilizing starting tracks - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
The IceCube Neutrino Observatory instruments a cubic-kilometer of glacial ice and has been the first experiment to identify high-energy astrophysical neutrinos. There are two main morphologies of IceCube events: tracks and cascades. Tracks result from muons, while cascades result from particle showers induced by in-ice interactions. The directional reconstruction of cascades is less precise than that of tracks, which limits the sensitivity of astrophysical neutrino analyses with cascade events. In order to improve the directional reconstruction of cascade events, accurate ice modeling is essential. However, potential biases might exist in data stemming from unconstrained systematic uncertainties. In this work, feasibility studies to better understand the ice using a data-driven approach are performed, where photons that are likely to have been induced by the hadronic cascade part of muon neutrino charged-current interactions are categorized using probability density functions in time, distance and angle, and the reconstructed direction with this pseudo-cascade is compared with the track direction. In this proceedings, methodology and results are detailed and a path towards better understanding of the ice is discussed.
CRIS-Team Scopus Importer:2025-02-04

Deep learning reconstruction in ANTARES - García-Méndez, J.; Geißelbrecht, Nicole; Eberl, Thomas; Ardid, M.; Ardid, S. (Journal of Instrumentation, 2021)
ANTARES is currently the largest undersea neutrino telescope, located in the Mediterranean Sea and taking data since 2007. It consists of a 3D array of photo sensors, instrumenting about 10Mt of seawater to detect Cherenkov light induced by secondary particles from neutrino interactions. The event reconstruction and background discrimination is challenging and machine-learning techniques are explored to improve the performance. In this contribution, two case studies using deep convolutional neural networks are presented. In the first one, this approach is used to improve the direction reconstruction of low-energy single-line events, for which the reconstruction of the azimuth angle of the incoming neutrino is particularly difficult. We observe a promising improvement in resolution over classical reconstruction techniques and expect to at least double our sensitivity in the low-energy range, important for dark matter searches. The second study employs deep learning to reconstruct the visible energy of neutrino interactions of all flavors and for the multi-line setup of the full detector.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Analysis and statistical methods; Data processing methods; Neutrino detectors; Pattern recognition; cluster finding; calibration and fitting methods

Deep-Sea Bioluminescence Blooms after Dense Water Formation at the Ocean Surface - Tamburini, Christian; Canals, Miquel; Houpert, Loic; Lefevre, Dominique; Martini, Verine; D'Ortenzio, Fabrizio; Robert, Anne; Testor, Pierre; Aguilar, Juan Antonio; Al Samarai, Imen; Albert, Arnaud; Andre, Michel; et al. (PLoS ONE, 2013)
The deep ocean is the largest and least known ecosystem on Earth. It hosts numerous pelagic organisms, most of which are able to emit light. Here we present a unique data set consisting of a 2.5-year long record of light emission by deep-sea pelagic organisms, measured from December 2007 to June 2010 at the ANTARES underwater neutrino telescope in the deep NW Mediterranean Sea, jointly with synchronous hydrological records. This is the longest continuous time-series of deep-sea bioluminescence ever recorded. Our record reveals several weeks long, seasonal bioluminescence blooms with light intensity up to two orders of magnitude higher than background values, which correlate to changes in the properties of deep waters. Such changes are triggered by the winter cooling and evaporation experienced by the upper ocean layer in the Gulf of Lion that leads to the formation and subsequent sinking of dense water through a process known as "open-sea convection". It episodically renews the deep water of the study area and conveys fresh organic matter that fuels the deep ecosystems. Luminous bacteria most likely are the main contributors to the observed deep-sea bioluminescence blooms. Our observations demonstrate a consistent and rapid connection between deep open-sea convection and bathypelagic biological activity, as expressed by bioluminescence. In a setting where dense water formation events are likely to decline under global warming scenarios enhancing ocean stratification, in situ observatories become essential as environmental sentinels for the monitoring and understanding of deep-sea ecosystem shifts.

Deep-sea deployment of the KM3NeT neutrino telescope detection units by self-unrolling - Aiello, S.; Domi, Alba; Albert, A.; Garre, S. Alves; Aly, Z.; Ameli, F.; Anassontzis, E.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; et al. (Journal of Instrumentation, 2020)
KM3NeT is a research infrastructure being installed in the deep Mediterranean Sea. It will house a neutrino telescope comprising hundreds of networked moorings - detection units or strings - equipped with optical instrumentation to detect the Cherenkov radiation generated by charged particles from neutrino-induced collisions in its vicinity. In comparison to moorings typically used for oceanography, several key features of the KM3NeT string are different: the instrumentation is contained in transparent and thus unprotected glass spheres; two thin Dyneema (R) ropes are used as strength members; and a thin delicate backbone tube with fibre-optics and copper wires for data and power transmission, respectively, runs along the full length of the mooring. Also, compared to other neutrino telescopes such as ANTARES in the Mediterranean Sea and GVD in Lake Baikal, the KM3NeT strings are more slender to minimise the amount of material used for support of the optical sensors. Moreover, the rate of deploying a large number of strings in a period of a few years is unprecedented. For all these reasons, for the installation of the KM3NeT strings, a custom-made, fast deployment method was designed. Despite the length of several hundreds of metres, the slim design of the string allows it to be compacted into a small, re-usable spherical launching vehicle instead of deploying the mooring weight down from a surface vessel. After being lowered to the seafloor, the string unfurls to its full length with the buoyant launching vehicle rolling along the two ropes. The design of the vehicle, the loading with a string, and its underwater self-unrolling are detailed in this paper.
CRIS-Team WoS Importer:2020-12-18

Deep sea tests of a prototype of the KM3NeT digital optical module - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; De Asmundis, R.; et al. (European Physical Journal C, 2014)
The first prototype of a photo-detection unit of the future KM3NeT neutrino telescope has been deployed in the deepwaters of the Mediterranean Sea. This digital optical module has a novel design with a very large photocathode area segmented by the use of 31 three inch photomultiplier tubes. It has been integrated in the ANTARES detector for in-situ testing and validation. This paper reports on the first months of data taking and rate measurements. The analysis results highlight the capabilities of the new module design in terms of background suppression and signal recognition. The directionality of the optical module enables the recognition of multiple Cherenkov photons from the same (40)Kdecay and the localisation of bioluminescent activity in the neighbourhood. The single unit can cleanly identify atmospheric muons and provide sensitivity to the muon arrival directions.

Demonstrating grating-based phase-contrast imaging of laser-driven shock waves - Wegert, Leonard; Schreiner, Stephan; Rauch, Constantin; Albertazzi, Bruno; Bleuel, Paulina; Fröjdh, Eric; Koenig, Michel; Ludwig, Veronika; Martynenko, Artem S.; Meyer, Pascal; Mozzanica, Aldo; Müller, Michael; et al. (Matter and Radiation at Extremes, 2024)
Single-shot X-ray phase-contrast imaging is used to take high-resolution images of laser-driven strong shock waves. Employing a two-grating Talbot interferometer, we successfully acquire standard absorption, differential phase-contrast, and dark-field images of the shocked target. Good agreement is demonstrated between experimental data and the results of two-dimensional radiation hydrodynamics simulations of the laser-plasma interaction. The main sources of image noise are identified through a thorough assessment of the interferometer’s performance. The acquired images demonstrate that grating-based phase-contrast imaging is a powerful diagnostic tool for high-energy-density science. In addition, we make a novel attempt at using the dark-field image as a signal modality of Talbot interferometry to identify the microstructure of a foam target.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Electromagnetic pulse; Gratings; Interferometry; Phase contrast microscopy; X-ray imaging; X-ray phase contrast imaging; Lasers; Shock waves; Hydrodynamics simulations

Density of GeV muons in air showers measured with IceTop - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Anton, Gisela; et al. (Physical Review D, 2022)
We present a measurement of the density of GeV muons in near-vertical air showers using three years of data recorded by the IceTop array at the South Pole. Depending on the shower size, the muon densities have been measured at lateral distances between 200 and 1000 m. From these lateral distributions, we derive the muon densities as functions of energy at reference distances of 600 and 800 m for primary energies between 2.5 and 40 PeV and between 9 and 120 PeV, respectively. The muon densities are determined using, as a baseline, the hadronic interaction model Sibyll 2.1 together with various composition models. The measurements are consistent with the predicted muon densities within these baseline interaction and composition models. The measured muon densities have also been compared to simulations using the post-LHC models EPOS-LHC and QGSJet-II.04. The result of this comparison is that the post-LHC models together with any given composition model yield higher muon densities than observed. This is in contrast to the observations above 1 EeV where all model simulations yield for any mass composition lower muon densities than the measured ones. The post-LHC models in general feature higher muon densities so that the agreement with experimental data at the highest energies is improved but the muon densities are not correct in the energy range between 2.5 and about 100 PeV.
CRIS-Team Scopus Importer:2022-09-02

Dependence of atmospheric muon flux on seawater depth measured with the first KM3NeT detection units: The KM3NeT Collaboration - Ageron, M.; Aiello, S.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Bagatelas, C.; Barbarino, G.; Baret, B.; et al. (European Physical Journal C: Particles and Fields, 2020)
KM3NeT is a research infrastructure located in the Mediterranean Sea, that will consist of two deep-sea Cherenkov neutrino detectors. With one detector (ARCA), the KM3NeT Collaboration aims at identifying and studying TeV–PeV astrophysical neutrino sources. With the other detector (ORCA), the neutrino mass ordering will be determined by studying GeV-scale atmospheric neutrino oscillations. The first KM3NeT detection units were deployed at the Italian and French sites between 2015 and 2017. In this paper, a description of the detector is presented, together with a summary of the procedures used to calibrate the detector in-situ. Finally, the measurement of the atmospheric muon flux between 2232–3386 m seawater depth is obtained.
CRIS-Team Scopus Importer:2020-02-18

Dependence of the atmospheric muon rate on the sea water depth with first KM3NeT data - Lincetto, Massimiliano; Biagi, Simone; Coniglione, Rosa; Hofestädt, Jannik; Kulikovskiy, Vladimir; Melis, Karel W.; Samtleben, Dorothea F. E. (Proceedings of 36th International Cosmic Ray Conference — PoS(ICRC2019), 2019)
The first detection units of the KM3NeT/ORCA and KM3NeT/ARCA neutrino telescopes have been deployed at the French and Italian sites in the Mediterranean Sea. The first collected data have been crucial to assess the detector performance and to establish the calibration procedures. The low-level data streams of the deployed ARCA and ORCA detection units, containing raw information on hits in coincidence between PMTs for each Digital Optical Module, have been analysed. The study of coincidence rates has been exploited to evaluate the dependence of the atmospheric muon rate as a function of the sea depth, which is found to be in good agreement with model predictions.
CRIS-Team Scopus Importer:2024-12-16

Deployment of the IceCube Upgrade Camera System in the SPICEcore hole - Tönnis, Christoph; Kim, Danim; Pollmann, Anna; Rott, Carsten; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; et al. (Proceedings of Science, 2022)
IceCube is a cubic-kilometer scale neutrino telescope located at the geographic South Pole. The detector utilizes the extremely transparent Antarctic ice as a medium for detecting Cherenkov radiation from neutrino interactions. While the optical properties of the glacial ice are generally well modeled and understood, the uncertainties which remain are still the dominant source of systematic uncertainties for many IceCube analyses. A camera and LED system is being built for the IceCube Upgrade that will enable the observation of optical properties throughout the Upgrade array. The SPICEcore hole, a 1.7 km deep ice-core hole located near the IceCube detector, has given the opportunity to test the performance of the camera system ahead of the Upgrade construction. In this contribution, we present the results of the camera and LED system deployment during the 2019/2020 austral summer season as part of a SPICEcore luminescence logger system.
CRIS-Team Scopus Importer:2024-12-16

Design and performance of the first IceAct demonstrator at the South Pole - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (Journal of Instrumentation, 2020)
In this paper we describe the first results of IceAct, a compact imaging air-Cherenkov telescope operating in coincidence with the IceCube Neutrino Observatory (IceCube) at the geographic South Pole. An array of IceAct telescopes (referred to as the IceAct project) is under consideration as part of the IceCube-Gen2 extension to IceCube. Surface detectors in general will be a powerful tool in IceCube-Gen2 for distinguishing astrophysical neutrinos from the dominant backgrounds of cosmic-ray induced atmospheric muons and neutrinos: the IceTop array is already in place as part of IceCube, but has a high energy threshold. Although the duty cycle will be lower for the IceAct telescopes than the present IceTop tanks, the IceAct telescopes may prove to be more effective at lowering the detection threshold for air showers. Additionally, small imaging air-Cherenkov telescopes in combination with IceTop, the deep IceCube detector or other future detector systems might improve measurements of the composition of the cosmic ray energy spectrum. In this paper we present measurements of a first 7-pixel imaging air Cherenkov telescope demonstrator, proving the capability of this technology to measure air showers at the South Pole in coincidence with IceTop and the deep IceCube detector.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Cherenkov detectors; Gamma telescopes; Large detector systems for particle and astroparticle physics; Neutrino detectors

Design of a Talbot phase-contrast microscopy imaging system with a digital detector for laser-driven X-ray backlighter sources - Schreiner, Stephan; Rauch, Constantin; Akstaller, Bernhard; Bleuel, Paulina; Fröjdh, Erik; Ludwig, Veronika; Martynenko, Artem S.; Meyer, Pascal; Mozzanica, Aldo; Müller, Maximilian; Neumayer, Paul; Schuster, Max; et al. (Journal of Instrumentation, 2024)
Laser-driven shock waves in matter propagate with multiple kilometers per second and therefore require sources like a laser-driven backlighter, which emit the X-rays within picoseconds, to be able to capture sharp images. The small spatial extent of shocks in low-density materials pose challenges on the imaging setup. In this work, we present a design process for a single-shot X-ray phase-contrast imaging system geared towards these objects, consisting of a two-grating Talbot interferometer and a digital X-ray detector. This imaging system is optimized with respect to the detectable refraction angle of the X-rays induced by an object, which implies a high phase sensitivity. Therefore, an optimization parameter is defined that considers experimental constraints such as the limited number of photons, the required magnification, the size and spectrum of the X-ray source, and the visibility of the moiré fringes. In this way, a large parameter space is sampled and a suitable imaging system is chosen. During a campaign at the PHELIX high-power laser facility a static test sample was imaged which is used to benchmark the optimization process and the imaging system under real conditions. The results show good agreement with the predicted performance, which demonstrates the reliability of the presented design process. Likewise, the process can be adapted to other types of laser experiments or X-ray sources and is not limited to the application presented here.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Inspection with x-rays; Models and simulations; Plasma diagnostics - interferometry; spectroscopy and imaging; X-ray radiography and digital radiography (DR)

Detection of a particle shower at the Glashow resonance with IceCube - Aartsen, M. G.; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Amin, N. M.; Andeen, K.; Anderson, T.; Ansseau, I.; et al. (Nature, 2021)
The Glashow resonance describes the resonant formation of a W- boson during the interaction of a high-energy electron antineutrino with an electron(1), peaking at an antineutrino energy of 6.3 petaelectronvolts (PeV) in the rest frame of the electron. Whereas this energy scale is out of reach for currently operating and future planned particle accelerators, natural astrophysical phenomena are expected to produce antineutrinos with energies beyond the PeV scale. Here we report the detection by the IceCube neutrino observatory of a cascade of high-energy particles (a particle shower) consistent with being created at the Glashow resonance. A shower with an energy of 6.05 +/- 0.72 PeV (determined from Cherenkov radiation in the Antarctic Ice Sheet) was measured. Features consistent with the production of secondary muons in the particle shower indicate the hadronic decay of a resonant W- boson, confirm that the source is astrophysical and provide improved directional localization. The evidence of the Glashow resonance suggests the presence of electron antineutrinos in the astrophysical flux, while also providing further validation of the standard model of particle physics. Its unique signature indicates a method of distinguishing neutrinos from antineutrinos, thus providing a way to identify astronomical accelerators that produce neutrinos via hadronuclear or photohadronic interactions, with or without strong magnetic fields. As such, knowledge of both the flavour (that is, electron, muon or tau neutrinos) and charge (neutrino or antineutrino) will facilitate the advancement of neutrino astronomy.
CRIS-Team WoS Importer:2021-03-19

Detection of gamma rays from a starburst galaxy - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, J.; et al. (Science, 2009)
Starburst galaxies exhibit in their central regions a highly increased rate of supernovae, the remnants of which are thought to accelerate energetic cosmic rays up to energies of -10 electron volts. We report the detection of gamma rays-tracers of such cosmic rays-from the starburst galaxy NGC 253 using the High Energy Stereoscopic System (H.E.S.S.) array of imaging atmospheric Cherenkov telescopes. The gamma-ray flux above 220 billion electron volts is F = (5.5 = 1.0 ± 2.8) x 10 cm s, implying a cosmic-ray density about three orders of magnitude larger than that in the center of the Milky Way. The fraction of cosmic-ray energy channeled into gamma rays in this starburst environment is five times as large as that in our Galaxy.

Detection of the Temporal Variation of the Sun's Cosmic Ray Shadow with the IceCube Detector - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Arguelles, C.; et al. (Astrophysical Journal, 2019)
We report on the observation of a deficit in the cosmic ray flux from the directions of the Moon and Sun with five years of data taken by the IceCube Neutrino Observatory. Between 2010 May and 2011 May the IceCube detector operated with 79 strings deployed in the glacial ice at the South Pole, and with 86 strings between 2011 May and 2015 May. A binned analysis is used to measure the relative deficit and significance of the cosmic ray shadows. Both the cosmic ray Moon and Sun shadows are detected with high statistical significance (> 10 sigma) for each year. The results for the Moon shadow are consistent with previous analyses and verify the stability of the IceCube detector over time. This work represents the first observation of the Sun shadow with the IceCube detector. We show that the cosmic ray shadow of the Sun varies with time. These results make it possible to study cosmic ray transport near the Sun with future data from IceCube.
CRIS-Team WoS Importer:2019-03-06

Detection of very high energy radiation from HESS J1908+063 confirms the Milagro unidentified source MGRO J1908+06 - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, Wystan; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astronomy & Astrophysics, 2009)
Aims. Detection of a γ-ray source above 300 GeV is reported, confirming the unidentified source MGRO J1908+06, discovered by the Milagro collaboration at a median energy of 20 TeV. Methods. The source was observed during 27 h as part of the extension of the HESS Galactic plane survey to longitudes >30°. Results. HESS J108+063 is detected at a significance level of 10.9σ with an integral flux above 1 TeV of (3.76 ± 0.29 ph cm s, and a spectral photon index Γ = 2.10 ± 0.07 ± 0.2. The positions and fluxes of HESS J1908+063 and MGRO J1908+06 are in good agreement. Possible counterparts at other wavelengths and the origin of the γ-ray emission are discussed. The nearby unidentified GeV source, GRO J1908+0556 (GeV) which also remains unidentified and the new Fermi pulsar 0FGL J1907.5+0617, may be connected to the TeV source. © ESO 2009.
Keywords: Gamma rays; Observations

Detection potential of the KM3NeT detector for high-energy neutrinos from the Fermi bubbles - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Aharonian, F.; Aiello, S.; Albert, A.; Alexandri, M.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; et al. (Astroparticle Physics, 2013)
A recent analysis of the Fermi Large Area Telescope data provided evidence for a high-intensity emission of high-energy gamma rays with a E-2 spectrum from two large areas, spanning 50 above and below the Galactic centre (the "Fermi bubbles"). A hadronic mechanism was proposed for this gamma-ray emission making the Fermi bubbles promising source candidates of high-energy neutrino emission. In this work Monte Carlo simulations regarding the detectability of high-energy neutrinos from the Fermi bubbles with the future multi-km(3) neutrino telescope KM3NeT in the Mediterranean Sea are presented. Under the hypothesis that the gamma-ray emission is completely due to hadronic processes, the results indicate that neutrinos from the bubbles could be discovered in about one year of operation, for a neutrino spectrum with a cutoff at 100 TeV and a detector with about 6 km(3) of instrumented volume. The effect of a possible lower cutoff is also considered. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino telescope; Fermi Bubbles; KM3NeT

Development of an analysis to probe the neutrino mass ordering with atmospheric neutrinos using three years of IceCube DeepCore data: IceCube Collaboration - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (European Physical Journal C: Particles and Fields, 2020)
The Neutrino Mass Ordering (NMO) remains one of the outstanding questions in the field of neutrino physics. One strategy to measure the NMO is to observe matter effects in the oscillation pattern of atmospheric neutrinos above ∼1GeV, as proposed for several next-generation neutrino experiments. Moreover, the existing IceCube DeepCore detector can already explore this type of measurement. We present the development and application of two independent analyses to search for the signature of the NMO with three years of DeepCore data. These analyses include a full treatment of systematic uncertainties and a statistically-rigorous method to determine the significance for the NMO from a fit to the data. Both analyses show that the dataset is fully compatible with both mass orderings. For the more sensitive analysis, we observe a preference for normal ordering with a p-value of pIO= 15.3 % and CL s= 53.3 % for the inverted ordering hypothesis, while the experimental results from both analyses are consistent within their uncertainties. Since the result is independent of the value of δCP and obtained from energies Eν≳5GeV, it is complementary to recent results from long-baseline experiments. These analyses set the groundwork for the future of this measurement with more capable detectors, such as the IceCube Upgrade and the proposed PINGU detector.
CRIS-Team Scopus Importer:2020-01-14

Development of a scintillation and radio hybrid detector array at the South Pole - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Proceedings of Science, 2022)
At the IceCube Neutrino Observatory, a Surface Array Enhancement is planned, consisting of 32 hybrid stations, placed within the current IceTop footprint. This surface enhancement will considerably increase the detection sensitivity to cosmic rays in the 100 TeV to 1 EeV primary energy range, measure the effects of snow accumulation on the existing IceTop tanks and serve as R&D for the possible future large-scale surface array of IceCube-Gen2. Each station has one central hybrid DAQ, which reads out 8 scintillation detectors and 3 radio antennas. The radio antenna SKALA-2 is used in this array due to its low-noise, high amplification and sensitivity in the 70-350 MHz frequency band. Every scintillation detector has an active area of 1.5 m2 organic plastic scintillators connected by wavelength-shifting fibers, which are connected to a silicon photomultiplier. The signals from the scintillation detectors are integrated and digitized by a local custom electronics board and transferred to the central DAQ. When triggered by the scintillation detectors, the filtered and amplified analog waveforms from the radio antennas are read out and digitized by the central DAQ. A full prototype station has been developed and built and was installed at the South Pole in January 2020. It is planned to install the full array by 2026. In this contribution the hardware design of the array as well as the installation plans will be presented.
CRIS-Team Scopus Importer:2024-12-16

Die Universität als Keimzelle und Betreiber des ESFZ - Fösel, Angela; Anton, Gisela (Best Practices und Tipps von Expert:innen für Schülerforschungszentren. Rahmenbedingungen. Kooperationen. Qualitätskriterien., 2020)
Keywords: Erlanger SchülerforschungsZentrum; ESFZ

Differential cross sections for neutron-proton scattering in the region of the d* (2380) dibaryon resonance - Adlarson, P.; Augustyniak, W.; Bardan, W.; Bashkanov, M.; Bergmann, F. S.; Berlowski, M.; Bhatt, H.; Buescher, M.; Calen, H.; Ciepal,; Clement, H.; Coderre, D.; et al. (Physical Review C - Nuclear Physics, 2020)
Differential cross sections have been extracted from exclusive and kinematically complete high-statistics measurements of quasifree polarized (n) over barp scattering performed in the energy region of the d* (2380) dibaryon resonance covering the range of beam energies T-n = 0.98-1.29 GeV (root s = 2.32-2.44 GeV). The experiment was carried out with the WASA-at-COSY setup having a polarized deuteron beam impinged on the hydrogen pellet target and utilizing the quasifree process dp -> np + p(spectator). In this way the np differential cross section sigma (Theta) was measured over a large angular range. The obtained angular distributions complement the corresponding analyzing power A(y)(Theta) measurements published previously. A SAID partial-wave analysis incorporating the new data strengthens the finding of a resonance pole in the coupled D-3(3) - (3)G(3) waves.
CRIS-Team WoS Importer:2020-07-31

Diffuse Galactic gamma-ray emission with H.E.S.S. - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2014)
Diffuse γ-ray emission is the most prominent observable signature of celestial cosmic-ray interactions at high energies. While already being investigated at GeV energies over several decades, assessments of diffuse γ-ray emission at TeV energies remain sparse. After completion of the systematic survey of the inner Galaxy, the H.E.S.S. experiment is in a prime position to observe large-scale diffuse emission at TeV energies. Data of the H.E.S.S. Galactic Plane Survey are investigated in regions off known γ-ray sources. Corresponding γ-ray flux measurements were made over an extensive grid of celestial locations. Longitudinal and latitudinal profiles of the observed γ-ray fluxes show characteristic excess emission not attributable to known γ-ray sources. For the first time large-scale γ-ray emission along the Galactic plane using imaging atmospheric Cherenkov telescopes has been observed. While the background subtraction technique limits the ability to recover modest variation on the scale of the H.E.S.S. field of view or larger, which is characteristic of the inverse Compton scatter-induced Galactic diffuse emission, contributions of neutral pion decay as well as emission from unresolved γ-ray sources can be recovered in the observed signal to a large fraction. Calculations show that the minimum γ-ray emission from π0 decay represents a significant contribution to the total signal. This detection is interpreted as a mix of diffuse Galactic γ-ray emission and unresolved sources.

Direction Reconstruction using a CNN for GeV-Scale Neutrinos in IceCube - Yu, Shiqi; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
The IceCube Neutrino Observatory observes neutrinos interacting deep within the South Pole ice. It consists of 5,160 digital optical modules, which are embedded within a cubic kilometer of ice, over depths of 1,450 m to 2,450 m. At the lower center of the array is the DeepCore subdetector. Its denser sensor configuration lowers the observable energy threshold to the GeV-scale, facilitating the study of atmospheric neutrino oscillations. The precise reconstruction of neutrino direction is critical in the measurements of oscillation parameters. This work presents a method to reconstruct the zenith angle of GeV-scale events in IceCube by using a convolutional neural network and compares the result to that of the current likelihood-based reconstruction algorithm.
CRIS-Team Scopus Importer:2024-12-16

Discovery and follow-up studies of the extended, off-plane, VHE gamma-ray source HESS J1507-622 - Acero, Fabio; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, Julien; et al. (Astronomy & Astrophysics, 2010)
Context. The detection of gamma-rays in the very-high-energy (VHE) range (100 GeV-100 TeV) offers the possibility of studying the parent population of ultrarelativistic particles found in astrophysical sources, so it is useful for understanding the underlying astrophysical processes in nonthermal sources. Aims. The discovery of the VHE gamma-ray source HESS J1507-622 is reported and possibilities regarding its nature are investigated. Methods. The H.E.S.S. array of imaging atmospheric Cherenkov telescopes (IACTs) has a high sensitivity compared with previous instruments (∼1% of the Crab flux in 25 h observation time for a 5σ point-source detection) and has a large field of view (∼5° in diameter). HESS J1507-622 was discovered within the ongoing H.E.S.S. survey of the inner Galaxy, and the source was also studied by means of dedicated multiwavelength observations. Results. A Galactic gamma-ray source, HESS J1507-622, located ∼3.5° from the Galactic plane was detected with a statistical significance >9σ. Its energy spectrum is well fitted by a power law with spectral index Γ = 2.24 ± 0.16 ± 0.20 and a flux above 1 TeV of (1.5 ± 0.4 ± 0.3) × 10 cm s. Possible interpretations (considering both hadronic and leptonic models) of the VHE gamma-ray emission are discussed in the absence of an obvious counterpart. © ESO 2010.
Keywords: gamma rays: general; X-rays: general

Discovery of gamma-ray emission from the extragalactic pulsar wind nebula N 157B with H.E.S.S. - Abramowski, A.; Acero, Fabio; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2012)
We present the significant detection of the first extragalactic pulsar wind nebula (PWN) detected in gamma rays, N- 157B, located in the large Magellanic Cloud (LMC). Pulsars with high spin-down luminosity are found to power energised nebulae that emit gamma rays up to energies of several tens of TeV. N- 157B is associated with PSR- J0537-6910, which is the pulsar with the highest known spin-down luminosity. The High Energy Stereoscopic System telescope array observed this nebula on a yearly basis from 2004 to 2009 with a dead-time corrected exposure of 46- h. The gamma-ray spectrum between 600- GeV and 12- TeV is well-described by a pure power-law with a photon index of 2.8 ± 0.2 ± 0.3 and a normalisation at 1- TeV of (8.2 ± 0.8 ± 2.5 ) × 10 cm - s - TeV . A leptonic multi-wavelength model shows that an energy of about 4 × 10 erg is stored in electrons and positrons. The apparent efficiency, which is the ratio of the TeV gamma-ray luminosity to the pulsar's spin-down luminosity, 0.08% ± 0.01%, is comparable to those of PWNe found in the Milky Way. The detection of a PWN at such a large distance is possible due to the pulsar's favourable spin-down luminosity and a bright infrared photon-field serving as an inverse-Compton-scattering target for accelerated leptons. By applying a calorimetric technique to these observations, the pulsar's birth period is estimated to be shorter than 10 ms. © ESO, 201
Keywords: Gamma rays: general; ISM: supernova remnants; Magellanic Clouds; Pulsars: individual: PSR J0537-6910

Discovery of high and very high-energy emission from the BL Lacertae object SHBL J001355.9-185406 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy and Astrophysics, 2013)
Keywords: BL Lacertae objects: individual: SHBL J001355.9-185406; gamma rays: general

Discovery of TeV γ-ray emission from PKS 0447-439 and derivation of an upper limit on its redshift - Abramowski, A.; Acero, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Behera, B.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
Very high-energy γ-ray emission from PKS 0447-439 was detected with the H.E.S.S. Cherenkov telescope array in December 2009. This blazar is one of the brightest extragalactic objects in the Fermi bright source list and has a hard spectrum in the MeV to GeV range. In the TeV range, a photon index of 3.89 ± 0.37 (stat) ±0.22 (sys) and a flux normalisation at 1 TeV, Φ = (3.5 ± 1.1(stat) ± 0.9(sys)) × 10 cm s TeV were found. The detection with H.E.S.S. triggered observations in the X-ray band with the Swift and RXTE telescopes. Simultaneous UV and optical data from Swift UVOT and data from the optical telescopes ATOM and ROTSE are also available. The spectrum and light curve measured with H.E.S.S. are presented and compared to the multi-wavelength data at lower energies. A rapid flare is seen in the Swift XRT and RXTE data, together with a flux variation in the UV band, at a time scale of the order of one day. A firm upper limit of z < 0.59 on the redshift of PKS 0447-439 is derived from the combined Fermi-LAT and H.E.S.S. data, given the assumptions that there is no upturn in the intrinsic spectrum above the Fermi-LAT energy range and that absorption on the extragalactic background light (EBL) is not weaker than the lower limit provided by current models. The spectral energy distribution is well described by a simple one-zone synchrotron self-Compton scenario, if the redshift of the source is less than z â‰ 0.4. © 2013 ESO.
Keywords: BL Lacertae objects: individual: PKS 0447-439; Galaxies: active; Gamma rays: galaxies; Radiation mechanisms: non-thermal

Discovery of the Hard Spectrum VHE γ-Ray Source HESS J1641-463 - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Uner, E. O. Ang; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astrophysical Journal Letters, 2014)
Keywords: cosmic rays; gamma rays: general; ISM: individual objects (SNR G338.30.0; SNR G338.5+0.1)

Discovery of the source HESS J1356-645 associated with the young and energetic PSR J1357-6429 - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Becherini, Y.; Becker, J.; Behera, B.; et al. (Astronomy & Astrophysics, 2011)
Context. Several newly discovered very-high-energy (VHE; E > 100 GeV) γ-ray sources in the Galaxy are thought to be associated with energetic pulsars. Among them, middle-aged (10 yr) systems exhibit large centre-filled VHE nebulae, offset from the pulsar position, which result from the complex relationship between the pulsar wind and the surrounding medium, and reflect the past evolution of the pulsar. Aims. Imaging Atmospheric Cherenkov Telescopes (IACTs) have been successful in revealing extended emission from these sources in the VHE regime. Together with radio and X-ray observations, this observational window allows one to probe the energetics and magnetic field inside these large-scale nebulae. Methods. H.E.S.S., with its large field of view, angular resolution of 0.1° and unprecedented sensitivity, has been used to discover a large population of such VHE sources. In this paper, the H.E.S.S. data from the continuation of the Galactic Plane Survey (-80° < < 60°, |b| < 3°), together with the existing multi-wavelength observations, are used. Results. A new VHE γ-ray source was discovered at RA (J2000) = 135600, Dec (J2000) =-64°30′00′′ with a 2′ statistical error in each coordinate, namely HESS J1356-645. The source is extended, with an intrinsic Gaussian width of (0.20 ± 0.02)°. Its integrated energy flux between 1 and 10 TeV of 8 × 10 erg cm s represents ∼11% of the Crab Nebula flux in the same energy band. The energy spectrum between 1 and 20 TeV is well described by a power law dN/dE E with photon index Γ = 2.2 ± 0.2 ± 0.2. The inspection of archival radio images at three frequencies and the analysis of X-ray data from ROSAT/PSPC and XMM-Newton/MOS reveal the presence of faint non-thermal diffuse emission coincident with HESS J1356-645. Conclusions. HESS J1356-645 is most likely associated with the young and energetic pulsar PSR J1357-6429 (d = 2.4 kpc, τ = 7.3 kyr and Å-= 3.1 × 10 erg s), located at a projected distance of ∼5 pc from the centroid of the VHE emission. HESS J1356-645 and its radio and X-ray counterparts would thus represent the nebula resulting from the past history of the PSR J1357-6429 wind. In a simple one-zone model, © 2011 ESO.
Keywords: gamma rays: general; ISM: individual objects: HESS J1356-645; ISM: individual objects: PSR J1357-6429; surveys

Discovery of the VHE gamma-ray source HESS J1832-093 in the vicinity of SNR G22.7-0.2 - Abramowski, A.; Acero, F.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguner, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Monthly Notices of the Royal Astronomical Society, 2015)
Keywords: astroparticle physics; ISM: individual objects: HESS J1832-093; ISM: individual objects: SNR G22.7-0.2; gamma-rays: general

Discovery of variable VHE gamma-ray emission from the binary system 1FGL J1018.6-5856 - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balzer, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; Bernhard, S.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2015)
Re-observations with the HESS telescope array of the very high-energy (VHE) source HESS J1018-589A that is coincident with the Fermi-LAT gamma-ray binary 1FGL J1018.6-5856 have resulted in a source detection significance of more than 9 sigma and the detection of variability (chi(2)/nu of 238.3/155) in the emitted gamma-ray flux. This variability confirms the association of HESS J1018-589A with the high-energy gamma-ray binary detected Fermi-LAT and also confirms the point-like source as a new VHE binary system. The spectrum of HESS J1018-589A is best fit with a power-law function with photon index Gamma = 2.20 +/- 0.14(stat) +/- 0.2(sys). Emission is detected up to similar to 20 TeV. The mean differential flux level is (2.9 +/- 0.4) x 10(-13) TeV-1 cm(-2) s(-1) at 1 TeV, equivalent to similar to 1% of the flux from the Crab Nebula at the same energy. Variability is clearly detected the night-by-night light curve. When folded on the orbital period of 16.58 days, the rebinned light curve peaks in phase with the observed X-ray high-energy phaseograms. The fit of the HESS phaseogram to a constant flux provides evidence of periodicity at the level of N-sigma > 3 sigma. The of the VHE phaseogram and measured spectrum suggest a low-inclination, low-eccentricity system with a modest impact from VHE gamma-ray due to pair production (tau less than or similar to 1 at 300 GeV).
Keywords: Acceleration of particles; Gamma rays: stars; Radiation mechanisms: non-thermal; Stars: individual: 1FGL J1018.6-5856; X-rays: binaries

Discovery of very high energy γ-ray emission from centaurus a with H.E.S.S. - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astrophysical Journal, 2009)
We report the discovery of faint very high energy (VHE; E > 100GeV) γ-ray emission from the radio galaxy Centaurus A in observations performed with the High Energy Stereoscopic System (H.E.S.S.) experiment, an imaging atmospheric Cherenkov telescope array consisting of four telescopes located in Namibia. Centaurus A has been observed for more than 120hr. A signal with a statistical significance of 5.0σ is detected from the region including the radio core and the inner kpc jets. The integral flux above an energy threshold of 250 GeV is measured to be 0.8% of the flux of the Crab Nebula (apparent luminosity: L(>250GeV) 2.6 × 10ergs, adopting a distance of 3.8Mpc). The spectrum can be described by a power law with a photon index of 2.7 0.5 0.2. No significant flux variability is detected in the data set. However, the low flux only allows detection of variability on the timescale of days to flux increments above a factor of 15-20 (3σ and 4σ, respectively). The discovery of VHE γ-ray emission from Centaurus A reveals particle acceleration in the source to >TeV energies and, together with M87, establishes radio galaxies as a class of VHE emitters. © 2009. The American Astronomical Society. All rights reserved..
Keywords: Galaxies: active; Galaxies: individual (Cen A); Gamma rays: observations

Discovery of very high energy γ-ray emission from the BL Lacertae object PKS 0301-243 with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2013)
The active galactic nucleus PKS 0301-243 (z = 0.266) is a high-synchrotron-peaked BL Lac object that is detected at high energies (HE, 100 MeV <e 0301-243="" 100="" at="" by="" discovery="" e="" energies="" fermi="" high="" lat.="" of="" on="" paper="" pks="" reports="" the="" this="" very=""> 100 GeV) by the High Energy Stereoscopic System (H.E.S.S.) from observations between September 2009 and December 2011 for a total live time of 34.9 h. Gamma rays above 200 GeV are detected at a significance of 9.4σ. A hint of variability at the 2.5σ level is found. An integral flux I(E > 200 GeV) = (3.3 ± 1.1 ± 0.7) × 10 ph cm s and a photon index Γ = 4.6 ± 0.7 ± 0.2 are measured. Multi-wavelength light curves in HE, X-ray and optical bands show strong variability, and a minimal variability timescale of eight days is estimated from the optical light curve. A single-zone leptonic synchrotron self-Compton scenario satisfactorily reproduces the multi-wavelength data. In this model, the emitting region is out of equipartition and the jet is particle dominated. Because of its high redshift compared to other sources observed at TeV energies, the very high energy emission from PKS 0301-243 is attenuated by the extragalactic background light (EBL) and the measured spectrum is used to derive an upper limit on the opacity of the EBL. © 2013 ESO.</e>
Keywords: BL Lacertae objects: general; BL Lacertae objects: individual: PKS 0301-243; Galaxies: active; Gamma rays: galaxies; Radiation mechanisms: non-thermal

Discovery of VHE γ-ray emission and multi-wavelength observations of the BL Lacertae object 1RXS J101015.9-311909 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Astronomy & Astrophysics, 2012)
Keywords: gamma rays: galaxies; galaxies: active; BL Lacertae objects: individual: 1RXS J101015.9-311909

Discovery of VHE emission towards the Carina arm region with the H.E.S.S. telescope array: HESS? J1018-589 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Astronomy & Astrophysics, 2012)
The Carina arm region, containing the supernova remnant SNR? G284.3-1.8, the high-energy (HE; E > 100 MeV) binary 1FGL? J1018.6-5856 and the energetic pulsar PSR? J1016-5857 and its nebula, has been observed with the H.E.S.S. telescope array. The observational coverage of the region in very-high-energy (VHE; E > 0.1? TeV) γ-rays benefits from deep exposure (40? h) of the neighboring open cluster Westerlund 2. The observations have revealed a new extended region of VHE γ-ray emission. The new VHE source HESS? J1018-589 shows a bright, point-like emission region positionally coincident with SNR? G284.3-1.8 and 1FGL? J1018.6-5856 and a diffuse extension towards the direction of PSR? J1016-5857. A soft (Γ = 2.7 ± 0.5) photon? index, with a differential flux at 1? TeV of N = (4.2 ± 1.1) × 10? TeV? cm? s is found for the point-like source, whereas the total emission region including the diffuse emission region is well fit by a power-law function with spectral index Γ = 2.9 ± 0.4 and differential flux at 1? TeV of N = (6.8 ± 1.6) × 10? TeV? cm? s. This H.E.S.S. detection motivated follow-up X-ray observations with the XMM-Newton satellite to investigate the origin of the VHE emission. The analysis of the XMM-Newton data resulted in the discovery of a bright, non-thermal point-like source (XMMU J101855.4-58564) with a photon index of Γ = 1.65 ± 0.08 in the center of SNR? G284.3-1.8, and a thermal, extended emission region coincident with its bright northern filament. The characteristics of this thermal emission are used to estimate the plasma density in the region as n 0.5 cm (2.9? kpc/d). The position of XMMU? J101855.4-58564 is compatible with the position reported by the Fermi-LAT collaboration for the binary system 1FGL? J1018.6-5856 and the variable Swift XRT source identified with it. The new X-ray data are used alongside archival multi-wavelength data to investigate the relationship between the VHE γ-ray emission from HESS? J1018-589 and the various potential counterparts in the Carina arm region. © ESO, 2012.
Keywords: Gamma rays: stars; ISM: individual objects: 1FGL J1018.6-5856; ISM: individual objects: PSRJ1016-5857; ISM: individual objects: SNRG284.3-1.8

Discovery of VHE γ -rays from the BL Lacertae object PKS 0548-322 - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, J.; et al. (Astronomy & Astrophysics, 2010)
Aims. PKS 0548-322 (z = 0.069) is a "high-frequency-peaked" BL Lac object and a candidate very high energy (VHE, E > 100 GeV) γ-ray emitter, due to its high X-ray and radio flux. Observations at the VHE band provide insights into the origin of very energetic particles present in this source and the radiation processes at work. Methods. We report observations made between October 2004 and January 2008 with the HESS array, a four imaging atmospheric-Cherenkov telescopes. Contemporaneous UV and X-ray observations with the Swift satellite in November 2006 are also reported. Results. PKS 0548-322 is detected for the first time in the VHE band with HESS We measure an excess of 216 γ-rays corresponding to a significance of 5.6 standard deviations. The photon spectrum of the source is described by a power-law, with a photon index of Γ = 2.86 ± 0.34 ± 0.10 . The integral flux above 200 GeV is ∼1.3% of the flux of the Crab Nebula, and is consistent with being constant in time. Contemporaneous Swift/XRT observations reveal an X-ray flux between 2 and 10 keV of F = (2.3±0.2)×10 erg cm s, an intermediate intensity state with respect to previous observations. The spectral energy distribution can be reproduced using a simple one-zone synchrotron self Compton model, with parameters similar those observed for other sources of this type. © 2010 ESO.
Keywords: BL Lacertae objects: individual: PKS 0548-322; galaxies: active; gamma rays: observations

Discrimination analysis of breast calcifications using x-ray dark-field radiography - Rauch, Thomas; Rieger, Jens; Pelzer, Georg; Horn, Florian; Erber, Ramona; Wunderle, Marius; Emons, Julius; Nabieva, Naiba; Fuhrich, Nicole; Michel, Thilo; Hartmann, Arndt; Fasching, Peter; et al. (Medical Physics, 2020)
Background X-ray dark-field radiography could enhance mammography by providing more information on imaged tissue and microcalcifications. The dark field signal is a measure of small angle scattering and can thus provide additional information on the imaged materials. This information can be useful for material distinction of calcifications and the diagnosis of breast cancer by classifying benign and malign association of these calcifications.
CRIS-Team WoS Importer:2020-03-06

Discrimination of muons for mass composition studies of inclined air showers detected with IceTop - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Proceedings of Science, 2022)
IceTop, the surface array of IceCube, measures air showers from cosmic rays within the energy range of 1 PeV to a few EeV and a zenith angle range of up to ≈ 36◦. This detector array can also measure air showers arriving at larger zenith angles at energies above 20 PeV. Air showers from lighter primaries arriving at the array will produce fewer muons when compared to heavier cosmic-ray primaries. A discrimination of these muons from the electromagnetic component in the shower can therefore allow a measurement of the primary mass. A study to discriminate muons using Monte-Carlo air showers of energies 20-100 PeV and within the zenith angular range of 45◦-60◦ will be presented. The discrimination is done using charge and time-based cuts which allows us to select muon-like signals in each shower. The methodology of this analysis, which aims at categorizing the measured air showers as light or heavy on an event-by-event basis, will be discussed.
CRIS-Team Scopus Importer:2024-12-16

Drift chamber calibration and particle identification in the P-349 experiment - Alfs, D.; Asaturyan, A.; Carmignotto, M.; Diermaier, M.; Eyrich, Wolfgang; Glowacz, B.; Grzonka, D.; Hauenstein, F.; Horn, T.; Kilian, K.; Lersch, D.; Malbrunot-Ettenauer, S.; et al. (MESON 2018 – 15th International Workshop on Meson Physics, 2019)
CRIS-Team WoS Importer:2019-06-28

Efficient propagation of systematic uncertainties from calibration to analysis with the SnowStorm method in IceCube - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Alispach, C.; Atoum, B. Al; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2019)
Efficient treatment of systematic uncertainties that depend on a large number of nuisance parameters is a persistent difficulty in particle physics and astrophysics experiments. Where low-level effects are not amenable to simple parameterization or re-weighting, analyses often rely on discrete simulation sets to quantify the effects of nuisance parameters on key analysis observables. Such methods may become computationally untenable for analyses requiring high statistics Monte Carlo with a large number of nuisance degrees of freedom, especially in cases where these degrees of freedom parameterize the shape of a continuous distribution. In this paper we present a method for treating systematic uncertainties in a computationally efficient and comprehensive manner using a single simulation set with multiple and continuously varied nuisance parameters. This method is demonstrated for the case of the depth-dependent effective dust distribution within the IceCube Neutrino Telescope.
CRIS-Team Scopus Importer:2019-12-13
Keywords: neutrino detectors; neutrino experiments; ultra high energy photons and neutrinos

Electromagnetic pulse protective shielding for digital x-ray detectors - Schreiner, Stephan; Rauch, Constantin; Akstaller, Bernhard; Bleuel, Paulina; Fröjdh, Eric; Martynenko, Artem S.; Mozzanica, Aldo; Neumayer, Paul; Wegert, Leonard; Zielbauer, Bernhard; Zink, Adrian; Anton, Gisela; et al. (Review of Scientific Instruments, 2023)
Laser-driven x-ray backlighting can be used to image fast dynamic processes like the propagation of laser-driven shock waves in matter. We demonstrate and evaluate the feasibility of operating the JUNGFRAU detector designed by PSI, a direct detecting x-ray detector, in environments with extreme electromagnetic pulses. The electromagnetic pulse-protective housing is specifically designed for this detector and optimized for pump-probe experiments at the Petawatt High-Energy Laser for Heavy Ion EXperiments (PHELIX) facility at the GSI Helmholtzzentrum für Schwerionenforschung GmbH. The beryllium x-ray entrance window of the protective housing has a high x-ray transmission of 94% at 8 keV. Measurements have shown that the housing simultaneously provides a relative damping of the electromagnetic field on average higher than 1000 in the frequency range of 100 MHz to 5 GHz. The results demonstrate the feasibility of operating digital detectors in experiments where strong electromagnetic pulses are present.
CRIS-Team Scopus Importer:2023-08-11

Energie - Umwelt - Gesellschaft - Hosemann, Gerhard; Finckh, Eberhard; Wirth, Eugen (Universitätsbund Erlangen, 1980)
UnivIS-Import:2017-12-18:Pub.1980.tech.IE.leen.energi

Erratum: H.E.S.S. detection of TeV emission from the interaction region between the supernova remnant G349.7+0.2 and a molecular cloud (Astronomy and Astrophysics (2015)) - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astronomy & Astrophysics, 2015)
Keywords: Errata; addenda; Gamma rays: general; ISM: clouds; ISM: supernova remnants

Erratum: Publisher's Note: "Electromagnetic pulse protective shielding for digital x-ray detectors" [Rev. Sci. Instrum. 94, 075106 (2023) (The Review of scientific instruments (2023) 94 7 PII: 089902) - Schreiner, Stephan; Rauch, Constantin; Akstaller, Bernhard; Bleuel, Paulina; Frojdh, Eric; Martynenko, Artem S.; Mozzanica, Aldo; Neumayer, Paul; Wegert, Leonard; Zielbauer, Bernhard; Zink, Adrian; Anton, Gisela; et al. (Review of Scientific Instruments, 2023)
CRIS-Team Scopus Importer:2023-12-22

Erratum: "Search for Dark Matter Annihilation Signals from the Fornax Galaxy Cluster with H.E.S.S.'' (2012, ApJ, 750, 123) - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Barres De Almeida, U.; Becherini, Y.; Becker, J.; Behera, B.; Bernlöhr, K.; et al. (Astrophysical Journal, 2014)

Erratum to HESS J1640-465 - an exceptionally luminous TeV γ -ray supernova remnant - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
Keywords: Addenda; Errata; ISM: individual objects: G338.3-0.0; ISM: supernova remnants; Radiation mechanisms: non-thermal

Erratum to “Results from the search for dark matter in the Milky Way with 9 years of data of the ANTARES neutrino telescope” [Phys. Lett. B 769 (2017)249–254](S037026931730254X)(10.1016/j.physletb.2017.03.063) - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Bertin, V.; Biagi, S.; et al. (Physics Letters B, 2019)
Limits on the neutrino flux for a given mass [Formula presented] and annihilation channel are calculated as in Eq. (7)(page 252), with the integrated acceptances defined in Eq. (8)(page 252)as the effective area averaged over the neutrino energy. A numerical approximation of WIMP annihilation spectra, adapted from [1]with a too coarse binning, led to an overestimation of the integrated acceptances for dark-matter induced neutrino events. The spectra were replaced with a fine-binned version both in the likelihood and in the acceptances. The main change is a weaker limit for WIMP masses larger than 1 TeV/ [Formula presented]. Updated versions of Figs. 3–6 are provided.
CRIS-Team Scopus Importer:2019-06-04

Erratum to: Search for annihilating dark matter in the Sun with 3 years of IceCube data: IceCube Collaboration (The European Physical Journal C, (2017), 77, 3, (146), 10.1140/epjc/s10052-017-4689-9) - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Archinger, M.; et al. (European Physical Journal C: Particles and Fields, 2019)
In the analysis published in 1, constraints on the number of signal events can be interpreted as constraints on the volumetric neutrino to muon conversion rate.
CRIS-Team Scopus Importer:2019-05-02

Estimating the coincidence rate between the optical and radio array of IceCube-Gen2 - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
The IceCube-Gen2 Neutrino Observatory is proposed to extend the all-flavour energy range of IceCube beyond PeV energies. It will comprise two key components: I) An enlarged 8 km3 in-ice optical Cherenkov array to measure the continuation of the IceCube astrophysical neutrino flux and improve IceCube’s point source sensitivity above ∼ 100 TeV; and II) A very large in-ice radio array with a surface area of about 500 km2. Radio waves propagate through ice with a kilometer-long attenuation length, hence a sparse radio array allows us to instrument a huge volume of ice to achieve a sufficient sensitivity to detect neutrinos with energies above tens of PeV. The different signal topologies for neutrino-induced events measured by the optical and in-ice radio detector - the radio detector is mostly sensitive to the cascades produced in the neutrino interaction, while the optical detector can detect long-ranging muon and tau leptons with high accuracy - yield highly complementary information. When detected in coincidence, these signals will allow us to reconstruct the neutrino energy and arrival direction with high fidelity. Furthermore, if events are detected in coincidence with a sufficient rate, they resemble the unique opportunity to study systematic uncertainties and to cross-calibrate both detector components. We present the expected rate of coincidence events for 10 years of operation. Furthermore, we analyzed possible detector optimizations to increase the coincidence rate.
CRIS-Team Scopus Importer:2025-02-04

Evaluation of an FPGA-based fast machine-learning trigger for neutrino telescopes - Capel, Francesca; Spannfellner, Christian; Haack, Christian; Prottung, Janik (Proceedings of Science, 2024)
Energetic neutrinos provide a view into the underlying processes of astrophysical particle accelerators, but their weakly interacting nature makes them challenging to detect. Current experiments instrument large volumes of ice or water with 3D grids of photomultiplier tubes (PMTs) to capture the Cherenkov light produced by interactions of high-energy neutrinos. Such detectors must be located in remote locations deep underwater or in ice to reduce atmospheric background signals. These challenging conditions impose strict limits on the power and bandwidth available for data transfer to the surface, and triggers are used to maintain manageable rates. We evaluate the potential of fast, intelligent machine-learning triggers that can be implemented on low-power field-programmable gate arrays (FPGAs). We aim to make the most of the given hardware with improved discrimination of signal and background and therefore improved sensitivity to low-energy events. In particular, we focus on the case of underwater neutrino detectors and the efficient discrimination of track-like signals from the bioluminescence background. We develop a machine-learning trigger by using the planned P-ONE experiment as a case study and implement a software testbench to compare its performance to a less complex trigger design based on coincident detections.
CRIS-Team Scopus Importer:2025-02-04

Evaluation of the Weighted Mean X-ray Energy for an Imaging System Via Propagation-Based Phase-Contrast Imaging - Seifert, Maria; Weule, Mareike; Cipiccia, Silvia; Flenner, Silja; Hagemann, Johannes; Ludwig, Veronika; Michel, Thilo; Neumayer, Paul; Schuster, Max; Wolf, Andreas; Anton, Gisela; Funk, Stefan; et al. (Journal of Imaging, 2020)
For imaging events of extremely short duration, like shock waves or explosions, it is necessary to be able to image the object with a single-shot exposure. A suitable setup is given by a laser-induced X-ray source such as the one that can be found at GSI (Helmholtzzentrum fur Schwerionenforschung GmbH) in Darmstadt (Society for Heavy Ion Research), Germany. There, it is possible to direct a pulse from the high-energy laser Petawatt High Energy Laser for Heavy Ion eXperiments (PHELIX) on a tungsten wire to generate a picosecond polychromatic X-ray pulse, called backlighter. For grating-based single-shot phase-contrast imaging of shock waves or exploding wires, it is important to know the weighted mean energy of the X-ray spectrum for choosing a suitable setup. In propagation-based phase-contrast imaging the knowledge of the weighted mean energy is necessary to be able to reconstruct quantitative phase images of unknown objects. Hence, we developed a method to evaluate the weighted mean energy of the X-ray backlighter spectrum using propagation-based phase-contrast images. In a first step wave-field simulations are performed to verify the results. Furthermore, our evaluation is cross-checked with monochromatic synchrotron measurements with known energy at Diamond Light Source (DLS, Didcot, UK) for proof of concepts.
CRIS-Team WoS Importer:2020-08-28

Evaluation of X-ray phase-contrast imaging with the Medipix - Bartl, Peter; Michel, Thilo; Nachtrab, F.; Uhlmann, N.; Anton, Gisela (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2011)
In the recent decade phase-contrast imaging in the X-ray regime has been developed as a competitive alternative to conventional absorption radiography and computed tomography Wilkins et al. (1996) [1]. As phase-contrast is an energy dependent phenomenon, the use of a spectroscopic detector like the Medipix is a key tool to characterize and optimize imaging methods such as in-line or interferometric phase-contrast imaging. In the following the energy dependency of interference patterns caused by phase shifts in a coherent wavefront will be shown. Moreover, the spatial coherence of X-rays, considered as wavefronts, is crucial for the formation of detectable interference effects. The newest generations of X-ray sources produce small but finite focal spot sizes, so that partial spatial coherence of the wave-field has to be taken into account. The contribution of partial coherence to the image recorded in the detector plane has been investigated and the outcome will be presented. For a fuller understanding of a complete phase-contrast imaging setup the incoherent scattering effects were additionally simulated with Monte-Carlo methods. Furthermore, to develop a realistic simulation-tool for X-ray phase-contrast imaging, a good comprehension of the detection system is needed. This was also achieved by Monte-Carlo simulations. The comparison with measurements of the simulations of a complete setup shows a very good agreement.
EAM Import::2019-03-14

Event reconstruction for KM3NeT/ORCA using convolutional neural networks - Aiello, S.; Albert, A.; Garre, S. Alves; Aly, Z.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; Ardid, M.; Aublin, J.; et al. (Journal of Instrumentation, 2020)
The KM3NeT research infrastructure is currently under construction at two locations in the Mediterranean Sea. The KM3NeT/ORCA water-Cherenkov neutrino detector off the French coast will instrument several megatons of seawater with photosensors. Its main objective is the determination of the neutrino mass ordering. This work aims at demonstrating the general applicability of deep convolutional neural networks to neutrino telescopes, using simulated datasets for the KM3NeT/ORCA detector as an example. To this end, the networks are employed to achieve reconstruction and classification tasks that constitute an alternative to the analysis pipeline presented for KM3NeT/ORCA in the KM3NeT Letter of Intent. They are used to infer event reconstruction estimates for the energy, the direction, and the interaction point of incident neutrinos. The spatial distribution of Cherenkov light generated by charged particles induced in neutrino interactions is classified as shower- or track-like, and the main background processes associated with the detection of atmospheric neutrinos are recognized. Performance comparisons to machine-learning classification and maximum-likelihood reconstruction algorithms previously developed for KM3NeT/ORCA are provided. It is shown that this application of deep convolutional neural networks to simulated datasets for a large-volume neutrino telescope yields competitive reconstruction results and performance improvements with respect to classical approaches.
CRIS-Team WoS Importer:2020-10-30

Event reconstruction in a liquid xenon Time Projection Chamber with an optically-open field cage - Stiegler, T.; Sangiorgio, S.; Brodsky, J. P.; Heffner, M.; Kharusi, S. Al; Anton, Gisela; Arnquist, I. J.; Badhrees, I.; Barbeau, P. S.; Beck, D.; Belov, V.; Bhatta, T.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2021)
nEXO is a proposed tonne-scale neutrinoless double beta decay (0νββ) experiment using liquid 136Xe (LXe) in a Time Projection Chamber (TPC) to read out ionization and scintillation signals. Between the field cage and the LXe vessel, a layer of LXe (“skin” LXe) is present, where no ionization signal is collected. Only scintillation photons are detected, owing to the lack of optical barrier around the field cage. In this work, we show that the light originating in the skin LXe region can be used to improve background discrimination by 5% over previous published estimates. This improvement comes from two elements. First, a fraction of the γ-ray background is removed by identifying light from interactions with an energy deposition in the skin LXe. Second, background from 222Rn dissolved in the skin LXe can be efficiently rejected by tagging the α decay in the 214Bi-214Po chain in the skin LXe.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Liquid xenon detectors; Monte Carlo methods; Neutrinoless double beta decay; Time-projection chambers

Evidence for a parity doublet Delta(1920)Rho33 and Delta(1940)Delta33 from gamma-rho -> rho-pi0eta - Horn, I.; Anisovich, A. V.; Anton, Gisela; Bantes, R.; Bartholomy, O.; Beck, R.; Beloglazov, Yu.; Bogendörfer, Regina; Castelijns, R.; Crede, V.; Ehmanns, A.; Ernst, J.; et al. (Physical Review Letters, 2008)

Evidence for neutrino emission from the nearby active galaxy NGC 1068 - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alispach, C.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; et al. (Science, 2022)
A supermassive black hole, obscured by cosmic dust, powers the nearby active galaxy NGC 1068. Neutrinos, which rarely interact with matter, could provide information on the galaxy's active core. We searched for neutrino emission from astrophysical objects using data recorded with the IceCube neutrino detector between 2011 and 2020. The positions of 110 known gamma-ray sources were individually searched for neutrino detections above atmospheric and cosmic backgrounds. We found that NGC 1068 has an excess of 79(-20)(+22) neutrinos at tera-electron volt energies, with a global significance of 4.2 sigma, which we interpret as associated with the active galaxy. The flux of high-energy neutrinos that we measured from NGC 1068 is more than an order of magnitude higher than the upper limit on emissions of tera-electron volt gamma rays from this source.
CRIS-Team WoS Importer:2023-01-27

Examination of the production of an isotensor dibaryon in the pp -> pp pi(+)pi(-) reaction - Adlarson, P.; Augustyniak, W.; Bardan, W.; Bashkanov, M.; Bergmann, F. S.; Berlowski, M.; Bondar, A.; Buescher, M.; Calen, H.; Ciepal, I.; Clement, H.; Czerwinski, E.; et al. (Physical Review C - Nuclear Physics, 2019)
The quasifree pp -> pp pi(+)pi(-) reaction has been measured by means of pd collisions at T-p = 1.2 GeV using the WASA detector setup at COSY enabling exclusive and kinematically complete measurements. Total and differential cross sections have been extracted for the energy region T-p = 1.08-1.36 GeV (root s = 2.35-2.46 GeV) covering thus the regions of N* (1440 ) and Delta(1232)Delta(1232) resonance excitations. Calculations describing these excitations by t-channel meson exchange as well as isospin relations based on the pp -> pp pi(0)pi(0) data underpredict substantially the measured total cross section. The calculations are also at variance with specific experimental differential cross sections. An isotensor Delta N dibaryon resonance with I(J(P)) = 2(1(+) ) produced associatedly with a pion is able to overcome these deficiencies. Such a dibaryon was predicted by Dyson and Xuong [Phys. Rev. Lett. 13, 815 (1964)] and more recently calculated by A. Gal and H. Garcilazo [Nucl. Phys. A 928, 73 (2014)].
CRIS-Team WoS Importer:2019-02-21

Examination of the production of an isotensor dibaryon in the pp→ppπ+π- reaction - Adlarson, P.; Augustyniak, W.; Bardan, W.; Bashkanov, Mikhail; Bergmann, F. S.; Berlowski, M.; Bondar, A.; Buescher, M.; Calen, H.; Ciepal, I.; Clement, H.; Czerwinski, E.; et al. (Physical Review C - Nuclear Physics, 2019)
The quasifree pp→ppπ+π- reaction has been measured by means of pd collisions at Tp=1.2GeV using the WASA detector setup at COSY enabling exclusive and kinematically complete measurements. Total and differential cross sections have been extracted for the energy region Tp=1.08-1.36 GeV (s=2.35-2.46GeV) covering thus the regions of N∗(1440) and Δ(1232)Δ(1232) resonance excitations. Calculations describing these excitations by t-channel meson exchange as well as isospin relations based on the pp→ppπ0π0 data underpredict substantially the measured total cross section. The calculations are also at variance with specific experimental differential cross sections. An isotensor ΔN dibaryon resonance with I(JP)=2(1+) produced associatedly with a pion is able to overcome these deficiencies. Such a dibaryon was predicted by Dyson and Xuong [Phys. Rev. Lett. 13, 815 (1964)PRLTAO0031-900710.1103/PhysRevLett.13.815] and more recently calculated by A. Gal and H. Garcilazo [Nucl. Phys. A 928, 73 (2014)NUPABL0375-947410.1016/j.nuclphysa.2014.02.019].
CRIS-Team Scopus Importer:2019-05-02

Expansion cone for the 3-inch PMTs of the KM3NeT optical modules - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Aharonian, F.; Aiello, S.; Albert, A.; Alexandri, M.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; et al. (Journal of Instrumentation, 2013)
Detection of high-energy neutrinos from distant astrophysical sources will open a new window on the Universe. The detection principle exploits the measurement of Cherenkov light emitted by charged particles resulting from neutrino interactions in the matter containing the telescope. A novel multi-PMT digital optical module (DOM) was developed to contain 31 3-inch photomultiplier tubes (PMTs). In order to maximize the detector sensitivity, each PMT will be surrounded by an expansion cone which collects photons that would otherwise miss the photocathode. Results for various angles of incidence with respect to the PMT surface indicate an increase in collection efficiency by 30% on average for angles up to 45 degrees with respect to the perpendicular. Ray-tracing calculations could reproduce the measurements, allowing to estimate an increase in the overall photocathode sensitivity, integrated over all angles of incidence, by 27% (for a single PMT). Prototype DOMs, being built by the KM3NeT consortium, will be equipped with these expansion cones.
Keywords: Optical detector readout concepts; Instrument optimisation; Cherenkov detectors; Large detector systems for particle and astroparticle physics

Exploration of different x-ray Talbot-Lau setups for dark-field lung imaging examined in a porcine lung - Ludwig, Veronika; Seifert, Maria; Hauke, Christian; Hellbach, Katharina; Horn, Florian; Pelzer, Georg; Radicke, Marcus; Rieger, Jens; Sutter, Sven-Martin; Michel, Thilo; Anton, Gisela (Physics in Medicine and Biology, 2019)
X-ray dark-field imaging is a promising technique for lung diagnosis. Due to the alveolar structure of lung tissue, a higher contrast is obtained by the dark-field image compared to the attenuation image. Animal studies indicate an enhancement regarding the detection of lung diseases in early stages. In this publication, we focus on the influence of different Talbot-Lau interferometer specifications while maintaining the x-ray source, sample magnification and detector system. By imaging the same porcine lung with three different grating sets, we analyze the contrast-to-noise ratio of the obtained dark-field images with respect to visibility and correlation length. We demonstrate that relatively large grating periods of the phase and of the analyzer grating are sufficient for high quality lung imaging at reasonable dose levels.
CRIS-Team WoS Importer:2019-03-29

Exploration of mass splitting and muon/tau mixing parameters for an eV-scale sterile neutrino with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Physics Letters B, 2024)
We present the first three-parameter fit to a 3+1 sterile neutrino model using 7.634 years of data from the IceCube Neutrino Observatory on νμ+ν‾μ charged-current interactions in the energy range 500–9976 GeV. Our analysis is sensitive to the mass-squared splitting between the heaviest and lightest mass state (Δm412), the mixing matrix element connecting muon flavor to the fourth mass state (|Uμ4|2), and the element connecting tau flavor to the fourth mass state (|Uτ4|2). Predicted propagation effects in matter enhance the signature through a resonance as atmospheric neutrinos from the Northern Hemisphere traverse the Earth to the IceCube detector at the South Pole. The remaining sterile neutrino matrix elements are left fixed, with |Ue4|2=0 and δ14=0, as they have a negligible effect, and δ24=π is set to give the most conservative limits. The result is consistent with the no-sterile neutrino hypothesis with a probability of 4.3%. Profiling the likelihood of each parameter yields the 90% confidence levels: 2.4eV2<Δm412<9.6eV2, 0.0081<|Uμ4|2<0.10, and |Uτ4|2<0.035, which narrows the allowed parameter-space for |Uτ4|2. However, the primary result of this analysis is the first map of the 3+1 parameter space exploring the interdependence of Δm412, |Uμ4|2, and |Uτ4|2.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Atmospheric neutrino IceCube TeV oscillation sterile

First air-shower measurements with the prototype station of the IceCube surface enhancement - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Proceedings of Science, 2022)
IceTop, the surface array of the IceCube Neutrino Observatory, consists of 162 ice-Cherenkov tanks distributed over an area of 1km2. Besides being used as a veto for the in-ice neutrino detector, IceTop is a powerful cosmic-ray detector. In the upcoming years, the capabilities of the IceTop array will be enhanced by augmenting the existing ice-Cherenkov tanks with an array of elevated scintillator panels and radio antennas. Combining the data obtained from the different detectors will improve the reconstruction of cosmic-ray energy and primary mass while reducing the energy threshold and increasing the aperture of the array. In January 2020, a prototype station consisting of 8 scintillation detectors and 3 antennas was deployed at the IceTop site. The prototype detectors are connected to one data-acquisition system and the readout of the radio antennas is triggered using the signals from the scintillators. This allows us to regularly observe secondary air shower particles hitting the scintillators, as well as the radio emission of high-energy air showers. In this contribution, we will discuss the results obtained from the prototype station in the past year, present the first cosmic-ray air showers measured with this prototype station, and show how the observations with the different detector types complement each other.
CRIS-Team Scopus Importer:2024-12-16

First all-flavor neutrino pointlike source search with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
A search for cosmic neutrino sources using the data collected with the ANTARES neutrino telescope between early 2007 and the end of 2015 is performed. For the first time, all neutrino interactions-charged and neutral-current interactions of all flavors-are considered in a search for point-like sources with the ANTARES detector. In previous analyses, only muon neutrino charged-current interactions were used. This is achieved by using a novel reconstruction algorithm for shower-like events in addition to the standard muon track reconstruction. The shower channel contributes about 23% of all signal events for an E-2 energy spectrum. No significant excess over background is found. The most signal-like cluster of events is located at (alpha, delta) = (343.8 degrees, 23.5 degrees) with a significance of 1.9 sigma. The neutrino flux sensitivity of the search is about E(2)d Phi/dE = 6 x 10(-9) GeV cm(-2) s(-1) for declinations from -90 degrees up to -42 degrees, and below 10(-8) GeV cm(-2) s(-1) for declinations up to 5 degrees. The directions of 106 source candidates and 13 muon track events from the IceCube high-energy sample events are investigated for a possible neutrino signal and upper limits on the signal flux are determined.

First all-flavor search for transient neutrino emission using 3-years of IceCube DeepCore data - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Ansseau, I.; et al. (Journal of Cosmology and Astroparticle Physics, 2022)
Since the discovery of a flux of high-energy astrophysical neutrinos, searches for their origins have focused primarily at TeV-PeV energies. Compared to sub-TeV searches, high-energy searches benefit from an increase in the neutrino cross section, improved angular resolution on the neutrino direction, and a reduced background from atmospheric neutrinos and muons. However, the focus on high energy does not preclude the existence of sub-TeV neutrino emission where IceCube retains sensitivity. Here we present the first all-flavor search from IceCube for transient emission of low-energy neutrinos, focusing on the energy region of 5.6-100 GeV using three years of data obtained with the IceCube-DeepCore detector. We find no evidence of transient neutrino emission in the data, thus leading to a constraint on the volumetric rate of astrophysical transient sources in the range of ∼ 705-2301 Gpc-3 yr-1 for sources following a subphotospheric energy spectrum with a mean energy of 100 GeV and a bolometric energy of 1052 erg.
CRIS-Team Scopus Importer:2022-02-11
Keywords: gamma ray burst experiments; neutrino astronomy; neutrino experiments

First detection of VHE γ-rays from SN 1006 by HESS - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Beilicke, M.; Bernloehr, K.; Bochow, A.; Boisson, C.; et al. (Astronomy & Astrophysics, 2010)
Aims. Recent theoretical predictions of the lowest very high energy (VHE) luminosity of SN 1006 are only a factor 5 below the previously published HESS upper limit, thus motivating further in-depth observations of this source. Methods. Deep observations at VHE energies (above 100 GeV) were carried out with the high energy stereoscopic system (HESS) of Cherenkov Telescopes from 2003 to 2008. More than 100 h of data have been collected and subjected to an improved analysis procedure. Results. Observations resulted in the detection of VHE γ-rays from SN 1006. The measured γ-ray spectrum is compatible with a power-law, the flux is of the order of 1% of that detected from the Crab Nebula, and is thus consistent with the previously established HESS upper limit. The source exhibits a bipolar morphology, which is strongly correlated with non-thermal X-rays. Conclusions. Because the thickness of the VHE-shell is compatible with emission from a thin rim, particle acceleration in shock waves is likely to be the origin of the γ-ray signal. The measured flux level can be accounted for by inverse Compton emission, but a mixed scenario that includes leptonic and hadronic components and takes into account the ambient matter density inferred from observations also leads to a satisfactory description of the multi-wavelength spectrum. © 2010 ESO.
Keywords: Gamma rays: stars; Supernovae: individual: SN 1006 (G327.6+14.6)

First intensity interferometry measurements with the H.E.S.S. telescopes - Zmija, Andreas; Vogel, Naomi; Wohlleben, Frederik; Anton, Gisela; Zink, Adrian; Funk, Stefan (Monthly Notices of the Royal Astronomical Society, 2024)
Intensity interferometry for astrophysical observations has gained increasing interest in the last decade. The method of correlating photon fluxes at different telescopes for high resolution astronomy without access to the phase of the incoming light is insensitive to atmospheric turbulence and does not require high-precision optical path control. The necessary large collection areas can be provided by Imaging Atmospheric Cherenkov Telescopes. Implementation of intensity interferometers to existing telescope systems such as VERITAS and MAGIC has proven to be successful for high-resolution imaging of stars. In 2022 April we equipped two telescopes of the H.E.S.S. array in Namibia with an intensity interferometry setup to measure southern sky stars and star systems during the bright moon period. We mounted an external optical system to the lid of the telescope cameras, which splits the incoming light and feeds it into two photomultipliers in order to measure the zero-baseline correlation within one telescope in addition to the cross-correlation between the telescopes. The optical elements are motorized, which enables live correction of tracking inaccuracies of the telescopes. During the campaign we measured the spatial correlation curves and thereby the angular diameters of λ Sco (Shaula) and σ Sgr (Nunki), while we also performed systematic studies of our interferometer using the multiple star system of α Cru (Acrux).
CRIS-Team Scopus Importer:2024-01-26
Keywords: instrumentation: high angular resolution; instrumentation: interferometers; methods: observational; stars: imaging; techniques: interferometric; telescopes

First limits on the very-high energy gamma-ray afterglow emission of a fast radio burst: H.E.S.S. Observations of FRB 150418 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; et al. (Astronomy & Astrophysics, 2017)
Aims. Following the detection of the fast radio burst FRB150418 by the SUPERB project at the Parkes radio telescope, we aim to search for very-high energy gamma-ray afterglow emission.Methods. Follow-up observations in the very-high energy gamma-ray domain were obtained with the H.E.S.S. imaging atmospheric Cherenkov telescope system within 14.5 h of the radio burst.Results. The obtained 1.4 h of gamma-ray observations are presented and discussed. At the 99% C.L. we obtained an integral upper limit on the gamma-ray flux of Phi(gamma)(E > 350 GeV) < 1.33 x 10(-8) m(-2) s(-1). Differential flux upper limits as function of the photon energy were derived and used to constrain the intrinsic high-energy afterglow emission of FRB 150418.Conclusions. No hints for high-energy afterglow emission of FRB 150418 were found. Taking absorption on the extragalactic background light into account and assuming a distance of z = 0 : 492 based on radio and optical counterpart studies and consistent with the FRB dispersion, we constrain the gamma-ray luminosity at 1 TeV to L < 5 : 1 x 10(47) erg/s at 99% C.L.
Keywords: Astroparticle physics; Gamma rays: general

First results on dark matter annihilation in the Sun using the ANTARES neutrino telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anton, L.; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
A search for high-energy neutrinos coming from the direction of the Sun has been performed using the data recorded by the ANTARES neutrino telescope during 2007 and 2008. The neutrino selection criteria have been chosen to maximize the selection of possible signals produced by the self-annihilation of weakly interacting massive particles accumulated in the centre of the Sun with respect to the atmospheric background. After data unblinding, the number of neutrinos observed towards the Sun was found to be compatible with background expectations. The 90% CL upper limits in terms of spin-dependent and spin-independent WIMP-proton cross-sections are derived and compared to predictions of two supersymmetric models, CMSSM and MSSM-7. The ANTARES limits are comparable with those obtained by other neutrino observatories and are more stringent than those obtained by direct search experiments for the spin-dependent WIMP-proton cross-section in the case of hard self-annihilation channels (W+W-, tau(+)tau(-)).
Keywords: neutrino experiments; dark matter detectors; supersymmetry and cosmology; particle physics - cosmology connection

First search for neutrinos in correlation with gamma-ray bursts with the ANTARES neutrino telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
A search for neutrino-induced muons in correlation with a selection of 40 gamma-ray bursts that occurred in 2007 has been performed with the ANTARES neutrino telescope. During that period, the detector consisted of 5 detection lines. The ANTARES neutrino telescope is sensitive to TeV-PeV neutrinos that are predicted from gamma-ray bursts. No events were found in correlation with the prompt photon emission of the gamma-ray bursts and upper limits have been placed on the flux and fluence of neutrinos for different models.
Keywords: neutrino experiments; neutrino astronomy; gamma ray bursts theory

FIRST SEARCH FOR POINT SOURCES OF HIGH-ENERGY COSMIC NEUTRINOS WITH THE ANTARES NEUTRINO TELESCOPE - Adrian-Martinez, S.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J. -J.; et al. (Astrophysical Journal Letters, 2011)
Results are presented of a search for cosmic sources of high-energy neutrinos with the ANTARES neutrino telescope. The data were collected during 2007 and 2008 using detector configurations containing between 5 and 12 detection lines. The integrated live time of the analyzed data is 304 days. Muon tracks are reconstructed using a likelihood-based algorithm. Studies of the detector timing indicate a median angular resolution of 0.5 +/- 0.1 deg. The neutrino flux sensitivity is 7.5 x 10(-8)(E(v)/GeV)(-2) GeV(-1) s(-1) cm(-2) for the part of the sky that is always visible (delta < -48 deg), which is better than limits obtained by previous experiments. No cosmic neutrino sources have been observed.
Keywords: astroparticle physics; cosmic rays; neutrinos

Flux upper limits for 47 AGN observed with H.E.S.S. in 2004 - 2011 - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2014)
Context. About 40% of the observation time of the High Energy Stereoscopic System (H.E.S.S.) is dedicated to studying active galactic nuclei (AGN), with the aim of increasing the sample of known extragalactic very-high-energy (VHE, E > 100 GeV) sources and constraining the physical processes at play in potential emitters. Aims. H.E.S.S. observations of AGN, spanning a period from April 2004 to December 2011, are investigated to constrain their γ-ray fluxes. Only the 47 sources without significant excess detected at the position of the targets are presented. Methods. Upper limits on VHE fluxes of the targets were computed and a search for variability was performed on the nightly time scale. Results. For 41 objects, the flux upper limits we derived are the most constraining reported to date. These constraints at VHE are compared with the flux level expected from extrapolations of Fermi-LAT measurements in the two-year catalog of AGN. The H.E.S.S. upper limits are at least a factor of two lower than the extrapolated Fermi-LAT fluxes for 11 objects. Taking into account the attenuation by the extragalactic background light reduces the tension for all but two of them, suggesting intrinsic curvature in the high-energy spectra of these two AGN. Conclusions. Compilation efforts led by current VHE instruments are of critical importance for target-selection strategies before the advent of the Cherenkov Telescope Array (CTA). © ESO, 2014.
Keywords: Galaxies: active; Gamma rays: galaxies

Follow-up of Astrophysical Transients in Real Time with the IceCube Neutrino Observatory - Aartsen, M. G.; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Amin, N. M.; Andeen, K.; Anderson, T.; Ansseau, I.; et al. (Astrophysical Journal, 2021)
In multi-messenger astronomy, rapid investigation of interesting transients is imperative. As an observatory with a 4 pi steradian field of view, and similar to 99% uptime, the IceCube Neutrino Observatory is a unique facility to follow up transients, as well as to provide valuable insights for other observatories and inform their observational decisions. Since 2016, IceCube has been using low-latency data to rapidly respond to interesting astrophysical events reported by the multi-messenger observational community. Here, we describe the pipeline used to perform these followup analyses, and provide a summary of the 58 analyses performed as of July 2020. We find no significant signal in the first 58 analyses performed. The pipeline has helped inform various electromagnetic observation strategies, and has constrained neutrino emission from potential hadronic cosmic accelerators.
CRIS-Team WoS Importer:2021-04-02

Framework and tools for the simulation and analysis of the radio emission from air showers at IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Anton, Gisela; et al. (Journal of Instrumentation, 2022)
The Surface Enhancement of the IceTop air-shower array will include the addition of radio antennas and scintillator panels, co-located with the existing ice-Cherenkov tanks and covering an area of about 1 km2. Together, these will increase the sensitivity of the IceCube Neutrino Observatory to the electromagnetic and muonic components of cosmic-ray-induced air showers at the South Pole. The inclusion of the radio technique necessitates an expanded set of simulation and analysis tools to explore the radio-frequency emission from air showers in the 70 MHz to 350 MHz band. In this paper we describe the software modules that have been developed to work with time- and frequency-domain information within IceCube's existing software framework, IceTray, which is used by the entire IceCube collaboration. The software includes a method by which air-shower simulation, generated using CoREAS, can be reused via waveform interpolation, thus overcoming a significant computational hurdle in the field.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Antennas; Data analysis; Simulation methods and programs; Software architectures (event data models; frameworks and databases)

Gamma-ray blazar spectra with H.E.S.S. II mono analysis: The case of PKS 2155-304 and PG 1553+113 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Astronomy & Astrophysics, 2017)
Context. The addition of a 28 m Cherenkov telescope (CT5) to the H.E.S.S. array extended the experiment's sensitivity to lower energies. The lowest energy threshold is obtained using monoscopic analysis of data taken with CT5, providing access to gamma-ray energies below 100 GeV for small zenith angle observations. Such an extension of the instrument's energy range is particularly beneficial for studies of active galactic nuclei with soft spectra, as expected for those at a redshift ≥0.5. The high-frequency peaked BL Lac objects PKS 2155-304 (z = 0:116) and PG 1553+113 (0:43 < z < 0:58) are among the brightest objects in the gamma-ray sky, both showing clear signatures of gamma-ray absorption at E > 100 GeV interpreted as being due to interactions with the extragalactic background light (EBL). Aims. The aims of this work are twofold: to demonstrate the monoscopic analysis of CT5 data with a low energy threshold, and to obtain accurate measurements of the spectral energy distributions (SED) of PKS 2155-304 and PG 1553+113 near their SED peaks at energies 100 GeV. Methods. Multiple observational campaigns of PKS 2155-304 and PG 1553+113 were conducted during 2013 and 2014 using the full H.E.S.S. II instrument (CT1'5). A monoscopic analysis of the data taken with the new CT5 telescope was developed along with an investigation into the systematic uncertainties on the spectral parameters which are derived from this analysis. Results. Using the data from CT5, the energy spectra of PKS 2155-304 and PG 1553+113 were reconstructed down to conservative threshold energies of 80 GeV for PKS 2155-304, which transits near zenith, and 110 GeV for the more northern PG 1553+113. The measured spectra, well fitted in both cases by a log-parabola spectral model (with a 5.0φ statistical preference for non-zero curvature for PKS 2155-304 and 4.5φ for PG 1553+113), were found consistent with spectra derived from contemporaneous Fermi-LAT data, indicating a sharp break in the observed spectra of both sources at E 100 GeV. When corrected for EBL absorption, the intrinsic H.E.S.S. II mono and Fermi-LAT spectrum of PKS 2155-304 was found to show significant curvature. For PG 1553+113, however, no significant detection of curvature in the intrinsic spectrum could be found within statistical and systematic uncertainties.
Keywords: BL Lacertae objects: individual: PG 1553+113; BL Lacertae objects: individual: PKS 2155-304; Galaxies: active; Gamma rays: galaxies

GAWBS noise reduction in microstructured fibers - Elser, Dominique Alexander; Korn, Alexander; Lorenz, Stefan; Glöckl, Oliver; Marquardt, Christoph; Andersen, Ulrik Lund; Leuchs, Gerd (2005 European Quantum Electronics Conference, EQEC '05, 2005)
Guided Acoustic Wave Brillouin Scattering (GAWBS) generates phase and polarization noise of light propagating in glass fibers. We experimentally demonstrate the reduction of GAWBS noise in microstructured fibers in comparison with standard fibers. © 2005 IEEE.
Created from Fastlane, Scopus look-up

Graph Neural Networks for low-energy event classification & reconstruction in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aggarwal, N.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alves Jr, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; et al. (Journal of Instrumentation, 2022)
IceCube, a cubic-kilometer array of optical sensors built to detect atmospheric and astrophysical neutrinos between 1 GeV and 1 PeV, is deployed 1.45 km to 2.45 km below the surface of the ice sheet at the South Pole. The classification and reconstruction of events from the in-ice detectors play a central role in the analysis of data from IceCube. Reconstructing and classifying events is a challenge due to the irregular detector geometry, inhomogeneous scattering and absorption of light in the ice and, below 100 GeV, the relatively low number of signal photons produced per event. To address this challenge, it is possible to represent IceCube events as point cloud graphs and use a Graph Neural Network (GNN) as the classification and reconstruction method. The GNN is capable of distinguishing neutrino events from cosmic-ray backgrounds, classifying different neutrino event types, and reconstructing the deposited energy, direction and interaction vertex. Based on simulation, we provide a comparison in the 1 GeV-100 GeV energy range to the current state-of-the-art maximum likelihood techniques used in current IceCube analyses, including the effects of known systematic uncertainties. For neutrino event classification, the GNN increases the signal efficiency by 18% at a fixed background rate, compared to current IceCube methods. Alternatively, the GNN offers a reduction of the background (i.e. false positive) rate by over a factor 8 (to below half a percent) at a fixed signal efficiency. For the reconstruction of energy, direction, and interaction vertex, the resolution improves by an average of 13%-20% compared to current maximum likelihood techniques in the energy range of 1 GeV-30 GeV. The GNN, when run on a GPU, is capable of processing IceCube events at a rate nearly double of the median IceCube trigger rate of 2.7 kHz, which opens the possibility of using low energy neutrinos in online searches for transient events.
CRIS-Team WoS Importer:2023-02-17

Gravitational Wave Follow-Up Using Low Energy Neutrinos in IceCube DeepCore - Balagopal, Aswathi V.; Hussain, Raamis; Pizzuto, Alex; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; et al. (Proceedings of Science, 2022)
The IceCube DeepCore is a dense infill array of the IceCube Neutrino Observatory at the South Pole. While IceCube is best suited for detecting neutrinos with energies of several 100 GeV and above, DeepCore allows to probe neutrinos with lower energies. We focus on a sample of neutrinos with energies above approximately 10 GeV, which was originally optimised for oscillation experiments. Recently, it has been adapted to enable searches for transient sources of astrophysical neutrinos in the sky. In particular, this low-energy dataset can be used to conduct follow-up searches of gravitational wave transients detected by the LIGO-Virgo instruments. A study of this, which complements IceCube's follow-up of gravitational wave events using high-energy neutrino samples, will be discussed here.
CRIS-Team Scopus Importer:2024-12-16

HESS and Fermi-LAT discovery of γ-rays from the blazar 1ES 1312-423 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2013)
A deep observation campaign carried out by the High Energy Stereoscopic System (HESS) on Centaurus A enabled the discovery of γ-rays from the blazar 1ES 1312-423, 2° away from the radio galaxy. With a differential flux at 1 TeV of f(1 TeV) = (1.9 ± 0.6 ± 0.4) × 10 cm s TeV corresponding to 0.5 per cent of the Crab nebula differential flux and a spectral index γ = 2.9 ± 0.5 ± 0.2, 1ES 1312-423 is one of the faintest sources ever detected in the very high energy (E <100 GeV) extragalactic sky. A careful analysis using three and a half years of Fermi Large Area Telescope (Fermi-LAT) data allows the discovery at high energies (100 < E MeV) of a hard spectrum (γ =1.4±0.4stat ±0.2sys) source coincident with 1ES 1312-423. Radio, optical, UV and X-ray observations complete the spectral energy distribution of this blazar, now covering 16 decades in energy. The emission is successfully fitted with a synchrotron self-Compton model for the non-thermal component, combined with a blackbody spectrum for the optical emission from the host galaxy. © 2013 The Authors. Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: Bl Lacertae objects: individual: 1ES 1312-423; Galaxies: active; Galaxies: jets; Gamma-rays: galaxies.; Radiation mechanisms: non-thermal

H.E.S.S. constraints on dark matter annihilations towards the sculptor and carina dwarf galaxies - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Barnacka, A.; Barres De Almeida, U.; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; Behera, B.; Bernlöhr, K.; et al. (Astroparticle Physics, 2011)
The Sculptor and Carina dwarf spheroidal galaxies were observed with the H.E.S.S. Cherenkov telescope array between January 2008 and December 2009. The data sets consist of a total of 11.8 h and 14.8 h of high quality data, respectively. No gamma-ray signal was detected at the nominal positions of these galaxies above 220 GeV and 320 GeV, respectively. Upper limits on the gamma-ray fluxes at 95% CL assuming two forms for the spectral energy distribution (a power law shape and one derived from dark matter annihilation) are obtained at the level of 10-10 cm s in the TeV range. Constraints on the velocity weighted dark matter particle annihilation cross section for both Sculptor and Carina dwarf galaxies range from 〈σv〉 ∼ 10 cm s down to 〈σv〉 ∼ 10 cm s depending on the dark matter halo model used. Possible enhancements of the gamma-ray flux are studied: the Sommerfeld effect, which is found to exclude some dark matter particle masses, the internal Bremsstrahlung and clumps in the dark-matter halo distributions. © 2011 Published by Elsevier B.V.
Keywords: Carina; Dark matter; Gamma-rays: observations - Dwarf spheroidal galaxy; Internal Bremsstrahlung; Sculptor; Sommerfeld enhancement

H.E.S.S. detection of TeV emission from the interaction region between the supernova remnant G349.7+0.2 and a molecular cloud - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguner, E. O.; Backes, Michael; Balenderans, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astronomy & Astrophysics, 2015)
G349.7+0.2 is a young Galactic supernova remnant (SNR) located at the distance of 11.5 kpc and observed across the entire electromagnetic spectrum from radio to high energy (HE; 0.1 GeV < E < 100 GeV) γ-rays. Radio and infrared observations indicate that the remnant is interacting with a molecular cloud. In this paper, the detection of very high energy (VHE, E > 100 GeV) γ-ray emission coincident with this SNR with the High Energy Stereoscopic System (H.E.S.S.) is reported. This makes it one of the farthest Galactic SNR ever detected in this domain. An integral flux F (E > 400 GeV) = (6.5 ± 1.1 ± 1.3) × 10 ph cm s corresponding to ∼0.7% of that of the Crab Nebula and to a luminosity of ∼10 erg s above the same energy threshold, and a steep photon index Γ = 2.8 ± 0.27stat ± 0.20 are measured. The analysis of more than 5 yr of Fermi-LAT data towards this source shows a power-law like spectrum with a best-fit photon index Γ = 2.2 ± 0.04 . The combined γ-ray spectrum of G349.7+0.2 can be described by either a broken power-law (BPL) or a power-law with exponential (or sub-exponential) cutoff(PLC). In the former case, the photon break energy is found at E = 55 GeV, slightly higher than what is usually observed in the HE/VHE γ-ray emitting middle-aged SNRs known to be interacting with molecular clouds. In the latter case, the exponential (respectively sub-exponential) cutoff energy is measured at E = 1.4 (respectively 0.35 ) TeV. A pion-decay process resulting from the interaction of the accelerated protons and nuclei with the dense surrounding medium is clearly the preferred scenario to explain the γ-ray emission. The BPL with a spectral steepening of 0.5-1 and the PLC provide equally good fits to the data. The product of the average gas density and the total energy content of accelerated protons and nuclei amounts to n W ∼ 5 × 10 erg cm.
Keywords: Gamma rays: General; ISM: clouds; ISM: supernova remnants

H.E.S.S. discovery of VHE γ-rays from the quasar PKS 1510-089 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Behera, B.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2013)
The quasar PKS 1510-089 (z = 0.361) was observed with the H.E.S.S. array of imaging atmospheric Cherenkov telescopes during high states in the optical and GeV bands, to search for very high energy (VHE, defined as E ≥ 0.1 TeV) emission. VHE γ-rays were detected with a statistical significance of 9.2 standard deviations in 15.8 h of H.E.S.S. data taken during March and April 2009. A VHE integral flux of I(0.15 TeV < E < 1.0TeV) = (1.0 ±0.2 ±0.2) ×10 cm s is measured. The best-fit power law to the VHE data has a photon index of γ = 5.4 ± 0.7 ± 0.3. The GeV and optical light curves show pronounced variability during the period of H.E.S.S. observations. However, there is insufficient evidence to claim statistically significant variability in the VHE data. Because of its relatively high redshift, the VHE flux from PKS 1510-089 should suffer considerable attenuation in the intergalactic space due to the extragalactic background light (EBL). Hence, the measured γ-ray spectrum is used to derive upper limits on the opacity due to EBL, which are found to be comparable with the previously derived limits from relatively-nearby BL Lac objects. Unlike typical VHE-detected blazars where the broadband spectrum is dominated by nonthermal radiation at all wavelengths, the quasar PKS 1510-089 has a bright thermal component in the optical to UV frequency band. Among all VHE detected blazars, PKS 1510-089 has the most luminous broad line region. The detection of VHE emission from this quasar indicates a low level of γ - γ absorption on the internal optical to UV photon field. © 2013 ESO.
Keywords: Gamma rays: galaxies; Infrared: diffuse background; Quasars: individual: PKS 1510; 089

HESS J1640-465-an exceptionally luminous TeV γ-ray supernova remnant - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
The results of follow-up observations of the TeV γ-ray source HESS J1640-465 from 2004 to 2011 with the High Energy Stereoscopic System (HESS) are reported in this work. The spectrum is well described by an exponential cut-offpower law with photon index γ = 2.11 ± 0.09 ± 0.10, and a cut-offenergy of E = 6.0 TeV. The TeV emission is significantly extended and overlaps with the northwestern part of the shell of the SNR G338.3-0.0. The new HESS results, a re-analysis of archival XMM-Newton data and multiwavelength observations suggest that a significant part of the γ-ray emission from HESS J1640-465 originates in the supernova remnant shell. In a hadronic scenario, as suggested by the smooth connection of the GeV and TeV spectra, the product of total proton energy and mean target density could be as high as W 4 × 10(d/10kpc) erg cm. © 2014 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: G338.3-0.0-ISM; Individual objects; Non-thermal-ISM; Radiation mechanisms; Supernova remnants

HESS J1818-154, a new composite supernova remnant discovered in TeV gamma rays and X-rays - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2014)
Composite supernova remnants (SNRs) constitute a small subclass of the remnants of massive stellar explosions where non-thermal radiation is observed from both the expanding shell-like shock front and from a pulsar wind nebula (PWN) located inside of the SNR. These systems represent a unique evolutionary phase of SNRs where observations in the radio, X-ray, and γ-ray regimes allow the study of the co-evolution of both these energetic phenomena. In this article, we report results from observations of the shell-type SNR G 15.4+0.1 performed with the High Energy Stereoscopic System (H.E.S.S.) and XMM-Newton. A compact TeV γ-ray source, HESS J1818-154, located in the center and contained within the shell of G 15.4+0.1 is detected by H.E.S.S. and featurs a spectrum best represented by a power-law model with a spectral index of-2.3 ± 0.3 ± 0.2 and an integral flux of F(> 0.42 TeV) = (0.9 ± 0.3 ± 0.2) × 10 cm s. Furthermore, a recent observation with XMM-Newton reveals extended X-ray emission strongly peaked in the center of G 15.4+0.1. The X-ray source shows indications of an energy-dependent morphology featuring a compact core at energies above 4 keV and more extended emission that fills the entire region within the SNR at lower energies. Together, the X-ray and VHE γ-ray emission provide strong evidence of a PWN located inside the shell of G 15.4+0.1 and this SNR can therefore be classified as a composite based on these observations. The radio, X-ray, and γ-ray emission from the PWN is compatible with a one-zone leptonic model that requires a low average magnetic field inside the emission region. An unambiguous counterpart to the putative pulsar, which is thought to power the PWN, has been detected neither in radio nor in X-ray observations of G 15.4+0.1. © 2014 ESO.
Keywords: Gamma rays: general; Methods: observational; Supernovae: individual: HESS J1818-154; X-rays: general; X-rays: individuals: G15.4+0.1

HESS J1943+213: A candidate extreme BL Lacertae object - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; et al. (Astronomy & Astrophysics, 2011)
Context. The H.E.S.S. Cherenkov telescope array has been surveying the Galactic plane for new VHE (>100 GeV) gamma-ray sources. Aims. We report on a newly detected point-like source, HESS J1943+213. This source coincides with an unidentified hard X-ray source IGR J19443+2117, which was proposed to have radio and infrared counterparts. Methods. We combine new H.E.S.S., Fermi/LAT and Nançay Radio Telescope observations with pre-existing non-simultaneous multi-wavelength observations of IGR J19443+2117 and discuss the likely source associations as well as the interpretation as an active galactic nucleus, a gamma-ray binary or a pulsar wind nebula. Results. HESS J1943+213 is detected at the significance level of 7.9σ (post-trials) at RA(J2000)= 19 4355 ± 1 ± 1 , Dec(J2000)= +21° 18'8" ± 17" ± 20". The source has a soft spectrum with photon index Γ = 3.1 ± 0.3 ± 0.2 and a flux above 470 GeV of (1.3 ± 0.2 ± 0.3) × 10 cm s . There is no Fermi/LAT counterpart down to a flux limit of 6 × 10 cm s in the 0.1-100 GeV energy range (95% confidence upper limit calculated for an assumed power-law model with a photon index Γ = 2.0). The data from radio to VHE gamma-rays do not show any significant variability. Conclusions. The lack of a massive stellar counterpart disfavors the binary hypothesis, while the soft VHE spectrum would be very unusual in case of a pulsar wind nebula. In addition, the distance estimates for Galactic counterparts places them outside of the Milky Way. All available observations favor an interpretation as an extreme, high-frequency peaked BL Lac object with a redshift z > 0.14. This would be the first time a blazar is detected serendipitously from ground-based VHE observations, and the first VHE AGN detected in the Galactic Plane. © 2011 ESO.
Keywords: BL Lacertae objects: individual: IGR J19443+2117; galaxies: active; gamma rays: general

H.E.S.S. Limits on Linelike Dark Matter Signatures in the 100 GeV to 2 TeV Energy Range Close to the Galactic Center - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Physical Review Letters, 2016)
A search for dark matter linelike signals iss performed in the vicinity of the Galactic Center by the H.E.S.S. experiment on observational data taken in 2014. An unbinned likelihood analysis iss developed to improve the sensitivity to linelike signals. The upgraded analysis along with newer data extend the energy coverage of the previous measurement down to 100 GeV. The 18 h of data collected with the H.E.S.S. array allow one to rule out at 95% C.L. the presence of a 130 GeV line (at l=-1.5°, b=0° and for a dark matter profile centered at this location) previously reported in Fermi-LAT data. This new analysis overlaps significantly in energy with previous Fermi-LAT and H.E.S.S. results. No significant excess associated with dark matter annihilations was found in the energy range of 100 GeV to 2 TeV and upper limits on the gamma-ray flux and the velocity weighted annihilation cross section are derived adopting an Einasto dark matter halo profile. Expected limits for present and future large statistics H.E.S.S. observations are also given.

H.E.S.S. observations of the binary system PSR B1259-63/LS 2883 around the 2010/2011 periastron passage - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
Aims. We present very high energy (VHE; E > 100 GeV) data from the γ-ray binary system PSR B1259-63/LS 2883 taken around its periastron passage on 15th of December 2010 with the High Energy Stereoscopic System (H.E.S.S.) of Cherenkov Telescopes. We aim to search for a possible TeV counterpart of the GeV flare detected by the Fermi LAT. In addition, we aim to study the current periastron passage in the context of previous observations taken at similar orbital phases, testing the repetitive behaviour of the source. Methods. Observations at VHEs were conducted with H.E.S.S. from 9th to 16th of January 2011. The total dataset amounts to 6 h of observing time. The data taken around the 2004 periastron passage were also re-analysed with the current analysis techniques in order to extend the energy spectrum above 3 TeV to fully compare observation results from 2004 and 2011. Results. The source is detected in the 2011 data at a significance level of 11.5σ revealing an averaged integral flux above 1 TeV of (1.01 ± 0.18 ± 0.20) × 10 cm s. The differential energy spectrum follows a power-law shape with a spectral index Γ = 2.92 ± 0.30 ± 0.20 and a flux normalisation at 1 TeV of N = (1.95 ± 0.32 ± 0.39) × 10 TeV cm s. The measured light curve does not show any evidence for variability of the source on the daily scale. The re-analysis of the 2004 data yields results compatible with the published ones. The differential energy spectrum measured up to 10 TeV is consistent with a power law with a spectral index Γ = 2.81 ± 0.10 ± 0.20 and a flux normalisation at 1 TeV of N = (1.29 ± 0.08 ± 0.26) × 10 TeV cm s. Conclusions. The measured integral flux and the spectral shape of the 2011 data are compatible with the results obtained around previous periastron passages. The absence of variability in the H.E.S.S. data indicates that the GeV flare observed by Fermi LAT in the time period covered also by H.E.S.S. observations originates in a different physical scenario than the TeV emission. Moreover, the comparison of the new results to the results from the 2004 observations made at a similar orbital phase provides a stronger evidence of the repetitive behaviour of the source. © ESO, 2013.
Keywords: Gamma rays: general; Pulsars: individual: PSR B1259-63; Stars: individual: LS 2883; X-rays: binaries

HESS observations of the Carina nebula and its enigmatic colliding wind binary Eta Carinae - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
The massive binary system Eta Carinae and the surrounding Hii complex, the Carina nebula, are potential particle acceleration sites from which very high energy (VHE; E≥ 100GeV) γ-ray emission could be expected. This paper presents data collected during VHE γ-ray observations with the HESS telescope array from 2004 to 2010, which cover a full orbit of Eta Carinae. In the 33.1-h data set no hint of significant γ-ray emission from Eta Carinae has been found and an upper limit on the γ-ray flux of (99per cent confidence level) is derived above the energy threshold of 470GeV. Together with the detection of high energy (HE; 0.1 ≤E≤ 100GeV) γ-ray emission by the Fermi Large Area Telescope up to 100GeV, and assuming a continuation of the average HE spectral index into the VHE domain, these results imply a cut-off in the γ-ray spectrum between the HE and VHE γ-ray range. This could be caused either by a cut-off in the accelerated particle distribution or by severe γ-γ absorption losses in the wind collision region. Furthermore, the search for extended γ-ray emission from the Carina nebula resulted in an upper limit on the γ-ray flux of (99per cent confidence level). The derived upper limit of ∼23 on the cosmic ray enhancement factor is compared with results found for the old-age mixed-morphology supernova remnant W28. © 2012 The Authors Monthly Notices of the Royal Astronomical Society © 2012 RAS.
Keywords: Acceleration of particles; ISM: individual objects: Carina nebula; ISM: individual objects: Eta Carina; Open clusters and associations: general; Radiation mechanisms: non-thermal; X-rays: binaries

H.E.S.S. observations of the Crab during its March 2013 GeV gamma-ray flare - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2014)
Context. On March 4, 2013 the Fermi-LAT and AGILE reported a flare from the direction of the Crab nebula in which the high-energy (HE; E > 100 MeV) flux was six times above its quiescent level. Simultaneous observations in other energy bands give us hints about the emission processes during the flare episode and the physics of pulsar wind nebulae in general. Aims. We search for variability in the emission of the Crab nebula at very-high energies (VHE; E > 100 GeV), using contemporaneous data taken with the H.E.S.S. array of Cherenkov telescopes. Methods. Observational data taken with the H.E.S.S. instrument on five consecutive days during the flare were analysed for the flux and spectral shape of the emission from the Crab nebula. Night-wise light curves are presented with energy thresholds of 1 TeV and 5 TeV. Results. The observations conducted with H.E.S.S. on March 6 to March 10, 2013 show no significant changes in the flux. They limit the variation in the integral flux above 1 TeV to less than 63% and the integral flux above 5 TeV to less than 78% at a 95% confidence level. © 2014 ESO.
Keywords: Gamma rays: ISM; ISM: individual objects: Crab nebula; Radiation mechanisms: non-thermal; Relativistic processes

H.E.S.S. observations of the globular clusters NGC 6388 and M15 and search for a dark matter signal - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; Behera, B.; et al. (Astrophysical Journal, 2011)
Observations of the globular clusters (GCs) NGC 6388 and M15 were carried out by the High Energy Stereoscopic System array of Cherenkov telescopes for a live time of 27.2 and 15.2 hr, respectively. No gamma-ray signal is found at the nominal target position of NGC 6388 and M15. In the primordial formation scenario, GCs are formed in a dark matter (DM) halo and DM could still be present in the baryon-dominated environment of GCs. This opens the possibility of observing a DM self-annihilation signal. The DM content of the GCs NGC 6388 and M15 is modeled taking into account the astrophysical processes that can be expected to influence the DM distribution during the evolution of the GC: the adiabatic contraction of DM by baryons, the adiabatic growth of a black hole in the DM halo, and the kinetic heating of DM by stars. Ninety-five percent confidence level exclusion limits on the DM particle velocity-weighted annihilation cross section are derived for these DM halos. In the TeV range, the limits on the velocity-weighted annihilation cross section are derived at the 10 cm s level and a few 10 cm s for NGC 6388 and M15, respectively. © 2011. The American Astronomical Society. All rights reserved..
Keywords: black hole physics; dark matter; gamma rays: general; globular clusters: individual (NGC 6388; M15)

H.E.S.S. reveals a lack of TeV emission from the supernova remnant Puppis A - Abramowski, A.; Aharonian, F.; Ait Benkhali, F.; Akhperjanian, A. G.; Angüner, E. O.; Backes, M.; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Becker Tjus, J.; Berge, D.; et al. (Astronomy & Astrophysics, 2015)
Results. The analysis of the H.E.S.S. data does not reveal any significant emission towards Puppis A. The derived upper limits on the differential photon flux imply that its broadband γ-ray spectrum must exhibit a spectral break or cutoff. By combining Fermi-LAT and H.E.S.S. measurements, the 99% confidence-level upper limits on such a cutoff are found to be 450 and 280 GeV, assuming a power law with a simple exponential and a sub-exponential cutoff, respectively. It is concluded that none of the standard limitations (age, size, radiative losses) on the particle acceleration mechanism, assumed to be continuing at present, can explain the lack of VHE signal. The scenario in which particle acceleration has ceased some time ago is considered as an alternative explanation. The HE/VHE spectrum of Puppis A could then exhibit a break of non-radiative origin (as observed in several other interacting SNRs, albeit at somewhat higher energies), owing to the interaction with dense and neutral material, in particular towards the NE region.
Keywords: Acceleration of particles; Cosmic rays; Gamma rays: ISM; ISM: individual objects: Puppis A; Radiation mechanisms: non-thermal

HESS upper limit on the very high energy γ-ray emission from the globular cluster 47 Tucanae - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2009)
Observations of the globular cluster 47 Tucanae (NGC 104), which contains at least 23 ms pulsars, were performed with the HESS telescope system. The observations lead to an upper limit of F(E < 800 GeV) < 6.7 × 10-13 cm-2 s-1 on the integral γ-ray photon flux from 47 Tucanae. Considering millisecond pulsars as the unique potential source of γ-rays in the globular cluster, constraints based on emission models are derived: on the magnetic field in the average pulsar nebula and on the conversion efficiency of spin-down power to γ-ray photons or to relativistic leptons. © 2009 ESO.
Keywords: Galaxy: globular clusters: individual: 47 Tucanae; Gamma rays: observations; Stars: pulsars: general

Hess upper limits on very high energy gamma-ray emission from the microquasar grs 1915+105 - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, Julien; et al. (Astronomy & Astrophysics, 2009)
Context: High energy particles reside in the relativistic jets of microquasars, making them possible sources of very high energy radiation (VHE, < 100 GeV). Detecting this emission would provide a new handle on jet physics. Aims: Observations of the microquasar GRS 1915+105 with the HESS telescope array were undertaken in 2004-2008 to search for VHE emission. Methods: Stereoscopic imaging of Cherenkov radiation from extensive air showers is used to reconstruct the energy and direction of the incident gamma rays. Results: There is no evidence for a VHE gamma-ray signal either from the direction of the microquasar or its vicinity. An upper limit of 6.1 × 10ph cms (99.9% confidence level) is set on the photon flux above 410 GeV, equivalent to a VHE luminosity of ̃ 10erg s at 11 kpc. Conclusions. The VHE to X-ray luminosity ratio in GRS 1915+105 is at least four orders of magnitude lower than the ratio observed in gamma-ray binaries. The VHE radiative efficiency of the compact jet is less than 0.01% based on its estimated total power of 10 erg s. Particle acceleration in GRS 1915+105 is not efficient at high energies and/or the magnetic field is too strong. It is also possible that VHE gamma-rays are produced by GRS 1915+105, but the emission is highly time-dependent. © 2009 ESO.
Keywords: Gamma rays: observations; X-rays: binaries; X-rays: individuals: GRS 1915+105

High-energy neutrino follow-up search of gravitational wave event GW150914 with ANTARES and IceCube - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2016)
We present the high-energy-neutrino follow-up observations of the first gravitational wave transient GW150914 observed by the Advanced LIGO detectors on September 14, 2015. We search for coincident neutrino candidates within the data recorded by the IceCube and Antares neutrino detectors. A possible joint detection could be used in targeted electromagnetic follow-up observations, given the significantly better angular resolution of neutrino events compared to gravitational waves. We find no neutrino candidates in both temporal and spatial coincidence with the gravitational wave event. Within ±500 s of the gravitational wave event, the number of neutrino candidates detected by IceCube and Antares were three and zero, respectively. This is consistent with the expected atmospheric background, and none of the neutrino candidates were directionally coincident with GW150914. We use this nondetection to constrain neutrino emission from the gravitational-wave event.

High-Energy X-Ray Talbot-Lau Radiography of a Human Knee - Horn, Florian; Gelse, Kolja; Jabari, Samir; Hauke, Christian; Käppler, Sebastian; Ludwig, Veronika; Meyer, Pascal; Michel, Thilo; Mohr, Jürgen; Pelzer, Georg; Rieger, Jens; Riess, Christian; et al. (Physics in Medicine and Biology, 2017)
Keywords: dark-field; high-energy; chondrocalcinosis; x-ray imaging; phase-contrast; TalbotLau imaging

High-performance direct conversion X-ray detectors based on sintered hybrid lead triiodide perovskite wafers - Shrestha, Shreetu; Fischer, Rene; Matt, Gebhard; Feldner, Patrick; Michel, Thilo; Osvet, Andres; Levchuk, Ievgen; Merle, Benoit; Golkar, Saeedeh; Chen, Haiwei; Tedde, Sandro F.; Schmidt, Oliver; et al. (Nature Photonics, 2017)
Lead halide perovskite semiconductors are in general known to have an inherently high X-ray absorption cross-section and a significantly higher carrier mobility than any other low-temperature solution-processed semiconductor. So far, the processing of several-hundred-micrometres-thick high-quality crystalline perovskite films over a large area has been unresolved for efficient X-ray detection. In this Article, we present a mechanical sintering process to fabricate polycrystalline methyl ammonium lead triiodide perovskite (MAPbI(3)) wafers with millimetre thickness and well-defined crystallinity. Benchmarking of the MAPbI(3) wafers against state-of-the-art CdTe detectors reveals competitive conversion efficiencies of 2,527 mu C Gy(air)(-1) cm(-2) under 70 kV(p) X-ray exposure. The high ambipolar mobility-lifetime product of 2 x 10(-4) cm(2) V-1 is suggested to be responsible for this exceptionally high sensitivity. Our findings inform a new generation of highly efficient and low-cost X-ray detectors based on perovskite wafer

IceCube-Gen2: The window to the extreme Universe - Aartsen, M. G.; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Amin, N. M.; Andeen, K.; Anderson, T.; et al. (Journal of Physics G: Nuclear and Particle Physics, 2021)
The observation of electromagnetic radiation from radio to γ-ray wavelengths has provided a wealth of information about the Universe. However, at PeV (1015 eV) energies and above, most of the Universe is impenetrable to photons. New messengers, namely cosmic neutrinos, are needed to explore the most extreme environments of the Universe where black holes, neutron stars, and stellar explosions transform gravitational energy into non-thermal cosmic rays. These energetic particles havemillions of times higher energies than those produced in the most powerful particle accelerators on Earth. As neutrinos can escape from regions otherwise opaque to radiation, they allow an unique view deep into exploding stars and the vicinity of the event horizons of black holes. The discovery of cosmic neutrinos with IceCube has opened this new window on the Universe. IceCube has been successful in finding first evidence for cosmic particle acceleration in the jet of an active galactic nucleus. Yet, ultimately, its sensitivity is too limited to detect even the brightest neutrino sources with high significance, or to detect populations of less luminous sources. In thiswhite paper, we present an overview of a next-generation instrument, IceCube-Gen2, which will sharpen our understanding of the processes and environments that govern the Universe at the highest energies. IceCube-Gen2 is designed to: (a) Resolve the high-energy neutrino sky from TeV to EeV energies (b) Investigate cosmic particle acceleration through multi-messenger observations (c) Reveal the sources and propagation of the highest energy particles in the Universe (d) Probe fundamental physics with high-energy neutrinos IceCube-Gen2 will enhance the existing IceCube detector at the South Pole. It will increase the annual rate of observed cosmic neutrinos by a factor of ten compared to IceCube, and will be able to detect sources five times fainter than its predecessor. Furthermore, through the addition of a radio array, IceCube- Gen2 will extend the energy range by several orders of magnitude compared to IceCube. Construction will take 8 years and cost about 350M. The goal is to have IceCube-Gen2 fully operational by 2033. IceCube-Gen2 will play an essential role in shaping the new era of multimessenger astronomy, fundamentally advancing our knowledge of the highenergy Universe. This challenging mission can be fully addressed only through the combination of the information from the neutrino, electromagnetic, and gravitational wave emission of high-energy sources, in concert with the new survey instruments across the electromagnetic spectrum and gravitational wave detectors which will be available in the coming years.
CRIS-Team Scopus Importer:2021-05-21
Keywords: High-energy astrophysics; Neutrino astronomy; Neutrino telescopes

IceCube high-energy starting event sample: Description and flux characterization with 7.5 years of data - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Ansseau,; et al. (Physical Review D, 2021)
The IceCube Neutrino Observatory has established the existence of a high-energy all-sky neutrino flux of astrophysical origin. This discovery was made using events interacting within a fiducial region of the detector surrounded by an active veto and with reconstructed energy above 60 TeV, commonly known as the high-energy starting event sample (HESE). We revisit the analysis of the HESE sample with an additional 4.5 years of data, newer glacial ice models, and improved systematics treatment. This paper describes the sample in detail, reports on the latest astrophysical neutrino flux measurements, and presents a source search for astrophysical neutrinos. We give the compatibility of these observations with specific isotropic flux models proposed in the literature as well as generic power-law-like scenarios. Assuming v(e): v(mu): v(tau) = 1:1:1, and an equal flux of neutrinos and antineutrinos, we find that the astrophysical neutrino spectrum is compatible with an unbroken power law, with a preferred spectral index of 2.87(-0.19)(+0.20) for the 68% confidence interval.
CRIS-Team WoS Importer:2021-07-23

IceCube Search for High-energy Neutrino Emission from TeV Pulsar Wind Nebulae - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Arguelles, C.; et al. (Astrophysical Journal, 2020)
Pulsar wind nebulae (PWNe) are the main gamma-ray emitters in the Galactic plane. They are diffuse nebulae that emit nonthermal radiation. Pulsar winds, relativistic magnetized outflows from the central star, shocked in the ambient medium produce a multiwavelength emission from the radio through gamma-rays. Although the leptonic scenario is able to explain most PWNe emission, a hadronic contribution cannot be excluded. A possible hadronic contribution to the high-energy gamma-ray emission inevitably leads to the production of neutrinos. Using 9.5 yr of all-sky IceCube data, we report results from a stacking analysis to search for neutrino emission from 35 PWNe that are high-energy gamma-ray emitters. In the absence of any significant correlation, we set upper limits on the total neutrino emission from those PWNe and constraints on hadronic spectral components.
CRIS-Team WoS Importer:2020-10-02

IceCube Search for Neutrinos Coincident with Compact Binary Mergers from LIGO-Virgo's First Gravitational-wave Transient Catalog - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (Astrophysical Journal Letters, 2020)
Using the IceCube Neutrino Observatory, we search for high-energy neutrino emission coincident with compact binary mergers observed by the LIGO and Virgo gravitational-wave (GW) detectors during their first and second observing runs. We present results from two searches targeting emission coincident with the sky localization of each GW event within a 1000 s time window centered around the reported merger time. One search uses a model-independent unbinned maximum-likelihood analysis, which uses neutrino data from IceCube to search for pointlike neutrino sources consistent with the sky localization of GW events. The other uses the Low-Latency Algorithm for Multi-messenger Astrophysics, which incorporates astrophysical priors through a Bayesian framework and includes LIGO-Virgo detector characteristics to determine the association between the GW source and the neutrinos. No significant neutrino coincidence is seen by either search during the first two observing runs of the LIGO-Virgo detectors. We set upper limits on the time-integrated neutrino emission within the 1000 s window for each of the 11 GW events. These limits range from 0.02 to 0.7 GeV cm-2. We also set limits on the total isotropic equivalent energy, E iso, emitted in high-energy neutrinos by each GW event. These limits range from 1.7 × 1051 to 1.8 × 1055 erg. We conclude with an outlook for LIGO-Virgo observing run O3, during which both analyses are running in real time.
CRIS-Team Scopus Importer:2020-08-14

IceCube Search for Neutrinos Coincident with Gravitational Wave Events from LIGO/Virgo Run O3 - Abbasi, R.; Ackermann, M.; Adams, J.; Aggarwal, N.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; et al. (Astrophysical Journal, 2023)
Using data from the IceCube Neutrino Observatory, we searched for high-energy neutrino emission from the gravitational-wave events detected by the advanced LIGO and Virgo detectors during their third observing run. We did a low-latency follow-up on the public candidate events released during the detectors' third observing run and an archival search on the 80 confident events reported in the GWTC-2.1 and GWTC-3 catalogs. An extended search was also conducted for neutrino emission on longer timescales from neutron star containing mergers. Follow-up searches on the candidate optical counterpart of GW190521 were also conducted. We used two methods; an unbinned maximum likelihood analysis and a Bayesian analysis using astrophysical priors, both of which were previously used to search for high-energy neutrino emission from gravitational-wave events. No significant neutrino emission was observed by any analysis, and upper limits were placed on the time-integrated neutrino flux as well as the total isotropic equivalent energy emitted in high-energy neutrinos.
CRIS-Team WoS Importer:2023-04-07

Identification of HESS J1303-631 as a pulsar wind nebula through γ -ray, X-ray, and radio observations - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2012)
Aims. The previously unidentified very high-energy (VHE; E > 100 GeV) γ-ray source HESS J1303-631, discovered in 2004, is re-examined including new data from the H.E.S.S. Cherenkov telescope array in order to identify this object. Archival data from the XMM-Newton X-ray satellite and from the PMN radio survey are also examined. Methods. Detailed morphological and spectral studies of VHE γ-ray emission as well as of the XMM-Newton X-ray data are performed. Radio data from the PMN survey are used as well to construct a leptonic model of the source. The γ-ray and X-ray spectra and radio upper limit are used to construct a one zone leptonic model of the spectral energy distribution (SED). Results. Significant energy-dependent morphology of the γ-ray source is detected with high-energy emission (E > 10 TeV) positionally coincident with the pulsar PSR J1301-6305 and lower energy emission (E < 2 TeV) extending ∼0.4° to the southeast of the pulsar. The spectrum of the VHE source can be described with a power-law with an exponential cut-off N = (5.6 ± 0.5) × 10 ± TeV ± cm ± s, Γ = 1.5 ± 0.2) and E = (7.7 ± ± ± 2.2) TeV. The pulsar wind nebula (PWN) is also detected in X-rays, extending ∼2-3′ from the pulsar position towards the center of the γ-ray emission region. A potential radio counterpart from the PMN survey is also discussed, showing a hint for a counterpart at the edge of the X-ray PWN trail and is taken as an upper limit in the SED. The extended X-ray PWN has an unabsorbed flux of F ∼ 1.6 × 10 erg cm and is detected at a significance of 6.5σ. The SED is well described by a one zone leptonic scenario which, with its associated caveats, predicts a very low average magnetic field for this source. Conclusions. Significant energy-dependent morphology of this source, as well as the identification of an associated X-ray PWN from XMM-Newton observations enable identification of the VHE source as an evolved PWN associated to the pulsar PSR J1301-6305. This identification is supported by the one zone leptonic model, which suggests that the energetics of the γ-ray and X-ray radiation are such that they may have a similar origin in the pulsar nebula. However, the large discrepancy in emission region sizes and the low level of synchrotron radiation suggest a multi-population leptonic nature. The low implied magnetic field suggests that the PWN has undergone significant expansion. This would explain the low level of synchrotron radiation and the difficulty in detecting counterparts at lower energies, the reason this source was originally classified as a "dark" VHE γ-ray source. © ESO, 2012.
Keywords: Gamma rays: general; ISM: individual objects: HESS J1303-631; Pulsars: individual: PSR J1301-6305

Image fusion in X-ray differential phase-contrast imaging - Haas, Wilhelm; Polyanskaya, Maria; Bayer, Florian; Gödel, Karl Christoph; Hofmann, Hannes; Rieger, Jens; Ritter, André; Weber, Thomas; Wucherer, Lukas; Durst, Jürgen; Michel, Thilo; Anton, Gisela; et al. (Medical Imaging 2012: Image Processing, 2012)
Phase-contrast imaging is a novel modality in the field of medical X-ray imaging. The pioneer method is the grating-based interferometry which has no special requirements to the X-ray source and object size. Furthermore, it provides three different types of information of an investigated object simultaneously - absorption, differential phase-contrast and dark-field images. Differential phase-contrast and dark-field images represent a completely new information which has not yet been investigated and studied in context of medical imaging. In order to introduce phase-contrast imaging as a new modality into medical environment the resulting information about the object has to be correctly interpreted. The three output images reflect different properties of the same object the main challenge is to combine and visualize these data in such a way that it diminish the information explosion and reduce the complexity of its interpretation. This paper presents an intuitive image fusion approach which allows to operate with grating-based phase-contrast images. It combines information of the three different images and provides a single image. The approach is implemented in a fusion framework which is aimed to support physicians in study and analysis. The framework provides the user with an intuitive graphical user interface allowing to control the fusion process. The example given in this work shows the functionality of the proposed method and the great potential of phase-contrast imaging in medical practice. © 2012 SPIE.

Imaging characteristics of intravascular spherical contrast agents for grating-based x-ray dark-field imaging – effects of concentrations, spherical sizes and applied voltage - Notohamiprodjo, Susan; Treitl, Karla Maria; Hauke, Christian; Sutter, Sven Martin; Auweter, Sigrid; Pfeiffer, Franz; Reiser, Maximilian Ferdinand; Hellbach, Katharina (Scientific Reports, 2020)
This study investigates the x-ray scattering characteristics of microsphere particles in x-ray-grating-based interferometric imaging at different concentrations, bubble sizes and tube voltages (kV). Attenuation (ATI), dark-field (DFI) and phase-contrast (PCI) images were acquired. Signal-to-noise (SNR) and contrast-to-noise ratios with water (CNRw) and air as reference (CNRa) were determined. In all modalities, a linear relationship between SNR and microbubbles concentration, respectively, microsphere size was found. A significant gain of SNR was found when varying kV. SNR was significantly higher in DFI and PCI than ATI. The highest gain of SNR was shown at 60 kV for all media in ATI and DFI, at 80 kV for PCI. SNR for all media was significantly higher compared to air and was slightly lower compared to water. A linear relationship was found between CNRa, CNRw, concentration and size. With increasing concentration and decreasing size, CNRa and CNRw increased in DFI, but decreased in PCI. Best CNRa and CNRw was found at specific combination of kV and concentration/size. Highest average CNRa and CNRw was found for microspheres in ATI and PCI, for microbubbles in DFI. Microspheres are a promising contrast-media for grating-based-interferometry, if kV, microsphere size and concentration are appropriately combined.
CRIS-Team Scopus Importer:2020-06-19

Imaging individual barium atoms in solid xenon for barium tagging in nEXO - Chambers, C.; Walton, T.; Fairbank, D.; Craycraft, A.; Yahne, D. R.; Todd, J.; Iverson, A.; Fairbank, W.; Alamre, A.; Albert, J. B.; Anton, Gisela; Arnquist, I. J.; et al. (Nature, 2019)
Double-β-decay involves the simultaneous conversion of two neutrons into two protons, and the emission of two electrons and two neutrinos; the neutrinoless process, although not yet observed, is thought to involve the emission of the two electrons but no neutrinos. The search for neutrinoless-double-β-decay probes fundamental properties of neutrinos, including whether or not the neutrino and antineutrino are distinct particles. Double-β-decay detectors are large and expensive, so it is essential to achieve the highest possible sensitivity with each study, and removing spurious contributions (‘background’) from detected signals is crucial. In the nEXO neutrinoless-double-β-decay experiment, the identification, or ‘tagging’, of the 136 Ba daughter atom resulting from the double-β decay of 136 Xe provides a technique for discriminating background. The tagging scheme studied here uses a cryogenic probe to trap the barium atom in a solid xenon matrix, where the barium atom is tagged through fluorescence imaging. Here we demonstrate the imaging and counting of individual barium atoms in solid xenon by scanning a focused laser across a solid xenon matrix deposited on a sapphire window. When the laser irradiates an individual atom, the fluorescence persists for about 30 seconds before dropping abruptly to the background level—a clear confirmation of one-atom imaging. Following evaporation of a barium deposit, the residual barium fluorescence is 0.16 per cent or less. Our technique achieves the imaging of single atoms in a solid noble element, establishing the basic principle of barium tagging for nEXO.
CRIS-Team Scopus Importer:2019-05-17

Implementation of a Talbot-Lau Interferometer in a Clinical-like C-Arm Setup: A Feasibility Study - Horn, Florian; Leghissa, Martino; Käppler, Sebastian; Pelzer, Georg; Rieger, Jens; Seifert, Maria; Wandner, Johannes; Weber, Thomas; Michel, Thilo; Riess, Christian; Anton, Gisela (Scientific Reports, 2018)

Improved Characterization of the Astrophysical Muon-neutrino Flux with 9.5 Years of IceCube Data - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alispach, C.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; et al. (Astrophysical Journal, 2022)
We present a measurement of the high-energy astrophysical muon-neutrino flux with the IceCube Neutrino Observatory. The measurement uses a high-purity selection of 650k neutrino-induced muon tracks from the northern celestial hemisphere, corresponding to 9.5 yr of experimental data. With respect to previous publications, the measurement is improved by the increased size of the event sample and the extended model testing beyond simple power-law hypotheses. An updated treatment of systematic uncertainties and atmospheric background fluxes has been implemented based on recent models. The best-fit single power-law parameterization for the astrophysical energy spectrum results in a normalization of φ@100TeVνμ+ν¯μ=1.44-0.26+0.25×10-18GeV-1cm-2s-1sr-1 and a spectral index γSPL=2.37-0.09+0.09, constrained in the energy range from 15 TeV to 5 PeV. The model tests include a single power law with a spectral cutoff at high energies, a log-parabola model, several source-class-specific flux predictions from the literature, and a model-independent spectral unfolding. The data are consistent with a single power-law hypothesis, however, spectra with softening above one PeV are statistically more favorable at a two-sigma level.
CRIS-Team Scopus Importer:2022-04-22

Improved modeling of in-ice particle showers for IceCube event reconstruction - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Journal of Instrumentation, 2024)
The IceCube Neutrino Observatory relies on an array of photomultiplier tubes to detect Cherenkov light produced by charged particles in the South Pole ice. IceCube data analyses depend on an in-depth characterization of the glacial ice, and on novel approaches in event reconstruction that utilize fast approximations of photoelectron yields. Here, a more accurate model is derived for event reconstruction that better captures our current knowledge of ice optical properties. When evaluated on a Monte Carlo simulation set, the median angular resolution for in-ice particle showers improves by over a factor of three compared to a reconstruction based on a simplified model of the ice. The most substantial improvement is obtained when including effects of birefringence due to the polycrystalline structure of the ice. When evaluated on data classified as particle showers in the high-energy starting events sample, a significantly improved description of the events is observed.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Cherenkov detectors; Neutrino detectors; programs; Simulation methods

Improved Reconstruction of Phase-Stepping Data for Talbot-Lau X-Ray Imaging - Käppler, Sebastian; Rieger, Jens; Pelzer, Georg; Horn, Florian; Michel, Thilo; Maier, Andreas; Anton, Gisela; Riess, Christian (Journal of Medical Imaging, 2017)
Keywords: phase contrast; phase stepping; moiré; reconstruction; Talbot-Lau

Increasing the darkfield contrast-to-noise ratio using a deconvolution-based information retrieval algorithm in X-ray grating-based phase-contrast imaging - Weber, Thomas; Pelzer, Georg; Bayer, Florian; Horn, Florian; Rieger, Jens; Ritter, André; Zang, Andrea; Durst, Jürgen; Anton, Gisela; Michel, Thilo (Optics Express, 2013)
A novel information retrieval algorithm for X-ray grating-based phase-contrast imaging based on the deconvolution of the object and the reference phase stepping curve (PSC) as proposed by Modregger et al. was investigated in this paper. We applied the method for the first time on data obtained with a polychromatic spectrum and compared the results to those, received by applying the commonly used method, based on a Fourier analysis. We confirmed the expectation, that both methods deliver the same results for the absorption and the differential phase image. For the darkfield image, a mean contrast-to-noise ratio (CNR) increase by a factor of 1.17 using the new method was found. Furthermore, the dose saving potential was estimated for the deconvolution method experimentally. It is found, that for the conventional method a dose which is higher by a factor of 1.66 is needed to obtain a similar CNR value compared to the novel method. A further analysis of the data revealed, that the improvement in CNR and dose efficiency is due to the superior background noise properties of the deconvolution method, but at the cost of comparability between measurements at different applied dose values, as the mean value becomes dependent on the photon statistics used. © 2013 Optical Society of America.
UnivIS-Import:2015-04-14:Pub.2013.nat.dphy.PI.LEPDF.increa

Indirect search for dark matter in the Galactic Centre with IceCube - Iovine, Nadège; Aguilar, Juan A.; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; et al. (Proceedings of Science, 2022)
Even though there are strong astrophysical and cosmological indications to support the existence of dark matter, its exact nature remains unknown. We expect dark matter to produce standard model particles when annihilating or decaying, assuming that it is composed of Weakly Interacting Massive Particles (WIMPs). These standard model particles could in turn yield neutrinos that can be detected by the IceCube neutrino telescope. The Milky Way is expected to be permeated by a dark matter halo with an increased density towards its centre. This halo is expected to yield the strongest dark matter annihilation signal at Earth coming from any celestial object, making it an ideal target for indirect searches. In this contribution, we present the sensitivities of an indirect search for dark matter in the Galactic Centre using IceCube data. This low energy dark matter search allows us to cover dark matter masses ranging from 5 GeV to 1 TeV. The sensitivities obtained for this analysis show considerable improvements over previous IceCube results in the considered energy range.
CRIS-Team Scopus Importer:2022-12-23

In-situ calibration of the single-photoelectron charge response of the IceCube photomultiplier tubes - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Arguelles, C.; et al. (Journal of Instrumentation, 2020)
We describe an improved in-situ calibration of the single-photoelectron charge distributions for each of the in-ice Hamamatsu Photonics R7081-02[MOD] photomultiplier tubes in the IceCube Neutrino Observatory. The characterization of the individual PMT charge distributions is important for PMT calibration, data and Monte Carlo simulation agreement, and understanding the effect of hardware differences within the detector. We discuss the single photoelectron identification procedure and how we extract the single-photoelectron charge distribution using a deconvolution of the multiple-photoelectron charge distribution.
CRIS-Team WoS Importer:2020-07-24

Intrinsic limits on resolutions in muon- and electron-neutrino charged-current events in the KM3NeT/ORCA detector - Adrian-Martinez, S.; Ageron, M.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Andre, Michel; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Avgitas, T.; et al. (Journal of High Energy Physics, 2017)
Studying atmospheric neutrino oscillations in the few-GeV range with a multimegaton detector promises to determine the neutrino mass hierarchy. This is the main science goal pursued by the future KM3NeT/ORCA water Cherenkov detector in the Mediterranean Sea. In this paper, the processes that limit the obtainable resolution in both energy and direction in charged-current neutrino events in the ORCA detector are investigated. These processes include the composition of the hadronic fragmentation products, the subsequent particle propagation and the photon-sampling fraction of the detector. GEANT simulations of neutrino interactions in seawater produced by GENIE are used to study the effects in the 1-20 GeV range. It is found that fluctuations in the hadronic cascade in conjunction with the variation of the inelasticity y are most detrimental to the resolutions. The effect of limited photon sampling in the detector is of significantly less importance. These results will therefore also be applicable to similar detectors/media, such as those in ic
Keywords: Neutrino Detectors and Telescopes (experiments)

Investigation of Two Fermi-LAT Gamma-Ray Blazars Coincident with High-energy Neutrinos Detected by IceCube - Garrappa, S.; Buson, S.; Franckowiak, A.; Shappee, B. J.; Beacom, J. F.; Dong, S.; Holoien, T. W-S; Kochanek, C. S.; Prieto, J. L.; Stanek, K. Z.; Thompson, T. A.; Aartsen, M. G.; et al. (Astrophysical Journal, 2019)
After the identification of the gamma-ray blazar TXS 0506+056 as the first compelling IceCube neutrino source candidate, we perform a systematic analysis of all high-energy neutrino events satisfying the IceCube realtime trigger criteria. We find one additional known gamma-ray source, the blazar GB6 J1040+0617, in spatial coincidence with a neutrino in this sample. The chance probability of this coincidence is 30% after trial correction. For the first time, we present a systematic study of the gamma-ray flux, spectral and optical variability, and multiwavelength behavior of GB6 J1040+0617 and compare it to TXS 0506+056. We find that TXS 0506+056 shows strong flux variability in the Fermi-Large Area Telescope gamma-ray band, being in an active state around the arrival of IceCube-170922A, but in a low state during the archival IceCube neutrino flare in 2014/15. In both cases the spectral shape is statistically compatible (<= 2 sigma) with the average spectrum showing no indication of a significant relative increase of a high-energy component. While the association of GB6 J1040+0617 with the neutrino is consistent with background expectations, the source appears to be a plausible neutrino source candidate based on its energetics and multiwavelength features, namely a bright optical flare and modestly increased gamma-ray activity. Finding one or two neutrinos originating from gamma-ray blazars in the given sample of high-energy neutrinos is consistent with previously derived limits of neutrino emission from gamma-ray blazars, indicating the sources of the majority of cosmic high-energy neutrinos remain unknown.
CRIS-Team WoS Importer:2019-08-16

Joint Constraints on Galactic Diffuse Neutrino Emission from the ANTARES and IceCube Neutrino Telescopes - Albert, A.; Grasso, D.; Andre, M.; Anghinolfi, M.; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Astrophysical Journal Letters, 2018)
The existence of diffuse Galactic neutrino production is expected from cosmic-ray interactions with Galactic gas and radiation fields. Thus, neutrinos are a unique messenger offering the opportunity to test the products of Galactic cosmic-ray interactions up to energies of hundreds of TeV. Here we present a search for this production using ten years of Astronomy with a Neutrino Telescope and Abyss environmental RESearch (ANTARES) track and shower data, as well as seven years of IceCube track data. The data are combined into a joint likelihood test for neutrino emission according to the KRA(gamma) model assuming a 5 PeV per nucleon Galactic cosmic-ray cutoff. No significant excess is found. As a consequence, the limits presented in this Letter start constraining the model parameter space for Galactic cosmic-ray production and transport.
Keywords: cosmic rays; diffusion; Galaxy: disk; gamma rays: diffuse background; neutrinos

KM3NeT front-end and readout electronics system: hardware, firmware, and software - Aiello, Sebastiano; Amllei, Fabrizio; Andre, Michel; Androulakis, Giorgos; Anghinolfi, Marco; Anton, Gisela; Ardid, Miquel; Aublin, Julien; Bagatelas, Christos; Barbarino, Giancarlo; Baret, Bruny; Du Pree, Suzan Basegmez; et al. (Journal of Astronomical Telescopes, Instruments, and Systems, 2019)
The KM3NeT research infrastructure being built at the bottom of the Mediterranean Sea will host water-Cherenkov telescopes for the detection of cosmic neutrinos. The neutrino telescopes will consist of large volume three-dimensional grids of optical modules to detect the Cherenkov light from charged particles produced by neutrino-induced interactions. Each optical module houses 31 3-in. photomultiplier tubes, instrumentation for calibration of the photomultiplier signal and positioning of the optical module, and all associated electronics boards. By design, the total electrical power consumption of an optical module has been capped at seven Watts. We present an overview of the front-end and readout electronics system inside the optical module, which has been designed for a 1-ns synchronization between the clocks of all optical modules in the grid during a life time of at least 20 years. (C) 2019 Society of Photo-Optical Instrumentation Engineers (SPIE)
CRIS-Team WoS Importer:2020-02-28

KM3Net time calibration - Coniglione, R.; Creusot, A.; Di Palma, I.; Guderian, D.; Hofestädt, Jannik; Riccobene, G.; Sánchez Losa, A. (Proceedings of Science, 2019)
The KM3NeT Collaboration aims at the construction of a distributed research infrastructure under the Mediterranean Sea that will host two underwater neutrino detectors: ARCA and ORCA. They are optimised to detect neutrinos using the Cherenkov technique and will play an important role in the detection of high energy astrophysical neutrinos, ARCA, and in the study of the neutrino mass hierarchy exploiting the flux of atmospheric neutrinos, ORCA. Both detectors share the same technology: thousands digital optical modules, each hosting 31 3-inch photomultipliers, distributed along tall detection units. The main difference is the distance between the optical modules, optimised to meet the requirements of the different scientific objectives. The reconstruction of the neutrino direction exploits the Cherenkov photons emitted along the path of the charged particles produced in the neutrino interactions and requires a nanosecond synchronisation between the photomultipliers in order to get high angular resolution. This contribution describes the accurate time calibration procedures developed to synchronise the time references of the photomultipliers within an optical module and of each optical module within the detection unit and also between detection units.
CRIS-Team Scopus Importer:2024-12-16

Latest improvements of microchannel-plate PMTS - Lehmann, Albert; Böhm, Merlin; Miehling, Daniel; Pfaffinger, Markus; Stelter, Samuel; Uhlig, Fred; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
The DIRC detectors of the P̄ANDA experiment at FAIR will use multi-anode MCP-PMTs as photon sensors. After long and extensive R&D work the performance parameters of the recent 2” MCP-PMT models are converging towards the required values. The lifetime of most ALD-coated MCP-PMTs is well surpassing the DIRC requirements with the best tube currently reaching >22 C/cm2 integrated anode charge without aging. The performance of the most advanced MCP-PMTs from PHOTONIS and Hamamatsu fulfill basically all requirements with a highlight being the high detective quantum efficiency (DQE) of almost 30% for the PHOTONIS 9002108. The improvements of the latest MCP-PMT models compared to former tubes are emphasized in this paper. In addition, some performance features of a recently developed 2” MCP-PMT by Photek Ltd are presented and discussed.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Atomic layer deposition (ALD); Cherenkov detectors; Lifetime; Microchannel-plate photomultipliers

Latest Technological Advances with MCP-PMTs - Lehmann, Albert; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Schwiening, J.; Traxler, M.; Schmitt, L.; Böhm, Merlin; et al. (Journal of Physics: Conference Series, 2022)
This paper discusses the most recent advances with 2-inch MCP-PMTs. The status in terms of lifetime, detection efficiency, rate capability, time resolution, and gain behavior in magnetic fields are summarized. Significant progress in collection (CE) and quantum efficiency (QE) led to an excellent detection efficiency DQE = QE∗CE of â1/430%. With a new DAQ setup up to several hundred anode pixels can be read out simultaneously in 3D allowing a glance "inside the PMT". Parameters like dark count rates and ion afterpulsing are measurable as a function of the incident photon position as well as the temporal and spacial spread of recoil electrons and electronic and charge-sharing crosstalk even inside a magnetic field.
CRIS-Team Scopus Importer:2022-12-30

LED as laboratory test source for astronomical intensity interferometry - Zmija, Andreas; Deiml, Peter; Malyshev, Dmitry; Zink, Adrian; Anton, Gisela; Michel, Thilo; Funk, Stefan (Optics Express, 2020)
The challenge of astronomical intensity interferometry is to detect the small photon-bunching signals of distant sources with a broad optical bandwidth. We have built a Hanbury Brown-Twiss-like laboratory intensity interferometer with a focus on a relatively broad bandwidth (1 nm FWHM optical filter) and high photon rates (up to 10 MHz) per channel compared to typical (non-astronomical) intensity interferometry applications. As a light source we use a green LED to simulate starlight. The LED has proven to be a compact high-power source of stochastic light with a special advantage of a small emission area, which favours spatial coherence. Using single-photon correlations, we detect a bunching signal in the second-order correlation function with a coherence time of <1 ps and an amplitude of <4 · 10−4 and describe signal and background quantitatively for a 40 hours measurement. In this paper we show our setup, present the correlation measurements and compare them to theoretical expectations.
CRIS-Team Scopus Importer:2020-02-21

LeptonInjector and LeptonWeighter: A neutrino event generator and weighter for neutrino observatories - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Computer Physics Communications, 2021)
We present a high-energy neutrino event generator, called LeptonInjector, alongside an event weighter, called LeptonWeighter. Both are designed for large-volume Cherenkov neutrino telescopes such as IceCube. The neutrino event generator allows for quick and flexible simulation of neutrino events within and around the detector volume, and implements the leading Standard Model neutrino interaction processes relevant for neutrino observatories: neutrino-nucleon deep-inelastic scattering and neutrino-electron annihilation. In this paper, we discuss the event generation algorithm, the weighting algorithm, and the main functions of the publicly available code, with examples. Program summary: Program Titles: LeptonInjector and LeptonWeighter CPC Library link to program files: https://doi.org/10.17632/662gkpjfd9.1 Developer's repository links: https://github.com/icecube/LeptonInjector and https://github.com/icecube/LeptonWeighter Licensing provisions: GNU Lesser General Public License, version 3. Programming Language: C++11 External Routines: • Boost • HDF5 • nuflux (https://github.com/icecube/nuflux) • nuSQuIDS (https://github.com/arguelles/nuSQuIDS) • Photospline (https://github.com/icecube/photospline) • SuiteSparse (https://github.com/DrTimothyAldenDavis/SuiteSparse) Nature of problem: LeptonInjector: Generate neutrino interaction events of all possible topologies and energies throughout and around a detector volume. LeptonWeighter: Reweight Monte Carlo events, generated by a set of LeptonInjector Generators, to any desired physical neutrino flux or cross section. Solution method: LeptonInjector: Projected ranges of generated leptons and the extent of the detector, in terms of column depth, are used to inject events in and around the detector volume. Event kinematics follow distributions provided in cross section files. LeptonWeighter: Event generation probabilities are calculated for each Generator, which are then combined into a generation weight and used to calculate an overall event weight.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Event generator; Neutrino generator; Neutrino interaction; Neutrino simulation; Weighting

Letter of intent for KM3NeT 2.0 - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E.; Andre, Michel; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; et al. (Journal of Physics G: Nuclear and Particle Physics, 2016)
The main objectives of the KM3NeT Collaboration are (i) the discovery and subsequent observation of high-energy neutrino sources in the Universe and (ii) the determination of the mass hierarchy of neutrinos. These objectives are strongly motivated by two recent important discoveries, namely: (1) the high-energy astrophysical neutrino signal reported by IceCube and (2) the sizable contribution of electron neutrinos to the third neutrino mass eigenstate as reported by Daya Bay, Reno and others. To meet these objectives, the KM3NeT Collaboration plans to build a new Research Infrastructure consisting of a network of deep-sea neutrino telescopes in the Mediterranean Sea. A phased and distributed implementation is pursued which maximises the access to regional funds, the availability of human resources and the synergistic opportunities for the Earth and sea sciences community. Three suitable deep-sea sites are selected, namely off-shore Toulon (France), Capo Passero (Sicily, Italy) and Pylos (Peloponnese, Greece). The infrastructure will consist of three so-called building blocks. A building block comprises 115 strings, each string comprises 18 optical modules and each optical module comprises 31 photo-multiplier tubes. Each building block thus constitutes a three-dimensional array of photo sensors that can be used to detect the Cherenkov light produced by relativistic particles emerging from neutrino interactions. Two building blocks will be sparsely configured to fully explore the IceCube signal with similar instrumented volume, different methodology, improved resolution and complementary field of view, including the galactic plane. One building block will be densely configured to precisely measure atmospheric neutrino oscillations.
Keywords: deep sea neutrino telescope; neutrino astronomy; neutrino mass hierarchy; neutrino physics

Letter of interest for a neutrino beam from Protvino to KM3NeT/ORCA - Akindinov, V.; Anassontzis, E. G.; Anton, Gisela; Ardid, M.; Aublin, J.; Baret, B.; Bertin,; Bourret, S.; Bozza, C.; Bruchner, M.; Bruijn, R.; Brunner, J.; et al. (European Physical Journal C: Particles and Fields, 2019)
The Protvino accelerator facility located in the Moscow region, Russia, is in a good position to offer a rich experimental research program in the field of neutrino physics. Of particular interest is the possibility to direct a neutrino beam from Protvino towards the KM3NeT/ORCA detector, which is currently under construction in the Mediterranean Sea 40 km offshore Toulon, France. This proposal is known as P2O. Thanks to its baseline of 2595 km, this experiment would yield an unparalleled sensitivity to matter effects in the Earth, allowing for the determination of the neutrino mass ordering with a high level of certainty after only a few years of running at a modest beam intensity of sensitivity to the leptonic CP-violating Dirac phase can be achieved. A second stage of the experiment, comprising a further intensity upgrade of the accelerator complex and a densified version of the ORCA detector (Super-ORCA), would allow for up to a 6 sigma[12pt] resolution on the CP phase after 10 years of running with a 450 kW beam, competitive with other planned experiments. The initial composition and energy spectrum of the neutrino beam would need to be monitored by a near detector, to be constructed several hundred meters downstream from the proton beam target. The same neutrino beam and near detector set-up would also allow for neutrino-nucleus cross section measurements to be performed. A short-baseline sterile neutrino search experiment would also be possible.
CRIS-Team WoS Importer:2019-10-04

Lifetime and performance of the very latest microchannel-plate photomultipliers - Miehling, Daniel; Böhm, Michael; Gumbert, Katja; Krauss, Steffen; Lehmann, Albert; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2023)
The PANDA experiment at the FAIR facility at GSI will study hadron physics using a high intensity antiproton beam of up to 15 GeV/c momentum to perform high precision spectroscopy. Two DIRC detectors with their image planes residing in an ∼1T magnetic field will be used in the experiment. The only suitable photon detectors for both DIRCs were identified to be Microchannel-Plate Photomultipliers (MCP-PMTs). Since the aging problems of MCP-PMTs were solved recently by coating the MCPs with the so-called ALD-technique (atomic layer depostion) we are investigating devices which are significantly improved with respect to other parameters, as, e.g., the collection efficiency (CE) and the quantum efficiency (QE). The latest generation of MCP-PMTs can reach a detective quantum efficiency DQE=QE⋅CE of 30%. This paper will present the performance of the most advanced 53 × 53 mm2 ALD-coated MCP-PMTs from Photonis (8 × 8 and 3 × 100 anodes) and Photek (8 × 8 anodes), also inside the magnetic field. With a picosecond laser and a multi-hit capable DAQ system which allows read out up to 300 pixels simultaneously, parameters like darkcount rate, afterpulse probability and time resolution can be investigated as a function of incident photon position.
CRIS-Team Scopus Importer:2023-06-02
Keywords: Atomic layer deposition (ALD); Cherenkov detectors; Lifetime; Microchannel-plate photomultipliers

Limits on dark matter annihilation in the sun using the ANTARES neutrino telescope - Adrian-Martineza, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physics Letters B, 2016)
A search for muon neutrinos originating from dark matter annihilations in the Sun is performed using the data recorded by the ANTARES neutrino telescope from 2007 to 2012. In order to obtain the best possible sensitivities to dark matter signals, an optimisation of the event selection criteria is performed taking into account the background of atmospheric muons, atmospheric neutrinos and the energy spectra of the expected neutrino signals. No significant excess over the background is observed and 90% C.L. upper limits on the neutrino flux, the spin-dependent and spin-independent WIMP-nucleon cross-sections are derived for WIMP masses ranging from 50 GeV to 5 TeV for the annihilation channels WIMP+WIMP→bb-,WW and ττ.
Keywords: Dark matter; Indirect detection; Neutralino; Neutrino telescope; Sun; WIMP

Localizing the VHE γ-ray source at the galactic centre - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, J.; et al. (Monthly Notices of the Royal Astronomical Society, 2010)
The inner 10 pc of our Galaxy contains many counterpart candidates of the very high energy (VHE; >100 GeV) γ-ray point source HESS J1745-290. Within the point spread function of the H.E.S.S. measurement, at least three objects are capable of accelerating particles to VHE and beyond and of providing the observed γ-ray flux. Previous attempts to address this source confusion were hampered by the fact that the projected distances between these objects were of the order of the error circle radius of the emission centroid (34 arcsec, dominated by the pointing uncertainty of the H.E.S.S. instrument). Here we present H.E.S.S. data of the Galactic Centre region, recorded with an improved control of the instrument pointing compared to H.E.S.S. standard pointing procedures. Stars observed during γ-ray observations by optical guiding cameras mounted on each H.E.S.S. telescope are used for off-line pointing calibration, thereby decreasing the systematic pointing uncertainties from 20 to 6 arcsec per axis. The position of HESS J1745-290 is obtained by fitting a multi-Gaussian profile to the background-subtracted γ-ray count map. A spatial comparison of the best-fitting position of HESS J1745-290 with the position and morphology of candidate counterparts is performed. The position is, within a total error circle radius of 13 arcsec, coincident with the position of the supermassive black hole Sgr A* and the recently discovered pulsar wind nebula candidate G359.95-0.04. It is significantly displaced from the centroid of the supernova remnant Sgr A East, excluding this object with high probability as the dominant source of the VHE γ-ray emission. © 2009 The Authors. Journal compilation © 2009 RAS.
Keywords: Galaxy: centre; Gamma-rays: observations; ISM: individual: G 359.95-0.04; ISM: individual: Sgr A East; ISM: individual: Sgr A*

Long-term monitoring of PKS 2155-304 with ATOM and H.E.S.S.: Investigation of optical/γ-ray correlations in different spectral states - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguner, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astronomy & Astrophysics, 2014)
In this paper we report on the analysis of all the available optical and very high-energy γ-ray (>200 GeV) data for the BL Lac object PKS 2155-304, collected simultaneously with the ATOM and H.E.S.S. telescopes from 2007 until 2009. This study also includes X-ray (RXTE, Swift) and high-energy γ-ray (Fermi-LAT) data. During the period analysed, the source was transitioning from its flaring to quiescent optical states, and was characterized by only moderate flux changes at different wavelengths on the timescales of days and months. A flattening of the optical continuum with an increasing optical flux can be noted in the collected dataset, but only occasionally and only at higher flux levels. We did not find any universal relation between the very high-energy γ-ray and optical flux changes on the timescales from days and weeks up to several years. On the other hand, we noted that at higher flux levels the source can follow two distinct tracks in the optical flux-colour diagrams, which seem to be related to distinct γ-ray states of the blazar. The obtained results therefore indicate a complex scaling between the optical and γ-ray emission of PKS 2155-304, with different correlation patterns holding at different epochs, and a γ-ray flux depending on the combination of an optical flux and colour rather than a flux alone.
Keywords: BL Lacertae objects: individual: PKS 2155-304; Black hole physics; Galaxies: active; Galaxies: jets; Gamma rays: galaxies; Radiation mechanisms: non-thermal

Long-term monitoring of the ANTARES optical module efficiencies using K-40 decays in sea water - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (European Physical Journal C, 2018)
Cherenkov light induced by radioactive decay products is one of the major sources of background light for deep-sea neutrino telescopes such as ANTARES. These decays are at the same time a powerful calibration source. Using data collected by the ANTARES neutrino telescope from mid 2008 to 2017, the time evolution of the photon detection efficiency of optical modules is studied. A modest loss of only 20% in 9 years is observed. The relative time calibration between adjacent modules is derived as well.

Long-term TeV and X-ray observations of the gamma-ray binary hess j0632+057 - Aliu, E.; Archambault, S.; Aune, T.; Behera, B.; Beilicke, M.; Benbow, W.; Berger, K.; Bird, Ralph; Bouvier, A.; Buckley, J. H.; Bugaev, V.; Byrum, K.; et al. (Astrophysical Journal, 2014)
HESS J0632+057 is the only gamma-ray binary known so far whose position in the sky allows observations with ground-based observatories in both the northern and southern hemispheres. Here we report on long-term observations of HESS J0632+057 conducted with the Very Energetic Radiation Imaging Telescope Array System and High Energy Stereoscopic System Cherenkov telescopes and the X-ray satellite Swift, spanning a time range from 2004 to 2012 and covering most of the system's orbit. The very-high-energy (VHE) emission is found to be variable and is correlated with that at X-ray energies. An orbital period of days is derived from the X-ray data set, which is compatible with previous results, P = (321 ± 5) days. The VHE light curve shows a distinct maximum at orbital phases close to 0.3, or about 100 days after periastron passage, which coincides with the periodic enhancement of the X-ray emission. Furthermore, the analysis of the TeV data shows for the first time a statistically significant (>6.5σ) detection at orbital phases 0.6-0.9. The obtained gamma-ray and X-ray light curves and the correlation of the source emission at these two energy bands are discussed in the context of the recent ephemeris obtained for the system. Our results are compared to those reported for other gamma-ray binaries. © 2014. The American Astronomical Society. All rights reserved..
Keywords: acceleration of particles; binaries:general

Look-up table-based simulation of scintillation detectors in computed tomography - Balda, Michael; Wirth, Stefan; Niederlöhner, Daniel; Heismann, Björn; Hornegger, Joachim (2008 IEEE Nuclear Science Symposium Conference Record, NSS/MIC 2008, 2008)
The design of a CT detector requires a precise detector model, since building prototypes for many different proposed detector geometries is too costly. We introduce a lookup table-based simulation of scintillation detectors on X-ray photon level. It uses energy-resolved sinograms of incoming X-ray intensities as input data and generates photon counts for each channel and reading. The effects of X-ray- and optical cross-talk, temporal cross-talk between readings, Poisson noise and electronics effects are covered. The photon interaction data as well as optical cross-talk distribution are provided in the form of detector specific look-up tables. Unlike standard MonteCarlo simulations of X-ray interaction processes, our approach is capable of simulating whole sinograms in a reasonable amount of time and still offers a very high precision of the detector model. This way the influence of detector effects can be investigated in the reconstructed image data. The simulation is verified against data measured with a CT scanner and data from a fully single photon-based Monte-Carlo simulation in terms of image modulation transfer function (MTF) and detector noise power spectrum (NPS). © 2008 IEEE.

Lust und Spaß am Forschen und Tüfteln - Das Erlanger Schülerforschungszentrum (ESFZ) für Bayern - Fösel, Angela; Anton, Gisela; Christl, Monika; Durst, Jürgen; Schreiner, Iris (PhyDid B - Didaktik der Physik - Beiträge zur DPG-Frühjahrstagung, 2010)

Machine learning for kM3Net/Orca - Hallmann, Steffen; Moser, Michael; Reck, Stefan; Eberl, Thomas (Proceedings of Science, 2019)
The KM3NeT research infrastructure is currently under construction in two locations in the Mediterranean Sea. The KM3NeT/ORCA water-Cherenkov neutrino detector off the French coast will instrument several megatons of seawater with photosensors. Its main objective is the determination of the neutrino mass ordering. For the first time, deep convolutional neural networks are employed to achieve three specific reconstruction and classification tasks that constitute a complete alternative analysis pipeline for KM3NeT/ORCA detector data. The values and uncertainties of the energy, direction, and the interaction vertex of the incident neutrinos are reconstructed. The neutrino interaction type is recognized as shower- or track-like, and the main backgrounds to the detection of atmospheric neutrinos are classified and suppressed. Performance comparisons to other machine-learning methods used and maximum-likelihood reconstruction algorithms previously developed for KM3NeT/ORCA are provided. It is shown that this image recognition technique yields competitive results and performance improvements for large-volume neutrino telescopes.
CRIS-Team Scopus Importer:2021-04-20

Machine learning methods for constructing probabilistic Fermi -LAT catalogs - Bhat, Aakash; Malyshev, Dmitry (Astronomy & Astrophysics, 2022)
Context. Classification of sources is one of the most important tasks in astronomy. Sources detected in one wavelength band, for example using gamma rays, may have several possible associations in other wavebands, or there may be no plausible association candidates. Aims. In this work we aim to determine the probabilistic classification of unassociated sources in the third Fermi Large Area Telescope (LAT) point source catalog (3FGL) and the fourth Fermi LAT data release 2 point source catalog (4FGL-DR2) using two classes - pulsars and active galactic nuclei (AGNs) - or three classes - pulsars, AGNs, and OTHER sources. Methods. We use several machine learning (ML) methods to determine a probabilistic classification of Fermi-LAT sources. We evaluate the dependence of results on the meta-parameters of the ML methods, such as the maximal depth of the trees in tree-based classification methods and the number of neurons in neural networks. Results. We determine a probabilistic classification of both associated and unassociated sources in the 3FGL and 4FGL-DR2 catalogs. We cross-check the accuracy by comparing the predicted classes of unassociated sources in 3FGL with their associations in 4FGL-DR2 for cases where such associations exist. We find that in the two-class case it is important to correct for the presence of OTHER sources among the unassociated ones in order to realistically estimate the number of pulsars and AGNs. We find that the three-class classification, despite different types of sources in the OTHER class, has a similar performance as the two-class classification in terms of reliability diagrams and, at the same time, it does not require adjustment due to presence of the OTHER sources among the unassociated sources. We show an example of the use of the probabilistic catalogs for population studies, which include associated and unassociated sources.
CRIS-Team Scopus Importer:2022-05-06
Keywords: Catalogs; Gamma rays: general; Methods: statistical

Machine learning techniques deep underwater in km3net - Circella, Marco; Eberl, Thomas (Europhysics News, 2022)
Deep in the water of the Mediterranean Sea, the KM3NeT detectors aim at the exploration of the cosmos through the detection of neutrinos and to determine the neutrino mass ordering. Machine learning techniques are widely used to push the performance of the detectors to the limit.

Maximum likelihood reconstruction for grating-based X-ray microscopy - Wolf, Andreas; Schuster, Max; Ludwig, Veronika; Anton, Gisela; Funk, Stefan (Optics Express, 2020)
The combination of grating-based phase-contrast imaging with X-ray microscopy can result in a complicated image formation. Generally, transverse shifts of the interference fringes are nonlinearly dependent on phase differences of the measured wave front. We present an iterative reconstruction scheme based on a regularized maximum likelihood cost function that fully takes this dependency into account. The scheme is validated by numerical simulations. It is particularly advantageous at low photon numbers and when the premises for deconvolution-based reconstructions are not met. Our reconstruction scheme hence enables a broader applicability of X-ray grating interferometry in imaging and wave front sensing.
CRIS-Team Scopus Importer:2020-05-22

Measurement of atmospheric neutrino mixing with improved IceCube DeepCore calibration and data processing - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Physical Review D, 2023)
We describe a new data sample of IceCube DeepCore and report on the latest measurement of atmospheric neutrino oscillations obtained with data recorded between 2011-2019. The sample includes significant improvements in data calibration, detector simulation, and data processing, and the analysis benefits from a sophisticated treatment of systematic uncertainties, with significantly greater level of detail since our last study. By measuring the relative fluxes of neutrino flavors as a function of their reconstructed energies and arrival directions we constrain the atmospheric neutrino mixing parameters to be sin2θ23=0.51±0.05 and Δm322=2.41±0.07×10-3 eV2, assuming a normal mass ordering. The errors include both statistical and systematic uncertainties. The resulting 40% reduction in the error of both parameters with respect to our previous result makes this the most precise measurement of oscillation parameters using atmospheric neutrinos. Our results are also compatible and complementary to those obtained using neutrino beams from accelerators, which are obtained at lower neutrino energies and are subject to different sources of uncertainties.
CRIS-Team Scopus Importer:2023-08-25

Measurement of atmospheric neutrino oscillations with the ANTARES neutrino telescope ANTARES Collaboration - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Basa, S.; et al. (Physics Letters B, 2012)
The data taken with the ANTARES neutrino telescope from 2007 to 2010, a total live time of 863 days, are used to measure the oscillation parameters of atmospheric neutrinos. Muon tracks are reconstructed with energies as low as 20 GeV. Neutrino oscillations will cause a suppression of vertical upgoing muon neutrinos of such energies crossing the Earth. The parameters determining the oscillation of atmospheric neutrinos are extracted by fitting the event rate as a function of the ratio of the estimated neutrino energy and reconstructed flight path through the Earth. Measurement contours of the oscillation parameters in a two-flavour approximation are derived. Assuming maximal mixing, a mass difference of Delta m(32)(2) = (3.1 +/- 0.9) . 10(-3) eV(2) is obtained, in good agreement with the world average value. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino oscillations; Neutrino telescope; ANTARES

Measurement of atmospheric tau neutrino appearance with IceCube DeepCore - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, Markus; Ahrens, M.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Arguelles, C.; et al. (Physical Review D, 2019)
We present a measurement of atmospheric tau neutrino appearance from oscillations with three years of data from the DeepCore subarray of the IceCube Neutrino Observatory. This analysis uses atmospheric neutrinos from the full sky with reconstructed energies between 5.6 and 56 GeV to search for a statistical excess of cascadelike neutrino events which are the signature of nu(tau) interactions. For CC thorn NC (CC-only) interactions, we measure the tau neutrino normalization to be 0.73(-0.24)(+0.30) (0.57(-0.30)(+0.36)) and exclude the absence of tau neutrino oscillations at a significance of 3.2 sigma (2.0 sigma) These results are consistent with, and of similar precision to, a confirmatory IceCube analysis also presented, as well as measurements performed by other experiments.
CRIS-Team WoS Importer:2019-02-27

Measurement of the atmospheric nu (mu) energy spectrum from 100 GeV to 200 TeV with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; et al. (European Physical Journal C, 2013)
Atmospheric neutrinos are produced during cascades initiated by the interaction of primary cosmic rays with air nuclei. In this paper, a measurement of the atmospheric energy spectrum in the energy range 0.1-200 TeV is presented, using data collected by the ANTARES underwater neutrino telescope from 2008 to 2011. Overall, the measured flux is similar to 25 % higher than predicted by the conventional neutrino flux, and compatible with the measurements reported in ice. The flux is compatible with a single power-law dependence with spectral index gamma (meas)=3.58 +/- 0.12. With the present statistics the contribution of prompt neutrinos cannot be established.

Measurement of the atmospheric νe and νμ energy spectra with the ANTARES neutrino telescope - Albert, A.; Alves, S.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bendahman, M.; et al. (Physics Letters B, 2021)
This letter presents a combined measurement of the energy spectra of atmospheric νe and νμ in the energy range between ∼100 GeV and ∼50 TeV with the ANTARES neutrino telescope. The analysis uses 3012 days of detector livetime in the period 2007–2017, and selects 1016 neutrinos interacting in (or close to) the instrumented volume of the detector, yielding shower-like events (mainly from νe+ν‾e charged current plus all neutrino neutral current interactions) and starting track events (mainly from νμ+ν‾μ charged current interactions). The contamination by atmospheric muons in the final sample is suppressed at the level of a few per mill by different steps in the selection analysis, including a Boosted Decision Tree classifier. The distribution of reconstructed events is unfolded in terms of electron and muon neutrino fluxes. The derived energy spectra are compared with previous measurements that, above 100 GeV, are limited to experiments in polar ice and, for νμ, to Super-Kamiokande.
CRIS-Team Scopus Importer:2021-04-02
Keywords: ANTARES; Atmospheric neutrinos; Neutrino telescope

Measurement of the EBL spectral energy distribution using the VHE gamma-ray spectra of HESS blazars - Abdalla, H.; Abramowski, A.; Aharonian, F.; Ait Benkhali, F.; Akhperjanian, A. G.; Andersson, T.; Angüner, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; et al. (Astronomy & Astrophysics, 2017)
Very high-energy gamma rays (VHE, E greater than or similar to 100 GeV) propagating over cosmological distances can interact with the low-energy photons of the extragalactic background light (EBL) and produce electron-positron pairs. The transparency of the Universe to VHE gamma rays is then directly related to the spectral energy distribution (SED) of the EBL. The observation of features in the VHE energy spectra of extragalactic sources allows the EBL to be measured, which otherwise is very difficult. An EBL model-independent measurement of the EBL SED with the H.E.S.S. array of Cherenkov telescopes is presented. It was obtained by extracting the EBL absorption signal from the reanalysis of high-quality spectra of blazars. From H.E.S.S. data alone the EBL signature is detected at a significance of 9.5 sigma, and the intensity of the EBL obtained in different spectral bands is presented together with the associated gamma-ray horizon.
CRIS-Team WoS Importer:2020-01-15
Keywords: Infrared: diffuse background; Cosmic background radiation; Gamma rays: galaxies; BL Lacertae objects: general

Measurement of the extragalactic background light imprint on the spectra of the brightest blazars observed with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
The extragalactic background light (EBL) is the diffuse radiation with the second highest energy density in the Universe after the cosmic microwave background. The aim of this study is the measurement of the imprint of the EBL opacity to γ-rays on the spectra of the brightest extragalactic sources detected with the High Energy Stereoscopic System (H.E.S.S.). The originality of the method lies in the joint fit of the EBL optical depth and of the intrinsic spectra of the sources, assuming intrinsic smoothness. Analysis of a total of ∼10γ-ray events enables the detection of an EBL signature at the 8.8σ level and constitutes the first measurement of the EBL optical depth using very-high energy (E > 100 GeV) γ-rays. The EBL flux density is constrained over almost two decades of wavelengths [0.30 μm, 17 μm] and the peak value at 1.4 μm is derived as λF = 15 ± 2 ± 3 nW m sr. © 2013 ESO.
Keywords: BL Lacertae objects: general; Cosmic background radiation; Gamma rays: galaxies

Measurement of the group velocity of light in sea water at the ANTARES site - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Astroparticle Physics, 2012)
The group velocity of light has been measured at eight different wavelengths between 385 nm and 532 nm in the Mediterranean Sea at a depth of about 2.2 km with the ANTARES optical beacon systems. A parametrisation of the dependence of the refractive index on wavelength based on the salinity, pressure and temperature of the sea water at the ANTARES site is in good agreement with these measurements. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino telescope; Optical beacon system; Velocity of light; Refractive index

Measurement of the high-energy all-flavor neutrino-nucleon cross section with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Ansseau,; et al. (Physical Review D, 2021)
The flux of high-energy neutrinos passing through the Earth is attenuated due to their interactions with matter. The interaction rate is determined by the neutrino interaction cross section and affects the flux arriving at the IceCube Neutrino Observatory, a cubic-kilometer neutrino detector embedded in the Antarctic ice sheet. We present a measurement of the neutrino cross section between 60 TeV and 10 PeV using the high-energy starting event (HESE) sample from IceCube with 7.5 years of data. The result is binned in neutrino energy and obtained using both Bayesian and frequentist statistics. We find it compatible with predictions from the Standard Model. While the cross section is expected to be flavor independent above 1 TeV, additional constraints on the measurement are included through updated experimental particle identification (PID) classifiers, proxies for the three neutrino flavors. This is the first such measurement to use a ternary PID observable and the first to account for neutrinos from tau decay.
CRIS-Team WoS Importer:2021-07-23

Measurement of the scintillation and ionization response of liquid xenon at MeV energies in the EXO-200 experiment - Anton, Gisela; Badhrees, I.; Barbeau, P. S.; Beck, D.; Belov, V.; Bhatta, T.; Breidenbach, M.; Brunner, T.; Cao, G. F.; Cen, W. R.; Chambers, C.; Cleveland, B.; et al. (Physical Review C - Nuclear Physics, 2020)
Liquid xenon (LXe) is employed in a number of current and future detectors for rare event searches. We use the EXO-200 experimental data to measure the absolute scintillation and ionization yields generated by gamma interactions from Th-228 (2615 keV), Ra-226 (1764 keV), and Co-60 (1332 keV and 1173 keV) calibration sources, over a range of electric fields. The W value that defines the recombination-independent energy scale is measured to be 11.5 +/- 0.5 (syst.) +/- 0.1 (stat.) eV. These data are also used to measure the recombination fluctuations in the number of electrons and photons produced by the calibration sources at the MeV scale, which deviate from extrapolations of lower-energy data. Additionally, a semiempirical model for the energy resolution of the detector is developed, which is used to constrain the recombination efficiency, i.e., the fraction of recombined electrons that result in the emission of a detectable photon. Detailed measurements of the absolute charge and light yields for MeV-scale electron recoils are important for predicting the performance of future neutrinoless double beta-decay detectors.
CRIS-Team WoS Importer:2020-06-30

Measurement of the Spectral Shape of the beta-Decay of Xe-137 to the Ground State of Cs-137 in EXO-200 and Comparison with Theory - Al Kharusi, S.; Anton, Gisela; Badhrees, I.; Barbeau, P. S.; Beck, D.; Belov, V.; Bhatta, T.; Breidenbach, M.; Brunner, T.; Cao, G. F.; Cen, W. R.; Chambers, C.; et al. (Physical Review Letters, 2020)
We report on a comparison between the theoretically predicted and experimentally measured spectra of the first-forbidden nonunique beta-decay transition Xe-137(7/2(-)) -> Cs-137(7/2(+)). The experimental data were acquired by the EXO-200 experiment during a deployment of an AmBe neutron source. The ultralow background environment of EXO-200, together with dedicated source deployment and analysis procedures, allowed for collection of a pure sample of the decays, with an estimated signal to background ratio of more than 99 to 1 in the energy range from 1075 to 4175 keV. In addition to providing a rare and accurate measurement of the first-forbidden nonunique beta-decay shape, this work constitutes a novel test of the calculated electron spectral shapes in the context of the reactor antineutrino anomaly and spectral bump.
CRIS-Team WoS Importer:2020-06-26

Measurements of electron transport in liquid and gas Xenon using a laser-driven photocathode - Njoya, O.; Tsang, T.; Tarka, M.; Fairbank, W.; Kumar, K. S.; Rao, T.; Wager, T.; Kharusi, S. Al; Anton, Gisela; Arnquist, I. J.; Badhrees, I.; Barbeau, P. S.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2020)
Measurements of electron drift properties in liquid and gaseous xenon are reported. The electrons are generated by the photoelectric effect in a semi-transparent gold photocathode driven in transmission mode with a pulsed ultraviolet laser. The charges drift and diffuse in a small chamber at various electric fields and a fixed drift distance of 2.0 cm. At an electric field of 0.5 kV/cm, the measured drift velocities and corresponding temperature coefficients respectively are 1.97±0.04mm∕μs and (−0.69±0.05)%/K for liquid xenon, and 1.42±0.03mm∕μs and (+0.11±0.01)%/K for gaseous xenon at 1.5 bar. In addition, we measure longitudinal diffusion coefficients of 25.7±4.6 cm2/s and 149±23 cm2/s, for liquid and gas, respectively. The quantum efficiency of the gold photocathode is studied at the photon energy of 4.73 eV in liquid and gaseous xenon, and vacuum. These charge transport properties and the behavior of photocathodes in a xenon environment are important in designing and calibrating future large scale noble liquid detectors.
CRIS-Team Scopus Importer:2020-05-29

Measurements using the inelasticity distribution of multi-TeV neutrino interactions in IceCube - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, Markus; Ahrens, M.; Al Samarai, I.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; et al. (Physical Review D, 2019)
Inelasticity, the fraction of a neutrino's energy transferred to hadrons, is a quantity of interest in the study of astrophysical and atmospheric neutrino interactions at multi-TeV energies with IceCube. In this work, a sample of contained neutrino interactions in IceCube is obtained from five years of data and classified as 2650 tracks and 965 cascades. Tracks arise predominantly from charged-current nu(mu) interactions, and we demonstrate that we can reconstruct their energy and inelasticity. The inelasticity distribution is found to be consistent with the calculation of Cooper-Sarkar et al. across the energy range from similar to 1 to similar to 100 TeV. Along with cascades from neutrinos of all flavors, we also perform a fit over the energy, zenith angle, and inelasticity distribution to characterize the flux of astrophysical and atmospheric neutrinos. The energy spectrum of diffuse astrophysical neutrinos is described well by a power law in both track and cascade samples, and a best-fit index gamma = 2.62 +/- 0.07 is found in the energy range from 3.5 TeV to 2.6 PeV. Limits are set on the astrophysical flavor composition and are compatible with a ratio of (1/3 : 1/3 : 1/3)(circle plus). Exploiting the distinct inelasticity distribution of nu(mu) and (nu) over bar (mu) interactions, the atmospheric nu(mu) to (nu) over bar (mu) flux ratio in the energy range from 770 GeV to 21 TeV is found to be 0.77(-0.25)(+0.44) times the calculation by Honda et al. Lastly, the inelasticity distribution is also sensitive to neutrino charged-current charm production. The data are consistent with a leading-order calculation, with zero charm production excluded at 91% confidence level. Future analyses of inelasticity distributions may probe new physics that affects neutrino interactions both in and beyond the Standard Model.
CRIS-Team WoS Importer:2019-02-27

Measuring the atmospheric neutrino oscillation parameters and constraining the 3+1 neutrino model with ten years of ANTARES data - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Belhorma, B.; et al. (Journal of High Energy Physics, 2019)
The ANTARES neutrino telescope has an energy threshold of a few tens of GeV. This allows to study the phenomenon of atmospheric muon neutrino disappearance due to neutrino oscillations. In a similar way, constraints on the 3+1 neutrino model, which foresees the existence of one sterile neutrino, can be inferred. Using data collected by the ANTARES neutrino telescope from 2007 to 2016, a new measurement of Δm322 and θ23 has been performed — which is consistent with world best-fit values — and constraints on the 3+1 neutrino model have been derived.[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2019-07-02
Keywords: Neutrino Detectors and Telescopes (experiments); Oscillation

Measuring the Neutrino Cross Section Using 8 years of Upgoing Muon Neutrinos Observed with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Proceedings of Science, 2022)
The IceCube Neutrino Observatory detects neutrinos at energies orders of magnitude higher than those available to current accelerators. Above 40 TeV, neutrinos traveling through the Earth will be absorbed as they interact via charged current interactions with nuclei, creating a deficit of Earth-crossing neutrinos detected at IceCube. The previous published results showed the cross section to be consistent with Standard Model predictions for 1 year of IceCube data. We present a new analysis that uses 8 years of IceCube data to fit the νμ absorption in the Earth, with statistics an order of magnitude better than previous analyses, and with an improved treatment of systematic uncertainties. It will measure the cross section in three energy bins that span the range 1 TeV to 100 PeV. We will present Monte Carlo studies that demonstrate its sensitivity.
CRIS-Team Scopus Importer:2024-12-16

Methods and stability tests associated with the sterile neutrino search using improved high-energy νμ event reconstruction in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Physical Review D, 2024)
We provide supporting details for the search for a 3+1 sterile neutrino using data collected over 10.7 years at the IceCube Neutrino Observatory. The analysis uses atmospheric muon-flavored neutrinos from 0.5 to 100 TeV that traverse Earth to reach the IceCube detector and finds a best-fit point at sin2(2θ24)=0.16 and Δm412=3.5 eV2 with a goodness-of-fit p value of 12% and consistency with the null hypothesis of no oscillations to sterile neutrinos with a p value of 3.1%. Several improvements were made over past analyses, which are reviewed in this article, including upgrades to the reconstruction and the study of sources of systematic uncertainty. We provide details of the fit quality and discuss stability tests that split the data for separate samples, comparing results. We find that the fits are consistent between split datasets.
CRIS-Team Scopus Importer:2024-11-29

Model-independent search for neutrino sources with the ANTARES neutrino telescope - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Bertin, V.; Biagi, S.; et al. (Astroparticle Physics, 2020)
A novel method to analyse the spatial distribution of neutrino candidates recorded with the ANTARES neutrino telescope is introduced, searching for an excess of neutrinos in a region of arbitrary size and shape from any direction in the sky. Techniques originating from the domains of machine learning, pattern recognition and image processing are used to purify the sample of neutrino candidates and for the analysis of the obtained skymap. In contrast to a dedicated search for a specific neutrino emission model, this approach is sensitive to a wide range of possible morphologies of potential sources of high-energy neutrino emission. The application of these methods to ANTARES data yields a large-scale excess with a post-trial significance of 2.5σ. Applied to public data from IceCube in its IC40 configuration, an excess consistent with the results from ANTARES is observed with a post-trial significance of 2.1σ.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Anisotropy; Astroparticle physics; Neutrino astronomy; Pattern recognition

Monte Carlo simulations for the ANTARES underwater neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2021)
Monte Carlo simulations are a unique tool to check the response of a detector and to monitor its performance. For a deep-sea neutrino telescope, the variability of the environmental conditions that can affect the behaviour of the data acquisition system must be considered, in addition to a reliable description of the active parts of the detector and of the features of physics events, in order to produce a realistic set of simulated events. In this paper, the software tools used to produce neutrino and cosmic ray signatures in the telescope and the strategy developed to represent the time evolution of the natural environment and of the detector efficiency are described.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Cosmic ray experiments; Neutrino astronomy; Neutrino detectors; Neutrino experiments

Multi-flavour neutrino searches from the Milky Way Galaxy - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
High-energy neutrinos are expected to be produced in the Milky Way by cosmic ray interactions at sites of acceleration or during their propagation. Neutrinos provide distinctive information on hadronic interactions and can be pointed back to production origins, unraveling unique properties of the Galaxy. We present an analysis on the search for the diffuse neutrino flux along the Galactic Plane by using data collected at the largest operating neutrino telescope in the world - the IceCube Neutrino Observatory. More than 10 years of data since the completion of the detector are used in this analysis. We utilize three event selections including through-going tracks, showers and starting-tracks to reach full-sky coverage and to be sensitive to all three neutrino flavours.
CRIS-Team Scopus Importer:2025-02-04

Multimessenger gamma-ray and neutrino coincidence alerts using hawc and icecube subthreshold data - Solares, H. A.Ayala; Coutu, S.; DeLaunay, J. J.; Fox, D. B.; Grégoire, T.; Keivani, A.; Krauß, F.; Mostafá, M.; Murase, K.; Turley, C. F.; Albert, A.; Alfaro, R.; et al. (Astrophysical Journal, 2021)
The High Altitude Water Cerenkov (HAWC) and IceCube observatories, through the Astrophysical Multimessenger Observatory Network (AMON) framework, have developed a multimessenger joint search for extragalactic astrophysical sources. This analysis looks for sources that emit both cosmic neutrinos and gamma rays that are produced in photohadronic or hadronic interactions. The AMON system is running continuously, receiving subthreshold data (i.e., data that are not suited on their own to do astrophysical searches) from HAWC and IceCube, and combining them in real time. Here we present the analysis algorithm, as well as results from archival data collected between 2015 June and 2018 August, with a total live time of 3.0 yr. During this period we found two coincident events that have a false-alarm rate (FAR) of <1 coincidence yr-1, consistent with the background expectations. The real-time implementation of the analysis in the AMON system began on 2019 November 20 and issues alerts to the community through the Gamma-ray Coordinates Network with an FAR threshold of <4 coincidences yr-1.
CRIS-Team Scopus Importer:2021-01-22

Multi-messenger Observations of a Binary Neutron Star Merger - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, Paolo; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; Afrough, M.; et al. (Astrophysical Journal Letters, 2017)
On 2017 August 17 a binary neutron star coalescence candidate (later designated GW170817) with merger time 12:41:04 UTC was observed through gravitational waves by the Advanced LIGO and Advanced Virgo detectors. The Fermi Gamma-ray Burst Monitor independently detected a gamma-ray burst (GRB 170817A) with a time delay of similar to 1.7 s with respect to the merger time. From the gravitational-wave signal, the source was initially localized to a sky region of 31 deg(2) at a luminosity distance of 40(-8)(+8) Mpc and with component masses consistent with neutron stars. The component masses were later measured to be in the range 0.86 to 2.26 M-circle dot. An extensive observing campaign was launched across the electromagnetic spectrum leading to the discovery of a bright optical transient (SSS17a, now with the IAU identification of AT 2017gfo) in NGC 4993 (at similar to 40 Mpc) less than 11 hours after the merger by the One-Meter, Two Hemisphere (1M2H) team using the 1 m Swope Telescope. The optical transient was independently detected by multiple teams within an hour. Subsequent observations targeted the object and its environment. Early ultraviolet observations revealed a blue transient that faded within 48 hours. Optical and infrared observations showed a redward evolution over similar to 10 days. Following early non-detections, X-ray and radio emission were discovered at the transient's position similar to 9 and similar to 16 days, respectively, after the merger. Both the X-ray and radio emission likely arise from a physical process that is distinct from the one that generates the UV/optical/near-infrared emission. No ultra-high-energy gamma-rays and no neutrino candidates consistent with the source were found in follow-up searches. These observations support the hypothesis that GW170817 was produced by the merger of two neutron stars in NGC4993 followed by a short gamma-ray burst (GRB 170817A) and a kilonova/macronova powered by the radioactive decay of r-process nuclei synthesized in the ejecta.
Keywords: gravitational waves; stars: neutron

Multimessenger observations of a flaring blazar coincident with high-energy neutrino IceCube-170922A - Aartsen, M. G.; Ackermann, Markus; Mitchell, Alison; Adams, J.; Aguilar, J. A.; Ahlers, Markus; Ahrens, M.; Al Samarai, I.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; et al. (Science, 2018)
CRIS-Team WoS Importer:2020-01-15

Multi-messenger searches via IceCube's high-energy neutrinos and gravitational-wave detections of LIGO/Virgo - Veske, Doğa; Hussain, Raamis; Márka, Zsuzsa; Countryman, Stefan; Pizzuto, Alex; Asali, Yasmeen; Oliveira, Ana Silva; Vandenbroucke, Justin; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; et al. (Proceedings of Science, 2022)
We summarize initial results for high-energy neutrino counterpart searches coinciding with gravitational-wave events in LIGO/Virgo's GWTC-2 catalog using IceCube's neutrino triggers. We did not find any statistically significant high-energy neutrino counterpart and derived upper limits on the time-integrated neutrino emission on Earth as well as the isotropic equivalent energy emitted in high-energy neutrinos for each event.
CRIS-Team Scopus Importer:2024-12-16

Multi-wavelength observations of H 2356-309 - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2010)
Aims. The properties of the broad-band emission from the high-frequency peaked BL Lac H 2356-309 (z = 0.165) are investigated. Methods. Very high energy (VHE; E > 100 GeV) observations of H 2356-309 were performed with the High Energy Stereoscopic System (HESS) from 2004 through 2007. Simultaneous optical/UV and X-ray observations were made with the XMM-Newton satellite on June 12/13 and June 14/15, 2005. NRT radio observations were also contemporaneously performed in 2005. ATOM optical monitoring observations were also made in 2007. Results. A strong VHE signal, ∼13σ total, was detected by HESS after the four years HESS observations (116.8 h live time). The integral flux above 240 GeV is I(>240 GeV) = (3.06 ± 0.26 ± 0.61) × 10 cm s, corresponding to ∼1.6% of the flux observed from the Crab Nebula. A time-averaged energy spectrum is measured from 200 GeV to 2 TeV and is characterized by a power law (photon index of Γ = 3.06 ± 0.15 ± 0.10). Significant small-amplitude variations in the VHE flux from H 2356-309 are seen on time scales of months and years, but not on shorter time scales. No evidence for any variations in the VHE spectral slope are found within these data. The XMM-Newton X-ray measurements show a historically low X-ray state, characterized by a hard, broken-power-law spectrum on both nights. Conclusions. The broad-band spectral energy distribution (SED) of the blazar can be adequately fit using a simple one-zone synchrotron self-Compton (SSC) model. In the SSC scenario, higher VHE fluxes could be expected in the future since the observed X-ray flux is at a historically low level. © 2010 ESO.
Keywords: BL Lacertae objects: individual: H 2356-309; Galaxies: active; Gamma rays: galaxies

MURCHISON WIDEFIELD ARRAY LIMITS on RADIO EMISSION from ANTARES NEUTRINO EVENTS - Croft, Steve; Kaplan, D. L.; Tingay, S. J.; Murphy, Tara; Bell, M. E.; Rowlinson, Antonia; Adrian-Martinez, S.; Ageron, M.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; et al. (Astrophysical Journal Letters, 2016)
We present a search, using the Murchison Widefield Array (MWA), for electromagnetic (EM) counterparts to two candidate high-energy neutrino events detected by the ANTARES neutrino telescope in 2013 November and 2014 March. These events were selected by ANTARES because they are consistent, within 0°.4, with the locations of galaxies within 20 Mpc of Earth. Using MWA archival data at frequencies between 118 and 182 MHz, taken ∼20 days prior to, at the same time as, and up to a year after the neutrino triggers, we look for transient or strongly variable radio sources that are consistent with the neutrino positions. No such counterparts are detected, and we set a 5σ upper limit for low-frequency radio emission of ∼10 erg s for progenitors at 20 Mpc. If the neutrino sources are instead not in nearby galaxies, but originate in binary neutron star coalescences, our limits place the progenitors at z 0.2. While it is possible, due to the high background from atmospheric neutrinos, that neither event is astrophysical, the MWA observations are nevertheless among the first to follow up neutrino candidates in the radio, and illustrate the promise of wide-field instruments like MWA for detecting EM counterparts to such events.
Keywords: neutrinos; radio continuum: general

N* and Delta* decays into N pi0 pi0 - Thoma, U.; Fuchs, M.; Anisovich, A. V.; Anton, Gisela; Bantes, R.; Bartholomy, O.; Beck, R.; Beloglazov, Yu.; Crede, V.; Ehmanns, A.; Ernst, J.; Fabry, I.; et al. (Physics Letters B, 2008)

Neutral Pion Photoproduction off Protons in the Energy Range 0.3 GeV < Eγ < 3 GeV - Bartholomy, O.; Crede, V.; van Pee, H.; Anisovich, A. V.; Anton, Gisela; Bantes, R.; Beloglazov, Yu.; Bogendörfer, Regina; Castelijns, R.; Ehmanns, A.; Ernst, J.; Fabry, I.; et al. (Physical Review Letters, 2005)

Neutrino Education, Outreach, and Communications Activities: Captivating Examples from IceCube - O'Keefe, Madeleine; Argueta, Jocelyn; Bechtol, Ellen; Madsen, Jim; Shirey, Katherine; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; et al. (Proceedings of Science, 2022)
The IceCube Neutrino Observatory at the South Pole has tremendous emotional appeal-the extreme Antarctic environment coupled with the aura of a pioneering experiment that explores the universe in a new way. However, as with most cutting-edge experiments, it is still challenging to translate the exotic, demanding science into accessible language. We present three examples of recent successful education, outreach, and communication activities that demonstrate how we leverage efforts and sustain connections to produce engaging results. First we describe our participation in the PolarTREC program, which pairs researchers with educators to provide deployments in the Antarctic, and how we have sustained relationships with these educators to produce high-quality experiences to reach target audiences even during a pandemic. We then focus on three activities from the past year: a summer enrichment program for high school students that was also modified for a 10-week IceCube after school program, a virtual visit to the South Pole for the ScienceWriters 2020 conference, and a series of short videos in English and Spanish suitable for all ages that explain traveling, living, and working at the South Pole.
CRIS-Team Scopus Importer:2024-12-16

Neutrinos below 100 TeV from the southern sky employing refined veto techniques to IceCube data - Aartsen, M. G.; Ackermann, M.; Adams, J.; A. Aguilar, J.; Ahlers, M.; Ahrens, M.; Alispach, C.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; et al. (Astroparticle Physics, 2020)
Many Galactic sources of gamma rays, such as supernova remnants, are expected to produce neutrinos with a typical energy cutoff well below 100 TeV. For the IceCube Neutrino Observatory located at the South Pole, the southern sky, containing the inner part of the Galactic plane and the Galactic Center, is a particularly challenging region at these energies, because of the large background of atmospheric muons. In this paper, we present recent advancements in data selection strategies for track-like muon neutrino events with energies below 100 TeV from the southern sky. The strategies utilize the outer detector regions as veto and features of the signal pattern to reduce the background of atmospheric muons to a level which, for the first time, allows IceCube searching for point-like sources of neutrinos in the southern sky at energies between 100 GeV and several TeV in the muon neutrino charged current channel. No significant clustering of neutrinos above background expectation was observed in four years of data recorded with the completed IceCube detector. Upper limits on the neutrino flux for a number of spectral hypotheses are reported for a list of astrophysical objects in the southern hemisphere.
CRIS-Team Scopus Importer:2019-11-22
Keywords: Neutrinos; Point sources; Veto techniques

Neutrino Telescopes - Anton, Gisela (Probing Particle Physics with Neutrino Telescopes, 2019)
This chapter addresses the working principle of neutrino telescopes, important detector parameters as well as the layout and performance of current and future neutrino telescopes.
CRIS-Team WoS Importer:2021-10-01

New constraints on all flavor Galactic diffuse neutrino emission with the ANTARES telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
The flux of very high-energy neutrinos produced in our Galaxy by the interaction of accelerated cosmic rays with the interstellar medium is not yet determined. The characterization of this flux will shed light on Galactic accelerator features, gas distribution morphology and Galactic cosmic ray transport. The central Galactic plane can be the site of an enhanced neutrino production, thus leading to anisotropies in the extraterrestrial neutrino signal as measured by the IceCube Collaboration. The ANTARES neutrino telescope, located in the Mediterranean Sea, offers a favorable view of this part of the sky, thereby allowing for a contribution to the determination of this flux. The expected diffuse Galactic neutrino emission can be obtained, linking a model of generation and propagation of cosmic rays with the morphology of the gas distribution in the Milky Way. In this paper, the so-called "gamma model" introduced recently to explain the high-energy gamma-ray diffuse Galactic emission is assumed as reference. The neutrino flux predicted by the "gamma model" depends on the assumed primary cosmic ray spectrum cutoff. Considering a radially dependent diffusion coefficient, this proposed scenario is able to account for the local cosmic ray measurements, as well as for the Galactic gamma-ray observations. Nine years of ANTARES data are used in this work to search for a possible Galactic contribution according to this scenario. All flavor neutrino interactions are considered. No excess of events is observed, and an upper limit is set on the neutrino flux of 1.1 (1.2) times the prediction of the "gamma model," assuming the primary cosmic ray spectrum cutoff at 5 (50) PeV. This limit excludes the diffuse Galactic neutrino emission as the major cause of the "spectral anomaly" between the two hemispheres measured by IceCube.

New Flux Limits in the Low Relativistic Regime for Magnetic Monopoles at IceCube - Lauber, Frederik Hermann; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
Magnetic monopoles are hypothetical particles that carry magnetic charge. Depending on their velocity, different light production mechanisms exist to facilitate detection. In this work, a previously unused light production mechanism, luminescence of ice, is introduced. This light production mechanism is nearly independent of the velocity of the incident magnetic monopole and becomes the only viable light production mechanism in the low relativistic regime (0.1-0.55c). An analysis in the low relativistic regime searching for magnetic monopoles in seven years of IceCube data is presented. While no magnetic monopole detection can be claimed, a new flux limit in the low relativistic regime is presented, superseding the previous best flux limit by 2 orders of magnitude.
CRIS-Team Scopus Importer:2022-12-23

New results on the Roper resonance and the P11 partial wave - Sarantsev, A. V.; Fuchs, M.; Kotulla, M.; Thoma, U.; Ahrens, J.; Annand, J. R. M.; Anisovich, A. V.; Anton, Gisela; Bantes, R.; Bartholomy, O.; Beck, R.; Beloglazov, Yu.; et al. (Physics Letters B, 2008)

Noise reduction for single-shot grating-based phase-contrast imaging at an x-ray backlighter - Schreiner, Stephan; Akstaller, Bernhard; Dietrich, Lou; Meyer, Pascal; Neumayer, Paul; Schuster, Max; Wolf, Andreas; Zielbauer, Bernhard; Ludwig, Veronika; Michel, Thilo; Anton, Gisela; Funk, Stefan (Journal of Imaging, 2021)
X-ray backlighters allow the capture of sharp images of fast dynamic processes due to extremely short exposure times. Moiré imaging enables simultaneously measuring the absorption and differential phase-contrast (DPC) of these processes. Acquiring images with one single shot limits the X-ray photon flux, which can result in noisy images. Increasing the photon statistics by repeating the experiment to gain the same image is not possible if the investigated processes are dynamic and chaotic. Furthermore, to reconstruct the DPC and transmission image, an additional measurement captured in absence of the object is required. For these reference measurements, shot-to-shot fluctuations in X-ray spectra and a source position complicate the averaging of several reference images for noise reduction. Here, two approaches of processing multiple reference images in combination with one single object image are evaluated regarding the image quality. We found that with only five reference images, the contrast-to-noise ratio can be improved by approximately 13% in the DPC image. This promises improvements for short-exposure single-shot acquisitions of rapid processes, such as laser-produced plasma shock-waves in high-energy density experiments at backlighter X-ray sources such as the PHELIX high-power laser facility.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Grating-based phase-contrast; Image processing; Image quality improvement; Single-shot X-ray phase-contrast imaging; X-ray back-lighter; X-ray generators and sources

Non-standard neutrino interactions in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Proceedings of Science, 2022)
Non-standard neutrino interactions (NSI) may arise in various types of new physics. Their existence would change the potential that atmospheric neutrinos encounter when traversing Earth matter and hence alter their oscillation behavior. This imprint on coherent neutrino forward scattering can be probed using high-statistics neutrino experiments such as IceCube and its low-energy extension, DeepCore. Both provide extensive data samples that include all neutrino flavors, with oscillation baselines between tens of kilometers and the diameter of the Earth. DeepCore event energies reach from a few GeV up to the order of 100 GeV - which marks the lower threshold for higher energy IceCube atmospheric samples, ranging up to 10 TeV. In DeepCore data, the large sample size and energy range allow us to consider not only flavor-violating and flavor-nonuniversal NSI in the μ − τ sector, but also those involving electron flavor. The effective parameterization used in our analyses is independent of the underlying model and the new physics mass scale. In this way, competitive limits on several NSI parameters have been set in the past. The 8 years of data available now result in significantly improved sensitivities. This improvement stems not only from the increase in statistics but also from substantial improvement in the treatment of systematic uncertainties, background rejection and event reconstruction.
CRIS-Team Scopus Importer:2022-06-03

Observation of high-energy neutrinos from the Galactic plane - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Anton, Gisela; et al. (Science, 2023)
The origin of high-energy cosmic rays, atomic nuclei that continuously impact Earth's atmosphere, is unknown. Because of deflection by interstellar magnetic fields, cosmic rays produced within the Milky Way arrive at Earth from random directions. However, cosmic rays interact with matter near their sources and during propagation, which produces high-energy neutrinos. We searched for neutrino emission using machine learning techniques applied to 10 years of data from the IceCube Neutrino Observatory. By comparing diffuse emission models to a background-only hypothesis, we identified neutrino emission from the Galactic plane at the 4.5σ level of significance. The signal is consistent with diffuse emission of neutrinos from the Milky Way but could also arise from a population of unresolved point sources.
CRIS-Team Scopus Importer:2023-07-21

Observation of high-energy neutrinos from the Galactic plane - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
IceCube has discovered a flux of astrophysical neutrinos and presented evidence for the first neutrino sources, a flaring blazar known as TXS 0506+056 and the active galaxy NGC 1068. However, the sources responsible for the majority of the astrophysical neutrino flux remain elusive. In addition to hypothetical sources within our Galaxy, high energy neutrinos are produced when cosmic rays interact at their acceleration sites and during propagation through the interstellar medium. The Galactic plane has therefore long been hypothesized as a neutrino source. In this contribution, new results are presented for searches of neutrino sources utilizing a dataset that builds upon recent advances in deep-learning-based reconstruction methods for neutrino-induced cascades. This work presents the first observation of high-energy neutrinos from the Milky Way Galaxy, rejecting the background-only hypothesis at 4.5 σ. The neutrino signal is consistent with diffuse emission from the Galactic plane, potentially in combination with emission by a population of sources.
CRIS-Team Scopus Importer:2025-02-04

Observation of seasonal variations of the flux of high-energy atmospheric neutrinos with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aggarwal, N.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; et al. (European Physical Journal C: Particles and Fields, 2023)
Atmospheric muon neutrinos are produced by meson decays in cosmic-ray-induced air showers. The flux depends on meteorological quantities such as the air temperature, which affects the density of air. Competition between decay and re-interaction of those mesons in the first particle production generations gives rise to a higher neutrino flux when the air density in the stratosphere is lower, corresponding to a higher temperature. A measurement of a temperature dependence of the atmospheric νμ flux provides a novel method for constraining hadronic interaction models of air showers. It is particularly sensitive to the production of kaons. Studying this temperature dependence for the first time requires a large sample of high-energy neutrinos as well as a detailed understanding of atmospheric properties. We report the significant (>10σ) observation of a correlation between the rate of more than 260,000 neutrinos, detected by IceCube between 2012 and 2018, and atmospheric temperatures of the stratosphere, measured by the Atmospheric Infrared Sounder (AIRS) instrument aboard NASA’s AQUA satellite. For the observed 10 % seasonal change of effective atmospheric temperature we measure a 3.5(3) % change in the muon neutrino flux. This observed correlation deviates by about 2-3 standard deviations from the expected correlation of 4.3 % as obtained from theoretical predictions under the assumption of various hadronic interaction models.
CRIS-Team Scopus Importer:2023-09-15

Observation of Seven Astrophysical Tau Neutrino Candidates with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Physical Review Letters, 2024)
We report on a measurement of astrophysical tau neutrinos with 9.7 yr of IceCube data. Using convolutional neural networks trained on images derived from simulated events, seven candidate ντ events were found with visible energies ranging from roughly 20 TeV to 1 PeV and a median expected parent ντ energy of about 200 TeV. Considering backgrounds from astrophysical and atmospheric neutrinos, and muons from π±/K± decays in atmospheric air showers, we obtain a total estimated background of about 0.5 events, dominated by non-ντ astrophysical neutrinos. Thus, we rule out the absence of astrophysical ντ at the 5σ level. The measured astrophysical ντ flux is consistent with expectations based on previously published IceCube astrophysical neutrino flux measurements and neutrino oscillations.
CRIS-Team Scopus Importer:2024-04-26

Observation of the cosmic ray shadow of the Sun with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin,; Biagi, S.; et al. (Physical Review D, 2020)
The ANTARES detector is an undersea neutrino telescope in the Mediterranean Sea. The search for pointlike neutrino sources is one of the main goals of the ANTARES telescope, requiring a reliable method to evaluate the detector angular resolution and pointing accuracy. This work describes the study of the Sun "shadow" effect with the ANTARES detector. The shadow is the deficit in the atmospheric muon flux in the direction of the Sun caused by the absorption of the primary cosmic rays. This analysis is based on the data collected between 2008 and 2017 by the ANTARES telescope. The observed statistical significance of the Sun shadow detection is 3.7 sigma, with an estimated angular resolution of 0.59 degrees +/- 0.10 degrees for downward-going muons. The pointing accuracy is found to be consistent with the expectations and no evidence of systematic pointing shifts is observed.
CRIS-Team WoS Importer:2021-01-15

On-Surface Synthesis of Porous Carbon Nanoribbons on Silver: Reaction Kinetics and the Influence of the Surface Structure - Ammon, Maximilian Michael; Haller, Martin; Sorayya, Shadi; Maier, Sabine (ChemPhysChem, 2019)
We report on the influence of the surface structure and the reaction kinetics in the bottom-up fabrication of porous nanoribbons on silver surfaces using low-temperature scanning tunneling microscopy. The porous carbon nanoribbons are fabricated by the polymerization of 1,3,5-tris(3-bromophenyl)benzene directly on the Ag surface using an Ullmann-type reaction in combination with dehydrogenative coupling reactions. We demonstrate the successful on-surface synthesis of porous nanoribbons on Ag(111) and Ag(100) even though the self-assemblies of the intermediate organometallic structures and covalently-linked polymer chains are different on both surfaces. Furthermore, we present the formation of isolated porous nanoribbons by kinetic control. Our results give valuable insights into the role of substrate-induced templating effects and the reaction kinetics in the on-surface synthesis of conformationally flexible molecules.
CRIS-Team Scopus Importer:2019-09-24
Keywords: molecular self-assembly; on-surface reactions; scanning probe microscopy; surface chemistry; Ullmann-type reaction

On the Characteristics of Helical 3-D X-ray Dark-field Imaging - Felsner, Lina; Hu, Shiyang; Ludwig, Veronika; Anton, Gisela; Maier, Andreas; Rieß, Christian (Bildverarbeitung für die Medizin (BVM 2019), 2019)

Optical and X-ray early follow-up of ANTARES neutrino alerts - Adrian-Martinez, S.; Ageron, M.; Albert, A.; Al Samarai, I.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; et al. (Journal of Cosmology and Astroparticle Physics, 2016)
High-energy neutrinos could be produced in the interaction of charged cosmic rays with matter or radiation surrounding astrophysical sources. Even with the recent detection of extraterrestrial high-energy neutrinos by the IceCube experiment, no astrophysical neutrino source has yet been discovered. Transient sources, such as gamma-ray bursts, core-collapse supernovae, or active galactic nuclei are promising candidates. Multi-messenger programs offer a unique opportunity to detect these transient sources. By combining the information provided by the ANTARES neutrino telescope with information coming from other observatories, the probability of detecting a source is enhanced, allowing the possibility of identifying a neutrino progenitor from a single detected event. A method based on optical and X-ray follow-ups of high-energy neutrino alerts has been developed within the ANTARES collaboration. This method does not require any assumptions on the relation between neutrino and photon spectra other than time-correlation. This program, denoted as TAToO, triggers a network of robotic optical telescopes (TAROT and ROTSE) and the Swift-XRT with a delay of only a few seconds after a neutrino detection, and is therefore well-suited to search for fast transient sources. To identify an optical or X-ray counterpart to a neutrino signal, the images provided by the follow-up observations are analysed with dedicated pipelines. A total of 42 alerts with optical and 7 alerts with X-ray images taken with a maximum delay of 24 hours after the neutrino trigger have been analysed. No optical or X-ray counterparts associated to the neutrino triggers have been found, and upper limits on transient source magnitudes have been derived. The probability to reject the gamma-ray burst origin hypothesis has been computed for each alert.

Optical intensity interferometry lab tests in preparation of stellar diameter measurements at IACTs at GHz photon rates - Zmija, Andreas; Vogel, Naomi; Anton, Gisela; Malyshev, Dmitry; Michel, Thilo; Zink, Adrian; Funk, Stefan (Monthly Notices of the Royal Astronomical Society, 2022)
Astronomical intensity interferometry enables quantitative measurements of the source geometry by measuring the photon fluxes in individual telescopes and correlating them, rather than correlating the electromagnetic waves' amplitudes. This simplifies the realization of large telescope baselines and high angular resolutions. Imaging Atmospheric Cherenkov Telescopes (IACTs), intended to detect the optical emission of γ-ray-induced air showers, are excellent candidates to perform intensity correlations in the optical at reasonable signal-to-noise ratios. The detected coherence time is on the scale of (10-12)-(10-15) s-depending on the optical bandwidth of the measurement-which challenges the detection system to work in a stable and accurate way. We developed an intensity interferometry set-up applicable to IACTs, which measures the photocurrents from photomultipliers and correlates them offline, and as such is designed to handle the very large photon rates provided by the telescopes. We present measurements in the lab simulating starlight using a xenon lamp and measured at different degrees of temporal and spatial coherence. Necessary calibration procedures are described with the goal of understanding the measurements quantitatively. Measured coherence times between 5 femtoseconds (corresponding signal-to-background ratio 5 × 10-7) and 110 femtoseconds (signal-to-background ratio 10-5) are in good agreement with expectations, and so are the noise levels in the correlations, reaching down to 6 × 10-8, after measurements between 30 min and 1 h.
CRIS-Team Scopus Importer:2021-12-24
Keywords: instrumentation: detectors; instrumentation: interferometers; stars: imaging; techniques: interferometric

Optimisation of Image Reconstruction for Phase-Contrast X-Ray Talbot-Lau Imaging with regard to Mechanical Robustness - Seifert, Maria; Käppler, Sebastian; Hauke, Christian; Horn, Florian; Pelzer, Georg; Rieger, Jens; Michel, Thilo; Riess, Christian; Anton, Gisela (Physics in Medicine and Biology, 2016)
Keywords: phase-contrast; reference phase; image reconstruction; PCA; x-ray imaging; robustness; TalbotLau

Optimization of the optical array geometry for IceCube-Gen2 - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
IceCube-Gen2 is a planned extension of the IceCube Neutrino Observatory at the South Pole designed to study the high-energy neutrino sky from TeV to EeV energies with a five times better point source sensitivity than the current IceCube detector. This is achieved by deploying 120 new strings with attached optical sensors in a pattern around IceCube that features considerably larger distances between individual strings than the ∼125 m for the existing detector. Here, we present the results of an optimization study searching for the best point source sensitivity while varying the IceCube-Gen2 string spacing between 150 m and 350 m.
CRIS-Team Scopus Importer:2023-08-15

Optimized Communication Scheme for Massively Parallel Simulations of Polydisperse Particle Systems with Large Size Ratios - Eibl, Sebastian; Preclik, Tobias; Rüde, Ulrich (Particles 2017, 2017)
The standard method to parallelize particle based simulations with a hard contact interaction model and impulsive contact reactions[1] is to subdivide the simulation domain into subdomains. Each subdomain is handled by a different process and particle related information is communicated to neighbouring domains. This next neighbour communication shows perfect scalability even for a very large number of processes[2]. However it imposes an upper limit for the particle size as information can not propagate to the subdomain after the next one. Making the subdomains larger is not an option as it limits the usage of supercomputers which require thousands of processes to run efficiently. One way to overcome this problem is to introduce global particles which are known on every process. This however requires all to all communication to keep the particles in sync which impedes good scaling performance on large systems. Here we propose a new communication scheme which can handle polydisperse particles of arbitrary size ratios. The largest particles are allowed to overlap more than one subdomain and are not restricted in size. The communication scheme is based on point to point communication and completely avoids expensive collective operations. Only processes which really have to know about a particle will participate in the communication corresponding to this particle. Aggressive message aggregation is used to reduce the amount of messages sent. Also an information caching system is applied to further reduce the number of messages. We implemented the communication scheme into our rigid body physics engine module pe of the waLBerla framework[3] and investigated the scaling behaviour on the Juqueen supercomputer in Jülich. We achieved perfect weak scalability up to the full machine. For the strong scaling the communication protocol converges to an all to all communication as large particles overlap more and more subdomains. Therefore as soon as this process starts the parallel efficiency deteriorates. REFERENCES [1] D. E. Stewart, Rigid-body dynamics with friction and impact. SIAM review 42.1 (2000): 3-39. [2] T. Preclik & U. Rüde, Ultrascale simulations of non-smooth granular dynamics., Computational Particle Mechanics 2 (2015), Nr. 2, S. 173–196 [3] C. Godenschwager et al., A framework for hybrid parallel flow simulations with a trillion cells in complex geometries, Proceedings of the International Conference on High Performance Computing, Networking, Storage and Analysis, 2013, 35 <br

Particle identification algorithms for the PANDA barrel DIRC - Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Schwiening, J.; Traxler, M.; Schmitt, L.; et al. (Journal of Instrumentation, 2020)
The PANDA experiment at the international accelerator Facility for Antiproton and Ion Research in Europe (FAIR) near GSI, Darmstadt, Germany will address fundamental questions of hadron physics. Excellent particle identification is required to achieve the PANDA physics goals. Hadronic particle identification (PID) in the barrel region of PANDA target spectrometer will be delivered by a fast focusing DIRC (Detection of Internally Reflecfted Cherenkov light) counter. The Barrel DIRC will cover the polar angle range of 22◦-140◦ and is designed to provide π/K separation for momenta up to 3.5 GeV/c with a separation power of at least 3 standard deviations. Several reconstruction algorithms have been developed to determine the performance of the detector. The “geometrical reconstruction” determines the Cherenkov angle by relying primarily on the position of the detected photons. The “time imaging”, however, utilizes both position and time measurements by directly performing the maximum likelihood fit. Simulations and experimental data from prototype tests at the CERN Proton Synchrotron (PS) were used to evaluate the performance of the algorithms. We will discuss both reconstruction approaches.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Cherenkov detectors; Detector modelling and simulations I; Interaction of hadrons with matter etc; Interaction of photons with matter; Interaction of radiation with matter; Particle identification methods; Performance of High Energy Physics Detectors

Particle identification with DIRCs at PANDA - Düren, M.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Schwiening, J.; Traxler, M.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
The DIRC technology (Detection of Internally Reflected Cherenkov light) offers an excellent possibility to minimize the form factor of Cherenkov detectors in hermetic high energy detectors. The PANDA experiment at FAIR in Germany will combine a barrel-shaped DIRC with a disc-shaped DIRC to cover an angular range of 5 to 140 degrees. Particle identification for pions and kaons with a separation power of 3 standard deviations or more will be provided for momenta between 0.5 GeV/c and 3.5 GeV in the barrel region and up to 4 GeV/c in the forward region. Even though the concept is simple, the design and construction of a DIRC is challenging. High precision optics and mechanics are required to maintain the angular information of the Cherenkov photons during multiple internal reflections and to focus the individual photons onto position sensitive photon detectors. These sensors must combine high efficiencies for single photons with low dark count rates and good timing resolution at high rates. The choice of radiation hard fused silica for the optical material and of MCP-PMT photon sensors is essential for DIRC detectors to survive in an environment of radiation and strong magnetic field. The two DIRC detectors differ in the focusing optics, in the treatment of chromatic dispersion and in the electronic readout systems. The technical design of the two DIRC detectors and their validation by testing prototypes in a mixed particle beam at CERN are presented.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Cherenkov-detector; PANDA; Particle identification

Performance analysis of X-Ray phase-contrast interferometers with respect to grating layouts - Haas, Wilhelm; Bartl, Peter; Bayer, Florian; Durst, Jürgen; Grund, T.; Kenntner, J.; Michel, Thilo; Ritter, André; Weber, Thomas; Anton, Gisela; Hornegger, Joachim (2010 IEEE Nuclear Science Symposium, Medical Imaging Conference, NSS/MIC 2010 and 17th International Workshop on Room-Temperature Semiconductor X-ray and Gamma-ray Detectors, RTSD 2010, 2010)
The grating-based phase-contrast imaging approach is highly dependent on the quality of the used gratings. While the fabrication of gratings for the soft X-ray range is more or less well controllable, the fabrication for the hard X-ray range (>30 keV) is more challenging as the gratings must have high aspect ratios and thus fine structures. One of the best fabrication technologies for such gratings is LIGA (Lithography, Electroplating and Molding). However, due to such small structures and high aspect ratio it is unavoidable that the gratings become non-perfect and have deformations. Since the fabrication is complex, expensive and time consuming, a simple way is needed to assess the influence of such deformations on the signal and also a simple way to design and test new grating layouts. This work presents a simulation framework for X-ray phase-contrast imaging which allows to model, simulate and assess the quality of arbitrary grating layouts in an easier, cheaper and faster way. Furthermore, it allows the assessment of the quality of new grating layouts as well as of existing gratings. © 2010 IEEE.

Performance of the most recent MCP-PMTs - Böhm, Merlin; Krauss, S.; Lehmann, Albert; Miehling, Daniel; Pfaffinger, Markus; Stelter, Samuel; Uhlig, Fred; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; et al. (Journal of Instrumentation, 2020)
For the identification of charged and fast moving particles two DIRC (detection of internally reflected Cherenkov light) detectors are being built for the PANDA experiment. They will provide hadronic particle identification in the PANDA target spectrometer and require lifetime-enhanced MCP-PMTs as sensors. MCP-PMTs are the only viable option for this task because they work in high magnetic fields of > 1 Tesla, have low dark count rates and an excellent time resolution of < 120 ps RMS. The tubes being deployed in the experiment have to be tested to find out if they comply with these requirements. These tests are performed in a semi-automatic setup which allows to measure time resolution, dark count rate, afterpulse probability, crosstalk behaviour, quantum efficiency, and gain distribution. The measurements are done with a picosecond laser attached to a 3-axis stepper to scan the sensor surface. Measurements and results of close-to-final prototype tubes are presented here.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Cherenkov detectors; Photon detectors for UV; Photon detectors for UV; Visible and IR photons (vacuum); Visible and IR photons (vacuum) (photomultipliers HPDs others)

Performance of the most recent Microchannel-Plate PMTs for the PANDA DIRC detectors at FAIR - Krauss, Steffen; Böhm, Merlin; Gumbert, Katja; Lehmann, Albert; Miehling, Daniel; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2023)
In the PANDA experiment at the FAIR facility at GSI two DIRC (Detection of Internally Reflected Cherenkov light) detectors will be used for π/K separation up to 4 GeV/c. Due to their location in a high magnetic field and other stringent requirements like high detection efficiency, low dark count rate, radiation hardness, long lifetime and good timing, MCP-PMTs (microchannel-plate photomultiplier) were the best choice of photon sensors for the DIRC detectors in the PANDA experiment. This paper will present the performance of some of the latest 2 × 2 inch 2 MCP-PMTs from Photek and Photonis, including the first mass production tubes for the PANDA Barrel DIRC from Photonis. Performance parameters like the collection efficiency (CE), quantum efficiency (QE), and gain homogeneity were determined. The effect of magnetic fields on some properties like gain and charge cloud width was investigated as well. Apart from that the spatial distribution of many internal parameters like time resolution, dark count rate, afterpulse ratio, charge sharing crosstalk and recoil electrons were measured simultaneously with a multihit capable DAQ system. The latest generation of Photonis MCP-PMTs shows a unexpected ”escalation” effect where the MCP-PMT itself produces photons.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Atomic layer deposition (ALD); DIRC; MCP-PMT; Microchannel-plate; PANDA; Photomultiplier

Performance studies for a next-generation optical sensor for IceCube-Gen2 - Shimizu, Nobuhiro; Ishihara, Aya; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Alves, A. A.; Amin, N. M.; et al. (Proceedings of Science, 2022)
For the in-ice component of the next generation neutrino observatory at the South Pole, IceCubeGen2, a new sensor module is being developed, which is an evolution of the D-Egg and mDOM sensors developed for the IceCube Upgrade. The sensor design features up to 18 4-inch PMTs distributed homogeneously in a borosilicate glass pressure vessel. Challenges arise for the mechanical design from the tight constraints on the bore hole diameter (which will be 2 inches smaller than for IceCube Upgrade) and from the close packing of the PMTs. The electronics design must meet the space constraints posed by the mechanical design as well as the power consumption and cost considerations from over 10,000 optical modules being deployed. This contribution presents forward-looking solutions to these design considerations. Prototype modules will be installed and integrated in the IceCube Upgrade.
CRIS-Team Scopus Importer:2023-08-15

Personal Dosimetry in Continuous Photon Radiation Fields with the Dosepix Detector - Haag, Dennis; Schmidt, Sebastian; Hufschmidt, Patrick; Eberle, Franziska; Michel, Thilo; Anton, Gisela; Hupe, Oliver; Roth, Jurgen; Fuhg, Christian; Zutz, Hayo; Behrens, Rolf; Campbell, Michael; et al. (IEEE Transactions on Nuclear Science, 2021)
First measurements characterizing dosimetric properties of a dosimetry system designed for the purpose of active personal dosimetry for photons with mean energies from 12.4 keV to 1250 keV according to PTB requirements are presented. The system consists of three Dosepix detectors, which is a hybrid, pixelated, photon-counting X-ray detector. The energy and angular dependence of the normalized response and the coefficients of variation of the personal dose equivalents Hp(10) and Hp(0.07) are determined on an ISO water slab phantom in continuous reference photon radiation fields according to ISO 4037-1 and ISO 4037-3. The energy response is presented for the narrow spectra N-15 to N-300 and the radiation qualities S-Cs and S-Co for angles of incidence of 0 °, 30 ° and ±60 °. The highest deviation of the response from the reference response is found at N-60, -60 ° with 1.179±0.007 (standard deviation) for Hp(10). The energy range of use for Hp(10) is expected to extend from 12.4 keV to 1250 keV. For the personal dose equivalent Hp(0.07) the normalized response at ±60 ° is below the lower limit for N-15, N-20 and N-25. It results in an energy range of use from 24.6 keV to 1250 keV. The coefficient of variation increases with increasing photon energy and stays below 1% for all measurements.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Active personal dosimetry; Aluminum; Detectors; Dosimetry; dosimetry with ionizing radiation; hybrid pixel detector; ISO Standards; Phantoms; Photonics; Uncertainty

Phasenkontrast Röntgen mit 2 Phasengittern und medizinisch relevanten Detektoren - Bopp, Johannes; Gallersdörfer, Michael; Ludwig, Veronika; Seifert, Maria; Maier, Andreas; Anton, Gisela; Riess, Christian (Proceedings des Workshops Bildverarbeitung für die Medizin 2018 - Algorithmen - Systeme - Anwendungen, 2018)

Phase-Sensitive Region-of-Interest Computed Tomography - Felsner, Lina; Berger, Martin; Käppler, Sebastian; Bopp, Johannes; Ludwig, Veronika; Weber, Thomas; Pelzer, Georg; Michel, Thilo; Maier, Andreas; Anton, Gisela; Riess, Christian (21st International Conference on Medical Image Computing and Computer Assisted Intervention, 2018)

Phase-unwrapping of differential phase-contrast data using attenuation information - Haas, Wilhelm; Bech, Martin; Bartl, Peter; Bayer, Florian; Ritter, André; Weber, T.; Pelzer, Georg; Willner, M.; Achterhold, K.; Durst, Jürgen; Michel, Thilo; Prümmer, Marcus; et al. (Medical Imaging 2011: Image Processing, 2011)
Phase-contrast imaging approaches suffer from a severe problem which is known in Magnetic Resonance Imaging (MRI) and Synthetic Aperture Radar (SAR) as phase-wrapping. This work focuses on an unwrapping solution for the grating based phase-contrast interferometer with X-rays. The approach delivers three types of information about the x-rayed object - the absorption, differential phase-contrast and dark-field information whereas the observed differential phase values are physically limited to the interval (-π, π]; values higher or lower than the interval borders are mapped (wrapped) back into it. In contrast to existing phase-unwrapping algorithms for MRI and SAR the presented algorithm uses the absorption image as additional information to identify and correct phase-wrapped values. The idea of the unwrapping algorithm is based on the observation that at locations with phase-wrapped values the contrast in the absorption image is high and the behavior of the gradient is similar to the real (unwrapped) phase values. This can be expressed as a cost function which has to be minimized by an integer optimizer. Applied on simulated and real datasets showed that 95.6% of phase-wraps were correctly unwrapped. Based on the results we conclude that it is possible to use the absorption information in order to identify and correct phase-wrapped values. © 2011 Copyright Society of Photo-Optical Instrumentation Engineers (SPIE).

Photoproduction of η -mesons off protons - Bartholomy, O.; Bogendörfer, Regina; Crede, V.; Fabry, I.; Anisovich, A. V.; Anton, Gisela; Bantes, R.; Beloglazov, Yu.; Castelijns, R.; Ehmanns, A.; Ernst, J.; Flemming, H.; et al. (European Physical Journal A, 2007)

Photoproduction of η Mesons off Protons for 0.75 GeV < Eγ < 3 GeV - Crede, V.; Bartholomy, O.; Anisovich, A. V.; Anton, Gisela; Bantes, R.; Beloglazov, Yu.; Bogendörfer, Regina; Castelijns, R.; Ehmanns, A.; Ernst, J.; Fabry, I.; Flemming, H.; et al. (Physical Review Letters, 2005)

Photoproduction of π0ω off protons for Eγ≤3 GeV - Flemming, H.; Messchendorp, J. G.; Menze, D.; Matthäy, H.; Funke, Chr.; Thoma, U.; Suft, Gabriele; Radkov, A.; Fösel, Angela; Schoch, B.; Schmidt, C.; Walther, D.; et al. (European Physical Journal A, 2007)
Differential and total cross-sections for photoproduction of γp→pπ0ω and γp→Δ+ω were determined from measurements of the CB-ELSA experiment, performed at the electron accelerator ELSA in Bonn. The measurements covered the photon energy range from the production threshold up to 3GeV.

Photoproduction of πº Mesons off Protons from the Δ(1232) Region to Eγ = 3 GeV - van Pee, H.; Crede, V.; Anisovich, A. V.; Anton, Gisela; Bantes, R.; Beloglazov, Yu.; Bogendörfer, Regina; Castelijns, R.; Ehmanns, A.; Ernst, J.; Fabry, I.; Flemming, H.; et al. (European Physical Journal A, 2007)
Photoproduction of π0-mesons was studied with the Crystal-Barrel detector at ELSA for incident energies from 300MeV to 3GeV. Differential cross-sections dσ/dΩ, dσ/dt, and the total cross-section are presented. For Eγ < 3GeV, the angular distributions agree well with the SAID parametrization. At photon energies above 1.5GeV, a strong forward peaking indicates t-channel exchange to be the dominant process. The rapid variations of the cross-section with energy and angle indicate production of resonances. An interpretation of the data within the Bonn-Gatchina partial-wave analysis is briefly discussed.

PKS2005-489 at VHE: Four years of monitoring with HESS and simultaneous multi-wavelength observations - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Bochow, A.; Boisson, C.; et al. (Astronomy & Astrophysics, 2010)
Aims: Our aim is to study the very high energy (VHE; E > 100 GeV) Γ-ray emission from BL Lac objects and the evolution in time of their broad-band spectral energy distribution (SED). Methods: VHE observations of the high-frequency peaked BL Lac object PKS 2005-489 were made with the High Energy Stereoscopic System (HESS) from 2004 through 2007. Three simultaneous multi-wavelength campaigns at lower energies were performed during the HESS data taking, consisting of several individual pointings with the XMM-Newton and RXTE satellites. Results: A strong VHE signal, ∼17ρ total, from PKS 2005-489 was detected during the four years of HESS observations (90.3 h live time). The integral flux above the average analysis threshold of 400 GeV is ∼3% of the flux observed from the Crab Nebula and varies weakly on time scales from days to years. The average VHE spectrum measured from ∼300 GeV to ∼5 TeV is characterized by a power law with a photon index, Γ = 3.20 ± 0.16 ± 0.10 At X-ray energies the flux is observed to vary by more than an order of magnitude between 2004 and 2005. Strong changes in the X-ray spectrum (ΔΓ ≈ 0.7) are also observed, which appear to be mirrored in the VHE band. Conclusions: The SED of PKS 2005-4 constructed for the first time with contemporaneous data on both humps, shows significant evolution. The large flux variations in the X-ray band, coupled with weak or no variations in the VHE band and a similar spectral behavior, suggest the emergence of a new, separate, harder emission component in September 2005. © 2010 ESO.
Keywords: BL Lacertae objects: individual: PKS 2005-489; Galaxies: active; Gamma rays: galaxies; X-rays: individuals: PKS 2005-489

Polarization analysis of <(p)over bar> produced in pA collisions - Grzonka, D.; Alfs, D.; Asaturyan, A.; Carmignotto, M.; Diermaier, M.; Eyrich, Wolfgang; Gowacz, B.; Hauenstein, F.; Horn, T.; Kilian, K.; Lersch, D.; Malbrunot-Ettenauer, S.; et al. (MESON 2018 – 15th International Workshop on Meson Physics, 2019)
CRIS-Team WoS Importer:2019-06-28

Polychromatic Maximum Likelihood Reconstruction for Talbot-Lau X-ray Tomography - Schiffers, Florian; Käppler, Sebastian; Pelzer, Georg; Wolf, Andreas; Maier, Andreas; Anton, Gisela; Riess, Christian (International Conference on Fully Three-Dimensional Image Reconstruction in Radiology and Nuclear Medicine (Fully3D), 2017)

Potential of neutrino telescopes to detect quantum gravity-induced decoherence in the presence of dark fermions - Domi, Alba; Eberl, Thomas; Hellmann, Dominik; Krieg, Sara; Päs, Heinrich (Journal of Cosmology and Astroparticle Physics, 2025)
We assess the potential of neutrino telescopes to discover quantum-gravity-induced decoherence effects modeled in the open-quantum system framework and with arbitrary numbers of active and dark fermion generations, such as particle dark matter or sterile neutrinos. The expected damping of neutrino flavor oscillation probabilities as a function of energy and propagation length thus encodes information about quantum gravity effects and the fermion generation multiplicity in the dark sector. We employ a public Monte-Carlo dataset provided by the IceCube Collaboration to model the detector response and estimate the sensitivity of IceCube to oscillation effects in atmospheric neutrinos induced by the presented model. Our findings confirm the potential of very-large-volume neutrino telescopes to test this class of models and indicate higher sensitivities for increasing numbers of dark fermions.
CRIS-Team Scopus Importer:2025-04-25
Keywords: neutrino experiments; neutrinos; quantum black holes; solar and atmospheric neutrinos; ultra high energy photons

Precision resonance energy scans with the PANDA experiment at FAIR: Sensitivity study for width and line shape measurements of the X(3872) - Barucca, G.; Davi, F.; Lancioni, G.; Mengucci, P.; Montalto, L.; Natali, P. P.; Paone, N.; Rinaldi, D.; Scalise, L.; Erni, W.; Krusche, B.; Steinacher, M.; et al. (European Physical Journal A, 2019)
.This paper summarises a comprehensive Monte Carlo simulation study for precision resonance energy scan measurements. Apart from the proof of principle for natural width and line shape measurements of very narrow resonances with PANDA, the achievable sensitivities are quantified for the concrete example of the charmonium-like X(3872) state discussed to be exotic, and for a larger parameter space of various assumed signal cross-sections, input widths and luminosity combinations. PANDA is the only experiment that will be able to perform precision resonance energy scans of such narrow states with quantum numbers of spin and parities that differ from JPC=1–.
CRIS-Team WoS Importer:2019-04-12

Probing the ATIC peak in the cosmic-ray electron spectrum with H.E.S.S. - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, Julien; Borrel, V.; et al. (Astronomy & Astrophysics, 2009)
The measurement of an excess in the cosmic-ray electron spectrum between 300 and 800 GeV by the ATIC experiment has - together with the PAMELA detection of a rise in the positron fraction up to ≈100 GeV - motivated many interpretations in terms of dark matter scenarios; alternative explanations assume a nearby electron source like a pulsar or supernova remnant. Here we present a measurement of the cosmic-ray electron spectrum with H.E.S.S. starting at 340 GeV. While the overall electron flux measured by H.E.S.S. is consistent with the ATIC data within statistical and systematic errors, the H.E.S.S. data exclude a pronounced peak in the electron spectrum as suggested for interpretation by ATIC. The H.E.S.S. data follow a power-law spectrum with spectral index of 3.0 ±0.1(stat.) ±0.3(syst.), which steepens at about 1 TeV. © ESO 2009.
Keywords: Cosmic rays; Methods: data analysis

Probing the Connection between IceCube Neutrinos and MOJAVE AGN - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Astrophysical Journal, 2024)
Active galactic nuclei (AGN) are prime candidate sources of the high-energy, astrophysical neutrinos detected by IceCube. This is demonstrated by the real-time multimessenger detection of the blazar TXS 0506+056 and the recent evidence of neutrino emission from NGC 1068 from a separate time-averaged study. However, the production mechanism of the astrophysical neutrinos in AGN is not well established, which can be resolved via correlation studies with photon observations. For neutrinos produced due to photohadronic interactions in AGN, in addition to a correlation of neutrinos with high-energy photons, there would also be a correlation of neutrinos with photons emitted at radio wavelengths. In this work, we perform an in-depth stacking study of the correlation between 15 GHz radio observations of AGN reported in the MOJAVE XV catalog, and 10 yr of neutrino data from IceCube. We also use a time-dependent approach, which improves the statistical power of the stacking analysis. No significant correlation was found for both analyses, and upper limits are reported. When compared to the IceCube diffuse flux, at 100 TeV and for a spectral index of 2.5, the upper limits derived are ∼3% and ∼9% for the time-averaged and time-dependent cases, respectively.
CRIS-Team Scopus Importer:2024-10-11

Probing the gamma-ray emission from HESS J1834-087 using H.E.S.S. and Fermi LAT observations - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2015)
Aims. Previous observations with the High Energy Stereoscopic System (H.E.S.S.) have revealed an extended very-high-energy (VHE; E > 100 GeV) γ-ray source, HESS J1834-087, coincident with the supernova remnant (SNR)W41. The origin of the γ-ray emission was investigated in more detail with the H.E.S.S. array and the Large Area Telescope (LAT) onboard the Fermi Gamma-ray Space Telescope. Methods. The γ-ray data provided by 61 h of observations with H.E.S.S., and four years with the Fermi LAT were analyzed, covering over five decades in energy from 1.8 GeV up to 30 TeV. The morphology and spectrum of the TeV and GeV sources were studied and multiwavelength data were used to investigate the origin of the γ-ray emission toward W41. Results. The TeV source can be modeled with a sum of two components: one point-like and one significantly extended (σ = 0.17° ± 0. 01°), both centered on SNR W41 and exhibiting spectra described by a power law with index Γ ≃ 2.6. The GeV source detected with Fermi LAT is extended (σ = 0.15° ± 0.03°) and morphologically matches the VHE emission. Its spectrum can be described by a power-law model with an index Γ = 2.15 ± 0.12 and smoothly joins the spectrum of the whole TeV source. A break appears in the γ-ray spectra around 100 GeV. No pulsations were found in the GeV range. Conclusions. Two main scenarios are proposed to explain the observed emission: a pulsar wind nebula (PWN) or the interaction of SNRW41 with an associated molecular cloud. X-ray observations suggest the presence of a point-like source (a pulsar candidate) near the center of the remnant and nonthermal X-ray di ffuse emission that could arise from the possibly associated PWN. The PWN scenario is supported by the compatible positions of the TeV and GeV sources with the putative pulsar. However, the spectral energy distribution from radio to γ-rays is reproduced by a one-zone leptonic model only if an excess of low-energy electrons is injected following a Maxwellian distribution by a pulsar with a high spin-down power (>10 ergs). This additional low-energy component is not needed if we consider that the point-like TeV source is unrelated to the extended GeV and TeV sources. The interacting SNR scenario is supported by the spatial coincidence between the γ-ray sources, the detection of OH (1720 MHz) maser lines, and the hadronic modeling.
Keywords: Acceleration of particles; Cosmic rays; Ism: Clouds; Ism: Supernova remnants

Prospects for the detection of transient neutrino sources with PLEnuM - Schumacher, Lisa; Oikonomou, Foteini (Proceedings of Science, 2024)
The discovery of high-energy astrophysical neutrinos in the TeV-PeV range by IceCube marked the start of neutrino astronomy, and the search for their sources continues. Two promising source candidates have been identified by IceCube: NGC 1068 in the 1 TeV-10 TeV range and TXS 0506+056 in the 0.1-1 PeV range. Both sources have gamma-ray counterparts, but additional time information of both neutrinos and gamma rays were essential for the identification of TXS 0506+056. The Planetary Neutrino Monitoring (PLEnuM) concept is an approach for combining the exposures of all current and future neutrino observatories - such as KM3NeT, Baikal-GVD, P-ONE in the Northern Hemisphere, and IceCube-Gen2 in the Southern Hemisphere. Using this PLEnuM approach, we estimate how the detection capability for transient sources candidates like blazars and GRBs improves once the future neutrino observatories come online. In addition, we present how the combined, instantaneous field of view of PLEnuM improves the real-time detection rate of rare, very-high-energy neutrinos across the entire sky.
CRIS-Team Scopus Importer:2025-02-04

Quantitative analysis of a wind energy conversion model - Zucker, Florian; Strunz, Andreas; Gräbner, Anna; Meyn, Jan-Peter (European Journal of Physics, 2015)
A rotor of 12 cm diameter is attached to a precision electric motor, used as a generator, to make a model wind turbine. Output power of the generator is measured in a wind tunnel with up to 15 m s-1 air velocity. The maximum power is 3.4 W, the power conversion factor from kinetic to electric energy is cp = 0.15. The v3 power law is confirmed. The model illustrates several technically important features of industrial wind turbines quantitatively.
UnivIS-Import:2015-04-14:Pub.2015.nat.dphy.PI.PDP.quanti
Keywords: Betz factor; demonstration experiment; model; renewable energy; wind energy; wind turbine

Radiation measurements and simulations at the PHELIX laser facility, GSI - Behrens, R.; Hufschmidt, Patrick; Roth, J.; Akstaller, Bernhard; Hupe, O.; Haag, D.; Schmidt, Sebastian; Schreiner, Stephan; Michel, Thilo (Journal of Instrumentation, 2022)
The absolute spectral electron and photon emission from a Tungsten target irradiated by the Petawatt High-Energy Laser for Heavy Ion EXperiments (PHELIX) facility was measured inside the PHELIX target chamber. For this, a thermo-lumi-nescence detector (TLD)-based few-channel spectrometer (FCS) was used in combination with a Bayesian data analysis. The results of the FCS measurement served as input for a Monte-Carlo particle transport simulation to determine the spectra and dose out of the PHELIX target chamber. Two different simulation methods proved to be consistent and, therefore, reliable. The simulation results were compared to the dose measured with a dosemeter that consists of three Dosepix detectors in combination with a neural network analysis. The two dose results show a satisfactory agreement.
CRIS-Team WoS Importer:2022-06-10

Radiofrequency ice dielectric measurements at Summit Station, Greenland - Aguilar, Juan Antonio; Allison, Patrick; Besson, Dave; Bishop, Abby; Botner, Olga; Bouma, Sjoerd; Buitink, Stijn; Cataldo, Maddalena; Clark, Brian A.; Couberly, Kenny; Curtis-Ginsberg, Zach; Dasgupta, Paramita; et al. (Journal of Glaciology, 2023)
We recently reported on the radio-frequency attenuation length of cold polar ice at Summit Station, Greenland, based on bi-static radar measurements of radio-frequency bedrock echo strengths taken during the summer of 2021. Those data also allow studies of (a) the relative contributions of coherent (such as discrete internal conducting layers with sub-centimeter transverse scale) vs incoherent (e.g. bulk volumetric) scattering, (b) the magnitude of internal layer reflection coefficients, (c) limits on signal propagation velocity asymmetries ('birefringence') and (d) limits on signal dispersion in-ice over a bandwidth of ∼100 MHz. We find that (1) attenuation lengths approach 1 km in our band, (2) after averaging 10 000 echo triggers, reflected signals observable over the thermal floor (to depths of ∼1500 m) are consistent with being entirely coherent, (3) internal layer reflectivities are ≈-60-70 dB, (4) birefringent effects for vertically propagating signals are smaller by an order of magnitude relative to South Pole and (5) within our experimental limits, glacial ice is non-dispersive over the frequency band relevant for neutrino detection experiments.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Arctic glaciology; ice physics; radio-echo sounding

Radio imaging of the very-high-energy γ-ray emission region in the central engine of a radio galaxy - van Eldik, Christopher; Acciari, V. A.; Aliu, E.; Arlen, T.; Bautista, M.; Beilicke, M.; Benbow, W.; Bradbury, S. M.; Buckley, J. H.; Bugaev, V.; Butt, Y.; Byrum, K.; et al. (Science, 2009)
The accretion of matter onto a massive black hole is believed to feed the relativistic plasma jets found in many active galactic nuclei (AGN). Although some AGN accelerate particles to energies exceeding 10 electron volts and are bright sources of very-high-energy (VHE) y-ray emission, it is not yet known where the VHE emission originates. Here we report on radio and VHE observations of the radio galaxy Messier 87, revealing a period of extremely strong VHE y-ray flares accompanied by a strong increase of the radio flux from its nucleus. These results imply that charged particles are accelerated to very high energies in the immediate vicinity of the black hole.

Realization of a computed tomography setup to achieve resolutions below 1μm - Salamon, M.; Hanke, R.; Krueger, P.; Uhlmann, Norman; Voland, V. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2008)
The amelioration of present X-ray imaging systems especially in computed tomography to resolutions below 1 extgreekmm necessitates very precise equipment details such as the manipulators, focus size and stability of the tube and the detector adjustment. In this paper, we present an experimental setup of a computed tomography system with sub-micrometer resolution. The requirements on and characteristics of the components and their influence on the measurements are discussed and exemplary results of different test objects in the field of non-destructive testing with sub-micrometer resolution are presented.
EAM Import::2019-03-13

Realtime Follow-up of Astrophysical Transients with the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Proceedings of Science, 2022)
Realtime analyses are necessary to identify the source of high energy neutrinos. As an observatory with a 4π steradian field of view and near-100% duty cycle, the IceCube Neutrino Observatory is a unique facility for investigating transients. In 2016, IceCube established a pipeline that uses low-latency data to rapidly respond to astrophysical events that were of interest to the multi-messenger observational community. Here, we describe this pipeline and summarize the results from all of the analyses performed since 2016. We focus not only on those analyses which were performed in response to transients identified using other messengers such as photons and gravitational waves, but also on how this pipeline can be used to constrain populations of astrophysical neutrino transients by following up high-energy neutrino alerts.
CRIS-Team Scopus Importer:2024-12-16

Recent Progress in Solar Atmospheric Neutrino Searches with IceCube - Villarreal, Josh; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
Cosmic-rays interacting with nucleons in the solar atmosphere produce a cascade of particles that give rise to a flux of high-energy neutrinos and gamma-rays. Fermi has observed this gamma-ray flux; however, the associated neutrino flux has escaped observation. In this contribution, we put forward two strategies to detect these neutrinos, which, if seen, would push forward our understanding of the solar atmosphere and provide a new testing ground of neutrino properties. First, we will extend the previous analysis, which used high-energy through-going muon events collected in the years of maximum solar activity and yielded only flux upper limits, to include data taken during the solar minimum from 2018 to 2020. Extending the analysis to the solar minimum is important as the gamma-ray data collected during past solar cycles indicates a possible enhancement in the high-energy neutrino flux. Second, we will incorporate sub-TeV events and include contributions from all neutrino flavors. These will improve our analysis sensitivity since the solar atmospheric spectrum is soft and, due to oscillation, contains significant contributions of all neutrino flavors. As we will present in this contribution, these complementary strategies yield a significant improvement in sensitivity, making substantial progress towards observing this flux.
CRIS-Team Scopus Importer:2024-12-16

Recent progress with microchannel-plate PMTs - Lehmann, Albert; Böhm, Merlin; Miehling, Daniel; Pfaffinger, Markus; Stelter, Samuel; Uhlig, Fred; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
Microchannel-plate (MCP) PMTs were identified as the only suitable photon sensors for the two DIRC detectors of the P̄ANDA experiment at FAIR. As the long-standing aging problem of MCP-PMTs was recently overcome by coating the MCP pores with an atomic layer deposition (ALD) technique, further improved 2″ MCP-PMTs were investigated. The best PHOTONIS device has reached a lifetime of >20 C/cm2 integrated anode charge without any sign of aging. Also the newly developed 2″ MCP-PMTs of Hamamatsu are maturing and are usable in high rate environments. The status of our long-term lifetime measurements and the performance parameters of the currently most advanced ALD-coated MCP-PMTs from PHOTONIS and Hamamatsu are presented. In addition, first results obtained with a new quality assurance setup for MCP-PMTs are discussed. This setup consists of a high performance DAQ system to measure the response of ≥64 anode pixels simultaneously. The system allows to study and quantify background parameters like position dependent dark count rates and ion afterpulsing as well as temporal and spacial distributions of recoil electrons and the effects of electronic and charge-sharing crosstalk among the anode pixels.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Atomic layer deposition (ALD); Cherenkov detectors; Lifetime; Microchannel-plate photomultipliers

Reconstruction of scalar and vectorial components in X-ray dark-field tomography - Bayer, Florian; Hu, Shiyang; Maier, Andreas; Weber, Thomas; Anton, Gisela; Michel, Thilo; Riess, Christian (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Grating-based X-ray dark-field imaging is a novel technique for obtaining image contrast for object structures at size scales below setup resolution. Such an approach appears particularly beneficial for medical imaging and nondestructive testing. It has already been shown that the dark-field signal depends on the direction of observation. However, up to now, algorithms for fully recovering the orientation dependence in a tomographic volume are still unexplored. In this publication, we propose a reconstruction method for grating-based X-ray dark-field tomography, which models the orientation- dependent signal as an additional observable from a standard tomographic scan. In detail, we extend the tomographic volume to a tensorial set of voxel data, containing the local orientation and contributions to dark-field scattering. In our experiments, we present the first results of several test specimens exhibiting a heterogeneous composition in microstructure, which demonstrates the diagnostic potential of the metho
UnivIS-Import:2015-04-14:Pub.2014.nat.dphy.PI.LEPDF.recons
Keywords: Anisotropic scattering; Grating interferometer; Microstructure orientation; X-ray phase contrast

Reduction of guided acoustic wave brillouin scattering in photonic crystal fibers - Elser, Dominique Alexander; Andersen, Ulrik Lund; Korn, Alexander; Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2006)
Guided acoustic wave Brillouin scattering (GAWBS) generates phase and polarization noise of light propagating in glass fibers. This excess noise affects the performance of various experiments operating at the quantum noise limit. We experimentally demonstrate the reduction of GAWBS noise in a photonic crystal fiber in a broad frequency range by tailoring the acoustic modes using the photonic also as a phononic crystal. We compare the noise spectrum to the one of a standard fiber and observe a tenfold noise reduction in the frequency range up to 200 MHz. Based on our measurement results as well as on numerical simulations, we establish a model for the reduction of GAWBS noise in photonic crystal fibers. © 2006 The American Physical Society.
Created from Fastlane, Scopus look-up

Reflectance of Silicon Photomultipliers at Vacuum Ultraviolet Wavelengths - Lv, P.; Cao, G. F.; Wen, L. J.; Kharusi, S. Al; Anton, Gisela; Arnquist, I. J.; Badhrees, I.; Barbeau, P. S.; Beck, D.; Belov, V.; Bhatta, T.; Breur, P. A.; et al. (IEEE Transactions on Nuclear Science, 2020)
Characterization of the vacuum ultraviolet (VUV) reflectance of silicon photomultipliers (SiPMs) is important for large-scale SiPM-based photodetector systems. We report the angular dependence of the specular reflectance in vacuum of SiPMs manufactured by Fondazionc Bruno Kessler (FBK) and Hamamatsu Photonics K.K. (HPK) over wavelengths ranging from 120 to 280 nm. Refractive index and extinction coefficient of the thin silicon-dioxide film deposited on the surface of the FBK SiPMs are derived from reflectance data of an FBK silicon wafer with the same deposited oxide film as SiPMs. The diffuse reflectance of SiPMs is also measured at 193 nm. We use the VUV spectral dependence of the optical constants to predict the reflectance of the FBK silicon wafer and FBK SiPMs in liquid xenon.
CRIS-Team WoS Importer:2021-01-01

Reflectance of VUV-sensitive SiPM surfaces in liquid xenon - Wagenpfeil, Michael; Ziegler, Tobias; Fieguth, Alexander; Schneider, Judith; Michel, Thilo; Weinheimer, Christian (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
The nEXO experiment will operate an ultra-low background time projection chamber filled with 5t of isotopically enriched liquid xenon (LXe) for the search for the neutrinoless double beta decay in Xe-136. The detector will use 4m2 of silicon photomultipliers (SiPMs) operated at about −104∘C to collect the scintillation light. There are strong requirements on the background levels, light collection efficiency and SiPM performance to set the most stringent limits on the half-life. Detecting the 0νββ-decay would have wide-spread implications for neutrino physics. The SiPMs need to be sensitive to the vacuum-ultraviolet scintillation light of LXe at 178nm which is not given for off-the-shelf SiPMs. The SiPM performance requirements adopted by nEXO are (among others) a photon detection efficiency of at least 15% at 178nm, a correlated avalanche probability of less than 20% and a low dark-rate. Additionally, the VUV-reflectance of the SiPM surface in LXe is an important parameter for optimal light collection and thus the energy resolution of nEXO. We present measurements with state-of-the-art VUV-sensitive SiPMs focusing on the surface VUV-reflectance in liquid xenon.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Liquid xenon; Reflectance; Silicon photomultipliers; VUV-sensitive

Reflectivity and PDE of VUV4 Hamamatsu SiPMs in liquid xenon - Nakarmi, P.; Ostrovskiy, I.; Soma, A. K.; Retière, F.; Kharusi, S. Al; Alfaris, M.; Anton, Gisela; Arnquist, I. J.; Badhrees, I.; Barbeau, P. S.; Beck, D.; Belov, V.; et al. (Journal of Instrumentation, 2020)
Understanding reflective properties of materials and photodetection efficiency (PDE) of photodetectors is important for optimizing energy resolution and sensitivity of the next generation neutrinoless double beta decay, direct detection dark matter, and neutrino oscillation experiments that will use noble liquid gases, such as nEXO, DARWIN, DarkSide-20k, and DUNE . Little information is currently available about reflectivity and PDE in liquid noble gases, because such measurements are difficult to conduct in a cryogenic environment and at short enough wavelengths. Here we report a measurement of specular reflectivity and relative PDE of Hamamatsu VUV4 silicon photomultipliers (SiPMs) with 50 μm micro-cells conducted with xenon scintillation light (∼175 nm) in liquid xenon. The specular reflectivity at 15ˆ incidence of three samples of VUV4 SiPMs is found to be 30.4±1.4%, 28.6±1.3%, and 28.0±1.3%, respectively. The PDE at normal incidence differs by ±8% (standard deviation) among the three devices. The angular dependence of the reflectivity and PDE was also measured for one of the SiPMs. Both the reflectivity and PDE decrease as the angle of incidence increases. This is the first measurement of an angular dependence of PDE and reflectivity of a SiPM in liquid xenon.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Dark Matter detectors (WIMPs; axions; etc.); Double-beta decay detectors; Noble liquid detectors (scintillation; ionization; double-phase); Photon detectors for UV; visible and IR photons (solid-state) (PIN diodes; APDs; Si-PMTs; G-APDs; CCDs; EBCCDs; EMCCDs; CMOS imagers; etc)

Refraction in a Talbot-Lau setup allows High Energy, Visibility, and Sensitivity - Preusche, Oliver; Weber, Thomas; Anton, Gisela (International Symposium on BioMedical Applications of X-Ray Phase Contrast Imaging (IMXP 2014), 2015)
Photon energies above 50 keV are rarely used in Talbot-Lau interferometers, because the analyzer grating G2 becomes quite transparent at higher photon energies [1-4]. For medical imaging, this transparency causes an inacceptable increase in radiation dose. To allow higher energies, several proposals exist to allow higher gold gratings: Edge-on illumination [2] strongly reduces the field-of-view, glancing angle geometry [3] may increase setup length, and phase gratings consisting of alternating prisms [4] reduce angular sensitivity. In this work, we present a further new proposal to solve the aspect ratio problem. Method: The basic idea is to use a refracting lens to combine N>1 fringes into a single fringe (see Fig. 1). An array of such lenses (called 'lens grating') replaces the analyzer grating G2. A new G2 (the period now is N times larger) is put into the focal plane of the lens-array. To this end, several problems have to be solved. Problem 1 – Refraction strongly depends on photon energy. Since G2 is now coarse, the refraction angle is allowed to change by a factor of 3. Problem 2 – Production of strong prisms for a fresnel-style lens. [4] inclines the light source during lithography by rotation around a grating bar (around the y-axis), this delivers strong alternating prisms. We incline by rotating within a grating bar (around the x-axis) and use a y-periodic contract in the grating layout to produce differently strong prisms – this allows to encode a complete fresnel lens in a simple binary layout. Problem 3 – The lenses must analyze the fringe phase. To do so, two arrays of fresnel lenses are interleaved into each other. The even lenses (black) focus on G2 grating bars, the odd lenses (magenta) focus on G2 grating slits. Problem 4 – This does not work with a regular source grating G0. An additional coherence constraint defines a set of planes in which G2 can be placed. Also required is a grouping: In each group of Q slits, only q < Q/2 slits may stay open – we need hierarchical coherence in the form of a darker G0 (see orange lines in Fig. 1). The resulting setup allows analyzer grating periods as large as in the source grating G0. A lens grating may consist of very narrow strips, allowing higher angular sensitivities (refraction is proportional to aspect ratio). Results: We present simulation results of a setup of 180 mm post-patient length for a design energy of 59 keV. The setup uses a modified binary phase grating G1 to operate in second talbot order. This increases sensitivity. The lens grating has a strip width of 0.9 µm ('period' 1.8 µm) and a gold height of 54 µm (aspect ratio 73). It combines 5 fringes to one, resulting in a period of 9.3 µm for G2. The simulation (see Fig. 2) is based on Fresnel-Kirchhoff diffraction. It shows that the lens grating keeps 92% of the visibility created by the first two gratings. Conclusion: The proposal solves the height-problem in the analyzer grating G2. However, G0 will become the critical component of the setup, because of the additional coherence requirements. One option to solve this might be the combination with the glacing angle [3] approach. References: [1] T. Donath, F. Pfeiffer, O. Bunk, W. Groot, M. Bednarzik, C. Grünzweig, E. Hempel, S. Popescu, M. Hoheisel and C. David, "Phase-contrast imaging and tomography at 60 keV using a conventional x-ray tube source", Review of Scientific Instruments 80, 053701 (2009), DOI 10.1063/1.3127712 [2] T. Thüring, M. Abis, Z. Wang, C. David, and M. Stampanoni, "X-ray phase-contrast imaging at 100 keV on a conventional source", Scientific Reports 4 : 5198 (2014), DOI: 10.1038/srep05198 [3] A. Sarapata, J. W. Stayman, M. Finkenthal, J. H. Siewerdsen, F. Pfeiffer, and D. Stutman, "High energy x-ray phase contrast CT using glancing-angle grating interferometers", Med Phys. Feb 2014; 41(2): 021904, Doi: 10.1118/1.4860275 [4] A. Yaroshenko, M. Bech, G. Potdevin, A. Malecki, T. Biernath, J. Wolf, A. Tapfer, M. Schüttler, J. Meiser, D. Kunka, M. Amberger, J. Mohr, and F. Pfeiffer, "Non-binary phase gratings for x-ray imaging with a compact Talbot interferometer," Opt. Express 22, 547-556 (2014), Doi: 10.1364/OE.22.000547</
Keywords: X-ray interferometry; gratings; talbot-lau interferometer; x-ray lenses

Report of improved performance in Talbot-Lau phase-contrast computed tomography - Weber, Thomas; Pelzer, Georg; Rieger, Jens; Ritter, André; Anton, Gisela (Medical Physics, 2015)
Conclusions: The authors' results indicate that the assumptions made in former performance analyses are pessimistic. The break-even point, when phase-contrast CT outperforms attenuation CT, is within reach even with realistic, nonperfect gratings. Further improvements to state-of-the-art clinical CT scanners, like increasing the spatial resolution, could change the balance in favor of phase-contrast computed tomography even more. This could be done by, e.g., quantum-counting pixel detectors with four-fold smaller pixel pitches. (C) 2015 American Association of Physicists in Medicine.
Keywords: x-ray imaging; phase-contrast; computed tomography; performance analysis

Resolving the Crab pulsar wind nebula at teraelectronvolt energies - Abdalla, H.; Aharonian, F.; Ait Benkhali, F.; Angüner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Backes, M.; Barnard, M.; Becherini, Y.; Becker Tjus, J.; Berge, D.; et al. (Nature Astronomy, 2019)
The Crab nebula is one of the most-studied cosmic particle accelerators, shining brightly across the entire electromagnetic spectrum up to very-high-energy gamma rays1,2. It is known from observations in the radio to gamma-ray part of the spectrum that the nebula is powered by a pulsar, which converts most of its rotational energy losses into a highly relativistic outflow. This outflow powers a pulsar wind nebula, a region of up to ten light-years across, filled with relativistic electrons and positrons. These particles emit synchrotron photons in the ambient magnetic field and produce very-high-energy gamma rays by Compton up-scattering of ambient low-energy photons. Although the synchrotron morphology of the nebula is well established, it has not been known from which region the very-high-energy gamma rays are emitted3–8. Here we report that the Crab nebula has an angular extension at gamma-ray energies of 52 arcseconds (assuming a Gaussian source width), much larger than at X-ray energies. This result closes a gap in the multi-wavelength coverage of the nebula, revealing the emission region of the highest-energy gamma rays. These gamma rays enable us to probe a previously inaccessible electron and positron energy range. We find that simulations of the electromagnetic emission reproduce our measurement, providing a non-trivial test of our understanding of particle acceleration in the Crab nebula.
CRIS-Team Scopus Importer:2019-11-15

Results from the search for dark matter in the Milky Way with 9 years of data of the ANTARES neutrino telescope - Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physics Letters B, 2017)
Using data recorded with the ANTARES telescope from 2007 to 2015, a new search for dark matter annihilation in the Milky Way has been performed. Three halo models and five annihilation channels, WIMP + WIMP -> b (b) over bar, W+W-, tau(+)tau(-), mu(+)mu(-) and v (v) over bar, with WIMP masses ranging from 50 2 GeV/C-2 to 100 Tev/C-2, were considered. No excess over the expected background was found, and limits on the thermally averaged annihilation cross-section were set. (C) 2017 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY license.
Keywords: Dark matter; WIMP; Indirect detection; Neutrino telescope; Galactic Centre; ANTARES

Revisiting the Westerlund 2 field with the HESS telescope array - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; Behera, B.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2011)
Aims. Previous observations with the HESS telescope array revealed the existence of extended very-high-energy (VHE; E > 100 GeV) γ-ray emission, HESS J1023-575, coincident with the young stellar cluster Westerlund 2. At the time of discovery, the origin of the observed emission was not unambiguously identified, and follow-up observations have been performed to further investigate the nature of this γ-ray source. Methods. The Carina region towards the open cluster Westerlund 2 has been re-observed, increasing the total exposure to 45.9 h. The combined dataset includes 33 h of new data and now permits a search for energy-dependent morphology and detailed spectroscopy. Results. A new, hard spectrum VHE γ-ray source, HESS J1026-582, was discovered with a statistical significance of 7σ. It is positionally coincident with the Fermi LAT pulsar PSR J1028-5819. The positional coincidence and radio/γ-ray characteristics of the LAT pulsar favors a scenario where the TeV emission originates from a pulsar wind nebula. The nature of HESS J1023-575 is discussed in light of the deep HESS observations and recent multi-wavelength discoveries, including the Fermi LAT pulsar PSR J1022-5746 and giant molecular clouds in the region. Despite the improved VHE dataset, a clear identification of the object responsible for the VHE emission from HESS J1023-575 is not yet possible, and contribution from the nearby high-energy pulsar and/or the open cluster remains a possibility. © 2010 ESO.
Keywords: gamma rays: stars; HII regions

Robust graphene membranes in a silicon carbide frame - Waldmann, Daniel; Butz, Benjamin; Bauer, Sebastian; Englert, Jan; Jobst, Johannes; Ullmann, Konrad; Fromm, Felix; Ammon, Maximilian Michael; Enzelberger-Heim, Michael; Hirsch, Andreas; Maier, Sabine; Schmuki, Patrik; et al. (ACS nano, 2013)
We present a fabrication process for freely suspended membranes consisting of bi- and trilayer graphene grown on silicon carbide. The procedure, involving photoelectrochemical etching, enables the simultaneous fabrication of hundreds of arbitrarily shaped membranes with an area up to 500 μm(2) and a yield of around 90%. Micro-Raman and atomic force microscopy measurements confirm that the graphene layer withstands the electrochemical etching and show that the membranes are virtually unstrained. The process delivers membranes with a cleanliness suited for high-resolution transmission electron microscopy (HRTEM) at atomic scale. The membrane, and its frame, is very robust with respect to thermal cycling above 1000 °C as well as harsh acidic or alkaline treatment.

Searches for clustering in the time integrated skymap of the ANTARES neutrino telescope - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2014)
This paper reports a search for spatial clustering of the arrival directions of high energy muon neutrinos detected by the ANTARES neutrino telescope. An improved two-point correlation method is used to study the autocorrelation of 3058 neutrino candidate events as well as cross-correlations with other classes of astrophysical objects: sources of high energy gamma rays, massive black holes and nearby galaxies. No significant deviations from the isotropic distribution of arrival directions expected from atmospheric backgrounds are observed.
Keywords: neutrino astronomy; neutrino detectors

Searches for connections between dark matter and high-energy neutrinos with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Anton, Gisela; et al. (Journal of Cosmology and Astroparticle Physics, 2023)
In this work, we present the results of searches for signatures of dark matter decay or annihilation into Standard Model particles, and secret neutrino interactions with dark matter. Neutrinos could be produced in the decay or annihilation of galactic or extragalactic dark matter. Additionally, if an interaction between dark matter and neutrinos exists then dark matter will interact with extragalactic neutrinos. In particular galactic dark matter will induce an anisotropy in the neutrino sky if this interaction is present. We use seven and a half years of the High-Energy Starting Event (HESE) sample data, which measures neutrinos in the energy range of approximately 60 TeV to 10 PeV, to study these phenomena. This all-sky event selection is dominated by extragalactic neutrinos. For dark matter of ∼ 1 PeV in mass, we constrain the velocity-averaged annihilation cross section to be smaller than 10−23 cm3/s for the exclusive µ+µ− channel and 10−22 cm3/s for the bb̄ channel. For the same mass, we constrain the lifetime of dark matter to be larger than 1028 s for all channels studied, except for decaying exclusively to bb̄ where it is bounded to be larger than 1027 s. Finally, we also search for evidence of astrophysical neutrinos scattering on galactic dark matter in two scenarios. For fermionic dark matter with a vector mediator, we constrain the dimensionless coupling associated with this interaction to be less than 0.1 for dark matter mass of 0.1 GeV and a mediator mass of 10−4 GeV. In the case of scalar dark matter with a fermionic mediator, we constrain the coupling to be less than 0.1 for dark matter and mediator masses below 1 MeV.
CRIS-Team Scopus Importer:2023-12-15
Keywords: dark matter experiments; neutrino astronomy; neutrino experiments; neutrinos; ultra high energy photons

Searches for neutrinos from cosmic-ray interactions in the Sun using seven years of IceCube data - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau,; Anton, Gisela; Arguelles, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2021)
Cosmic-ray interactions with the solar atmosphere are expected to produce particle showers which in turn produce neutrinos from weak decays of mesons. These solar atmospheric neutrinos (SAνs) have never been observed experimentally. A detection would be an important step in understanding cosmic-ray propagation in the inner solar system and the dynamics of solar magnetic fields. SAνs also represent an irreducible background to solar dark matter searches and a detection would allow precise characterization of this background. Here, we present the first experimental search based on seven years of data collected from May 2010 to May 2017 in the austral winter with the IceCube Neutrino Observatory. An unbinned likelihood analysis is performed for events reconstructed within 5 degrees of the center of the Sun. No evidence for a SAν flux is observed. After inclusion of systematic uncertainties, we set a 90% upper limit of 1.02+0.20-0.18·10-13 GeV-1cm-2s-1 at 1 TeV.
CRIS-Team Scopus Importer:2021-03-26
Keywords: neutrino astronomy; neutrino detectors; neutrino experiments; solar and atmospheric neutrinos

Searches for Neutrinos from Gamma-Ray Bursts Using the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Anton, Gisela; et al. (Astrophysical Journal, 2022)
Gamma-ray bursts (GRBs) are considered as promising sources of ultra-high-energy cosmic rays (UHECRs) due to their large power output. Observing a neutrino flux from GRBs would offer evidence that GRBs are hadronic accelerators of UHECRs. Previous IceCube analyses, which primarily focused on neutrinos arriving in temporal coincidence with the prompt gamma-rays, found no significant neutrino excess. The four analyses presented in this paper extend the region of interest to 14 days before and after the prompt phase, including generic extended time windows and targeted precursor searches. GRBs were selected between 2011 May and 2018 October to align with the data set of candidate muon-neutrino events observed by IceCube. No evidence of correlation between neutrino events and GRBs was found in these analyses. Limits are set to constrain the contribution of the cosmic GRB population to the diffuse astrophysical neutrino flux observed by IceCube. Prompt neutrino emission from GRBs is limited to less than or similar to 1% of the observed diffuse neutrino flux, and emission on timescales up to 10(4) s is constrained to 24% of the total diffuse flux.
CRIS-Team WoS Importer:2023-01-20

Searches for Neutrinos from Large High Altitude Air Shower Observatory Ultra-high-energy γ-Ray Sources Using the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Aggarwal, N.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Anton, Gisela; et al. (Astrophysical Journal Letters, 2023)
Galactic PeV cosmic-ray accelerators (PeVatrons) are Galactic sources theorized to accelerate cosmic rays up to PeV in energy. The accelerated cosmic rays are expected to interact hadronically with nearby ambient gas or the interstellar medium, resulting in γ-rays and neutrinos. Recently, the Large High Altitude Air Shower Observatory (LHAASO) identified 12 γ-ray sources with emissions above 100 TeV, making them candidates for PeVatrons. While at these high energies the Klein-Nishina effect exponentially suppresses leptonic emission from Galactic sources, evidence for neutrino emission would unequivocally confirm hadronic acceleration. Here, we present the results of a search for neutrinos from these γ-ray sources and stacking searches testing for excess neutrino emission from all 12 sources as well as their subcatalogs of supernova remnants and pulsar wind nebulae with 11 yr of track events from the IceCube Neutrino Observatory. No significant emissions were found. Based on the resulting limits, we place constraints on the fraction of γ-ray flux originating from the hadronic processes in the Crab Nebula and LHAASO J2226+6057.
CRIS-Team Scopus Importer:2023-03-24

SEARCHES FOR POINT-LIKE AND EXTENDED NEUTRINO SOURCES CLOSE TO THE GALACTIC CENTER USING THE ANTARES NEUTRINO TELESCOPE - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J-J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Astrophysical Journal Letters, 2014)
A search for cosmic neutrino sources using six years of data collected by the ANTARES neutrino telescope has been performed. Clusters of muon neutrinos over the expected atmospheric background have been looked for. No clear signal has been found. The most signal-like accumulation of events is located at equatorial coordinates R.A. = -46 degrees.8 and decl. = -64 degrees.9 and corresponds to a 2.2 sigma background fluctuation. In addition, upper limits on the flux normalization of an E-2 muon neutrino energy spectrum have been set for 50 pre-selected astrophysical objects. Finally, motivated by an accumulation of seven events relatively close to the Galactic Center in the recently reported neutrino sample of the IceCube telescope, a search for point sources in a broad region around this accumulation has been carried out. No indication of a neutrino signal has been found in the ANTARES data and upper limits on the flux normalization of an E-2 energy spectrum of neutrinos from point sources in that region have been set. The 90% confidence level upper limits on the muon neutrino flux normalization vary between 3.5 and 5.1 x 10(-8) GeV cm(-2) s(-1), depending on the exact location of the source.
Keywords: astroparticle physics; Galaxy: center; neutrinos

SEARCH FOR A CORRELATION BETWEEN ANTARES NEUTRINOS AND PIERRE AUGER OBSERVATORY UHECRs ARRIVAL DIRECTIONS - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Astrophysical Journal, 2013)
A multimessenger analysis optimized for a correlation of arrival directions of ultra-high energy cosmic rays (UHECRs) and neutrinos is presented and applied to 2190 neutrino candidate events detected in 2007-2008 by the ANTARES telescope and 69 UHECRs observed by the Pierre Auger Observatory between 2004 January 1 and 2009 December 31. No significant correlation is observed. Assuming an equal neutrino flux (E-2 energy spectrum) from all UHECR directions, a 90% CL upper limit on the neutrino flux of 5.0 x 10(-8) GeV cm(-2) s(-1) per source is derived.
Keywords: astroparticle physics; cosmic rays; neutrinos

Search for a dark matter annihilation signal from the galactic center halo with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; Behera, B.; Bernloehr, K.; et al. (Physical Review Letters, 2011)
A search for a very-high-energy (VHE; 100GeV) γ-ray signal from self-annihilating particle dark matter (DM) is performed towards a region of projected distance r∼45-150pc from the Galactic center. The background-subtracted γ-ray spectrum measured with the High Energy Stereoscopic System (H.E.S.S.) γ-ray instrument in the energy range between 300-GeV and 30-TeV shows no hint of a residual γ-ray flux. Assuming conventional Navarro-Frenk-White and Einasto density profiles, limits are derived on the velocity-weighted annihilation cross section σv as a function of the DM particle mass. These are among the best reported so far for this energy range and in particular differ only little between the chosen density profile parametrizations. In particular, for the DM particle mass of ∼1TeV, values for σ above 3×1025cm3s1 are excluded for the Einasto density profile. © 2011 American Physical Society.

Search for a light sterile neutrino with 7.5 years of IceCube DeepCore data - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Physical Review D, 2024)
We present a search for an eV-scale sterile neutrino using 7.5 years of data from the IceCube DeepCore detector. The analysis uses a sample of 21,914 events with energies between 5 and 150 GeV to search for sterile neutrinos through atmospheric muon neutrino disappearance. Improvements in event selection and treatment of systematic uncertainties provide greater statistical power compared to previous DeepCore sterile neutrino searches. Our results are compatible with the absence of mixing between active and sterile neutrino states, and we place constraints on the mixing matrix elements |Uμ4|2<0.0534 and |Uτ4|2<0.0574 at 90% CL under the assumption that Δm412≥1 eV2. These null results add to the growing tension between anomalous appearance results and constraints from disappearance searches in the 3+1 sterile neutrino landscape.
CRIS-Team Scopus Importer:2024-11-01

Search for an eV-Scale Sterile Neutrino Using Improved High-Energy νμ Event Reconstruction in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Physical Review Letters, 2024)
This Letter presents the result of a 3+1 sterile neutrino search using 10.7 yr of IceCube data. We analyze atmospheric muon neutrinos that traverse the Earth with energies ranging from 0.5 to 100 TeV, incorporating significant improvements in modeling neutrino flux and detector response compared to earlier studies. Notably, for the first time, we categorize data into starting and throughgoing events, distinguishing neutrino interactions with vertices inside or outside the instrumented volume, to improve energy resolution. The best-fit point for a 3+1 model is found to be at sin2(2θ24)=0.16 and Δm412=3.5 eV2, which agrees with previous iterations of this Letter. The result is consistent with the null hypothesis of no sterile neutrinos with a p value of 3.1%.
CRIS-Team Scopus Importer:2024-12-06

Search for Correlations of High-energy Neutrinos Detected in IceCube with Radio-bright AGN and Gamma-Ray Emission from Blazars - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Astrophysical Journal, 2023)
The IceCube Neutrino Observatory sends realtime neutrino alerts with a high probability of being astrophysical in origin. We present a new method to correlate these events and possible candidate sources using 2089 blazars from the Fermi-LAT 4LAC-DR2 catalog and with 3413 active galactic nuclei (AGNs) from the Radio Fundamental Catalog. No statistically significant neutrino emission was found in any of the catalog searches. The result suggests that a small fraction, <1%, of the studied AGNs emit neutrinos that pass the alert criteria, and is compatible with prior evidence for neutrino emission presented by IceCube and other authors from sources such as TXS 0506 + 056 and PKS 1502 + 106. We also present cross-checks to other analyses that claim a significant correlation using similar data samples.
CRIS-Team Scopus Importer:2023-10-20

SEARCH FOR COSMIC NEUTRINO POINT SOURCES WITH FOUR YEARS OF DATA FROM THE ANTARES TELESCOPE - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J; Baret, B.; Basa, S.; et al. (Astrophysical Journal, 2012)
In this paper, a time-integrated search for point sources of cosmic neutrinos is presented using the data collected from 2007 to 2010 by the ANTARES neutrino telescope. No statistically significant signal has been found and upper limits on the neutrino flux have been obtained. Assuming an E-nu(-2). spectrum, these flux limits are at 1-10x10(-8) GeV cm(-2) s(-1) for declinations ranging from -90 degrees to 40 degrees. Limits for specific models of RX J1713.7-3946 and Vela X, which include information on the source morphology and spectrum, are also given.
Keywords: astroparticle physics; cosmic rays; neutrinos

Search for dark matter annihilation in the earth using the ANTARES neutrino telescope - Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physics of the Dark Universe, 2017)
A search for a neutrino signal from WIMP pair annihilations in the centre of the Earth has been performed with the data collected with the ANTARES neutrino telescope from 2007 to 2012. The event selection criteria have been developed and tuned to maximise the sensitivity of the experiment to such a neutrino signal. No significant excess of neutrinos over the expected background has been observed. Upper limits at 90% C.L. on the WIMP annihilation rate in the Earth and the spin independent scattering cross-section of WIMPs to nucleons sigma(SI)(p) were calculated for WIMP pair annihilations into either iota(+) iota(-), W+W-, b (b) over bar or the non-SUSY v mu(v) over bar as a function of the WIMP mass (between 25 GeV/c(2) and 1000 GeV/c(2)) and as a function of the thermally averaged annihilation cross section times velocity (Earth) of the WIMPs in the centre of the Earth. For masses of the WIMP close to the mass of iron nuclei (50 GeV/c(2)), the obtained limits on sigma(SI)(p) are more stringent than those obtained by other indirect searches. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Dark matter; Neutrino telescope; ANTARES; Indirect detection; WIMP

Search for dark matter annihilation signals from the Fornax galaxy cluster with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Becherini, Y.; Becker, J.; Behera, B.; Bernloehr, K.; et al. (Astrophysical Journal, 2012)
The Fornax galaxy cluster was observed with the High Energy Stereoscopic System for a total live time of 14.5hr, searching for very high energy (VHE; E > 100GeV) γ-rays from dark matter (DM) annihilation. No significant signal was found in searches for point-like and extended emissions. Using several models of the DM density distribution, upper limits on the DM velocity-weighted annihilation cross-section 〈σv〉 as a function of the DM particle mass are derived. Constraints are derived for different DM particle models, such as those arising from Kaluza-Klein and supersymmetric models. Various annihilation final states are considered. Possible enhancements of the DM annihilation γ-ray flux, due to DM substructures of the DM host halo, or from the Sommerfeld effect, are studied. Additional γ-ray contributions from internal bremsstrahlung and inverse Compton radiation are also discussed. For a DM particle mass of 1TeV, the exclusion limits at 95% of confidence level reach values of 〈σv〉 10 cm s, depending on the DM particle model and halo properties. Additional contribution from DM substructures can improve the upper limits on 〈σv〉 by more than two orders of magnitude. At masses around 4.5TeV, the enhancement by substructures and the Sommerfeld resonance effect results in a velocity-weighted annihilation cross-section upper limit at the level of 〈σv〉 10 cm s. © 2012. The American Astronomical Society. All rights reserved.

Search for dark matter annihilation signatures in H.E.S.S. observations of dwarf spheroidal galaxies - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2014)
Dwarf spheroidal galaxies of the Local Group are close satellites of the Milky Way characterized by a large mass-to-light ratio and are not expected to be the site of nonthermal high-energy gamma-ray emission or intense star formation. Therefore they are among the most promising candidates for indirect dark matter searches. During the last years the High Energy Stereoscopic System (H.E.S.S.) of imaging atmospheric Cherenkov telescopes observed five of these dwarf galaxies for more than 140 hours in total, searching for TeV gamma-ray emission from annihilation of dark matter particles. The new results of the deep exposure of the Sagittarius dwarf spheroidal galaxy, the first observations of the Coma Berenices and Fornax dwarves and the reanalysis of two more dwarf spheroidal galaxies already published by the H.E.S.S. Collaboration, Carina and Sculptor, are presented. In the absence of a significant signal new constraints on the annihilation cross section applicable to weakly interacting massive particles (WIMPs) are derived by combining the observations of the five dwarf galaxies. The combined exclusion limit depends on the WIMP mass and the best constraint is reached at 1-2 TeV masses with a cross-section upper bound of ∼3.9×10-24cm3s-1 at a 95% confidence level.

Search for Dark Matter Annihilations towards the Inner Galactic Halo from 10 Years of Observations with HESS - Abdallah, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Physical Review Letters, 2016)
The inner region of the Milky Way halo harbors a large amount of dark matter (DM). Given its proximity, it is one of the most promising targets to look for DM. We report on a search for the annihilations of DM particles using gamma-ray observations towards the inner 300 pc of the Milky Way, with the H.E.S.S. array of ground-based Cherenkov telescopes. The analysis is based on a 2D maximum likelihood method using Galactic Center (GC) data accumulated by H.E.S.S. over the last 10 years (2004-2014), and does not show any significant gamma-ray signal above background. Assuming Einasto and Navarro-Frenk-White DM density profiles at the GC, we derive upper limits on the annihilation cross section <sigma nu="">. These constraints are the strongest obtained so far in the TeV DM mass range and improve upon previous limits by a factor 5. For the Einasto profile, the constraints reach <sigma nu=""> values of 6 x 10(-26) cm(3) s(-1) in the W+W- channel for a DM particle mass of 1.5 TeV, and 2 x 10(-26) cm(3) s(-1) in the tau(+)tau(-) channel for a 1 TeV mass. For the first time, ground-based gamma-ray observations have reached sufficient sensitivity to probe <sigma nu=""> values expected from the thermal relic density for TeV DM particles.</sigma></sigma></sigma>

Search for dark matter from the center of the Earth with 8 years of IceCube data - Renzi, Giovanni; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
The nature of Dark Matter (DM) remains one of the most important unresolved questions of fundamental physics. Many models, including Weakly Interacting Massive Particles (WIMPs), assume DM to be a particle and predict a weak coupling with Standard Model matter. If DM particles can scatter off nuclei in the vicinity of a massive object such as a star or a planet, they may lose kinetic energy and become gravitationally trapped in the center of such objects, including Earth. As DM accumulates in the center of the Earth, self-annihilation of WIMPs into Standard Model particles can result in an excess of neutrinos which are detectable at the IceCube Neutrino Observatory, situated at the geographic South Pole. A search for excess neutrinos from these annihilations has been performed using 8 years of IceCube data, and results have been interpreted in the context of a number of WIMP annihilation channels (XX → τ+τ−/W+W−/bb¯) and masses ranging from 10 GeV to 10 TeV. We present the latest results from this analysis and compare the outcome with previous analyses by IceCube and other experiments, showing competitive results, which are even world-leading in some parts of the parameter space.
CRIS-Team Scopus Importer:2022-12-23

Search for dark matter towards the Galactic Centre with 11 years of ANTARES data - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Physics Letters B, 2020)
Neutrino detectors participate in the indirect search for the fundamental constituents of dark matter (DM) in form of weakly interacting massive particles (WIMPs). In WIMP scenarios, candidate DM particles can pair-annihilate into Standard Model products, yielding considerable fluxes of high-energy neutrinos. A detector like ANTARES, located in the Northern Hemisphere, is able to perform a complementary search looking towards the Galactic Centre, where a high density of dark matter is thought to accumulate. Both this directional information and the spectral features of annihilating DM pairs are entered into an unbinned likelihood method to scan the data set in search for DM-like signals in ANTARES data. Results obtained upon unblinding 3170 days of data reconstructed with updated methods are presented, which provides a larger, and more accurate, data set than a previously published result using 2101 days. A non-observation of dark matter is converted into limits on the velocity-averaged cross section for WIMP pair annihilation.
CRIS-Team Scopus Importer:2020-05-12
Keywords: ANTARES; Dark matter indirect detection; Galactic Centre; Neutrino telescope

Search for decoherence from quantum gravity with atmospheric neutrinos - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Nature Physics, 2024)
Neutrino oscillations at the highest energies and longest baselines can be used to study the structure of spacetime and test the fundamental principles of quantum mechanics. If the metric of spacetime has a quantum mechanical description, its fluctuations at the Planck scale are expected to introduce non-unitary effects that are inconsistent with the standard unitary time evolution of quantum mechanics. Neutrinos interacting with such fluctuations would lose their quantum coherence, deviating from the expected oscillatory flavour composition at long distances and high energies. Here we use atmospheric neutrinos detected by the IceCube South Pole Neutrino Observatory in the energy range of 0.5–10.0 TeV to search for coherence loss in neutrino propagation. We find no evidence of anomalous neutrino decoherence and determine limits on neutrino–quantum gravity interactions. The constraint on the effective decoherence strength parameter within an energy-independent decoherence model improves on previous limits by a factor of 30. For decoherence effects scaling as E2, our limits are advanced by more than six orders of magnitude beyond past measurements compared with the state of the art.
CRIS-Team Scopus Importer:2024-06-14

Search for extended γ-ray emission around AGN with H.E.S.S. and Fermi -LAT - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2014)
Context. Very-high-energy (VHE; E > 100 GeV) γ-ray emission from blazars inevitably gives rise to electron-positron pair production through the interaction of these γ-rays with the extragalactic background light (EBL). Depending on the magnetic fields in the proximity of the source, the cascade initiated from pair production can result in either an isotropic halo around an initially beamed source or a magnetically broadened cascade flux. Aims. Both extended pair-halo (PH) and magnetically broadened cascade (MBC) emission from regions surrounding the blazars 1ES 1101-232, 1ES 0229+200, and PKS 2155-304 were searched for using VHE γ-ray data taken with the High Energy Stereoscopic System (H.E.S.S.) and high-energy (HE; 100 MeV < E < 100 GeV) γ-ray data with the Fermi Large Area Telescope (LAT). Methods. By comparing the angular distributions of the reconstructed γ-ray events to the angular profiles calculated from detailed theoretical models, the presence of PH and MBC was investigated. Results. Upper limits on the extended emission around 1ES 1101-232, 1ES 0229+200, and PKS 2155-304 are found to be at a level of a few per cent of the Crab nebula flux above 1 TeV, depending on the assumed photon index of the cascade emission. Assuming strong extra-Galactic magnetic field (EGMF) values, >10 G, this limits the production of pair haloes developing from electromagnetic cascades. For weaker magnetic fields, in which electromagnetic cascades would result in MBCs, EGMF strengths in the range (0.3-3) × 10 G were excluded for PKS 2155-304 at the 99% confidence level, under the assumption of a 1 Mpc coherence length. © ESO, 2014.
Keywords: BL Lacertae objects: individual: 1ES 0229+200; BL Lacertae objects: individual: 1ES 1101-232; BL Lacertae objects: individual: PKS 2155-304; Galaxies: magnetic fields; Gamma rays: galaxies; Intergalactic medium

Search for Galactic Core-collapse Supernovae in a Decade of Data Taken with the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Astrophysical Journal, 2024)
The IceCube Neutrino Observatory has been continuously taking data to search for O(0.5–10) s long neutrino bursts since 2007. Even if a Galactic core-collapse supernova is optically obscured or collapses to a black hole instead of exploding, it will be detectable via the O(10) MeV neutrino burst emitted during the collapse. We discuss a search for such events covering the time between 2008 April 17 and 2019 December 31. Considering the average data taking and analysis uptime of 91.7% after all selection cuts, this is equivalent to 10.735 yr of continuous data taking. In order to test the most conservative neutrino production scenario, the selection cuts were optimized for a model based on an 8.8 solar mass progenitor collapsing to an O–Ne–Mg core. Conservative assumptions on the effects of neutrino oscillations in the exploding star were made. The final selection cut was set to ensure that the probability to detect such a supernova within the Milky Way exceeds 99%. No such neutrino burst was found in the data after performing a blind analysis. Hence, a 90% C.L. upper limit on the rate of core-collapse supernovae out to distances of ≈25 kpc was determined to be 0.23 yr−1. For the more distant Magellanic Clouds, only high neutrino luminosity supernovae will be detectable by IceCube, unless external information on the burst time is available. We determined a model-independent limit by parameterizing the dependence on the neutrino luminosity and the energy spectrum.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Core-collapse supernovae (304); Neutrino telescopes (1105); Supernova neutrinos (1666)

Search for gamma-Ray Line Signals from Dark Matter Annihilations in the Inner Galactic Halo from 10 Years of Observations with HESS - Abdallah, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Physical Review Letters, 2018)
Spectral lines are among the most powerful signatures for dark matter (DM) annihilation searches in very-high-energy gamma rays. The central region of the Milky Way halo is one of the most promising targets given its large amount of DM and proximity to Earth. We report on a search for a monoenergetic spectral line from self-annihilations of DM particles in the energy range from 300 GeV to 70 TeV using a two-dimensional maximum likelihood method taking advantage of both the spectral and spatial features of the signal versus background. The analysis makes use of Galactic center observations accumulated over ten years (2004-2014) with the H.E.S.S. array of ground-based Cherenkov telescopes. No significant gamma-ray excess above the background is found. We derive upper limits on the annihilation cross section (sigma v) for monoenergetic DM lines at the level of 4 x 10(-28) cm(3) s(-1) at 1 TeV, assuming an Einasto DM profile for the Milky Way halo. For a DM mass of 1 TeV, they improve over the previous ones by a factor of 6. The present constraints are the strongest obtained so far for DM particles in the mass range 300 GeV-70 TeV. Ground-based gamma-ray observations have reached sufficient sensitivity to explore relevant velocity-averaged cross sections for DM annihilation into two gamma-ray photons at the level expected from the thermal relic density for TeV DM particles.

Search for GeV neutrino emission during intense gamma-ray solar flares with the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Physical Review D, 2021)
Solar flares convert magnetic energy into thermal and nonthermal plasma energy, the latter implying particle acceleration of charged particles such as protons. Protons are injected out of the coronal acceleration region and can interact with dense plasma in the lower solar atmosphere, producing mesons that subsequently decay into gamma rays and neutrinos at O(MeV-GeV) energies. We present the results of the first search for GeV neutrinos emitted during solar flares carried out with the IceCube Neutrino Observatory. While the experiment was originally designed to detect neutrinos with energies between 10 GeV and a few PeV, a new approach allowing for a O(GeV) energy threshold will be presented. The resulting limits allow us to constrain some of the theoretical estimates of the expected neutrino flux.
CRIS-Team Scopus Importer:2021-05-28

Search for GeV-scale dark matter annihilation in the Sun with IceCube DeepCore - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alispach, C.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; et al. (Physical Review D, 2022)
The Sun provides an excellent target for studying spin-dependent dark matter-proton scattering due to its high matter density and abundant hydrogen content. Dark matter particles from the Galactic halo can elastically interact with Solar nuclei, resulting in their capture and thermalization in the Sun. The captured dark matter can annihilate into Standard Model particles including an observable flux of neutrinos. We present the results of a search for low-energy (<500 GeV) neutrinos correlated with the direction of the Sun using 7 years of IceCube data. This work utilizes, for the first time, new optimized cuts to extend IceCube's sensitivity to dark matter mass down to 5 GeV. We find no significant detection of neutrinos from the Sun. Our observations exclude capture by spin-dependent dark matter-proton scattering with cross section down to a few times 10-41 cm2, assuming there is equilibrium with annihilation into neutrinos/antineutrinos for dark matter masses between 5 GeV and 100 GeV. These are the strongest constraints at GeV energies for dark matter annihilation directly to neutrinos.
CRIS-Team Scopus Importer:2022-04-22

Search for High-energy Neutrinos from Binary Neutron Star Merger GW170817 with ANTARES, IceCube, and the Pierre Auger Observatory - Albert, A.; Andre, M.; Anghinolfi, M.; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Astrophysical Journal Letters, 2017)
The Advanced LIGO and Advanced Virgo observatories recently discovered gravitational waves from a binary neutron star inspiral. A short gamma-ray burst (GRB) that followed the merger of this binary was also recorded by the Fermi Gamma-ray Burst Monitor (Fermi-GBM), and the Anti-Coincidence Shield for the Spectrometer for the International Gamma-Ray Astrophysics Laboratory (INTEGRAL), indicating particle acceleration by the source. The precise location of the event was determined by optical detections of emission following the merger. We searched for high-energy neutrinos from the merger in the GeV-EeV energy range using the ANTARES, IceCube, and Pierre Auger Observatories. No neutrinos directionally coincident with the source were detected within +/- 500 s around the merger time. Additionally, no MeV neutrino burst signal was detected coincident with the merger. We further carried out an extended search in the direction of the source for high-energy neutrinos within the 14 day period following the merger, but found no evidence of emission. We used these results to probe dissipation mechanisms in relativistic outflows driven by the binary neutron star merger. The non-detection is consistent with model predictions of short GRBs observed at a large off-axis angle.
Keywords: gamma-ray burst: general; gravitational waves; neutrinos

Search for high-energy neutrinos from bright GRBs with ANTARES - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
Gamma-ray bursts are thought to be sites of hadronic acceleration, thus neutrinos are expected from the decay of charged particles, produced in p gamma interactions. The methods and results of a search for muon neutrinos in the data of the ANTARES neutrino telescope from four bright GRBs (GRB 080916C, GRB 110918A, GRB 130427A and GRB 130505A) observed between 2008 and 2013 are presented. Two scenarios of the fireball model have been investigated: the internal shock scenario, leading to the production of neutrinos with energies mainly above 100 TeV, and the photospheric scenario, characterized by a low-energy component in neutrino spectra due to the assumption of neutrino production closer to the central engine. Since no neutrino events have been detected in temporal and spatial coincidence with these bursts, upper limits at 90 per cent confidence level on the expected neutrino fluxes are derived. The non-detection allows for directly constraining the bulk Lorentz factor of the jet Gamma and the baryon loading f(p).
Keywords: acceleration of particles; neutrinos; gamma-ray burst: individual: GRB 080916C; gamma-ray burst: individual: GRB 110918A; gamma-ray burst: individual: GRB 130427A; gamma-ray burst: individual: GRB 130505A

Search for high-energy neutrinos from gravitational wave event GW151226 and candidate LVT151012 with ANTARES and IceCube - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
The Advanced LIGO observatories detected gravitational waves from two binary black hole mergers during their first observation run (O1). We present a high-energy neutrino follow-up search for the second gravitational wave event, GW151226, as well as for gravitational wave candidate LVT151012. We find two and four neutrino candidates detected by IceCube, and one and zero detected by ANTARES, within +/- 500 s around the respective gravitational wave signals, consistent with the expected background rate. None of these neutrino candidates are found to be directionally coincident with GW151226 or LVT151012. We use nondetection to constrain isotropic-equivalent high-energy neutrino emission from GW151226, adopting the GW event's 3D localization, to less than 2 x 10(51)-2 x 10(54) erg.

Search for High-energy Neutrinos from Ultraluminous Infrared Galaxies with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Astrophysical Journal, 2022)
Ultraluminous infrared galaxies (ULIRGs) have infrared luminosities L-IR >= 10(12) L-circle dot, making them the most luminous objects in the infrared sky. These dusty objects are generally powered by starbursts with star formation rates that exceed 100M(circle dot) yr(-1), possibly combined with a contribution from an active galactic nucleus. Such environments make ULIRGs plausible sources of astrophysical high-energy neutrinos, which can be observed by the IceCube Neutrino Observatory at the South Pole. We present a stacking search for high-energy neutrinos from a representative sample of 75 ULIRGs with redshift z <= 0.13 using 7.5 yr of IceCube data. The results are consistent with a background-only observation, yielding upper limits on the neutrino flux from these 75 ULIRGs. For an unbroken E-2.5 power-law spectrum, we report an upper limit on the stacked flux Phi(90%)(nu mu+(nu) over bar mu) = 3.24 x 10(-14) TeV-1 cm(-2) S-1 (E/10 TeV)(-2.5) at 90% confidence level. In addition, we constrain the contribution of the ULIRG source population to the observed diffuse astrophysical neutrino flux as well as model predictions.
CRIS-Team WoS Importer:2022-03-04

Search for high-energy neutrino sources from the direction of IceCube alert events - Karl, Martina; Eller, Philipp; Schubert, Anna; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; et al. (Proceedings of Science, 2022)
We use IceCube's high-statistics, neutrino-induced, through-going muon samples to search for astrophysical neutrino sources. Specifically, we analyze the arrival directions of IceCube's highest energy neutrinos. These high-energy events allow for a good angular reconstruction of their origin. Additionally, they have a high probability to come from an astrophysical source. On average, 8 neutrino events that satisfy these selection criteria are detected per year. Using these neutrino events as a source catalog, we present a search for the production sites of cosmic neutrinos. In this contribution we explore a time-dependent analysis, and present preliminary 3σ discovery potential fluences of ≈ 2.7 · 10−2GeV/cm2. We construct the fluences using expectation maximization.
CRIS-Team Scopus Importer:2024-12-16

Search for Joint Multimessenger Signals from Potential Galactic Cosmic-Ray Accelerators with HAWC and IceCube - Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistrán, T.; Carramiñana, A.; Casanova, S.; Cotti, U.; et al. (Astrophysical Journal, 2024)
The origin of high-energy galactic cosmic rays is yet to be understood, but some galactic cosmic-ray accelerators can accelerate cosmic rays up to PeV energies. The high-energy cosmic rays are expected to interact with the surrounding material or radiation, resulting in the production of gamma-rays and neutrinos. To optimize for the detection of such associated production of gamma-rays and neutrinos for a given source morphology and spectrum, a multimessenger analysis that combines gamma-rays and neutrinos is required. In this study, we use the MultiMission Maximum Likelihood framework with IceCube Maximum Likelihood Analysis software and HAWC Accelerated Likelihood to search for a correlation between 22 known gamma-ray sources from the third HAWC gamma-ray catalog and 14 yr of IceCube track-like data. No significant neutrino emission from the direction of the HAWC sources was found. We report the best-fit gamma-ray model and 90% CL neutrino flux limit from the 22 sources. From the neutrino flux limit, we conclude that, for five of the sources, the gamma-ray emission observed by HAWC cannot be produced purely from hadronic interactions. We report the limit for the fraction of gammarays produced by hadronic interactions for these five sources.
CRIS-Team Scopus Importer:2024-11-29

Search for magnetic monopoles with ten years of the ANTARES neutrino telescope - Albert, A.; Alves, S.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Ardid, S.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; et al. (Journal of High Energy Astrophysics, 2022)
This work presents a new search for magnetic monopoles using data taken with the ANTARES neutrino telescope over a period of 10 years (January 2008 to December 2017). Compared to previous ANTARES searches, this analysis uses a run-by-run simulation strategy, with a larger exposure as well as a new simulation of magnetic monopoles taking into account the Kasama, Yang and Goldhaber model for their interaction cross-section with matter. No signal compatible with the passage of relativistic magnetic monopoles is observed, and upper limits on the flux of magnetic monopoles with β=v/c≥0.55, are presented. For ultra-relativistic magnetic monopoles the flux limit is ∼7×10−18 cm−2s−1sr−1.
CRIS-Team Scopus Importer:2022-03-25
Keywords: ANTARES telescope; Magnetic monopoles; Neutrino

Search for Multi-flare Neutrino Emissions in 10 yr of IceCube Data from a Catalog of Sources - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Astrophysical Journal Letters, 2021)
A recent time-integrated analysis of a catalog of 110 candidate neutrino sources revealed a cumulative neutrino excess in the data collected by IceCube between 2008 April 6 and 2018 July 10. This excess, inconsistent with the background hypothesis in the Northern Hemisphere at the 3.3 sigma level, is associated with four sources: NGC 1068, TXS 0506+056, PKS 1424+240, and GB6 J1542+6129. This Letter presents two time-dependent neutrino emission searches on the same data sample and catalog: a point-source search that looks for the most significant time-dependent source of the catalog by combining space, energy, and time information of the events, and a population test based on binomial statistics that looks for a cumulative time-dependent neutrino excess from a subset of sources. Compared to previous time-dependent searches, these analyses enable a feature to possibly find multiple flares from a single direction with an unbinned maximum-likelihood method. M87 is found to be the most significant time-dependent source of this catalog at the level of 1.7 sigma post-trial, and TXS 0506+056 is the only source for which two flares are reconstructed. The binomial test reports a cumulative time-dependent neutrino excess in the Northern Hemisphere at the level of 3.0 sigma associated with four sources: M87, TXS 0506+056, GB6 J1542+6129, and NGC 1068.
CRIS-Team WoS Importer:2021-11-05

Search for Multimessenger Sources of Gravitational Waves and High-energy Neutrinos with Advanced LIGO during Its First Observing Run, ANTARES, and IceCube - Albert, A.; Andre, M.; Anghinolfi, M.; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin,; et al. (Astrophysical Journal, 2019)
Astrophysical sources of gravitational waves, such as binary neutron star and black hole mergers or core-collapse supernovae, can drive relativistic outflows, giving rise to non-thermal high-energy emission. High-energy neutrinos are signatures of such outflows. The detection of gravitational waves and high-energy neutrinos from common sources could help establish the connection between the dynamics of the progenitor and the properties of the outflow. We searched for associated emission of gravitational waves and high-energy neutrinos from astrophysical transients with minimal assumptions using data from Advanced LIGO from its first observing run O1, and data from the ANTARES and IceCube neutrino observatories from the same time period. We focused on candidate events whose astrophysical origins could not be determined from a single messenger. We found no significant coincident candidate, which we used to constrain the rate density of astrophysical sources dependent on their gravitational-wave and neutrino emission processes.
Keywords: gravitational waves; neutrinos

Search for muon-neutrino emission from GeV and TeV gamma-ray flaring blazars using five years of data of the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2015)
The ANTARES telescope is well-suited for detecting astrophysical transient neutrino sources as it can observe a full hemisphere of the sky at all times with a high duty cycle. The background due to atmospheric particles can be drastically reduced, and the point-source sensitivity improved, by selecting a narrow time window around possible neutrino production periods. Blazars, being radio-loud active galactic nuclei with their jets pointing almost directly towards the observer, are particularly attractive potential neutrino point sources, since they are among the most likely sources of the very high-energy cosmic rays. Neutrinos and gamma rays may be produced in hadronic interactions with the surrounding medium. Moreover, blazars generally show high time variability in their light curves at different wavelengths and on various time scales. This paper presents a time-dependent analysis applied to a selection of flaring gamma-ray blazars observed by the FERMI/LAT experiment and by TeV Cherenkov telescopes using five years of ANTARES data taken from 2008 to 2012. The results are compatible with fluctuations of the background. Upper limits on the neutrino fluence have been produced and compared to the measured gamma-ray spectral energy distribution.
Keywords: X-ray binaries; neutrino astronomy

Search for muon neutrinos from gamma-ray bursts with the ANTARES neutrino telescope using 2008 to 2011 data - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; et al. (Astronomy & Astrophysics, 2013)
Aims. We search for muon neutrinos in coincidence with GRBs with the ANTARES neutrino detector using data from the end of 2007 to 2011.Methods. Expected neutrino fluxes were calculated for each burst individually. The most recent numerical calculations of the spectra using the NeuCosmA code were employed, which include Monte Carlo simulations of the full underlying photohadronic interaction processes. The discovery probability for a selection of 296 GRBs in the given period was optimised using an extended maximum-likelihood strategy.Results. No significant excess over background is found in the data, and 90% confidence level upper limits are placed on the total expected flux according to the model.
Keywords: neutrinos; gamma-ray burst: general; methods: numerical

Search for neutrino counterparts of gravitational-wave events detected by LIGO and Virgo during run O2 with the ANTARES telescope - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (European Physical Journal C: Particles and Fields, 2020)
An offline search for a neutrino counterpart to gravitational-wave (GW) events detected during the second observation run (O2) of Advanced-LIGO and Advanced-Virgo performed with ANTARES data is presented. In addition to the search for long tracks induced by νμ (ν¯ μ) charged current interactions, a search for showering events induced by interactions of neutrinos of any flavour is conducted. The severe spatial and time coincidence provided by the gravitational-wave alert allows regions above the detector horizon to be probed, extending the ANTARES sensitivity over the entire sky. The results of this all-neutrino-flavour and all-sky time dependent analysis are presented. The search for prompt neutrino emission within ±500 s around the time of six GW events yields no neutrino counterparts. Upper limits on the neutrino spectral fluence and constraints on the isotropic energy radiated via high-energy neutrinos (from a few TeV to a few tens of PeV) are set for each GW event analysed.
CRIS-Team Scopus Importer:2020-06-16

Search for neutrino emission from gamma-ray flaring blazars with the ANTARES telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Astroparticle Physics, 2012)
The ANTARES telescope is well-suited to detect neutrinos produced in astrophysical transient sources as it can observe a full hemisphere of the sky at all times with a high duty cycle. Radio-loud active galactic nuclei with jets pointing almost directly towards the observer, the so-called blazars, are particularly attractive potential neutrino point sources. The all-sky monitor LAT on board the Fermi satellite probes the variability of any given gamma-ray bright blazar in the sky on time scales of hours to months. Assuming hadronic models, a strong correlation between the gamma-ray and the neutrino fluxes is expected. Selecting a narrow time window on the assumed neutrino production period can significantly reduce the background.An unbinned method based on the minimization of a likelihood ratio was applied to a subsample of data collected in 2008 (61 days live time). By searching for neutrinos during the high state periods of the AGN light curve, the sensitivity to these sources was improved by about a factor of two with respect to a standard time-integrated point source search. First results on the search for neutrinos associated with ten bright and variable Fermi sources are presented. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino astronomy; Fermi LAT transient sources; Time-dependent search; Blazars

Search for Neutrinoless Double- β Decay with the Complete EXO-200 Dataset - Anton, Gisela; Badhrees, I.; Barbeau, P. S.; Beck, D.; Belov, V.; Bhatta, T.; Breidenbach, M.; Brunner, T.; Cao, G. F.; Cen, W. R.; Chambers, C.; Cleveland, B.; et al. (Physical Review Letters, 2019)
A search for neutrinoless double-β decay (0νββ) in Xe136 is performed with the full EXO-200 dataset using a deep neural network to discriminate between 0νββ and background events. Relative to previous analyses, the signal detection efficiency has been raised from 80.8% to 96.4±3.0%, and the energy resolution of the detector at the Q value of Xe136 0νββ has been improved from σ/E=1.23% to 1.15±0.02% with the upgraded detector. Accounting for the new data, the median 90% confidence level 0νββ half-life sensitivity for this analysis is 5.0×1025 yr with a total Xe136 exposure of 234.1 kg yr. No statistically significant evidence for 0νββ is observed, leading to a lower limit on the 0νββ half-life of 3.5×1025 yr at the 90% confidence level.
CRIS-Team Scopus Importer:2019-10-29

Search for Neutrinos from the Tidal Disruption Events AT2019dsg and AT2019fdr with the ANTARES Telescope - Albert, A.; Alves, S.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bendahman, M.; et al. (Astrophysical Journal, 2021)
On 2019 October 1, the IceCube Collaboration detected a muon track neutrino with a high probability of being of astrophysical origin, IC191001A. After a few hours, the tidal disruption event (TDE) AT2019dsg, observed by the Zwicky Transient Facility (ZTF), was indicated as the most likely counterpart of the IceCube track. More recently, the follow-up campaign of the IceCube alerts by ZTF suggested a second TDE, AT2019fdr, as a promising counterpart of another IceCube muon track candidate, IC200530A, detected on 2020 May 30. Here, these intriguing associations are followed-up by searching for neutrinos in the ANTARES detector from the directions of AT2019dsg and AT2019fdr using a time-integrated approach. As no significant evidence for space clustering is found in the ANTARES data, upper limits on the one-flavor neutrino flux and fluence are set.
CRIS-Team WoS Importer:2021-10-29

Search for PeV Gamma-Ray Emission from the Southern Hemisphere with 5 Yr of Data from the IceCube Observatory - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (Astrophysical Journal, 2020)
The measurement of diffuse PeV gamma-ray emission from the Galactic plane would provide information about the energy spectrum and propagation of Galactic cosmic rays, and the detection of a pointlike source of PeV gamma-rays would be strong evidence for a Galactic source capable of accelerating cosmic rays up to at least a few PeV. This paper presents several unbinned maximum-likelihood searches for PeV gamma-rays in the Southern Hemisphere using 5 yr of data from the IceTop air shower surface detector and the in-ice array of the IceCube Observatory. The combination of both detectors takes advantage of the low muon content and deep shower maximum of gamma-ray air showers and provides excellent sensitivity to gamma-rays between ∼0.6 and 100 PeV. Our measurements of pointlike and diffuse Galactic emission of PeV gamma-rays are consistent with the background, so we constrain the angle-integrated diffuse gamma-ray flux from the Galactic plane at 2 PeV to 2.61 × 10-19 cm-2 s-1 TeV-1 at 90% confidence, assuming an E -3 spectrum, and we estimate 90% upper limits on pointlike emission at 2 PeV between 10-21 and 10-20 cm-2 s-1 TeV-1 for an E -2 spectrum, depending on decl. Furthermore, we exclude unbroken power-law emission up to 2 PeV for several TeV gamma-ray sources observed by the High Energy Spectroscopic System and calculate upper limits on the energy cutoffs of these sources at 90% confidence. We also find no PeV gamma-rays correlated with neutrinos from IceCube's high-energy starting event sample. These are currently the strongest constraints on PeV gamma-ray emission.
CRIS-Team Scopus Importer:2020-06-09

Search for photon-linelike signatures from dark matter annihilations with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Physical Review Letters, 2013)
Gamma-ray line signatures can be expected in the very-high-energy (E >100 GeV) domain due to self-annihilation or decay of dark matter (DM) particles in space. Such a signal would be readily distinguishable from astrophysical γ-ray sources that in most cases produce continuous spectra that span over several orders of magnitude in energy. Using data collected with the H.E.S.S. γ-ray instrument, upper limits on linelike emission are obtained in the energy range between ∼500 GeV and ∼25 TeV for the central part of the Milky Way halo and for extragalactic observations, complementing recent limits obtained with the Fermi-LAT instrument at lower energies. No statistically significant signal could be found. For monochromatic γ-ray line emission, flux limits of (2×107- 2×105) m2 s1 sr1 and (1×108-2×106) m2 s1 sr1 are obtained for the central part of the Milky Way halo and extragalactic observations, respectively. For a DM particle mass of 1 TeV, limits on the velocity-averaged DM annihilation cross section âŸ̈σvâŸ© reach ∼1027 cm3 s 1, based on the Einasto parametrization of the Galactic DM halo density profile. © 2013 American Physical Society.

Search for polarized antiproton production - Grzonka, D.; Alfs, D.; Asaturyan, A.; Carmignotto, M.; Diermaier, M.; Eyrich, Wolfgang; Głowacz, B.; Hauenstein, F.; Horn, T.; Kilian, K.; Lersch, D.; Malbrunot-Ettenauer, S.; et al. (Hyperfine Interactions, 2019)
The production of antiprotons is studied in view of possible polarization effects as basis for a polarized antiproton beam. If antiprotons are produced with some polarization, a quite simple procedure for the generation of a polarized antiproton beam could be worked out. The experiments are performed at the CERN PS test beam T11 where secondary particles with momenta around 3.5 GeV/c are selected. The polarization analysis is performed by measuring the asymmetry of the elastic p̄ p-scattering in the Coulomb-nuclear interference region. The detection system includes Cherenkov and tracking detectors for the particle identification and the 3d track reconstruction. Details on the detection system and the status of the analysis are given.
CRIS-Team Scopus Importer:2019-05-09
Keywords: 24.70.+s; CNI; DIRC; Drift chamber; Elastic scattering; Polarized antiproton; Track reconstruction

Search for quantum gravity using astrophysical neutrino flavour with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alispach, C.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; et al. (Nature Physics, 2022)
Along their long propagation from production to detection, neutrinos undergo flavour conversions that convert their types or flavours1,2. High-energy astrophysical neutrinos propagate unperturbed over a billion light years in vacuum3 and are sensitive to small effects caused by new physics. Effects of quantum gravity4 are expected to appear at the Planck energy scale. Such a high-energy universe would have existed only immediately after the Big Bang and is inaccessible by human technologies. On the other hand, quantum gravity effects may exist in our low-energy vacuum5–8, but are suppressed by inverse powers of the Planck energy. Measuring the coupling of particles to such small effects is difficult via kinematic observables, but could be observable through flavour conversions. Here we report a search with the IceCube Neutrino Observatory, using astrophysical neutrino flavours9,10 to search for new space–time structure. We did not find any evidence of anomalous flavour conversion in the IceCube astrophysical neutrino flavour data. We apply the most stringent limits of any known technologies, down to 10−42 GeV−2 with Bayes factor greater than 10 on the dimension-six operators that parameterize the space–time defects. We thus unambiguously reach the parameter space of quantum-gravity-motivated physics.
CRIS-Team Scopus Importer:2022-11-04

Search for Relativistic Magnetic Monopoles with Eight Years of IceCube Data - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Physical Review Letters, 2022)
We present an all-sky 90% confidence level upper limit on the cosmic flux of relativistic magnetic monopoles using 2886 days of IceCube data. The analysis was optimized for monopole speeds between 0.750c and 0.995c, without any explicit restriction on the monopole mass. We constrain the flux of relativistic cosmic magnetic monopoles to a level below 2.0 x 10(-19) cm(-2) s(-1) sr(-1) over the majority of the targeted speed range. This result constitutes the most strict upper limit to date for magnetic monopoles with beta > 0.8 and up to beta similar to 0.995 and fills the gap between existing limits on the cosmic flux of nonrelativistic and ultrarelativistic magnetic monopoles.
CRIS-Team WoS Importer:2022-02-18

Search for relativistic magnetic monopoles with five years of the ANTARES detector data - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Journal of High Energy Physics, 2017)
A search for magnetic monopoles using five years of data recorded with the ANTARES neutrino telescope from January 2008 to December 2012 with a total live time of 1121 days is presented. The analysis is carried out in the range beta > 0.6 of magnetic monopole velocities using a strategy based on run-by-run Monte Carlo simulations. No signal above the background expectation from atmospheric muons and atmospheric neutrinos is observed, and upper limits are set on the magnetic monopole flux ranging from 5.7 x 10(-16) to 1.5 x 10(-18) cm(-2).s(-1).sr(-1).
Keywords: Exotics; Neutrino Detectors and Telescopes (experiments)

Search for relativistic magnetic monopoles with the ANTARES neutrino telescope - Adrian-Martinez, S.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; et al. (Astroparticle Physics, 2012)
Magnetic monopoles are predicted in various unified gauge models and could be produced at intermediate mass scales. Their detection in a neutrino telescope is facilitated by the large amount of light emitted compared to that from muons. This paper reports on a search for upgoing relativistic magnetic monopoles with the ANTARES neutrino telescope using a data set of 116 days of live time taken from December 2007 to December 2008. The one observed event is consistent with the expected atmospheric neutrino and muon background, leading to a 90% C.L. upper limit on the monopole flux between 1.3 x 10-(17) and 8.9 x 10(-17) CM-2 s(-1) sr(-1) for monopoles with velocity beta >= 0.625. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Magnetic monopole; Neutrino telescopes; ANTARES

Search for secluded dark matter with 6 years of IceCube data - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Proceedings of Science, 2022)
The IceCube neutrino observatory–installed in the Antarctic ice–is the largest neutrino telescope to date. It consists of 5,160 photomultiplier-tubes spread among 86 vertical strings making a total detector volume of more than a cubic kilometer. IceCube detects neutrinos via Cherenkov light emitted by charged relativistic particles produced when a neutrino interacts in or near the detector. The detector is particularly sensitive to high-energy neutrinos of due to its size and photosensor spacing. In this analysis we search for dark matter that annihilates into a metastable mediator that subsequently decays into Standard Model particles. These models yield an enhanced high-energy neutrino flux from dark matter annihilation inside the Sun compared to models without a mediator. Neutrino signals that are produced directly inside the Sun are strongly attenuated at higher energies due to interactions with the solar plasma. In the models considered here, the mediator can escape the Sun before producing any neutrinos, thereby avoiding attenuation. We present the results of an analysis of six years of IceCube data looking for dark matter in the Sun. We consider mediator lifetimes between 1 ms to 10 s and dark matter masses between 200 GeV and 75 TeV.
CRIS-Team Scopus Importer:2024-12-16

Search for solar atmospheric neutrinos with the ANTARES neutrino telescope - Albert, A.; Alves, S.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Ardid, S.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; et al. (Journal of Cosmology and Astroparticle Physics, 2022)
Solar Atmospheric Neutrinos (SA nu s) are produced by the interaction of cosmic rays with the solar medium. The detection of SA nu s would provide useful information on the composition of primary cosmic rays as well as the solar density. These neutrinos represent an irreducible source of background for indirect searches for dark matter towards the Sun and the measurement of their flux would allow for a better assessment of the uncertainties related to these searches. In this paper we report on the analysis performed, based on an unbinned likelihood maximisation, to search for SA nu s with the ANTARES neutrino telescope. After analysing the data collected over 11 years, no evidence for a solar atmospheric neutrino signal has been found. An upper limit at 90% confidence level on the flux of solar atmospheric neutrinos has been obtained, equal to 7x10(-11) [TeV-1 cm(-2) s(-1)] b at E-nu = 1 TeV for the reference cosmic ray model assumed.
CRIS-Team WoS Importer:2022-08-19
Keywords: dark matter experiments; neutrino experiments; neutrino detectors; solar and atmospheric neutrinos

Search for sources of astrophysical neutrinos using seven years of icecube cascade events - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (Astrophysical Journal, 2019)
Low-background searches for astrophysical neutrino sources anywhere in the sky can be performed using cascade events induced by neutrinos of all flavors interacting in IceCube with energies as low as ∼1 TeV. Previously we showed that, even with just two years of data, the resulting sensitivity to sources in the southern sky is competitive with IceCube and ANTARES analyses using muon tracks induced by charge current muon neutrino interactions - especially if the neutrino emission follows a soft energy spectrum or originates from an extended angular region. Here, we extend that work by adding five more years of data, significantly improving the cascade angular resolution, and including tests for point-like or diffuse Galactic emission to which this data set is particularly well suited. For many of the signal candidates considered, this analysis is the most sensitive of any experiment to date. No significant clustering was observed, and thus many of the resulting constraints are the most stringent to date. In this paper we will describe the improvements introduced in this analysis and discuss our results in the context of other recent work in neutrino astronomy.
CRIS-Team Scopus Importer:2020-02-21

Search for Spatial Correlations of Neutrinos with Ultra-high-energy Cosmic Rays - Albert, A.; Domi, Alba; Alves, S.; Andre, M.; Anghinolfi, M.; Ardid, S.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bendahman, M.; et al. (Astrophysical Journal, 2022)
For several decades, the origin of ultra-high-energy cosmic rays (UHECRs) has been an unsolved question of high-energy astrophysics. One approach for solving this puzzle is to correlate UHECRs with high-energy neutrinos, since neutrinos are a direct probe of hadronic interactions of cosmic rays and are not deflected by magnetic fields. In this paper, we present three different approaches for correlating the arrival directions of neutrinos with the arrival directions of UHECRs. The neutrino data are provided by the IceCube Neutrino Observatory and ANTARES, while the UHECR data with energies above similar to 50 EeV are provided by the Pierre Auger Observatory and the Telescope Array. All experiments provide increased statistics and improved reconstructions with respect to our previous results reported in 2015. The first analysis uses a high-statistics neutrino sample optimized for point-source searches to search for excesses of neutrino clustering in the vicinity of UHECR directions. The second analysis searches for an excess of UHECRs in the direction of the highest-energy neutrinos. The third analysis searches for an excess of pairs of UHECRs and highest-energy neutrinos on different angular scales. None of the analyses have found a significant excess, and previously reported overfluctuations are reduced in significance. Based on these results, we further constrain the neutrino flux spatially correlated with UHECRs.
CRIS-Team WoS Importer:2022-08-26

Search for steady point-like sources in the astrophysical muon neutrino flux with 8 years of IceCube data - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Arguelles, C.; et al. (European Physical Journal C, 2019)
The IceCube Collaboration has observed a high-energy astrophysical neutrino flux and recently found evidence for neutrino emission from the blazar TXS 0506+056. These results open a new window into the high-energy universe. However, the source or sources of most of the observed flux of astrophysical neutrinos remains uncertain. Here, a search for steady point-like neutrino sources is performed using an unbinned likelihood analysis. The method searches for a spatial accumulation of muon-neutrino events using the very high-statistics sample of about 497,000 neutrinos recorded by IceCube between 2009 and 2017. The median angular resolution is approximate to 1 degrees at 1 TeV and improves to approximate to 0.3 degrees for neutrinos with an energy of 1 PeV. Compared to previous analyses, this search is optimized for point-like neutrino emission with the same flux-characteristics as the observed astrophysical muon-neutrino flux and introduces an improved event-reconstruction and parametrization of the background. The result is an improvement in sensitivity to the muon-neutrino flux compared to the previous analysis of approximate to 35% assuming an E-2 spectrum. The sensitivity on the muon-neutrino flux is at a level of E2dN/dE=310-13s-1. No new evidence for neutrino sources is found in a full sky scan and in an a priori candidate source list that is motivated by gamma-ray observations. Furthermore, no significant excesses above background are found from populations of sub-threshold sources. The implications of the non-observation for potential source classes are discussed.
CRIS-Team WoS Importer:2019-03-29

Search for sub-TeV Neutrino Emission from Novae with IceCube-DeepCore - Abbasi, R.; Ackermann, M.; Adams, J.; Aggarwal, N.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Anton, Gisela; et al. (Astrophysical Journal, 2023)
The understanding of novae, the thermonuclear eruptions on the surfaces of white dwarf stars in binaries, has recently undergone a major paradigm shift. Though the bolometric luminosity of novae was long thought to arise directly from photons supplied by the thermonuclear runaway, recent gigaelectronvolt (GeV) gamma-ray observations have supported the notion that a significant portion of the luminosity could come from radiative shocks. More recently, observations of novae have lent evidence that these shocks are acceleration sites for hadrons for at least some types of novae. In this scenario, a flux of neutrinos may accompany the observed gamma rays. As the gamma rays from most novae have only been observed up to a few GeV, novae have previously not been considered as targets for neutrino telescopes, which are most sensitive at and above teraelectronvolt (TeV) energies. Here, we present the first search for neutrinos from novae with energies between a few GeV and 10 TeV using IceCube-DeepCore, a densely instrumented region of the IceCube Neutrino Observatory with a reduced energy threshold. We search both for a correlation between gamma-ray and neutrino emission as well as between optical and neutrino emission from novae. We find no evidence for neutrino emission from the novae considered in this analysis and set upper limits for all gamma-ray detected novae.
CRIS-Team Scopus Importer:2023-12-01

Search for TeV gamma-ray emission from GRB 100621A, an extremely bright GRB in X-rays, with H.E.S.S. - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2014)
The long gamma-ray burst (GRB) 100621A, at the time the brightest X-ray transient ever detected by Swift-XRT in the 0.3-10 keV range, has been observed with the H.E.S.S. imaging air Cherenkov telescope array, sensitive to gamma radiation in the very-high-energy (VHE, >100 GeV) regime. Due to its relatively small redshift of z 0.5, the favourable position in the southern sky and the relatively short follow-up time (<700 s after the satellite trigger) of the H.E.S.S. observations, this GRB could be within the sensitivity reach of the H.E.S.S. instrument. The analysis of the H.E.S.S. data shows no indication of emission and yields an integral flux upper limit above 380 GeV of 4.2 × 10 cm s (95% confidence level), assuming a simple Band function extension model. A comparison to a spectral-temporal model, normalised to the prompt flux at sub-MeV energies, constraints the existence of a temporally extended and strong additional hard power law, as has been observed in the other bright X-ray GRB 130427A. A comparison between the H.E.S.S. upper limit and the contemporaneous energy output in X-rays constrains the ratio between the X-ray and VHE gamma-ray fluxes to be greater than 0.4. This value is an important quantity for modelling the afterglow and can constrain leptonic emission scenarios, where leptons are responsible for the X-ray emission and might produce VHE gamma rays. © 2014 ESO.
Keywords: Gamma rays: general; Gamma rays: stars; Gamma-ray burst: individual: GRB 100621A; X-rays: stars

Search for the eta mesic He-3 in the pd -> dp pi(0) reaction with the WASA-at-COSY facility - Adlarson, P.; Augustyniak, W.; Bashkanov, M.; Bass, S. D.; Bergmann, F. S.; Berlowski, M.; Bondar, A.; Buescher, M.; Calen, H.; Ciepal, I.; Clement, H.; Czerwinski, E.; et al. (Physical Review C - Nuclear Physics, 2020)
The excitation function for the pd -> dp pi(0) reaction has been measured byWASA-at-COSY experiment with the aim of searching for He-3-h mesic nuclei. The measurement in the vicinity of h meson production was performed using a ramped proton beam. The data analysis and interpretation was carried out with the assumption that the h mesic helium decays via the formation of an intermediate N*(1535) resonance. No direct signal of the. mesic nucleus is observed in the excitation function. We determine a new improved upper limit for the total cross section for the bound state production and decay in the pd -> (He-3-eta)(bound) -> dp pi(0) process. It varies between 13 nb to 24 nb for the bound state with width in the range Gamma is an element of ( 5, 50) MeV.
CRIS-Team WoS Importer:2020-11-06

Search for the Prompt Atmospheric Neutrino Flux in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
For about a decade the IceCube Neutrino Observatory has been observing a high-energy diffuse astrophysical neutrino flux. At these energies, an important source of background are the prompt atmospheric neutrinos produced in decays of charmed mesons that are part of cosmic-ray-induced air showers. The production yield of charmed mesons in the very forward phase space of hadronic interactions, and thus the flux of prompt neutrinos, is not well known and has not yet been observed by IceCube. A measurement of the flux of prompt neutrinos will improve the modeling of hadronic interactions in cosmic-ray induced air showers at high energies. Additionally, in the context of astrophysical neutrino measurements, understanding this background flux will improve the measurement precision of the spectral shape in the future. In particular, the analysis of up-going muon neutrino-induced tracks in IceCube provides a large sample of atmospheric neutrinos which likely includes prompt neutrinos. However, the measurement of a subdominant prompt neutrino flux strongly depends on the hypothesis for the dominant astrophysical neutrino flux. This makes the estimation of upper limits on the prompt neutrino flux challenging. We discuss the extent of this model dependency on the astrophysical flux and propose a method to calculate robust upper limits. Furthermore, a possible dedicated search of the prompt neutrino flux using multiple IceCube detection channels is outlined.
CRIS-Team Scopus Importer:2025-02-04

Search for transient optical counterparts to high-energy IceCube neutrinos with Pan-STARRS1 - Kankare, E.; Huber, M.; Smartt, S. J.; Chambers, K.; Smith, K. W.; Mcbrien, O.; Chen, T-W; Flewelling, H.; Lowe, T.; Magnier, E.; Schultz, A.; Waters, C.; et al. (Astronomy & Astrophysics, 2019)
In order to identify the sources of the observed diffuse high-energy neutrino flux, it is crucial to discover their electromagnetic counterparts. To increase the sensitivity of detecting counterparts of transient or variable sources by telescopes with a limited field of view, IceCube began releasing alerts for single high-energy (Eνâ> â60 TeV) neutrino detections with sky localisation regions of order 1° radius in 2016. We used Pan-STARRS1 to follow-up five of these alerts during 2016-2017 to search for any optical transients that may be related to the neutrinos. Typically 10-20 faint (miP1âââ22.5 mag) extragalactic transients are found within the Pan-STARRS1 footprints and are generally consistent with being unrelated field supernovae (SNe) and AGN. We looked for unusual properties of the detected transients, such as temporal coincidence of explosion epoch with the IceCube timestamp, or other peculiar light curve and physical properties. We found only one transient that had properties worthy of a specific follow-up. In the Pan-STARRS1 imaging for IceCube-160427A (probability to be of astrophysical origin of ∼50%), we found a SN PS16cgx, located at 10.0′ from the nominal IceCube direction. Spectroscopic observations of PS16cgx showed that it was an H-poor SN at redshift zâ=â0.2895â ±â 0.0001. The spectra and light curve resemble some high-energy Type Ic SNe, raising the possibility of a jet driven SN with an explosion epoch temporally coincident with the neutrino detection. However, distinguishing Type Ia and Type Ic SNe at this redshift is notoriously difficult. Based on all available data we conclude that the transient is more likely to be a Type Ia with relatively weak Siâ» II absorption and a fairly normal rest-frame r-band light curve. If, as predicted, there is no high-energy neutrino emission from Type Ia SNe, then PS16cgx must be a random coincidence, and unrelated to the IceCube-160427A. We find no other plausible optical transient for any of the five IceCube events observed down to a 5σ limiting magnitude of miP1â≈â22 mag, between 1 day and 25 days after detection.
CRIS-Team Scopus Importer:2019-07-12
Keywords: Astroparticle physics; Neutrinos; Supernovae: general

Search for Unstable Sterile Neutrinos with the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Anton, Gisela; et al. (Physical Review Letters, 2022)
We present a search for an unstable sterile neutrino by looking for a resonant signal in eight years of atmospheric νμ data collected from 2011 to 2019 at the IceCube Neutrino Observatory. Both the (stable) three-neutrino and the 3+1 sterile neutrino models are disfavored relative to the unstable sterile neutrino model, though with p values of 2.8% and 0.81%, respectively, we do not observe evidence for 3+1 neutrinos with neutrino decay. The best-fit parameters for the sterile neutrino with decay model from this study are Δm412=6.7-2.5+3.9 eV2, sin22θ24=0.33-0.17+0.20, and g2=2.5π±1.5π, where g is the decay-mediating coupling. The preferred regions of the 3+1+decay model from short-baseline oscillation searches are excluded at 90% C.L.
CRIS-Team Scopus Importer:2022-10-28

Search for very-high-energy γ-ray emission from Galactic globular clusters with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
Context. Globular clusters (GCs) are established emitters of high-energy (HE, 100 MeV < E < 100 GeV) γ-ray radiation which could originate from the cumulative emission of the numerous millisecond pulsars (msPSRs) in the clusters' cores or from inverse Compton (IC) scattering of relativistic leptons accelerated in the GC environment. These stellar clusters could also constitute a new class of sources in the very-high-energy (VHE, E > 100 GeV) γ-ray regime, judging from the recent detection of a signal from the direction of Terzan 5 with the H.E.S.S. telescope array. Aims. To search for VHE γ-ray sources associated with other GCs, and to put constraints on leptonic emission models, we systematically analyzed the observations towards 15 GCs taken with the H.E.S.S. array of imaging atmospheric Cherenkov telescopes. Methods. We searched for point-like and extended VHE γ-ray emission from each GC in our sample and also performed a stacking analysis combining the data from all GCs to investigate the hypothesis of a population of faint emitters. Assuming IC emission as the origin of the VHE γ-ray signal from the direction of Terzan 5, we calculated the expected γ-ray flux from each of the 15 GCs, based on their number of millisecond pulsars, their optical brightness and the energy density of background photon fields. Results. We did not detect significant VHE γ-ray emission from any of the 15 GCs in either of the two analyses. Given the uncertainties related to the parameter determinations, the obtained flux upper limits allow to rule out the simple IC/msPSR scaling model for NGC 6388 and NGC 7078. The upper limits derived from the stacking analyses are factors between 2 and 50 below the flux predicted by the simple leptonic scaling model, depending on the assumed source extent and the dominant target photon fields. Therefore, Terzan 5 still remains exceptional among all GCs, as the VHE γ-ray emission either arises from extra-ordinarily efficient leptonic processes, or from a recent catastrophic event, or is even unrelated to the GC itself. © 2013 ESO.
Keywords: Gamma rays: general; Globular clusters: general; Pulsars: general; Radiation mechanisms: non-thermal

Search for η mesic 3He with the WASA-at-COSY facility in the pd→3He2γ and pd→3He6γ reactions - Adlarson, P.; Augustyniak, W.; Bardan, W.; Bashkanov, M.; Bass, S. D.; Berłowski, M.; Bondar, A.; Büscher, M.; Calén, H.; Ciepał, I.; Clement, H.; Czerwiński, E.; et al. (Physics Letters B, 2020)
We report on the experimental search for the bound state of an η meson and He3 nucleus performed using the WASA-at-COSY detector setup. In order to search for the η-mesic nucleus decay, the pd→3He2γ and pd→3He6γ channels have been analysed. These reactions manifest the direct decay of the η meson bound in a He3 nucleus. This non-mesonic decay channel has been considered for the first time. When taking into account only statistical errors, the obtained excitation functions reveal a slight indication for a possible bound state signal corresponding to a 3He-η nucleus width Γ above 20 MeV and binding energy Bs between 0 and 15 MeV. However, the determined cross sections are consistent with zero in the range of the systematic uncertainty. Therefore, as final result we estimate only the upper limit for the cross section of the η-mesic He3 nucleus formation followed by the η meson decay which varies between 2 nb and 15 nb depending on possible bound state parameters.
CRIS-Team Scopus Importer:2020-01-24
Keywords: η meson; η-mesic nuclei

Searching for VHE gamma-ray emission associated with IceCube neutrino alerts using FACT, H.E.S.S., MAGIC, and VERITAS - Dorner, Daniela; Mezek, Gašper Kukec; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; et al. (Proceedings of Science, 2022)
The realtime follow-up of neutrino events is a promising approach to search for astrophysical neutrino sources. It has so far provided compelling evidence for a neutrino point source: the flaring gamma-ray blazar TXS 0506+056 observed in coincidence with the high-energy neutrino IceCube-170922A detected by IceCube. The detection of very-high-energy gamma rays (VHE, E > 100 GeV) from this source helped establish the coincidence and constrained the modeling of the blazar emission at the time of the IceCube event. The four major imaging atmospheric Cherenkov telescope arrays (IACTs) - FACT, H.E.S.S., MAGIC, and VERITAS - operate an active follow-up program of target-of-opportunity observations of neutrino alerts sent by IceCube. This program has two main components. One are the observations of known gamma-ray sources around which a cluster of candidate neutrino events has been identified by IceCube (Gamma-ray Follow-Up, GFU). Second one is the follow-up of single high-energy neutrino candidate events of potential astrophysical origin such as IceCube-170922A. GFU has been recently upgraded by IceCube in collaboration with the IACT groups. We present here recent results from the IACT follow-up programs of IceCube neutrino alerts and a description of the upgraded IceCube GFU system.
CRIS-Team Scopus Importer:2024-12-16

Search of dark matter annihilation in the galactic centre using the ANTARES neutrino telescope - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2015)
A search for high-energy neutrinos coming from the direction of the Galactic Centre is performed using the data recorded by the ANTARES neutrino telescope from 2007 to 2012. The event selection criteria are chosen to maximise the sensitivity to possible signals produced by the self-annihilation of weakly interacting massive particles accumulated around the centre of the Milky Way with respect to the atmospheric background. After data unblinding, the number of neutrinos observed in the line of sight of the Galactic Centre is found to be compatible with background expectations. The 90% C.L. upper limits in terms of the neutrino+anti-neutrino flux, Phi(nu mu + (nu) over bar mu), and the velocity averaged annihilation cross-section, , are derived for the WIMP self-annihilation channels into b (b) over bar; W+W-; tau(+)tau(-); mu(+)mu(-); nu(nu) over bar. The ANTARES limits for are shown to be the most stringent for a neutrino telescope over the WIMP masses 25 GeV < M-WIMP < 10TeV.
Keywords: neutrino experiments; dark matter experiments; neutrino astronomy

Seasonal Variations of the Unfolded Atmospheric Neutrino Spectrum with IceCube - Hymon, Karolin; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
The IceCube Neutrino Observatory is a detector array at the South Pole with the central aim of studying astrophysical neutrinos. However, the majority of the detected neutrinos originates from cosmic ray interactions in the atmosphere. The rate of these atmospheric neutrinos shows a seasonal variation indicating that the rate changes with the temperature in the stratosphere. These seasonal changes of the atmospheric neutrino energy spectrum will be investigated using the Dortmund Spectrum Estimation Algorithm (DSEA). Based on results obtained from 10% of IceCube’s atmospheric muon neutrino data, taken between 2011 and 2018, the differences of the measured fluxes during the Austral summer and winter will be discussed.
CRIS-Team Scopus Importer:2024-12-16

Sensitivity for astrophysical neutrino searches with KM3NeT-ORCA - de Wasseige, Gwenhael; Kouchner, Antoine; Molla, Marta Colomer; Dornic, Damien; Hallmann, Steffen (Proceedings of Science, 2019)
The KM3NeT facility, the next generation of large neutrino detectors, is currently being deployed in the Mediterranean Sea. KM3NeT will consist of two ARCA ("Astroparticle Research with Cosmics in the Abyss") building blocks, optimized for very high-energy astrophysical neutrinos, and of the ORCA one ("Oscillation Research with Cosmics in the Abyss"). While ORCA has originally been designed to study neutrino oscillations using atmospheric neutrinos, this dense array may also be used for astrophysical neutrino searches. We present a first estimate of the sensitivity for GeV-100GeV neutrino searches in time/space coincidence with GW alerts sent by the LIGO and Virgo collaborations (LVC). We use the final configuration of ORCA, i.e. ORCA-115 detection units, to estimate the sensitivity of ORCA to gravitational wave events that may be detected by LVC during O3.
CRIS-Team Scopus Importer:2024-12-16

Sensitivity of the KM3NeT/ARCA neutrino telescope to point-like neutrino sources - Aiello, S.; Akrame, S. E.; Ameli, F.; G. Anassontzis, E.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Avgitas, T.; Bagatelas, C.; et al. (Astroparticle Physics, 2019)
KM3NeT will be a network of deep-sea neutrino telescopes in the Mediterranean Sea. The KM3NeT/ARCA detector, to be installed at the Capo Passero site (Italy), is optimised for the detection of high-energy neutrinos of cosmic origin. Thanks to its geographical location on the Northern hemisphere, KM3NeT/ARCA can observe upgoing neutrinos from most of the Galactic Plane, including the Galactic Centre. Given its effective area and excellent pointing resolution, KM3NeT/ARCA will measure or significantly constrain the neutrino flux from potential astrophysical neutrino sources. At the same time, it will test flux predictions based on gamma-ray measurements and the assumption that the gamma-ray flux is of hadronic origin. Assuming this scenario, discovery potentials and sensitivities for a selected list of Galactic sources and to generic point sources with an E −2 spectrum are presented. These spectra are assumed to be time independent. The results indicate that an observation with 3σ significance is possible in about six years of operation for the most intense sources, such as Supernovae Remnants RX J1713.7-3946 and Vela Jr. If no signal will be found during this time, the fraction of the gamma-ray flux coming from hadronic processes can be constrained to be below 50% for these two objects.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Astrophysical neutrino sources; Cherenkov underwater neutrino telescope; KM3NeT

Sensitivity studies for the IceCube-Gen2 radio array - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
The IceCube Neutrino Observatory at the South Pole has measured the diffuse astrophysical neutrino flux up to ∼PeV energies and is starting to identify first point source candidates. The next generation facility, IceCube-Gen2, aims at extending the accessible energy range to EeV in order to measure the continuation of the astrophysical spectrum, to identify neutrino sources, and to search for a cosmogenic neutrino flux. As part of IceCube-Gen2, a radio array is foreseen that is sensitive to detect Askaryan emission of neutrinos beyond ∼30 PeV. Surface and deep antenna stations have different benefits in terms of effective area, resolution, and the capability to reject backgrounds from cosmic-ray air showers and may be combined to reach the best sensitivity. The optimal detector configuration is still to be identified. This contribution presents the full-array simulation efforts for a combination of deep and surface antennas, and compares different design options with respect to their sensitivity to fulfill the science goals of IceCube-Gen2.
CRIS-Team Scopus Importer:2023-08-15

Sensitivity to light sterile neutrino mixing parameters with KM3NeT/ORCA - Aiello, S.; Albert, A.; Alshamsi, M.; Garre, S. Alves; Aly, Z.; Ambrosone, Antonio; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; et al. (Journal of High Energy Physics, 2021)
KM3NeT/ORCA is a next-generation neutrino telescope optimised for atmospheric neutrino oscillations studies. In this paper, the sensitivity of ORCA to the presence of a light sterile neutrino in a 3+1 model is presented. After three years of data taking, ORCA will be able to probe the active-sterile mixing angles theta(14), theta(24), theta(34) and the effective angle theta(mu e), over a broad range of mass squared difference Delta m(41)(2) similar to [10(-5), 10] eV(2), allowing to test the eV-mass sterile neutrino hypothesis as the origin of short baseline anomalies, as well as probing the hypothesis of a very light sterile neutrino, not yet constrained by cosmology. ORCA will be able to explore a relevant fraction of the parameter space not yet reached by present measurements.
CRIS-Team WoS Importer:2021-11-12

Shading Correction for Grating-based Differential Phase Contrast X-ray Imaging - Käppler, Sebastian; Wandner, Johannes; Weber, Thomas; Maier, Andreas; Anton, Gisela; Hornegger, Joachim; Riess, Christian (IEEE Nuclear Science Symposium and Medical Imaging Conference (NSS/MIC), 2014)

Signal decomposition for X-ray dark-field imaging - Käppler, Sebastian; Bayer, Florian; Weber, Thomas; Maier, Andreas; Anton, Gisela; Hornegger, Joachim; Beckmann, Matthias; Fasching, Peter; Hartmann, Arndt; Heindl, Felix; Michel, Thilo; Oezguel, Gueluemser; et al. (MICCAI 2014, 2014)
Grating-based X-ray dark-field imaging is a new imaging modality. It allows the visualization of structures at micrometer scale due to small-angle scattering of the X-ray beam. However, reading darkfield images is challenging as absorption and edge-diffraction effects also contribute to the dark-field signal, without adding diagnostic value. In this paper, we present a novel–and to our knowledge the first–algorithm for isolating small-angle scattering in dark-field images, which greatly improves their interpretability. To this end, our algorithm utilizes the information available from the absorption and differential phase images to identify clinically irrelevant contributions to the dark-field image. Experimental results on phantom and ex-vivo breast data promise a greatly enhanced diagnostic value of dark-field image
EVALuna2:6632

Simulation and sensitivities for a phased IceCube-Gen2 deployment - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
The IceCube Neutrino Observatory opened the window on high-energy neutrino astronomy by confirming the existence of PeV astrophysical neutrinos and identifying the first compelling astrophysical neutrino source in the blazar TXS0506+056. Planning is underway to build an enlarged detector, IceCube-Gen2, which will extend measurements to higher energies, increase the rate of observed cosmic neutrinos and provide improved prospects for detecting fainter sources. IceCube-Gen2 is planned to have an extended in-ice optical array, a radio array at shallower depths for detecting ultra-high-energy (>100 PeV) neutrinos, and a surface component studying cosmic rays. In this contribution, we will discuss the simulation of the in-ice optical component of the baseline design of the IceCube-Gen2 detector, which foresees the deployment of an additional ∼ 120 new detection strings to the existing 86 in IceCube over ∼ 7 Antarctic summer seasons. Motivated by the phased construction plan for IceCube-Gen2, we discuss how the reconstruction capabilities and sensitivities of the instrument are expected to progress throughout its deployment.
CRIS-Team Scopus Importer:2023-08-15

Simulation of charge readout with segmented tiles in nEXO - Li, Z.; Cen, W. R.; Robinson, A.; Moore, D. C.; Wen, L. J.; Odian, A.; Kharusi, S. Al; Anton, Gisela; Arnquist, I. J.; Badhrees, I.; Barbeau, P. S.; Beck, D.; et al. (Journal of Instrumentation, 2019)
nEXO is a proposed experiment to search for the neutrino-less double beta decay (0νββ) of 136Xe in a tonne-scale liquid xenon time projection chamber (TPC) . The nEXO TPC will be equipped with charge collection tiles to form the anode. In this work, the charge reconstruction performance of this anode design is studied with a dedicated simulation package. A multi-variate method and a deep neural network are developed to distinguish simulated 0νββ signals from backgrounds arising from trace levels of natural radioactivity in the detector materials. These simulations indicate that the nEXO TPC with charge-collection tiles shows promising capability to discriminate the 0νββ signal from backgrounds. The estimated half-life sensitivity for 0νββ decay is improved by ∼20 (32)% with the multi-variate (deep neural network) methods considered here, relative to the sensitivity estimated in the nEXO pre-conceptual design report.
CRIS-Team Scopus Importer:2019-11-08
Keywords: Double-beta decay detectors; Noble liquid detectors (scintillation; ionization; doublephase)

Simulation study for the future IceCube-Gen2 surface array - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
The next generation of the IceCube Neutrino Observatory, IceCube-Gen2, will constitute a much larger detector, increasing the rate of high-energy neutrinos. IceCube-Gen2 will address the long-standing questions about astrophysical accelerators. The experiment will also include a surface air-shower detector which will allow for measurements of cosmic rays in the energy region where a transition between Galactic and extragalactic accelerators is expected. As a baseline design for the surface detector, we consider a surface array above the optical in-ice array consisting of the same type of stations used for the IceTop enhancement, i.e., scintillation detectors and radio antennas. In order to better understand the capabilities of such an array, we performed simulations of its response to air showers, including both detector types. We will show the results of this simulation study and discuss the prospects for the surface array of IceCube-Gen2.
CRIS-Team Scopus Importer:2023-08-15

Simulation Study of the Observed Radio Emission of Air Showers by the IceTop Surface Extension - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Proceedings of Science, 2022)
Multi-detector observations of individual air showers are critical to make significant progress to precisely determine cosmic-ray quantities such as mass and energy of individual events and thus bring us a step forward in answering the open questions in cosmic-ray physics. An enhancement of IceTop, the surface array of the IceCube Neutrino Observatory, is currently underway and includes adding antennas and scintillators to the existing array of ice-Cherenkov tanks. The radio component will improve the characterization of the primary particles by providing an estimation of Xmax and a direct sampling of the electromagnetic cascade, both important for per-event mass classification. A prototype station has been operated at the South Pole and has observed showers, simultaneously, with the tanks, scintillator panels, and antennas. The observed radio signals of these events are unique as they are measured in the 70 to 350 MHz band, higher than many other cosmic-ray experiments. We present a comparison of the detected events with the waveforms from CoREAS simulations, convoluted with the end-to-end electronics response, as a verification of the analysis chain. Using the detector response and the measurements of the prototype station as input, we update a Monte-Carlo-based study on the potential of the enhanced surface array for the hybrid detection of air showers by scintillators and radio antennas.
CRIS-Team Scopus Importer:2024-12-16

Simulation study on X-ray phase contrast imaging with dual-phase gratings - Bopp, Johannes; Ludwig, Veronika; Seifert, Maria; Pelzer, Georg; Maier, Andreas; Anton, Gisela; Riess, Christian (International Journal of Computer Assisted Radiology and Surgery, 2019)
Keywords: Dual-phase grating; Grating-based interferometry; Phase contrast imaging; Talbot–Lau

Simultaneous multiwavelength observations of the second exceptional γ-ray flare of PKS 2155-304 in July 2006 - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astronomy & Astrophysics, 2009)
Keywords: galaxies: active; galaxies: BL Lacertae objects: individual: PKS 2155-304; gamma rays: observations; X-rays: galaxies

Simultaneous observations of pks 2155-304 with hess, fermi, rxte, and atom: Spectral energy distributions and variability in a low state - van Eldik, Christopher; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astrophysical Journal, 2009)
We report on the first simultaneous observations that cover the optical, X-ray, and high-energy gamma-ray bands of the BL Lac object PKS2155-304. The gamma-ray bands were observed for 11 days, between 2008 August 25 and 2008 September 6 (MJD 54704-54715), jointly with the Fermi Gamma-ray Space Telescope and the HESS atmospheric Cherenkov array, providing the first simultaneous MeV-TeV spectral energy distribution (SED) with the new generation of γ-ray telescopes. The ATOM telescope and the RXTE and Swift observatories provided optical and X-ray coverage of the low-energy component over the same time period. The object was close to the lowest archival X-ray and very high energy (VHE; >100 GeV) state, whereas the optical flux was much higher. The light curves show relatively little (30%) variability overall when compared to past flaring episodes, but we find a clear optical/VHE correlation and evidence for a correlation of the X-rays with the high-energy spectral index. Contrary to previous observations in the flaring state, we do not find any correlation between the X-ray and VHE components. Although synchrotron self-Compton models are often invoked to explain the SEDs of BL Lac objects, the most common versions of these models are at odds with the correlated variability we find in the various bands for PKS2155-304. © 2009. The American Astronomical Society. All rights reserved.
Keywords: BL Lacertae objects: individual (PKS 2155-304); Galaxies: active; Gamma rays: observations

Single-exposure X-ray phase imaging microscopy with a grating interferometer - Wolf, Andreas; Akstaller, Bernhard; Cipiccia, Silvia; Flenner, Silja; Hagemann, Johannes; Ludwig, Veronika; Meyer, Pascal; Schropp, Andreas; Schuster, Max; Seifert, Maria; Weule, Mareike; Michel, Thilo; et al. (Journal of Synchrotron Radiation, 2022)
The advent of hard X-ray free-electron lasers enables nanoscopic X-ray imaging with sub-picosecond temporal resolution. X-ray grating interferometry offers a phase-sensitive full-field imaging technique where the phase retrieval can be carried out from a single exposure alone. Thus, the method is attractive for imaging applications at X-ray free-electron lasers where intrinsic pulse-to-pulse fluctuations pose a major challenge. In this work, the single-exposure phase imaging capabilities of grating interferometry are characterized by an implementation at the I13-1 beamline of Diamond Light Source (Oxfordshire, UK). For comparison purposes, propagation-based phase contrast imaging was also performed at the same instrument. The characterization is carried out in terms of the quantitativeness and the contrast-to-noise ratio of the phase reconstructions as well as via the achievable spatial resolution. By using a statistical image reconstruction scheme, previous limitations of grating interferometry regarding the spatial resolution can be mitigated as well as the experimental applicability of the technique.
CRIS-Team Scopus Importer:2022-05-27
Keywords: grating interferometry; phase contrast X-ray imaging; phase retrieval; X-ray microscopy

Single-shot grating-based phase-contrast imaging of a micrometer sample at a laser-driven x-ray backlighter source - Akstaller, Bernhard; Schreiner, Stephan; Hofmann, Fabian; Meyer, P.; Neumayer, P.; Schuster, Max; Wolf, Andreas; Zielbauer, B.; Ludwig, Veronika; Michel, Thilo; Anton, Gisela; Funk, Stefan (Journal of Instrumentation, 2021)
A single-shot x-ray phase-contrast imaging technique with short exposure time allows to capture sharp images of fast dynamic processes despite low absorption contrast. We demonstrate the capabilities of a robust single-shot grating-based phase-contrast imaging setup at the Petawatt High-Energy Laser for Heavy Ion EXperiments (PHELIX) at the GSI Helmholtzzentrum für Schwerionenforschung GmbH. A static test sample was imaged at 47-fold magnification using a laser-driven high-energy x-ray backlighter source. The retrieved transmission and phase-contrast images yield reproducible results. The reconstructed differential phase-images are quantitatively explained. In addition to the phase-images, propagation signatures are found in the data and used for result verification. The obtained results demonstrate the capabilities of the grating setup which can be used to image microscopic dynamic processes in high-energy density plasma experiments at PHELIX or similar high-power laser facilities.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Inspection with x-rays; Plasma diagnostics - interferometry; spectroscopy and imaging; X-ray radiography and digital radiography (DR)

Spectral analysis and interpretation of the γ-ray emission from the starburst galaxy NGC253 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Astrophysical Journal, 2012)
Very high energy (VHE; E ≥ 100 GeV) and high-energy (HE; 100 MeV ≤ E ≤ 100 GeV) data from γ-ray observations performed with the H.E.S.S. telescope array and the Fermi-LAT instrument, respectively, are analyzed in order to investigate the non-thermal processes in the starburst galaxy NGC253. The VHE γ-ray data can be described by a power law in energy with differential photon index Γ = 2.14 ± 0.18 ± 0.30 and differential flux normalization at 1TeV of F = (9.6 ± 1.5(+ 5.7, -2.9)) × 10 TeV cm s. A power-law fit to the differential HE γ-ray spectrum reveals a photon index of Γ = 2.24 ± 0.14 ± 0.03 and an integral flux between 200MeV and 200GeV of F(0.2-200 GeV) = (4.9 ± 1.0 ± 0.3) × 10 cm s. No evidence for a spectral break or turnover is found over the dynamic range of both the LAT instrument and the H.E.S.S. experiment: a combined fit of a power law to the HE and VHE γ-ray data results in a differential photon index Γ = 2.34 ± 0.03 with a p-value of 30%. The γ-ray observations indicate that at least about 20% of the energy of the cosmic rays (CRs) capable of producing hadronic interactions is channeled into pion production. The smooth alignment between the spectra in the HE and VHE γ-ray domain suggests that the same transport processes dominate in the entire energy range. Advection is most likely responsible for charged particle removal from the starburst nucleus from GeV to multiple TeV energies. In a hadronic scenario for the γ-ray production, the single overall power-law spectrum observed would therefore correspond to the mean energy spectrum produced by the ensemble of CR sources in the starburst region. © 2012. The American Astronomical Society. All rights reserved.
Keywords: convection; diffusion; galaxies: individual (NGC 253); galaxies: starburst; gamma rays: galaxies; radiation mechanisms: non-thermal

Spectrum and variability of the Galactic center VHE γ-ray source HESS J1745-290 - van Eldik, Christopher; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astronomy & Astrophysics, 2009)
Aims. A detailed study of the spectrum and variability of the source HESS J1745-290 in the Galactic Center (GC) region using new data from the H.E.S.S. array of Cherenkov telescopes is presented. Flaring activity and quasi periodic oscillations (QPO) of HESS J1745-290 are investigated. Methods. The image analysis is performed with a combination of a semi-analytical shower model and the statistical moment-based Hillas technique. The spectrum and lightcurves of HESS J1745-290 are derived with a likelihood method based on a spectral shape hypothesis. Rayleigh tests and Fourier analysis of the H.E.S.S. GC signal are used to study the periodicity of the source. Results. With a three-fold increase in statistics compared to previous work, a deviation from a simple power law spectrum is detected for the first time. The measured energy spectrum over the three years 2004, 2005 and 2006 of data taking is compatible with both a power law spectrum with an exponential cut-off and a broken power law spectrum. The curvature of the energy spectrum is likely to be intrinsic to the photon source, as opposed to effects of interstellar absorption. The power law spectrum with an exponential cut-off is characterized by a photon index of 2.10 ± 0.04 ± 0.10 and a cut-off energy at 15.7 ± 3.4±2.5 TeV. The broken power law spectrum exhibits spectral indices of 2.02 ± 0.08 ± 0.10 and 2.63 ± 0.14 ± 0.10 with a break energy at 2.57 ± 0.19stat ± 0.44 TeV. No significant flux variation is found. Increases in the γ-ray flux of HESS J1745-290 by at least a factor of two would be required for a 3cr detection of a flare with time scales of an hour. Investigation of possible QPO activity at periods claimed to be detected in X-rays does not show any periodicities in the H.E.S.S. signal. © ESO 2009.
Keywords: Galaxy: center; gamma rays: observations; methods: data analysis

Sperm whale long-range echolocation sounds revealed by ANTARES, a deep-sea neutrino telescope - Andre, Michel; Caballe, A.; Van Der Schaar, M.; Solsona, A.; Houegnigan, L.; Zaugg, S.; Sanchez, A. M.; Castell, J. V.; Sole, Marta; Vila, F.; Djokic, D.; Adrian-Martinez, S.; et al. (Scientific Reports, 2017)
Despite dedicated research has been carried out to adequately map the distribution of the sperm whale in the Mediterranean Sea, unlike other regions of the world, the species population status is still presently uncertain. The analysis of two years of continuous acoustic data provided by the ANTARES neutrino telescope revealed the year-round presence of sperm whales in the Ligurian Sea, probably associated with the availability of cephalopods in the region. The presence of the Ligurian Sea sperm whales was demonstrated through the real-time analysis of audio data streamed from a cabled-to-shore deep-sea observatory that allowed the hourly tracking of their long-range echolocation behaviour on the Internet. Interestingly, the same acoustic analysis indicated that the occurrence of surface shipping noise would apparently not condition the foraging behaviour of the sperm whale in the area, since shipping noise was almost always present when sperm whales were acoustically detected. The continuous presence of the sperm whale in the region confirms the ecological value of the Ligurian sea and the importance of ANTARES to help monitoring its ecosystems.

Status and perspectives of vacuum-based photon detectors - Lehmann, Albert (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2023)
In this overview article vacuum-based photon detectors are reviewed emphasizing their applications in Cherenkov imaging devices. After the discussion of the basic detector stages such as photo cathode, electron multiplication, and (anode) readout, the status and recent progress with single- and multi-anode dynode photomultipliers (PMTs), hybrid (avalanche) photodetectors and microchannel-plate PMTs are presented. For all of these devices selected examples of their current and planned applications in neutrino, astroparticle, and high energy physics experiments are given. Possible future developments and innovations are also debated. The last part of this review is dedicated to a comparison of important performance parameters like particle detection efficiency, gain inside a magnetic field, rate capability, aging and lifetime issues, and radiation tolerance.
CRIS-Team Scopus Importer:2023-08-25
Keywords: DIRC detectors; Dynode photomultipliers (PMTs); Hybrid photodetectors; Microchannel-plate PMTs; RICH detectors

Status of the PANDA Barrel DIRC - Schwarz, C.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwiening, J.; Traxler, M.; Schmitt, L.; et al. (Journal of Instrumentation, 2020)
The PANDA experiment will use cooled antiproton beams with high intensity stored in the High Energy Storage Ring at FAIR. Reactions on a fixed target producing charmed hadrons will shed light on the strong QCD. Three ring imaging Cherenkov counters are used for charged particle identification. The status of the Barrel DIRC (Detection of Internally Reflected Cherenkov light) is described. Its design is robust and its performance validated in experiments with test beams. The PANDA Barrel DIRC has entered the construction phase and will be installed in 2023/2024.
CRIS-Team WoS Importer:2020-05-08

Status of the PANDA Endcap Disc DIRC project - Koeseoglu,; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Schwiening, J.; Traxler, M.; et al. (Journal of Instrumentation, 2020)
The PANDA experiment at FAIR near Darmstadt, Germany, is under construction, planned to investigate fundamental questions of hadron physics with a fixed proton target by using an antiproton beam within a momentum range of 1.5 to 15 GeV/c. A novel Cherenkov detector, the Endcap Disc DIRC (EDD), has been developed to separate pi(+/-) and K-+/- by at least 3 standard deviation up to 4 GeV/c. It will cover the polar angle range of the forward endcap of the PANDA target spectrometer from 5 degrees to 22 degrees. The EDD uses a 2 cm thick fused silica radiator plate with focusing elements at the outer rim and lifetime-enhanced Microchannel-PlatePMTs (MCP-PMTs) as light sensors. The Cherenkov radiator of the EDD consists of four identical independent quadrants, polished with highest precision in order to conserve the internally reflected Cherenkov angle during light propagation. This manuscript confirms basic functionalities of the EDD design and tests of the prototype with particle beams at CERN in 2018.
CRIS-Team WoS Importer:2020-05-08

Strong Constraints on Neutrino Nonstandard Interactions from TeV-Scale ν_μ Disappearance at IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alispach, C.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; et al. (Physical Review Letters, 2022)
We report a search for nonstandard neutrino interactions (NSI) using eight years of TeV-scale atmospheric muon neutrino data from the IceCube Neutrino Observatory. By reconstructing incident energies and zenith angles for atmospheric neutrino events, this analysis presents unified confidence intervals for the NSI parameter ε_μτ. The best-fit value is consistent with no NSI at a p value of 25.2%. With a 90% confidence interval of -0.0041≤ε_μτ≤0.0031 along the real axis and similar strength in the complex plane, this result is the strongest constraint on any NSI parameter from any oscillation channel to date.
CRIS-Team Scopus Importer:2022-08-05

Studies of a muon-based mass sensitive parameter for the IceTop surface array - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Proceedings of Science, 2022)
IceTop is the surface instrumentation of the IceCube Neutrino Observatory at the South Pole. It is designed to measure extensive air showers of cosmic rays in the primary energy range from PeV to EeV. Air showers induced by heavier primary particles develop earlier in the atmosphere and produce more muons observable at ground level than lighter cosmic rays with the same primary energy. Therefore, the fraction of muons to all charged particles measured by IceTop characterizes the mass of primary particles. This analysis seeks a muon-based mass sensitive parameter by using the charge signal distribution for each individual cosmic ray event. In this contribution we present the analysis method for the mass-sensitive parameter and our studies of its possible application to the measurement of cosmic ray mass composition with the IceTop surface array.
CRIS-Team Scopus Importer:2024-12-16

Study of the reaction γp → pπ0η - Horn, I.; Anisovich, A. V.; Anton, Gisela; Bantes, R.; Bartholomy, O.; Beck, R.; Beloglazov, Yu.; Bogendörfer, Regina; Castelijns, R.; Credé, V.; Ehmanns, A.; Ernst, J.; et al. (European Physical Journal A, 2008)

Super-ORCA: Measuring the leptonic CP-phase with atmospheric neutrinos and beam neutrinos - Hofestädt, Jannik; Bruchner, Marc; Eberl, Thomas (Proceedings of Science, 2019)
Studying the atmospheric neutrino oscillation probabilities below 2 GeV with a multi-megaton Cherenkov detector allows for a measurement of the leptonic CP-phase dCP. The most relevant CP-sensitive energy range is below the neutrino detection threshold of KM3NeT/ORCA, which is an underwater Cherenkov detector optimised to determine the neutrino mass ordering by measuring the oscillation pattern of 3-30 GeV atmospheric neutrinos. With Super-ORCA, a 10 times more-densely instrumented version of ORCA, the detection threshold can be lowered and the event reconstruction capabilities improved. In this paper, the key detector performance indicators for a possible Super-ORCA detector and the sensitivity to dCP with atmospheric neutrinos are presented. Including systematics, a 1s-resolution on dCP of about 38? (23?) is achieved for dCP = 0 (dCP = p/2) after 10 years. In addition, the potential of using a neutrino beam from the Protvino accelerator facility to the Super-ORCA detector is discussed. With this, a 1s-resolution on dCP of about 10? (16?) is achieved for dCP = 0 (dCP = p/2) after 10 years.
CRIS-Team Scopus Importer:2021-04-20

Systematic approach to measure the performance of microchannel-plate photomultipliers - Lehmann, Albert; Böhm, Merlin; Götz, Klaus; Gumbert, Katja; Krauss, Steffen; Miehling, Daniel; Pfaffinger, Markus (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2024)
In this paper, we present our approach to systematically measure numerous performance parameters of microchannel plate photomultiplier tubes. The experimental setups, the analyses and selected results are discussed. Although the techniques used may be different in other locations, the document is intended as a guide for comparable measurements with other types of microchannel plate photomultiplier tubes. Measurements are shown for the following performance parameters: spectral and spatial quantum efficiency, collection efficiency, gain as a function of voltage, position and magnetic field, time resolution, rate capability and lifetime. By using a dedicated 3-axis stepper and an FPGA-based data acquisition system, also inner PMT parameters are measured as a function of the active area, such as relative detection efficiency, dark count rate, time resolution, recoil electron and afterpulse distributions, as well as charge sharing and electronic crosstalk. In addition, some of the parameters are investigated inside a strong magnetic field. For many of these measurements, the change of most setup parameters and the subsequent analysis can be controlled semi-automatically by software scripts.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Afterpulses; Collection efficiency; Crosstalk; Dark count rate; Gain; Lifetime; Magnetic field; Multianode microchannel-plate PMTs; PANDA; Performance parameters; Quantum efficiency; Rate capability; Recoil electrons; Time resolution

Talbot-Lau X-ray phase contrast for tiling-based acquisitions without reference scanning - Käppler, Sebastian; Seifert, Maria; Horn, Florian; Pelzer, Georg; Rieger, Jens; Michel, Thilo; Maier, Andreas; Anton, Gisela; Riess, Christian (Medical Physics, 2017)
Keywords: grating interferometer; reference image; phase-contrast; x-ray imaging

Talbot-Lau x-ray phase-contrast setup for fast scanning of large samples - Seifert, Maria; Ludwig, Veronika; Käppler, Sebastian; Horn, Florian; Meyer, Pascal; Pelzer, Georg; Rieger, Jens; Sand, Daniel; Michel, Thilo; Mohr, Juergen; Riess, Christian; Anton, Gisela (Scientific Reports, 2019)
Compared to conventional attenuation x-ray radiographic imaging, the x-ray Talbot-Lau technique provides further information about the scattering and the refractive properties of the object in the beam path. Hence, this additional information should improve the diagnostic process concerning medical applications and non-destructive testing. Nevertheless, until now, due to grating fabrication process, Talbot-Lau imaging suffers from small grating sizes (70 mm diameter). This leads to long acquisition times for imaging large objects. Stitching the gratings is one solution. Another one consists of scanning Talbot-Lau setups. In this publication, we present a compact and very fast scanning setup which enables imaging of large samples. With this setup a maximal scanning velocity of 71.7 mm/s is possible. A resolution of 4.1 lines/mm can be achieved. No complex alignment procedures are necessary while the field of view comprises 17.5 x 150 cm2. An improved reconstruction algorithm concerning the scanning approach, which increases robustness with respect to mechanical instabilities, has been developed and is presented. The resolution of the setup in dependence of the scanning velocity is evaluated. The setup imaging qualities are demonstrated using a human knee ex-vivo as an example for a high absorbing human sample.
CRIS-Team WoS Importer:2019-03-29

TANAMI blazars in the IceCube PeV-neutrino fields - Krauß, Felicia; Kadler, Matthias; Mannheim, K.; Schulz, Robert; Truestedt, J.; Wilms, Jörn; Ojha, R.; Ros, Eduardo; Anton, Gisela; Baumgartner, W.; Beuchert, Tobias; Blanchard, J.; et al. (Astronomy & Astrophysics, 2014)
The IceCube Collaboration has announced the discovery of a neutrino flux in excess of the atmospheric background. Owing to the steeply falling atmospheric background spectrum, events at PeV energies most likely have an extraterrestrial origin. We present the multiwavelength properties of the six radio-brightest blazars that are positionally coincident with these events using contemporaneous data of the TANAMI blazar sample, including high-resolution images and spectral energy distributions. Assuming the X-ray to gamma-ray emission originates in the photoproduction of pions by accelerated protons, the integrated predicted neutrino luminosity of these sources is high enough to explain the two detected PeV events.
Keywords: neutrinos; galaxies: active; quasars: general

TANAMI: Tracking Active Galactic Nuclei with Austral Milliarcsecond Interferometry - Mueller, C.; Kadler, M.; Ojha, R.; Schulz, Robert; Truestedt, J.; Edwards, P. G.; Ros, E.; Carpenter, B.; Angioni, R.; Blanchard, J.; Böck, Moritz; Burd, P. R.; et al. (Astronomy & Astrophysics, 2018)
Context. TANAMI is a multiwavelength program monitoring active galactic nuclei (AGN) south of -30 degrees declination including high-resolution very long baseline interferometry (VLBI) imaging, radio, optical/UV, X-ray, and gamma-ray studies. We have previously published first-epoch 8.4 GHz VLBI images of the parsec-scale structure of the initial sample. In this paper, we present images of 39 additional sources. The full sample comprises most of the radio-and gamma-ray brightest AGN in the southern quarter of the sky, overlapping with the region from which high-energy (>100 TeV) neutrino events have been found.Aims. We characterize the parsec-scale radio properties of the jets and compare them with the quasi-simultaneous Fermi/LAT gamma-ray data. Furthermore, we study the jet properties of sources which are in positional coincidence with high-energy neutrino events compared to the full sample. We test the positional agreement of high-energy neutrino events with various AGN samples.Methods. TANAMI VLBI observations at 8.4 GHz are made with southern hemisphere radio telescopes located in Australia, Antarctica, Chile, New Zealand, and South Africa.Results. Our observations yield the first images of many jets below -30 degrees declination at milliarcsecond resolution. We find that gamma-ray loud TANAMI sources tend to be more compact on parsec-scales and have higher core brightness temperatures than gamma-ray faint jets, indicating higher Doppler factors. No significant structural difference is found between sources in positional coincidence with high-energy neutrino events and other TANAMI jets. The 22 gamma-ray brightest AGN in the TANAMI sky show only a weak positional agreement with high-energy neutrinos demonstrating that the >100 TeV IceCube signal is not simply dominated by a small number of the gamma-ray brightest blazars. Instead, a larger number of sources have to contribute to the signal with each individual source having only a small Poisson probability for producing an event in multi-year integrations of current neutrino detectors.
Keywords: galaxies: active; galaxies: jets; galaxies: nuclei; radio continuum: galaxies; techniques: high angular resolution; neutrinos

Technical design report for the (P)over-barANDA Barrel DIRC detector - Singh, B.; Erni, W.; Krusche, B.; Steinacher, M.; Walford, N.; Liu, B.; Liu, H.; Liu, Z.; Shen, X.; Wang, C.; Zhao, J.; Albrecht, M.; et al. (Journal of Physics G: Nuclear and Particle Physics, 2019)
The (P) over bar ANDA (anti-Proton ANnihiliation at DArmstadt) experiment will be one of the four flagship experiments at the new international accelerator complex FAIR (Facility for Antiproton and Ion Research) in Darmstadt, Germany. (P) over bar ANDA will address fundamental questions of hadron physics and quantum chromodynamics using high-intensity cooled antiproton beams with momenta between 1.5 and 15 GeV/c and a design luminosity of up to 2 x 10(32) cm(-2) S-1. Excellent particle identification (PID) is crucial to the success of the (P) over bar ANDA physics program. Hadronic PID in the barrel region of the target spectrometer will be performed by a fast and compact Cherenkov counter using the detection of internally reflected Cherenkov light (DIRC) technology. It is designed to cover the polar angle range from 22 degrees to 140 degrees and will provide at least 3 standard deviations (s.d.) pi/K separation up to 3.5 GeV/c, matching the expected upper limit of the final state kaon momentum distribution from simulation. This documents describes the technical design and the expected performance of the (P) over bar ANDA Barrel DIRC detector. The design is based on the successful BaBar DIRC with several key improvements. The performance and system cost were optimized in detailed detector simulations and validated with full system prototypes using particle beams at GSI and CERN. The final design meets or exceeds the PID goal of clean pi/K separation with at least 3 s.d. over the entire phase space of charged kaons in the Barrel DIRC.
CRIS-Team WoS Importer:2019-03-15

Testing the AGN Radio and Neutrino correlation using the MOJAVE catalog and 10 years of IceCube Data - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Proceedings of Science, 2022)
On 22 September 2017, IceCube reported a high-energy neutrino event which was found to be coincident with a flaring blazar, TXS 0506+056. This multi-messenger observation hinted at blazars contributing to the observed high-energy astrophysical neutrinos and raised a need for extensive correlation studies. Recent work shows that the internal absorption of gamma rays, and their interactions intrinsic to the source and with the extragalactic background, will cause a lack of energetic gamma-ray and neutrino correlation while hinting towards a correlation between neutrinos and lower photon energy observations in the X-ray and radio bands. Studies based on published IceCube alerts and radio observations report a possible radio-neutrino correlation in both gamma-ray bright and gamma-ray dim active galactic nuclei (AGN). However, they have marginal statistical significance due to limited available data. We present a correlation analysis between 15 GHz radio observations of AGN reported in the MOJAVE XV catalog and 10 years of IceCube detector data and discuss the results derived from a time-averaged stacking analysis.
CRIS-Team Scopus Importer:2024-12-16

TeV γ-ray observations of the young synchrotron-dominated SNRs G1.9+0.3 and G330.2+1.0 with H.E.S.S. - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
The non-thermal nature of the X-ray emission from the shell-type supernova remnants (SNRs) G1.9+0.3 and G330.2+1.0 is an indication of intense particle acceleration in the shock fronts of both objects. This suggests that the SNRs are prime candidates for very-high-energy (VHE; E > 0.1 TeV) γ -ray observations. G1.9+0.3, recently established as the youngest known SNR in the Galaxy, also offers a unique opportunity to study the earliest stages of SNR evolution in the VHE domain. The purpose of this work is to probe the level of VHE γ -ray emission from both SNRs and use this to constrain their physical properties. Observations were conducted with the H.E.S.S. (High Energy Stereoscopic System) Cherenkov Telescope Array over a more than six-year period spanning 2004-2010. The obtained data have effective livetimes of 67 h for G1.9+0.3 and 16 h for G330.2+1.0. The data are analysed in the context of the multiwavelength observations currently available and in the framework of both leptonic and hadronic particle acceleration scenarios. No significant γ -ray signal from G1.9+0.3 or G330.2+1.0 was detected. Upper limits (99 per cent confidence level) to the TeV flux from G1.9+0.3 and G330.2+1.0 for the assumed spectral index Γ = 2.5 were set at 5.6 × 10 cm s above 0.26 TeV and 3.2 × 10 cm s above 0.38 TeV, respectively. In a one-zone leptonic scenario, these upper limits imply lower limits on the interior magnetic field to B ≳ 12 μG for G1.9+0.3 and to B ≳ 8 μG for G330.2+1.0. In a hadronic scenario, the low ambient densities and the large distances to the SNRs result in very low predicted fluxes, for which the H.E.S.S. upper limits are not constraining. © 2014 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: Gamma-rays: ISM; ISM: magnetic fields; ISM: supernova remnants; Radiation mechanisms: non-thermal

The 2012 flare of PG 1553+113 seen with H.E.S.S. and Fermi-lat - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, Anna; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astrophysical Journal, 2015)
Very high energy (VHE, E > 100 GeV) γ-ray flaring activity of the high-frequency peaked BL Lac object PG 1553+113 has been detected by the H.E.S.S. telescopes. The flux of the source increased by a factor of 3 during the nights of 2012 April 26 and 27 with respect to the archival measurements with a hint of intra-night variability. No counterpart of this event has been detected in the Fermi-Large Area Telescope data. This pattern is consistent with VHE γ-ray flaring being caused by the injection of ultrarelativistic particles, emitting γ-rays at the highest energies. The dataset offers a unique opportunity to constrain the redshift of this source at z = 0.49 ± 0.04 using a novel method based on Bayesian statistics. The indication of intra-night variability is used to introduce a novel method to probe for a possible Lorentz invariance violation (LIV), and to set limits on the energy scale at which Quantum Gravity (QG) effects causing LIV may arise. For the subluminal case, the derived limits are E,1 > 4.10 × 10 GeV and E,2 > 2.10 × 10 GeV for linear and quadratic LIV effects, respectively.
Keywords: BL Lacertae objects: individual (PG 1553+113); galaxies: active; galaxies: distances and redshifts; gamma-rays: galaxies

The ANTARES telescope neutrino alert system - Ageron, M.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J. -J.; et al. (Astroparticle Physics, 2012)
The ANTARES telescope has the capability to detect neutrinos produced in astrophysical transient sources. Potential sources include gamma-ray bursts, core collapse supernovae, and flaring active galactic nuclei. To enhance the sensitivity of ANTARES to such sources, a new detection method based on coincident observations of neutrinos and optical signals has been developed. A fast online muon track reconstruction is used to trigger a network of small automatic optical telescopes. Such alerts are generated for special events, such as two or more neutrinos, coincident in time and direction, or single neutrinos of very high energy. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino astronomy; Transient sources; Optical follow-up

The cosmic ray shadow of the Moon observed with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Martit, J.; Basa, S.; Belhorma, B.; et al. (European Physical Journal C, 2018)
One of the main objectives of the ANTARES telescope is the search for point- like neutrino sources. Both the pointing accuracy and the angular resolution of the detector are important in this context and a reliableway to evaluate this performance is needed. In order to measure the pointing accuracy of the detector, one possibility is to study the shadow of the Moon, i. e. the deficit of the atmospheric muon flux from the direction of the Moon induced by the absorption of cosmic rays. Analysing the data taken between 2007 and 2016, theMoon shadow is observed with 3.5s statistical significance. The detector angular resolution for downwardgoing muons is 0.73. +/- 0.14.. The resulting pointing performance is consistent with the expectations. An independent check of the telescope pointing accuracy is realised with the data collected by a shower array detector onboard of a ship temporarily moving around the ANTARES location.

The development of a long pine (Pinus wallichiana) chronology from western Nepal from living trees and 14C-dated historic wood samples - Bräuning, Achim; Scharf, Andreas; Kretschmer, Wolfgang; Gierl, Stefanie; Leichmann, Katrin; Burchardt, Iris (TRACE - Tree Rings in Archaeology, Climatology and Ecology, Vol. 9: Proceedings of the DENDROSYMPOSIUM 2010 Scientific Technical Report STR 11/07, GFZ Potsdam, 2011)
UnivIS-Import:2017-12-18:Pub.2011.nat.dgeo.IG.LGIPDT.thedev

The Endcap Disc DIRC detector of PANDA - Föhl, K.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Götzen, K.; Krebs, M.; Lehmann, D.; Nerling, F.; Patsyuk, M.; Peters, K.; Schepers, G.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
At the international FAIR laboratory, an upcoming significant enlargement of the GSI installations near Darmstadt, Germany, the PANDA antiproton experiment will investigate fundamental questions of hadron physics in the charm quark energy range. Antiprotons in the 1.5 to15 GeV/c momentum range will interact with gas jet or pellet fixed targets. The Endcap Disc DIRC (Detection of Internally Reflected Cherenkov light) covers the forward endcap solid angle of the PANDA target spectrometer to positively identify charged kaons. Monte-Carlo simulations indicate that from 1 up to 4 GeV/c one can achieve kaon–pion separation with a separation power of at least 3 standard deviations. For the upcoming CERN test beam in August 2018 the read-out electronics has been upgraded to the TOFPET-ASIC Version 2.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Cherenkov light; DIRC; Particle identification

The endcap disc DIRC for PANDA at FAIR - Schmidt, M.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Schwiening, J.; Traxler, M.; et al. (Nuovo Cimento Della Societa Italiana Di Fisica C, 2019)
The Endcap Disc DIRC for the PANDA experiment is going to provide an excellent particle identification up to particle momenta of 4GeV/c. It covers the polar angles from 5° to 22° and guarantees a separation power of more than 3 standard deviations (s.d.) for pions and kaons in the required phase space. The simulated detector performance has been validated during several testbeam campaigns. Additionally, the transmission losses of the optical filter has been investigated to estimate the filter performance at the end of the PANDA lifetime.
CRIS-Team Scopus Importer:2019-07-19

The energy calibration system for CANDLES using (n, gamma) reaction - Iida, T.; Mizukoshi, K.; Ohata, T.; Uehara, T.; Batpurev, T.; Fushimi, K.; Hazama, R.; Ishikawa, M.; Kakubata, H.; Kanagawa, K.; Katagiri, S.; Khai, B. T.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2021)
Calcium fluoride for the study of Neutrinos and Dark matters by Low-energy Spectrometer (CANDLES) searches for neutrino-less double-beta decay of Ca-48 using a CaF2 scintillator array. A high Q-value of Ca-48 at 4268 keV enabled us to achieve low background, however, at the same time it causes difficulties in calibrating the detector's Q-value region because of the absence of a standard high-energy gamma-ray source. Therefore, we have developed a novel calibration system based on gamma-ray emission by neutron capture on Si-28, Fe-56, and Ni-58 nuclei. In this paper, we report the development of the new calibration system as well as the results of energy calibration in CANDLES up to 9 MeV.
CRIS-Team WoS Importer:2021-01-08

The exceptionally powerful TeV γ-ray emitters in the Large Magellanic Cloud - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, M.; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Becker-Tjus, J.; Berge, D.; et al. (Science, 2015)
The Large Magellanic Cloud, a satellite galaxy of the Milky Way, has been observed with the High Energy Stereoscopic System (H.E.S.S.) above an energy of 100 billion electron volts for a deep exposure of 210 hours. Three sources of different types were detected: the pulsar wind nebula of the most energetic pulsar known, N 157B; the radio-loud supernova remnant N 132D; and the largest nonthermal x-ray shell, the superbubble 30 Dor C. The unique object SN 1987A is, unexpectedly, not detected, which constrains the theoretical framework of particle acceleration in very young supernova remnants. These detections reveal the most energetic tip of a γ-ray source population in an external galaxy and provide via 30 Dor C the unambiguous detection of γ-ray emission from a superbubble.

The EXO-200 detector, part II: Auxiliary systems - Ackerman, N.; Albert, J.; Auger, M.; Auty, D. J.; Badhrees, I.; Barbeau, P. S.; Bartoszek, L.; Baussan, E.; Belov, V.; Benitez-Medina, C.; Bhatta, T.; Breidenbach, M.; et al. (Journal of Instrumentation, 2022)
The EXO-200 experiment searched for neutrinoless double-beta decay of 136Xe with a single-phase liquid xenon detector. It used an active mass of 110 kg of 80.6%-enriched liquid xenon in an ultra-low background time projection chamber with ionization and scintillation detection and readout. This paper describes the design and performance of the various support systems necessary for detector operation, including cryogenics, xenon handling, and controls. Novel features of the system were driven by the need to protect the thin-walled detector chamber containing the liquid xenon, to achieve high chemical purity of the Xe, and to maintain thermal uniformity across the detector.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Cryogenic detectors; Double-beta decay detectors; Liquid detectors; Time projection Chambers (TPC)

THE FIRST COMBINED SEARCH for NEUTRINO POINT-SOURCES in the SOUTHERN HEMISPHERE with the ANTARES and ICECUBE NEUTRINO TELESCOPES - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bormuth, R.; et al. (Astrophysical Journal, 2016)
We present the results of searches for point-like sources of neutrinos based on the first combined analysis of data from both the ANTARES and IceCube neutrino telescopes. The combination of both detectors, which differ in size and location, forms a window in the southern sky where the sensitivity to point sources improves by up to a factor of 2 compared with individual analyses. Using data recorded by ANTARES from 2007 to 2012, and by IceCube from 2008 to 2011, we search for sources of neutrino emission both across the southern sky and from a preselected list of candidate objects. No significant excess over background has been found in these searches, and flux upper limits for the candidate sources are presented for E and E power-law spectra with different energy cut-offs.
Keywords: astroparticle physics; neutrinos

The HESS Galactic plane survey - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
We present the results of the most comprehensive survey of the Galactic plane in very high-energy (VHE) gamma-rays, including a public release of Galactic sky maps, a catalog of VHE sources, and the discovery of 16 new sources of VHE gamma-rays. The High Energy Spectroscopic System (H.E.S.S.) Galactic plane survey (HGPS) was a decade-long observation program carried out by the H.E.S.S. I array of Cherenkov telescopes in Namibia from 2004 to 2013. The observations amount to nearly 2700 h of quality-selected data, covering the Galactic plane at longitudes from l = 250 degrees to 65 degrees and latitudes vertical bar b vertical bar <= 3 degrees. In addition to the unprecedented spatial coverage, the HGPS also features a relatively high angular resolution (0.08 degrees approximate to 5 arcmin mean point spread function 68% containment radius), sensitivity (less than or similar to 1.5% Crab flux for point-like sources), and energy range (0.2-100 TeV). We constructed a catalog of VHE gamma-ray sources from the HGPS data set with a systematic procedure for both source detection and characterization of morphology and spectrum. We present this likelihood-based method in detail, including the introduction of a model component to account for unresolved, large-scale emission along the Galactic plane. In total, the resulting HGPS catalog contains 78 VHE sources, of which 14 are not reanalyzed here, for example, due to their complex morphology, namely shell-like sources and the Galactic center region. Where possible, we provide a firm identification of the VHE source or plausible associations with sources in other astronomical catalogs. We also studied the characteristics of the VHE sources with source parameter distributions. 16 new sources were previously unknown or unpublished, and we individually discuss their identifications or possible associations. We firmly identified 31 sources as pulsar wind nebulae (PWNe), supernova remnants (SNRs), composite SNRs, or gamma-ray binaries. Among the 47 sources not yet identified, most of them (36) have possible associations with cataloged objects, notably PWNe and energetic pulsars that could power VHE PWNe.
Keywords: gamma rays: general; surveys; Galaxy: general

The high-energy γ-ray emission of AP Librae - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2015)
The γ-ray spectrum of the low-frequency-peaked BL Lac (LBL) object AP Librae is studied, following the discovery of very-high-energy (VHE; E > 100 GeV) γ-ray emission up to the TeV range by the H.E.S.S. experiment. This makes AP Librae one of the few VHE emitters of the LBL type. The measured spectrum yields a flux of (8.8 ± 1.5stat ± 1.8sys) × 10-12 cm-2 s-1 above 130 GeV and a spectral index of Γ = 2.65 ± 0.19stat ± 0.20sys. This study also makes use of Fermi-LAT observations in the high energy (HE, E> 100 MeV) range, providing the longest continuous light curve (5 years) ever published on this source. The source underwent a flaring event between MJD 56 306-56 376 in the HE range, with a flux increase of a factor of 3.5 in the 14 day bin light curve and no significant variation in spectral shape with respect to the low-flux state. While the H.E.S.S. and (low state) Fermi-LAT fluxes are in good agreement where they overlap, a spectral curvature between the steep VHE spectrum and the Fermi-LAT spectrum is observed. The maximum of the γ-ray emission in the spectral energy distribution is located below the GeV energy range.
Keywords: BL Lacertae objects: individual: AP Librae; Galaxies: active; Gamma rays: galaxies

The innovative design of the endcap disc DIRC detector for PANDA at FAIR - Schmidt, M.; Duren, M.; Etzelmüller, E.; Föhl, K.; Hayrapetyan, A.; Köseoglu, I.; Kreutzfeld, K.; Rieke, J.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; et al. (Proceedings of the 2019 Meeting of the Division of Particles and Fields of the American Physical Society, DPF 2019, 2019)
The key component of the future PANDA experiment at FAIR is a fixed-target detector for collisions of antiprotons with a proton target up to a beam momentum of 15 GeV/c and is designed to address a large number of open questions in the hadron physics sector. In order to guarantee an excellent PID for charged hadrons in the polar angle range between 5° and 22°, a new type of Cherenkov detector called Endcap Disc DIRC (EDD) has been developed for the forward endcap of the PANDA target spectrometer. The desired separation power of at least 3 s.d. for the separation of π± and K± up to particle momenta of 4 GeV/c was determined with simulation studies and validated during various testbeam campaigns at CERN and DESY.
CRIS-Team Scopus Importer:2021-04-20

The innovative design of the PANDA Barrel DIRC - Schepers, G.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schwarz, C.; Schwiening, J.; Traxler, M.; Schmitt, L.; et al. (Nuovo Cimento Della Societa Italiana Di Fisica C, 2019)
The Barrel DIRC of the PANDA experiment at FAIR will cleanly separate pions from kaons for the physics program of PANDA. Innovative solutions for key components of the detector sitting in the strong magnetic field of the compact PANDA target spectrometer as well as two reconstruction methods were developed in an extensive prototype program. The technical design and present results from the test beam campaigns at the CERN PS in 2017 and 2018 are discussed.
CRIS-Team Scopus Importer:2019-07-19

The KM3NeT potential for the next core-collapse supernova observation with neutrinos: KM3NeT Collaboration - Aiello, S.; Domi, Alba; Albert, A.; Garre, S. Alves; Aly, Z.; Ambrosone, A.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; et al. (European Physical Journal C: Particles and Fields, 2021)
The KM3NeT research infrastructure is under construction in the Mediterranean Sea. It consists of two water Cherenkov neutrino detectors, ARCA and ORCA, aimed at neutrino astrophysics and oscillation research, respectively. Instrumenting a large volume of sea water with ∼ 6200 optical modules comprising a total of ∼ 200 , 000 photomultiplier tubes, KM3NeT will achieve sensitivity to ∼10MeV neutrinos from Galactic and near-Galactic core-collapse supernovae through the observation of coincident hits in photomultipliers above the background. In this paper, the sensitivity of KM3NeT to a supernova explosion is estimated from detailed analyses of background data from the first KM3NeT detection units and simulations of the neutrino signal. The KM3NeT observational horizon (for a 5σ discovery) covers essentially the Milky-Way and for the most optimistic model, extends to the Small Magellanic Cloud (∼60kpc). Detailed studies of the time profile of the neutrino signal allow assessment of the KM3NeT capability to determine the arrival time of the neutrino burst with a few milliseconds precision for sources up to 5–8 kpc away, and detecting the peculiar signature of the standing accretion shock instability if the core-collapse supernova explosion happens closer than 3–5 kpc, depending on the progenitor mass. KM3NeT’s capability to measure the neutrino flux spectral parameters is also presented.
CRIS-Team Scopus Importer:2021-06-11

The mDOM - A multi-PMT optical module for IceCube-Gen2 - Classen, Lew; Kappes, Alexander; Karg, Timo; Kretzschmann, Axel; Kölpin, Alexander; Lindner, Stefan; Röber, Jürgen (DPG-Verhandlungen, 2016)
Following the discovery of an astrophysical neutrino flux by IceCube in 2013, planning is under way for the next generation neutrino telescope at the South Pole, IceCube-Gen2, which will significantly enhance and expand IceCube’s sensitivity both towards high neutrino energies as well as in the low-energy regime. In the scope of these efforts, a novel multi-PMT optical sensor is being developed which, following the KM3NeT design, consists of an array of several small PMTs inside a transparent pressure vessel. This design provides some significant advantages compared to the conventional single-PMT module design, such as an increased effective area, homogeneous coverage of the full solid angle, and intrinsic angular sensitivity. The talk presents an overview of the project and its current status, featuring hardware development, testing, and simulation efforts.

The PANDA Barrel DIRC - Dzhygadlo, R.; Belias, A.; Gerhardt, A.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Schwiening, J.; Traxler, M.; Wolf, Y.; Schmitt, L.; Böhm, Merlin; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2023)
The PANDA experiment at the international accelerator Facility for Antiproton and Ion Research in Europe (FAIR), Darmstadt, Germany, will address fundamental questions of hadron physics using p̄p annihilations. Excellent Particle Identification (PID) over a large range of solid angles and particle momenta will be essential to meet the objectives of the rich physics program. Charged PID in the target region will be provided by a Barrel DIRC (Detection of Internally Reflected Cherenkov light) counter. The Barrel DIRC, covering the polar angle range of 22–140 degrees, will provide a π/K separation power of at least 3 standard deviations for charged particle momenta up to 3.5 GeV/c. The design of the Barrel DIRC features narrow radiator bars made from synthetic fused silica, an innovative multi-layer spherical lens focusing system, a prism-shaped synthetic fused silica expansion volume, and an array of lifetime-enhanced Microchannel Plate PMTs (MCP-PMTs) to detect the hit location and arrival time of the Cherenkov photons. Detailed Monte-Carlo simulations were performed, and reconstruction methods were developed to study the performance of the system. All critical aspects of the design and the performance were validated with system prototypes in a mixed hadron beam at the CERN PS. In 2020 the PANDA Barrel DIRC project advanced from the design stage to component fabrication. The series production of the fused silica bars was successfully completed in 2021 and delivery of the MCP-PMTs started in May 2022.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Cherenkov counter; DIRC; Particle identification; Ring imaging

The P̄ANDA Barrel Time-of-Flight detector - Zimmermann, S.; Suzuki, K.; Steinschaden, D.; Kratochwil, N.; Nalti, W.; Orth, H.; Schwarz, C.; Lehmann, Albert; Böhm, Merlin; Brinkmann, K. Th (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2020)
The Barrel-Time-of-Flight detector is one of the outer layers in the multi-layer design of the P̄ANDA target spectrometer, covering a polar angle region of 22°<θlab<150°. P̄ANDA, which is being built at the FAIR facility, will use cooled antiprotons on a Hydrogen or nuclei target, to study a variety of topics in hadron physics. The detector is a scintillating tile hodoscope with an SiPM readout. A single unit consists of a 90×30×5 mm3 fast plastic scintillator tile and 3 × 3 mm2 SiPM photosensors on both ends. Four SiPMs are connected in series to overcome the limited sensor size of a single SiPM sensor and to improve the time resolution drastically (100 ps to 50 ps). While the P̄ANDA experiment is equipped with DIRC detectors for PID of faster particles, the Barrel TOF complements the setup by providing additional PID information with a π/K separation of 4 sigma up to the Cherenkov threshold.
CRIS-Team Scopus Importer:2020-01-21
Keywords: Photo detectors; PID

The PANDA barrel-TOF detector at FAIR - Zimmermann, S.; Suzuki, K.; Steinschaden, D.; Kratochwil, N.; Nalti, W.; Orth, H.; Schwarz, C.; Lehmann, Albert; Böhm, Merlin; Brinkmann, K. Th (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
The barrel-Time-of-Flight detector is one of the outer layers of the multi-layer design of the PANDA target spectrometer. PANDA, which is being built at the FAIR facility, will use cooled antiprotons on a fixed Hydrogen or nuclei target, to study broad topics in hadron physics. The detector is designed to achieve a time resolution below 100 ps and provides the interaction times of events as well as the particle ID. The B-TOF is designed with a minimal material budget in mind mainly consisting of 5 mm thin plastic scintillator tiles read out by a serial connection of 4 SiPMs. The signal transmission is embedded in large 16 layer PCB in micro strip lines. We will first review the detector concept which is described in the TDR then some more recent developments, with a study of different PCB layouts for signal transmission, the readout with the TOFPET2 ASIC and its performance and presenting the results of a study on the influence of the scintillator thickness on the time resolution.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Photo detectors; PID

The PANDA DIRC detectors - Etzelmüller, E.; Schwiening, J.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Traxler, M.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
The PANDA experiment at the future Facility for Antiproton and Ion Research (FAIR) will address fundamental questions of hadron physics with unprecedented precision. To reach this goal excellent Particle Identification (PID) is essential over a large range of particle momenta and solid angles. Most of the phase space will be covered by two innovative DIRC (Detection of Internally Reflected Cherenkov light) detectors. The Endcap Disc DIRC and Barrel DIRC will cover the polar angle range from 5 to 22°and 22 to 140° respectively. Both detectors rely on high precision optical components, lifetime-enhanced Microchannel Plate PMTs (MCP-PMTs), and fast readout electronics.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Cherenkov detector; DIRC; MCP-PMT; Particle identification

The PANDA DIRCs - Schwarz, C.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwiening, J.; Traxler, M.; Schmitt, L.; et al. (Journal of Instrumentation, 2020)
The PANDA experiment at the FAIR facility adresses open questions in hadron physics with antiproton beams in the momentum range of 1.5-15 GeV/c. The antiprotons are stored and cooled in a High Energy Storage RING (HESR) with a momentum spread down to ∆p/p = 4 · 10−5. A high luminosity of up to 2 · 1032 cm−2s−1 can be achieved. An excellent hadronic particle identification (PID) will be provided by two Cherenkov detectors using the priciple of Detection of Internally Reflected Cherenkov light (DIRC). In the forward direction from polar angles of 5◦ to 22◦, the Endcap Disc DIRC (EDD) separates pions from kaons up to momenta of 4 GeV/c. Between 22◦ and 140◦ the Barrel DIRC cleanly separates pions from kaons for momenta up to 3.5 GeV/c. This article describes the design of the Barrel DIRC and of the Endcap Disc DIRC and the validation of their designs in particle beams at the CERN PS.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Cherenkov detectors; Data acquisition concepts; Detector design and construction technologies and materials; Performance of High Energy Physics Detectors

The positioning system of the ANTARES Neutrino Telescope - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; et al. (Journal of Instrumentation, 2012)
The ANTARES neutrino telescope, located 40km off the coast of Toulon in the Mediterranean Sea at a mooring depth of about 2475m, consists of twelve detection lines equipped typically with 25 storeys. Every storey carries three optical modules that detect Cherenkov light induced by charged secondary particles (typically muons) coming from neutrino interactions. As these lines are flexible structures fixed to the sea bed and held taut by a buoy, sea currents cause the lines to move and the storeys to rotate. The knowledge of the position of the optical modules with a precision better than 10cm is essential for a good reconstruction of particle tracks. In this paper the ANTARES positioning system is described. It consists of an acoustic positioning system, for distance triangulation, and a compass-tiltmeter system, for the measurement of the orientation and inclination of the storeys. Necessary corrections are discussed and the results of the detector alignment procedure are described.
Keywords: Timing detectors; Detector modelling and simulations II (electric fields; charge transport; multiplication and induction; pulse formation; electron emission; etc); Detector alignment and calibration methods (lasers; sources; particle-beams); Detector control systems (detector and experiment monitoring and slow-control systems; architecture; hardware; algorithms; databases)

The prototype detection unit of the KM3NeT detector: KM3NeT Collaboration - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Androulakis, G. C.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, M.; et al. (European Physical Journal C: Particles and Fields, 2016)
A prototype detection unit of the KM3NeT deep-sea neutrino telescope has been installed at 3500m depth 80 km offshore the Italian coast. KM3NeT in its final configuration will contain several hundreds of detection units. Each detection unit is a mechanical structure anchored to the sea floor, held vertical by a submerged buoy and supporting optical modules for the detection of Cherenkov light emitted by charged secondary particles emerging from neutrino interactions. This prototype string implements three optical modules with 31 photomultiplier tubes each. These optical modules were developed by the KM3NeT Collaboration to enhance the detection capability of neutrino interactions. The prototype detection unit was operated since its deployment in May 2014 until its decommissioning in July 2015. Reconstruction of the particle trajectories from the data requires a nanosecond accuracy in the time calibration. A procedure for relative time calibration of the photomultiplier tubes contained in each optical module is described. This procedure is based on the measured coincidences produced in the sea by the ^4040K background light and can easily be expanded to a detector with several thousands of optical modules. The time offsets between the different optical modules are obtained using LED nanobeacons mounted inside them. A set of data corresponding to 600 h of livetime was analysed. The results show good agreement with Monte Carlo simulations of the expected optical background and the signal from atmospheric muons. An almost background-free sample of muons was selected by filtering the time correlated signals on all the three optical modules. The zenith angle of the selected muons was reconstructed with a precision of about 3^° ∘.

Thermo-acoustic sound generation in the interaction of pulsed proton and laser beams with a water target - Lahmann, Robert; Anton, Gisela; Graf, Kay; Hossl, J.; Kappes, Alexander; Katz, Uli; Mecke, Klaus; Schwemmer, S. (Astroparticle Physics, 2015)
The generation of hydrodynamic radiation in interactions of pulsed proton and laser beams with matter is explored. The beams were directed into a water target and the resulting acoustic signals were recorded with pressure sensitive sensors. Measurements were performed with varying pulse energies, sensor positions, beam diameters and temperatures. The obtained data are matched by simulation results based on the thermo-acoustic model with uncertainties at a level of 10%. The results imply that the primary mechanism for sound generation by the energy deposition of particles propagating in water is the local heating of the medium. The heating results in a fast expansion or contraction and a pressure pulse of bipolar shape is emitted into the surrounding medium. An interesting, widely discussed application of this effect could be the detection of ultra-high energetic cosmic neutrinos in future large-scale acoustic neutrino detectors. For this application a validation of the sound generation mechanism to high accuracy, as achieved with the experiments discussed in this article, is of high importance.
Keywords: Acoustic neutrino detection; Beam interaction; Cosmic neutrinos; Thermo-acoustic model; Ultra-high energy cosmic rays

The search for high-energy neutrinos coincident with fast radio bursts with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
In the past decade, a new class of bright transient radio sources with millisecond duration has been discovered. The origin of these so-called fast radio bursts (FRBs) is still a mystery, despite the growing observational efforts made by various multiwavelength and multimessenger facilities. To date, many models have been proposed to explain FRBs, but neither the progenitors nor the radiative and the particle acceleration processes at work have been clearly identified. In this paper, we assess whether hadronic processes may occur in the vicinity of the FRB source. If they do, FRBs may contribute to the high-energy cosmic-ray and neutrino fluxes. A search for these hadronic signatures was carried out using the ANTARES neutrino telescope. The analysis consists in looking for high-energy neutrinos, in the TeV-PeV regime, that are spatially and temporally coincident with the detected FRBs. Most of the FRBs discovered in the period 2013-2017 were in the field of view of the ANTARES detector, which is sensitive mostly to events originating from the Southern hemisphere. From this period, 12 FRBs were selected and no coincident neutrino candidate was observed. Upper limits on the per-burst neutrino fluence were derived using a power-law spectrum, dN/DE nu proportional to E-nu(-gamma), for the incoming neutrino flux, assuming spectral indexes gamma = 1.0, 2.0, 2.5. Finally, the neutrino energy was constrained by computing the total energy radiated in neutrinos, assuming different distances for the FRBs. Constraints on the neutrino fluence and on the energy released were derived from the associated null results.
Keywords: acceleration of particles; neutrinos; astroparticle physics; radio continuum: transients; methods: data analysis

The Search for Neutrinos from TXS 0506+056 with the ANTARES Telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Astrophysical Journal Letters, 2018)
The results of three different searches for neutrino candidates, associated with the IceCube-170922A event or from the direction of TXS 0506+056, by the ANTARES neutrino telescope, are presented. The first search refers to the online follow-up of the IceCube alert; the second is based on the standard time-integrated method employed by the Collaboration to search for point-like neutrino sources; the third uses information from the IceCube time-dependent analysis that reported bursting activity centered on 2014 December 13, as input for an ANTARES time-dependent analysis. The online follow-up and the time-dependent analysis yield no events related to the source. The time-integrated study performed over a period from 2007 to 2017 fits 1.03 signal events, which corresponds to a p-value of 3.4% (not considering trial factors). Only for two other astrophysical objects in our candidate list has a smaller p-value been found. When considering that 107 sources have been investigated, the post-trial p-value for TXS 0506+056 corresponds to 87%.
Keywords: astroparticle physics; elementary particles; galaxies: active

The SkyLLH framework for IceCube point-source search - Kontrimas, Tomas; Wolf, Martin; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; et al. (Proceedings of Science, 2022)
Hypothesis tests based on unbinned log-likelihood (LLH) functions are a common technique used in multi-messenger astronomy, including IceCube’s neutrino point-source searches. We present the general Python-based tool "SkyLLH", which provides a modular framework for implementing and executing log-likelihood functions to perform data analyses with multi-messenger astronomy data. Specific SkyLLH framework features for a new and improved time-integrated IceCube point-source analysis are highlighted, including the support for kernel density estimation (KDE) based probability density functions. In addition, the support for a variety of point-source analysis types, such as stacked and time-variable searches, will be presented.
CRIS-Team Scopus Importer:2024-12-16

The Surface Array planned for IceCube-Gen2 - Schröder, Frank G.; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Alves, A. A.; Amin, N. M.; An, R.; et al. (Proceedings of Science, 2022)
IceCube-Gen2, the extension of the IceCube Neutrino Observatory, will feature three main components: an optical array in the deep ice, a large-scale radio array in the shallow ice and firn, and a surface detector above the optical array. Thus, IceCube-Gen2 will not only be an excellent detector for PeV neutrinos, but also constitutes a unique setup for the measurement of cosmic-ray air showers, where the electromagnetic component and low-energy muons are measured at the surface and high-energy muons are measured in the ice. As for ongoing enhancement of IceCube's current surface array, IceTop, we foresee a combination of elevated scintillation and radio detectors for the Gen2 surface array, aiming at high measurement accuracy for air showers. The science goals are manifold: The in-situ measurement of the cosmic-ray flux and mass composition, as well as more thorough tests of hadronic interaction models, will improve the understanding of muons and atmospheric neutrinos detected in the ice, in particular, regarding prompt muons. Moreover, the surface array provides a cosmic-ray veto for the in-ice detector and contributes to the calibration of the optical and radio arrays. Last but not least, the surface array will make major contributions to cosmic-ray science in the energy range of the transition from Galactic to extragalactic sources. The increased sensitivities for photons and for cosmic-ray anisotropies at multi-PeV energies provide a chance to solve the puzzle of the origin of the most energetic Galactic cosmic rays and will serve IceCube's multimessenger mission.
CRIS-Team Scopus Importer:2023-08-15

The SUrvey for Pulsars and Extragalactic Radio Bursts - II. New FRB discoveries and their follow-up - Bhandari, S.; Keane, E. F.; Barr, E. D.; Jameson, A.; Petroff, E.; Johnston, Simon; Bailes, Matthew; Bhat, N. D. R.; Burgay, M.; Burke-Spolaor, S.; Caleb, M.; Eatough, R. P.; et al. (Monthly Notices of the Royal Astronomical Society, 2018)
We report the discovery of four Fast Radio Bursts (FRBs) in the ongoing SUrvey for Pulsars and Extragalactic Radio Bursts at the Parkes Radio Telescope: FRBs 150610, 151206, 151230 and 160102. Our real-time discoveries have enabled us to conduct extensive, rapid multimessenger follow-up at 12 major facilities sensitive to radio, optical, X-ray, gamma-ray photons and neutrinos on time-scales ranging from an hour to a few months post-burst. No counterparts to the FRBs were found and we provide upper limits on afterglow luminosities. None of the FRBs were seen to repeat. Formal fits to all FRBs show hints of scattering while their intrinsic widths are unresolved in time. FRB 151206 is at low Galactic latitude, FRB 151230 shows a sharp spectral cut-off, and FRB 160102 has the highest dispersion measure (DM = 2596.1 +/- 0.3 pc cm(-3)) detected to date. Three of the FRBs have high dispersion measures (DM > 1500 pc cm(-3)), favouring a scenario where the DMis dominated by contributions from the intergalactic medium. The slope of the Parkes FRB source counts distribution with fluences > 2 Jy ms is alpha = - 2.2(-1.2)(+0.6) and still consistent with a Euclidean distribution (alpha = -3/2). We also find that the all-sky rate is 1.7(-0.9)(+1.5) x 10(3)FRBs/(4 pi sr)/day above similar to 2 Jy ms and there is currently no strong evidence for a latitude- dependent FRB sky rate.
Keywords: radiation mechanisms: general; methods: data analysis; methods: observational; surveys; intergalactic medium; radio continuum: general

The Wavelength-Shifting Optical Module in Application to the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
The Wavelength-shifting Optical Module (WOM) is a novel photosensor concept developed as part of the upcoming Upgrade for the IceCube Neutrino Observatory. It uses the technique of wavelength shifting and total internal reflection to increase the photon light yield in the UV-regime of the Cherenkov spectrum. The decoupling of the effective area from the size of light sensors enhances the signal-to-noise-ratio. Twelve WOM modules will be deployed in the IceCube Upgrade to increase the photon detection efficiency and thus enhance future low-energy analyses. The general concept can also be applied at the future IceCube-Gen2 detector, where passive light collecting extensions to the optical sensor modules locally increase the light collection efficiency. This technique would benefit the detection of supernova neutrinos or other particles with low light emissions. We report on new results in characterizing and optimizing the WOM concept, the production status of the modules to be deployed in 2025/26 as well as possible applications of the concept for IceCube-Gen2.
CRIS-Team Scopus Importer:2025-02-04

Three-dimensional imaging of xylem at cell wall level through near field nano holotomography - Koddenberg, Tim; Greving, Imke; Hagemann, Johannes; Flenner, Silja; Krause, Andreas; Laipple, Daniel; Klein, Kim C.; Schmitt, Uwe; Schuster, Max; Wolf, Andreas; Seifert, Maria; Ludwig, Veronika; et al. (Scientific Reports, 2021)
Detailed imaging of the three-dimensionally complex architecture of xylary plants is important for studying biological and mechanical functions of woody plants. Apart from common two-dimensional microscopy, X-ray micro-computed tomography has been established as a three-dimensional (3D) imaging method for studying the hydraulic function of wooden plants. However, this X-ray imaging method can barely reach the resolution needed to see the minute structures (e.g. pit membrane). To complement the xylem structure with 3D views at the nanoscale level, X-ray near-field nano-holotomography (NFH) was applied to analyze the wood species Pinus sylvestris and Fagus sylvatica. The demanded small specimens required focused ion beam (FIB) application. The FIB milling, however, influenced the image quality through gallium implantation on the cell-wall surfaces. The measurements indicated that NFH is appropriate for imaging wood at nanometric resolution. With a 26 nm voxel pitch, the structure of the cell-wall surface in Pinus sylvestris could be visualized in genuine detail. In wood of Fagus sylvatica, the structure of a pit pair, including the pit membrane, between two neighboring fibrous cells could be traced tomographically.
CRIS-Team Scopus Importer:2021-03-19

Three-year performance of the IceAct telescopes at the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
IceAct is an array of compact Imaging Air Cherenkov Telescopes at the ice surface as part of the IceCube Neutrino Observatory. The telescopes, featuring a camera of 61 silicon photomultipliers and fresnel-lens-based optics, are optimized to be operated in harsh environmental conditions, such as at the South Pole. Since 2019, the first two telescopes have been operating in a stereoscopic configuration in the center of IceCube’s surface detector IceTop. With an energy threshold of about 10 TeV and a wide field-of-view, the IceAct telescopes show promising capabilities of improving current cosmic-ray composition studies: measuring the Cherenkov light emissions in the atmosphere adds new information about the shower development not accessible with the current detectors. First simulations indicate that the added information of a single telescope leads, e.g., to an improved discrimination between flux contributions from different primary particle species in the sensitive energy range. We review the performance and detector operations of the telescopes during the past 3 years (2020-2022) and give an outlook on the future of IceAct.
CRIS-Team Scopus Importer:2025-02-04

Time calibration with atmospheric muon tracks in the ANTARES neutrino telescope - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Baret, B.; Barrios-Marti, Javier; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Astroparticle Physics, 2016)
The ANTARES experiment consists of an array of photomultipliers distributed along 12 lines and located deep underwater in the Mediterranean Sea. It searches for astrophysical neutrinos collecting the Cherenkov light induced by the charged particles, mainly muons, produced in neutrino interactions around the detector. Since at energies of ∼10 TeV the muon and the incident neutrino are almost collinear, it is possible to use the ANTARES detector as a neutrino telescope and identify a source of neutrinos in the sky starting from a precise reconstruction of the muon trajectory. To get this result, the arrival times of the Cherenkov photons must be accurately measured. A to perform time calibrations with the precision required to have optimal performances of the instrument is described. The reconstructed tracks of the atmospheric muons in the ANTARES detector are used to determine the relative time offsets between photomultipliers. Currently, this method is used to obtain the time calibration constants for photomultipliers on different lines at a precision level of 0.5 ns. It has also been validated for calibrating photomultipliers on the same line, using a system of LEDs and laser light devices.
Keywords: ANTARES; Atmospheric muon tracks; Neutrino Telescopes; Time calibration

Time-dependent search for neutrino emission from X-ray binaries with the ANTARES telescope - Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bormuth, R.; et al. (Journal of Cosmology and Astroparticle Physics, 2017)
ANTARES is currently the largest neutrino telescope operating in the Northern Hemisphere, aiming at the detection of high-energy neutrinos from astrophysical sources. Neutrino telescopes constantly monitor at least one complete hemisphere of the sky, and are thus well-suited to detect neutrinos produced in transient astrophysical sources. A time-dependent search has been applied to a list of 33 X-ray binaries undergoing high flaring activities in satellite data (RXTE/ASM, MAXI and Swift/BAT) and during hardness transition states in the 2008-2012 period. The background originating from interactions of charged cosmic rays in the Earth's atmosphere is drastically reduced by requiring a directional and temporal coincidence with astrophysical phenomena. The results of this search are presented together with comparisons between the neutrino flux upper limits and the neutrino flux predictions from astrophysical models. The neutrino flux upper limits resulting from this search limit the jet parameter space for some astrophysical models.
Keywords: neutrino astronomy; X-ray binaries; X-ray telescopes

Time imaging reconstruction for the PANDA barrel DIRC - Dzhygadlo, R.; Ali, A.; Belias, A.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Schwiening, J.; Traxler, M.; Schmitt, L.; et al. (Journal of Instrumentation, 2020)
The innovative Barrel DIRC (Detection of Internally Reflected Cherenkov light) counter will provide hadronic particle identification (PID) in the central region of the PANDA experiment at the new Facility for Antiproton and Ion Research (FAIR), Darmstadt, Germany. This detector is designed to separate charged pions and kaons with at least 3 standard deviations for momenta up to 3.5 GeV/c, covering the polar angle range of 22◦-140◦. An array of microchannel plate photomultiplier tubes is used to detect the location and arrival time of the Cherenkov photons with a position resolution of 2 mm and time precision of about 100 ps. The time imaging reconstruction has been developed to make optimum use of the observables and to determine the performance of the detector. This reconstruction algorithm performs particle identification by directly calculating the maximum likelihoods using probability density functions based on detected photon propagation time in each pixel, determined directly from the data, or analytically, or from detailed simulations.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Cherenkov detectors; Particle identification methods

Time-Integrated Neutrino Source Searches with 10 Years of IceCube Data - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Arguelles, C.; et al. (Physical Review Letters, 2020)
This Letter presents the results from pointlike neutrino source searches using ten years of IceCube data collected between April 6, 2008 and July 10, 2018. We evaluate the significance of an astrophysical signal from a pointlike source looking for an excess of clustered neutrino events with energies typically above similar to 1 TeV among the background of atmospheric muons and neutrinos. We perform a full-sky scan, a search within a selected source catalog, a catalog population study, and three stacked Galactic catalog searches.
CRIS-Team WoS Importer:2020-02-21

Towards a dual phase grating interferometer on clinical hardware - Bopp, Johannes; Ludwig, Veronika; Gallersdörfer, Michael; Seifert, Maria; Pelzer, Georg; Maier, Andreas; Anton, Gisela; Riess, Christian (Medical Imaging 2018: Physics of Medical Imaging, 2018)
Keywords: Phase contrast imaging; Talbot-Lau; Dual phase grating; Grating based interferometry

Towards cartilage diagnosis in X-ray phase-contrast interferometry - Bopp, Johannes; Bartl, Peter; Ritschl, Ludwig; Radicke, Marcus; Maier, Andreas; Anton, Gisela; Riess, Christian (14th IEEE International Symposium on Biomedical Imaging, 2017)

Towards Equitable, Diverse, and Inclusive science collaborations: The Multimessenger Diversity Network - Bechtol, E.; Bechtol, K.; BenZvi, S.; Bleve, C.; Castro, D.; Cenko, B.; Corlies, L.; Furniss, A.; Hui, C. M.; Kaplan, D. L.; Key, J. S.; Madsen, J.; et al. (Proceedings of Science, 2022)
The Multimessenger Diversity Network (MDN), formed in 2018, extends the basic principle of multimessenger astronomy - that working collaboratively with different approaches enhances understanding and enables previously impossible discoveries - to equity, diversity, and inclusion (EDI) in science research collaborations. With support from the National Science Foundation INCLUDES program, the MDN focuses on increasing EDI by sharing knowledge, experiences, training, and resources among representatives from multimessenger science collaborations. Representatives to the MDN become engagement leads in their collaboration, extending the reach of the community of practice. An overview of the MDN structure, lessons learned, and how to join are presented.
CRIS-Team Scopus Importer:2024-12-16

Towards quantification of kidney stones using X-ray dark-field tomography - Hu, Shiyang; Yang, F.; Kaufmann, R.; Griffa, M.; Anton, Gisela; Maier, Andreas; Riess, Christian (14th IEEE International Symposium on Biomedical Imaging, 2017)

Treatment of acute myeloid leukemia models by targeting a cell surface RNA-binding protein - George, Benson M.; Eleftheriou, Maria; Yankova, Eliza; Perr, Jonathan; Chai, Peiyuan; Nestola, Gian Luca; Almahayni, Karim; Evans, Siân; Damaskou, Aristi; Hemberger, Helena; Lebedenko, Charlotta G.; Rak, Justyna; et al. (Nature Biotechnology, 2025)
Immunotherapies for acute myeloid leukemia (AML) and other cancers are limited by a lack of tumor-specific targets. Here we discover that RNA-binding proteins and glycosylated RNAs (glycoRNAs) form precisely organized nanodomains on cancer cell surfaces. We characterize nucleophosmin (NPM1) as an abundant cell surface protein (csNPM1) on a variety of tumor types. With a focus on AML, we observe csNPM1 on blasts and leukemic stem cells but not on normal hematopoietic stem cells. We develop a monoclonal antibody to target csNPM1, which exhibits robust anti-tumor activity in multiple syngeneic and xenograft models of AML, including patient-derived xenografts, without observable toxicity. We find that csNPM1 is expressed in a mutation-agnostic manner on primary AML cells and may therefore offer a general strategy for detecting and treating AML. Surface profiling and in vivo work also demonstrate csNPM1 as a target on solid tumors. Our data suggest that csNPM1 and its neighboring glycoRNA–cell surface RNA-binding protein (csRBP) clusters may serve as an alternative antigen class for therapeutic targeting or cell identification.
CRIS-Team Scopus Importer:2025-05-02

Understanding gravitationally induced decoherence parameters in neutrino oscillations using a microscopic quantum mechanical model - Domi, Alba; Eberl, Thomas; Fahn, Max Joseph; Giesel, Kristina; Hennig, Lukas; Katz, Uli; Kemper, Roman; Kobler, Michael (Journal of Cosmology and Astroparticle Physics, 2024)
In this work, a microscopic quantum mechanical model for gravitationally induced decoherence introduced by Blencowe and Xu is investigated in the context of neutrino oscillations. The focus is on the comparison with existing phenomenological models and the physical interpretation of the decoherence parameters in such models. The results show that for neutrino oscillations in vacuum gravitationally induced decoherence can be matched with phenomenological models with decoherence parameters of the form Γij ∼ Δ m 4ij E -2. When matter effects are included, the decoherence parameters exhibit a dependence on the varying matter density across the Earth layers. This behavior can be explained by the nature of the coupling between neutrinos and the gravitational wave environment, as suggested by linearised gravity. On a theoretical level, these different models can be characterised by a different choice of Lindblad operators, with the model with decoherence parameters that do not include matter effects being less suitable from the point of view of linearised gravity. Consequently, in the case of neutrino oscillations in matter, the microscopic model does not agree with many existing phenomenological models that assume constant decoherence parameters in matter. Nonetheless, we identify the KamLAND experimental setup as particularly well-suited to establish the first experimental constraints on the model parameters, namely the neutrino coupling to the gravitational wave environment and its temperature, based on a prior analysis using the phenomenological model.
CRIS-Team Scopus Importer:2024-11-22
Keywords: gravity; neutrino experiments; neutrino theory; solar and atmospheric neutrinos

Unoccupied electronic states in atomic chains on Si(557)-Au: Time-resolved two-photon photoemission investigation - Rügheimer, Tilman; Fauster, Thomas; Himpsel, F. J. (Physical Review B, 2007)
The prototypical one-dimensional Si(557)-Au surface is investigated with time-resolved two-photon photoemission. Three new states are found near (Gamma) over bar, two of them in the band gap of silicon. These states cannot be explained by existing band calculations. As a possible solution, we suggest a closer examination of the atomic and electronic structure near the step edge.

Velocity independent constraints on spin-dependent DM-nucleon interactions from IceCube and PICO - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (European Physical Journal C: Particles and Fields, 2020)
Adopting the Standard Halo Model (SHM) of an isotropic Maxwellian velocity distribution for dark matter (DM) particles in the Galaxy, the most stringent current constraints on their spin-dependent scattering cross-section with nucleons come from the IceCube neutrino observatory and the PICO-60 C 3F 8 superheated bubble chamber experiments. The former is sensitive to high energy neutrinos from the self-annihilation of DM particles captured in the Sun, while the latter looks for nuclear recoil events from DM scattering off nucleons. Although slower DM particles are more likely to be captured by the Sun, the faster ones are more likely to be detected by PICO. Recent N-body simulations suggest significant deviations from the SHM for the smooth halo component of the DM, while observations hint at a dominant fraction of the local DM being in substructures. We use the method of Ferrer et al. (JCAP 1509: 052, 2015) to exploit the complementarity between the two approaches and derive conservative constraints on DM-nucleon scattering. Our results constrain σSD≲ 3 × 10 - 39cm 2 (6 × 10 - 38cm 2) at ≳ 90 % C.L. for a DM particle of mass 1 TeV annihilating into τ+τ- (bb¯) with a local density of ρDM=0.3GeV/cm3. The constraints scale inversely with ρDM and are independent of the DM velocity distribution.
CRIS-Team Scopus Importer:2020-09-18

Very high energy gamma-ray observations of the galaxy clusters Abell 496 and Abell 85 with HESS - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2009)
Aims. The nearby galaxy clusters Abell 496 and Abell 85 are studied in the very high-energy (VHE, 100]]> GeV) band to investigate VHE cosmic rays (CRs) in this class of objects which are the largest gravitationally bound systems in the Universe.Methods. HESS, an array of four imaging atmospheric cherenkov telescopes (IACT), was used to observe the targets in the range of VHE gamma rays.Results. No significant gamma-ray signal is found at the respective position of the two clusters with several different source size assumptions for each target. In particular, emission regions corresponding to the high-density core, to the extension of the entire X-ray emission in these clusters, and to the very extended region where the accretion shock is expected are investigated. Upper limits are derived for the gamma-ray flux at energies 570]]> GeV for Abell 496 and 460]]> GeV for Abell 85.Conclusions. From the non-detection in VHE gamma rays, upper limits on the total energy of hadronic CRs in the clusters are calculated. If the cosmic-ray energy density follows the large-scale gas density profile, the limit on the fraction of energy in these non-thermal particles with respect to the total thermal energy of the intra-cluster medium (ICM) is 51% for Abell 496 and only 8% for Abell 85 due to its higher mass and higher gas density. These upper limits are compared with theoretical estimates. They predict about ∼10% of the thermal energy of the ICM in non-thermal particles. The observations presented here can constrain these predictions especially for the case of the Abell 85 cluster. © 2009 ESO.
Keywords: Galaxies: clusters: individual: Abell 496; Galaxies: clusters: individual: Abell 85; Gamma rays: observations

Very high energy γ-ray observations of the binary PSR B1259-63/SS2883 around the 2007 Periastron - van Eldik, Christopher; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, J.; et al. (Astronomy & Astrophysics, 2009)
Aims. This article presents very-high-energy (VHE; E > 100 GeV) data from the-ray binary PSRB1259-63 as taken during the years 2005, 2006 and before as well as shortly after the 2007 periastron passage. These data extend the knowledge of the lightcurve of this object to all phases of the 3.4 year binary orbit. The lightcurve constrains physical mechanisms present in this TeV source. Methods. Observations of VHE-rays with the HESS telescope array using the Imaging Atmospheric Cherenkov Technique were performed. The HESS instrument features an angular resolution of <0.1° and an energy resolution of <20%. Gamma-ray events in an energy range of 0.5-70 TeV were recorded. From these data, energy spectra and lightcurve with a monthly time sampling were extracted. Results. VHE-ray emission from PSRB1259-63 was detected with an overall significance of 9.5 standard deviations using 55 h of exposure, obtained from April to August 2007. The monthly flux of-rays during the observation period was measured, yielding VHE lightcurve data for the early pre-periastron phase of the system for the first time. No spectral variability was found on timescales of months. The spectrum is described by a power law with a photon index of G = 2.8 ± 0.2stat ± 0.2sys and flux normalisation F0 = (1.1 ± 0.1stat ± 0.2sys) × 10-12 TeV-1 cm-2 s-1. PSRB1259-63 was also monitored in 2005 and 2006, far from periastron passage, comprising 8.9 h and 7.5 h of exposure, respectively. No significant excess of-rays is seen in those observations. Conclusions.PSRB1259-63 has been re-confirmed as a variable TeV-ray emitter. The firm detection of VHE photons emitted at a true anomaly ? ≈-0.35 of the pulsar orbit, i.e. already 50 days prior to the periastron passage, disfavors the stellar disc target scenario as a primary emission mechanism, based on current knowledge about the companion star's disc inclination, extension, and density profile. © 2009 ESO.
Keywords: radiation mechanisms: non-thermal; methods: observational; stars: binaries: general; stars: neutron; gamma rays: observations; telescopes

VHE γ-ray emission of PKS2155-304: Spectral and temporal variability - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2010)
Context. Observations of very high-energy γ-rays from blazars provide information about acceleration mechanisms occurring in their innermost regions. Studies of variability in these objects lead to a better understanding of the mechanisms in play. Aims. To investigate the spectral and temporal variability of VHE (>100 GeV) γ-rays of the well-known high-frequency-peaked BL Lac object PKS 2155-304 with the HESS imaging atmospheric Cherenkov telescopes over a wide range of flux states. Methods. Data collected from 2005 to 2007 were analyzed. Spectra were derived on time scales ranging from 3 years to 4 min. Light curve variability was studied through doubling timescales and structure functions and compared with red noise process simulations. Results. The source was found to be in a low state from 2005 to 2007, except for a set of exceptional flares that occurred in July 2006. The quiescent state of the source is characterized by an associated mean flux level of (4.32 ± 0.09 ± 0.86) × 10 cm s above 200 GeV, or approximately 15% of the Crab Nebula, and a power-law photon index of Γ = 3.53 ± 0.06 ± 0.10. During the flares of July 2006, doubling timescales of ∼2 min are found. The spectral index variation is examined over two orders of magnitude in flux, yielding different behavior at low and high fluxes, which is a new phenomenon in VHE γ-ray emitting blazars. The variability amplitude characterized by the fractional rms F is strongly energy-dependent and is E. The light curve rms correlates with the flux. This is the signature of a multiplicative process that can be accounted for as a red noise with a Fourier index of ∼2. Conclusions. This unique data set shows evidence of a low-level γ-ray emission state from PKS 2155-304 that possibly has a different origin than the outbursts. The discovery of the light curve lognormal behavior might be an indicator of the origin of aperiodic variability in blazars. © ESO, 2010.
Keywords: BL Lacertae objects: individual: PKS 2155-304; galaxies: active; galaxies: jets; gamma rays: general

X-ray Dark-Field Imaging for Improved Contrast in Historical Handwritten Literature - Akstaller, Bernhard; Schreiner, Stephan; Dietrich, Lou; Rauch, Constantin; Schuster, Max; Ludwig, Veronika; Hofmann-Randall, Christina; Michel, Thilo; Anton, Gisela; Funk, Stefan (Journal of Imaging, 2022)
If ancient documents are too fragile to be opened, X-ray imaging can be used to recover the content non-destructively. As an extension to conventional attenuation imaging, dark-field imaging provides access to microscopic structural object information, which can be especially advantageous for materials with weak attenuation contrast, such as certain metal-free inks in paper. With cotton paper and different self-made inks based on authentic recipes, we produced test samples for attenuation and dark-field imaging at a metal-jet X-ray source. The resulting images show letters written in metal-free ink that were recovered via grating-based dark-field imaging. Without the need for synchrotron-like beam quality, these results set the ground for a mobile dark-field imaging setup that could be brought to a library for document scanning, avoiding long transport routes for valuable historic documents.
CRIS-Team Scopus Importer:2022-10-07
Keywords: cultural heritage; grating-based phase-contrast imaging; X-ray dark-field imaging

X-ray dynamic defectoscopy utilizing digital image correlation - Jandejsek, Ivan; Nachtrab, Frank; Uhlmann, Norman; Vavrik, Daniel (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2010)
This paper presents the utilization of the image processing technique known as digital image correlation for X-ray dynamic defectoscopy purpose. Digital image correlation is a non-contact technique (optical or X-ray) that provides full-field and high resolution measurement of deformation fields within an object subjected to loading. In this case it was used for crack detection in a bar specimen subjected to tension loading.
EAM Import::2019-03-12

Zukunft mammographie-basierter Bildgebung [Future of mammography-based imaging] - Schulz-Wendtland, Rüdiger; Wittenberg, Thomas; Michel, Thilo; Hartmann, Arndt; Beckmann, Matthias; Rauh, Claudia; Judt, Sebastian; Brehm, Barbara; Meier-Meitinger, Martina; Anton, Gisela; Uder, Michael; Fasching, Peter (Radiologe, 2014)
Mammography is the central diagnostic method for clinical diagnostics of breast cancer and the breast cancer screening program. In the clinical routine complementary methods, such as ultrasound, tomosynthesis and optional magnetic resonance imaging (MRI) are already combined for the diagnostic procedure. Future developments will utilize investigative procedures either as a hybrid (combination of several different imaging modalities in one instrument) or as a fusion method (the technical fusion of two or more of these methods) to implement fusion imaging into diagnostic algorithms. For screening there are reasonable hypotheses to aim for studies that individualize the diagnostic process within the screening procedure. Individual breast cancer risk prediction and individualized knowledge about sensitivity and specificity for certain diagnostic methods could be tested. The clinical implementation of these algorithms is not yet in sight. (orig.) [German] Die Mammographie ist die zentrale diagnostische Methode der klinischen symptombezogenen Abklaerung von Brusterkrankungen und des Brustkrebsscreenings. In der klinischen Diagnostik wird sie heute schon oft durch zusaetzliche Untersuchungsmethoden wie dem Ultraschall, der Tomosynthese und ggf. auch der MRT-Bildgebung unterstuetzt. Zukuenftige Entwicklungen gehen in die Richtung, dass diese Kombination aus 2 oder mehr Untersuchungsverfahren entweder in Hybrid- (Aufnahme mehrerer unterschiedlicher Bildmodalitaeten in einem einzigen Geraet) oder in Fusionsmethoden (Zusammenfuehrung und Registrierung von Bilddaten aus verschiedenen Modalitaeten) technisch professionalisiert werden. Des Weiteren koennten an subgruppenbezogene Erkrankungsrisiken und individuelle Sensitivitaeten und Spezifitaeten angepasste Diagnostikkombinationen fuer eine Screeningdiagnostik Gegenstand kuenftiger Studien sein. Wir stellen die aktuellen Entwicklungen auf diesen Gebieten und deren momentane Relevanz fuer die klinische Praxis und Entwicklungspotenzial fuer die Zukunft dar. (orig
UnivIS-Import:2015-04-14:Pub.2014.tech.IMMD.IMMD9.zukunf
Keywords: MAMMOgraphy